A combined breast health/weight loss intervention for Black women. - Fitzgibbon ML; Stolley MR; Schiffer L; Sanchez-Johnsen LAP; Wells AM; Dyer A (Preventive Medicine, 2005)
BACKGROUND: Overall incidence of breast cancer is slightly lower, but mortality rates are higher, for Black women compared to White women. Higher body mass index (BMI), sedentary lifestyles, and lower compliance with recommended breast health behaviors may contribute to higher risk and mortality. METHODS: A randomized pilot intervention trial was conducted to assess feasibility and efficacy of a combined breast health/weight loss intervention for 64 overweight or obese Black women, ages 35-65. The primary objectives were to determine whether a 20-week (twice weekly) intervention could decrease weight and dietary fat intake and increase physical activity and breast self-exam (BSE) proficiency. RESULTS: The project was implemented in two cohorts and retention was high for both (96% and 89%, respectively). Both cohorts showed increased proficiency in BSE in the intervention versus the control group (2.4 vs. -0.4, P<0.05; 3.3 vs. -0.2, P<0.001, respectively), but only cohort 2 showed decreased percent body weight (4.0% decrease vs. 0.9% increase, P<0.01), increased physical activity frequency (2.4 vs. 0.1 times/week, P<0.05), and a trend for decreased dietary fat (-2.6% kcal vs. 0.0% kcal, P=0.07) in the intervention compared to the control group. CONCLUSION: Few studies have documented weight loss among Black women, and no combined breast health/weight loss intervention has been conducted. This study documents the feasibility of recruiting, randomizing, and retaining women in a combined intervention and demonstrated weight loss and associated lifestyle changes. Copyright © 2005 by Elsevier Science (USA).
Keywords: Black Persons; Breast Neoplasms -- Prevention and Control; Weight Control; Adult; Aged; Breast Self-Examination; Chi Square Test; Clinical Trials; Conceptual Framework; Cultural Competence; Descriptive Statistics; Dietary Fats; Female; Illinois; Interviews; Logistic Regression; Middle Age; P-Value; Physical Activity; Pilot Studies; Prospective Studies; Research Instruments; Self Report; T-Tests; Wilcoxon Rank Sum Test; Funding Source; Human

A community-based trial of educational interventions with fecal immunochemical tests for colorectal cancer screening uptake among blacks in community settings. - Christy, Shannon M.; Davis, Stacy N.; Williams, Kimberly R.; Zhao, Xiuhua; Govindaraju, Swapomthi K.; Quinn, Gwendolyn P.; Vadaparampil, Susan T.; Lin, Hui‐Yi; Sutton, Steven K.; Roethzeim, Richard R.; Shibata, David; Meade, Cathy D.; et al. (Cancer (0008543X), 2016)
Background: Intervention studies among individuals in diverse community settings are needed to reduce health disparities in colorectal cancer (CRC) screening and mortality rates. The current study compared the efficacy of 2 intervention conditions promoting CRC screening among black individuals.Methods: Black individuals ages 50 to 75 years (N = 330) were recruited in community settings in 4 Tampa Bay counties. After obtaining consent and conducting a baseline interview to assess sociodemographic and health-related variables, participants received either a culturally targeted CRC photonovella booklet plus a fecal immunochemical test (FIT) kit or a standard CRC screening brochure plus an FIT kit. The primary outcome was FIT kit screening uptake.Results: FIT screening uptake at 6 months was 86.7% overall (90.3% in the brochure group and 81.9% in the photonovella group). Controlling for baseline between-group differences, there was no influence of intervention on FIT kit uptake (P = .756). Significant predictors of not returning an FIT kit included being unable to work (P = .010), having higher religious belief scores (P = .015), and living farther from the cancer center (P = .015).Conclusions: Providing FIT kits and educational print materials to black individuals in community settings resulted in high rates of CRC screening. The study also identified subgroups of participants who were less likely to return an FIT kit and provides insight for future interventions. Cancer 2016;122:3288-3296. © 2016 American Cancer Society.
Keywords: Occult Blood; Black Persons -- Psychosocial Factors; Early Detection of Cancer -- Utilization; Community Health Services -- Utilization; Reagent Kits, Diagnostic -- Utilization; Patient Education; Male; Middle Age; Health Care Delivery; Attitude to Health; Colorectal Neoplasms -- Diagnosis; Colorectal Neoplasms -- Psychosocial Factors; Aged; Neoplasm Staging; Prognosis; Immunochemistry; Patient Attitudes; Colorectal Neoplasms -- Ethnology; Early Childhood Intervention; Prospective Studies; Female; Funding Source; Human; Random Assignment; Randomized Controlled Trials

A community-based, culturally relevant intervention to promote healthy eating and physical activity among middle-aged African American women in rural Alabama: findings from a group randomized controlled trial. - Scarinci, Isabel C; Moore, Artisha; Wynn-Wallace, Theresa; Cherrington, Andrea; Fouad, Mona; Li, Yufeng (Preventive Medicine, 2014)
Objective: We examined the efficacy of a community-based, culturally relevant intervention to promote healthy eating and physical activity among African American (AA) women between the ages of 45-65 years, residing in rural Alabama.Methods: We conducted a group randomized controlled trial with counties as the unit of randomization that evaluated two interventions based on health priorities identified by the community: (1) promotion of healthy eating and physical activity; and (2) promotion of breast and cervical cancer screening. A total of 6 counties with 565 participants were enrolled in the study between November 2009 and October 2011.Results: The overall retention rate at 24-month follow-up was 54.7%. Higher retention rate was observed in the "healthy lifestyle" arm (63.1%) as compared to the "screening" arm (45.3%). Participants in the "healthy lifestyle" arm showed significant positive changes compared to the "screening" arm at 12-month follow-up with regard to decrease in fried food consumption and an increase in both fruit/vegetable intake and physical activity. At 24-month follow-up, these positive changes were maintained with healthy eating behaviors, but not engagement in physical activity.Conclusions: A culturally relevant intervention, developed in collaboration with the target audience, can improve (and maintain) healthy eating among AA women living in rural areas.

A comparative effectiveness analysis of the PBCG vs. PCPT risks calculators in a multi-ethnic cohort. - Carbunaru, Samuel; Nettey, Oluwarotimi S.; Gogana, Pooja; Helenowski, Irene B.; Jovanovic, Borko; Ruden, Maria; Hollowell, Courtney M. P.; Sharifi, Roohollah; Kittles, Rick A.; Schaeffer, Edward; Gann, Peter; Murphy, Adam B. (BMC Urology, 2019)
Background: Predictive models that take race into account like the Prostate Cancer Prevention Trial Risk Calculator 2.0 (PCPT RC) and the new Prostate Biopsy Collaborative Group (PBCG) RC have been developed to equitably mitigate the overdiagnosis of prostate specific antigen (PSA) screening. Few studies have compared the performance of both calculators across racial groups.Methods: From 1485 prospectively recruited participants, 954 men were identified undergoing initial prostate biopsy for abnormal PSA or digital rectal examination in five Chicago hospitals between 2009 and 2014. Discrimination, calibration, and frequency of avoided biopsies were calculated to assess the performance of both risk calculators.Results: Of 954 participants, 463 (48.5%) were Black, 355 (37.2%) were White, and 136 (14.2%) identified as Other. Biopsy results were as follows: 310 (32.5%) exhibited no cancer, 323 (33.9%) indolent prostate cancer, and 321 (33.6%) clinically significant prostate cancer (csPCa). Differences in area under the curve (AUC)s for the detection of csPCa between PCPT and PBCG were not statistically different across all racial groups. PBCG did not improve calibration plots in Blacks and Others, as it showed higher levels of overprediction at most risk thresholds. PCPT led to an increased number of avoidable biopsies in minorities compared to PBCG at the 30% threshold (68% vs. 28% of all patients) with roughly similar rates of missed csPCa (23% vs. 20%).Conclusion: Significant improvements were noticed in PBCG's calibrations and net benefits in Whites compared to PCPT. Since PBCG's improvements in Blacks are disputable and potentially biases a greater number of low risk Black and Other men towards unnecessary biopsies, PCPT may lead to better biopsy decisions in racial minority groups. Further comparisons of commonly used risk calculators across racial groups is warranted to minimize excessive biopsies and overdiagnosis in ethnic minorities.
Keywords: Ethnic Groups; Prostatic Neoplasms -- Pathology; Risk Assessment -- Methods; Prostatic Neoplasms -- Prevention and Control; Prospective Studies; Male; Biopsy; Middle Age; Human; Aged; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Funding Source

A comparison of prostate knowledge of African-American and Caucasian men: changes from prescreening baseline to postintervention. - Abbott RR; Taylor DK; Barber K (Cancer Journal from Scientific American, 1998)
PURPOSE. This study was undertaken to determine if a community screening program designed to overcome key barriers (lack of awareness, cost of program, ease of access to care) could successfully impact on African-American males' knowledge, attitudes, and behaviors regarding prostate cancer screening. The focus of this report is knowledge. To date, there are no reported studies that examine differences in knowledge from a prescreening baseline to a postintervention level for minority participants. PATIENTS AND METHODS. A total of 944 men were enrolled in the study in a 20-month period. Prostate screening and education were offered as a new service at an existing senior health clinic. In addition, mass screenings were offered approximately monthly at various locations in the community (including senior community centers, senior apartment complexes, and some public housing projects). Screening included both the digital rectal examination and the prostate specific antigen test. A brief questionnaire was administered during client intake (the pretest) and repeated after the education and screening participation (the posttest). Test items targeted three constructs: (1) etiology, (2) risk status, and (3) clinical factors. RESULTS. The largest difference on pretest scores between the racial group's resulted from clinical factor knowledge. African-American men were significantly less likely than Caucasian men to correctly identify early symptoms of prostate cancer and the basic components of a prostate checkup. Although scores were initially significantly lower for African-American participants, these differences were not evident after program involvement. There was a significant increase in knowledge level for all men when comparing pretest and posttest scores. Significant improvement was noted for each test item, with the exception of one key item. Even after participation in the program, African-American men were stiff more likely to believe that 'pain' was die first symptom of prostate cancer. DISCUSSION. An itern-by-item analysis revealed that there was only one test item in which program participation did not 'correct' knowledge. African-American men were stiff more likely to believe that pain was the first symptom that would alert them to the presence of cancer. The screening program included information (both printed and oral content) that emphasized the importance of routine screening to detect cancer at an early stage, because most men would experience no symptoms. The only other reported study that examined knowledge documented similar findings with respect to an understanding of symptomology. These findings can be used to direct or guide the educational component of future screening programs that hope to target African-American men.
Keywords: Health Knowledge; Black Persons; Prostatic Neoplasms -- Prevention and Control; Health Screening; White Persons; Health Behavior; Prostatic Neoplasms -- Diagnosis; Health Screening -- Economics; Pretest-Posttest Design; Item Analysis; Questionnaires; Adult; Middle Age; Male; Funding Source; Human

A Demonstration of ‘‘Less Can Be More’’ in Risk Graphics. - Zikmund-Fisher, Brian J.; Fagerlin, Angela; Ubel, Peter A. (Medical Decision Making, 2010)
Background. Online tools such as Adjuvant! provide tailored estimates of the possible outcomes of adjuvant therapy options available to breast cancer patients. The graphical format typically displays 4 outcomes simultaneously: survival, mortality due to cancer, other-cause mortality, and incremental survival due to adjuvant treatment. Objective. To test whether simpler formats that present only baseline and incremental survival would improve comprehension of the relevant risk statistics and/or affect treatment intentions. Design. Randomized experimental manipulation of risk graphics shown included in Internet-administered survey vignettes about adjuvant therapy decisions for breast cancer patients with ER + tumors. Participants. Demographically diverse, stratified random samples of women ages 40 to 74 y recruited from an Internet research panel. Intervention. Participants were randomized to view either pictographs (icon arrays) that displayed all 4 possible outcomes or pictographs that showed only survival outcomes. Measurements. Comprehension of key statistics, task completion times, graph evaluation ratings, and perceived interest in adjuvant chemotherapy. Results. In the primary study (N = 832), participants who viewed survival-only pictographs had better accuracy when reporting the total chance of survival with both chemotherapy and hormonal therapy (63% v. 50%, P < 0.001), higher graph evaluation ratings (x = 7.98 v. 7.67, P = 0.04), and less interest in adding chemotherapy to hormonal therapy (43% v. 50%, P = 0.04; adjusted odds ratio [OR] = 0.68, P = 0.008). A replication study (N = 714) confirmed that participants who viewed survival-only graphs had higher graph evaluation ratings (x = 8.06 v. 7.72, P = 0.04) and reduced interest in chemotherapy (OR=0.67,P=0.03). Limitations. Studies used general public samples; actual patients may process risk information differently. Conclusions. Taking a ‘‘less is more’’ approach by omitting redundant mortality outcome statistics can be an effective method of risk communication and may be preferable when using visual formats such as pictographs.
Keywords: Breast Neoplasms -- Drug Therapy; Survival; Human; Adult; Middle Age; Aged; Female; Surveys; Descriptive Statistics; P-Value; Chemotherapy, Cancer -- Evaluation; Odds Ratio; Hormone Therapy -- Evaluation; Vignettes; Random Assignment; Black Persons; Hispanic Americans; White Persons; Chi Square Test; T-Tests; Wilcoxon Rank Sum Test; Data Analysis, Statistical; Data Analysis Software; Logistic Regression

A genome wide SNP genotyping study in the Tunisian population: specific reporting on a subset of common breast cancer risk loci. - Hamdi, Yosr; Ben Rekaya, Mariem; Jingxuan, Shan; Nagara, Majdi; Messaoud, Olfa; Benammar Elgaaied, Amel; Mrad, Ridha; Chouchane, Lotfi; Boubaker, Mohamed Samir; Abdelhak, Sonia; Boussen, Hamouda; Romdhane, Lilia (BMC Cancer, 2018)
Background: Breast cancer is the most common cancer in women worldwide. Around 50% of breast cancer familial risk has been so far explained by known susceptibility alleles with variable levels of risk and prevalence. The vast majority of these breast cancer associated variations reported to date are from populations of European ancestry. In spite of its heterogeneity and genetic wealth, North-African populations have not been studied by the HapMap and the 1000Genomes projects. Thus, very little is known about the genetic architecture of these populations.Methods: This study aimed to investigate a subset of common breast cancer loci in the general Tunisian population and to compare their genetic composition to those of other ethnic groups. We undertook a genome-wide haplotype study by genotyping 135 Tunisian subjects using the Affymetrix 6.0-Array. We compared Tunisian allele frequencies and linkage disequilibrium patterns to those of HapMap populations and we performed a comprehensive assessment of the functional effects of several selected variants.Results: Haplotype analyses showed that at risk haplotypes on 2p24, 4q21, 6q25, 9q31, 10q26, 11p15, 11q13 and 14q32 loci are considerably frequent in the Tunisian population (> 20%). Allele frequency comparison showed that the frequency of rs13329835 is significantly different between Tunisian and all other HapMap populations. LD-blocks and Principle Component Analysis revealed that the genetic characteristics of breast cancer variants in the Tunisian, and so probably the North-African populations, are more similar to those of Europeans than Africans. Using eQTl analysis, we characterized rs9911630 as the most strongly expression-associated SNP that seems to affect the expression levels of BRCA1 and two long non coding RNAs (NBR2 and LINC008854). Additional in-silico analysis also suggested a potential functional significance of this variant.Conclusions: We illustrated the utility of combining haplotype analysis in diverse ethnic groups with functional analysis to explore breast cancer genetic architecture in Tunisia. Results presented in this study provide the first report on a large number of common breast cancer genetic polymorphisms in the Tunisian population which may establish a baseline database to guide future association studies in North Africa.
Keywords: Genome; Black Persons; Breast Neoplasms; Sequence Analysis; Disease Susceptibility; Haplotypes; Tunisia; Male; Research Subjects; Adult; Human; Middle Age; Genetics; Computer Simulation; Female; Polymorphism, Genetic; Genes; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Clinical Assessment Tools; Questionnaires

A multi-center study of using carbon nanoparticles to track lymph node metastasis in T1-2 colorectal cancer. - Yan, Jun; Xue, Fangqin; Chen, Hongyuan; Wu, Xiufeng; Zhang, Hui; Chen, Gang; Lu, Jianping; Cai, Lisheng; Xiang, Gao; Deng, Zhenwei; Zheng, Yu; Zheng, Xiaoling; et al. (Surgical Endoscopy, 2014)
Background: How to identify whether T1-2 colorectal cancers have lymph nodes metastases pre-op or intra-op is a crucial problem in clinic. The purpose of this study was to evaluate the feasibility of using carbon nanoparticles to track lymph nodes metastases in T1-2 colorectal cancers.Methods: A multi-center study was performed between July 2012 and January 2014. Seventy-three patients with T1-2 colorectal cancer identified by pre-op endoscopic ultrasonography (EUS) were recruited. 1 ml carbon nanoparticles suspension was endoscopically injected into the submucosal layer at four points around the site of the primary tumor 1 day before surgery. Laparoscopic radical resection with lymphadenectomy was performed. Sentinel lymph nodes (SLNs) were defined as nodes that were black-dyed by carbon nanoparticles. Pathology confirmed whether lymph nodes have cancer metastases and the SLNs accuracy.Results: SLNs were easily found under laparoscopy. The mean number of SLNs was 3 (range 1-5). All patients had SLNs lying alongside the mesenteric vessel or main arterial vessel. After pathological analysis, 2 patients (9.52%) had lymph node metastasis in 21 patients with EUS T1 cancers, and 10 patients (19.23%) had lymph node metastasis in 52 patients with EUS T2 cancers. In two T1 cases with lymph node metastasis, SLNs were positive with 100% accuracy. In ten T2 cases with lymph node metastasis, SLNs were positive in nine cases. In pathology, carbon nanoparticles were seen in lymphatic vessels, and lymphoid sinus and macrophages in negative SLNs. When SLNs were positive, carbon nanoparticles were seen around cancer cells in lymph nodes. The overall sensitivity, specificity, accuracy of SLNs in T1-2 colorectal cancers were 91.67, 100, 98.63%, respectively.Conclusions: We demonstrated the feasibility of using carbon nanoparticles to track lymph nodes metastases in T1-2 colorectal cancers. Carbon nanoparticles black-dyed lymph nodes play a role as SLNs in T1-2 colorectal cancers.
Keywords: Carbon -- Diagnostic Use; Colorectal Neoplasms -- Pathology; Dyes -- Diagnostic Use; Lymph Nodes -- Pathology; Nanoparticles; Adolescence; Adult; Aged; Clinical Trials; Colectomy; Colorectal Neoplasms -- Surgery; Female; Human; Laparoscopy; Lymph Node Excision; Lymph Nodes -- Surgery; Male; Mesentery; Middle Age; Neoplasm Metastasis; Pilot Studies; Rectum -- Surgery; Sensitivity and Specificity; Young Adult

A multimodal intervention to promote mammography and colorectal cancer screening in a safety-net practice. - Fiscella K; Humiston S; Hendren S; Winters P; Idris A; Li SX; Ford P; Specht R; Marcus S; Fiscella, Kevin; Humiston, Sharon; Hendren, Samantha; et al. (Journal of the National Medical Association, 2011)
Background: There are limited data regarding interventions designed to improve cancer screening rates in safety-net practices with "real world" patients.Objective: To examine the impact of a multimodal intervention on mammography and colorectal cancer (CRC) screening rates in a safety-net practice caring for underserved patients.Methods: At an inner-city family medicine practice, all patients past due for mammography or CRC screening were assigned to receive or not receive a screening promotion intervention based on their medical record number. The 12-month intervention included outreach to patients (tailored letters, automated and personal phone calls) and point-of-care patient and clinician prompts. The trial was registered at clinicaltrials.gov, NCT00818857.Results: We enrolled 469 participants aged 40 to 74 years, including 28% African Americans, 5% Latinos, 25% with Medicaid, and 10% without any form of insurance. Participants in the intervention group showed statistically significantly higher rates of cancer screening; rates were 41% vs 16.8% for mammography and 28.8% vs 10% for CRC screening. These findings were confirmed in multivariable analysis. Similar relative improvements in screening were seen across race, ethnicity, socioeconomic status, and insurance groups.Discussion: A multimodal intervention shows promise for improving rates of mammography and colorectal cancer screening within a safety-net practice. Further study will identify the most cost-effective components of the intervention.
Keywords: Colonoscopy -- Statistics and Numerical Data; Health Promotion -- Administration; Health Promotion -- Statistics and Numerical Data; Mammography -- Statistics and Numerical Data; Occult Blood; Sigmoidoscopy -- Statistics and Numerical Data; Adult; Aged; Breast Neoplasms -- Prevention and Control; Female; Human; Male; Middle Age; Multivariate Analysis; Urban Population; Clinical Trials

A novel community-based study to address disparities in hypertension and colorectal cancer: a study protocol for a randomized control trial. - Ravenell, Joseph; Thompson, Hayley; Cole, Helen; Plumhoff, Jordan; Cobb, Gia; Afolabi, Lola; Boutin-Foster, Carla; Wells, Martin; Scott, Marian; Ogedegbe, Gbenga (Trials, 2013)
Background: Black men have the greatest burden of premature death and disability from hypertension (HTN) in the United States, and the highest incidence and mortality from colorectal cancer (CRC). While several clinical trials have reported beneficial effects of lifestyle changes on blood pressure (BP) reduction, and improved CRC screening with patient navigation (PN), the effectiveness of these approaches in community-based settings remains understudied, particularly among Black men.Methods/design: MISTER B is a two-parallel-arm randomized controlled trial that will compare the effect of a motivational interviewing tailored lifestyle intervention (MINT) versus a culturally targeted PN intervention on improvement of BP and CRC screening among black men aged ≥50 with uncontrolled HTN who are eligible for CRC screening. Approximately 480 self-identified black men will be randomly assigned to one of the two study conditions. This innovative research design allows each intervention to serve as the control for the other. Specifically, the MINT arm is the control condition for the PN arm, and vice-versa. This novel, simultaneous testing of two community-based interventions in a randomized fashion is an economical and yet rigorous strategy that also enhances the acceptability of the project. Participants will be recruited during scheduled screening events at barbershops in New York City. Trained research assistants will conduct the lifestyle intervention, while trained community health workers will deliver the PN intervention. The primary outcomes will be 1) within-patient change in systolic and diastolic BP from baseline to six months and 2) CRC screening rates at six months.Discussion: This innovative study will provide a unique opportunity to test two interventions for two health disparities simultaneously in community-based settings. Our study is one of the first to test culturally targeted patient navigation for CRC screening among black men in barbershops. Thus, our study has the potential to improve the reach of hypertension control and cancer prevention efforts within a high-risk population that is under-represented in primary care settings.Trial Registration: ClinicalTrials.gov, NCT01092078.
Keywords: Black Persons -- Psychosocial Factors; Colorectal Neoplasms -- Prevention and Control; Early Detection of Cancer; Attitude to Health -- Ethnology; Hypertension -- Therapy; Motivational Interviewing; Study Design; Behavior; Age Factors; Occupations and Professions; Blood Pressure; Protocols; Colorectal Neoplasms -- Diagnosis; Colorectal Neoplasms -- Ethnology; Colorectal Neoplasms -- Psychosocial Factors; Community Health Services; Culture; Health Promotion; Health Status Disparities; Healthcare Disparities; Human; Hypertension -- Diagnosis; Hypertension -- Ethnology; Hypertension -- Physiopathology; Hypertension -- Psychosocial Factors; Male; Middle Age; New York; Patient Navigation; Patient Selection; Predictive Value of Tests; Risk Factors; Sex Factors; Time Factors; Treatment Outcomes

A pilot phase II trial of magnesium supplements to reduce menopausal hot flashes in breast cancer patients. - Park H; Parker GL; Boardman CH; Morris MM; Smith TJ; Park, Haeseong; Parker, Gwendolyn L; Boardman, Cecelia H; Morris, Monica M; Smith, Thomas J (Supportive Care in Cancer, 2011)
Background: We tested if magnesium would diminish bothersome hot flashes in breast cancer patients.Methods: Breast cancer patients with at least 14 hot flashes a week received magnesium oxide 400 mg for 4 weeks, escalating to 800 mg if needed. Hot flash score (frequency × severity) at baseline was compared to the end of treatment.Results: Of 29 who enrolled, 25 women completed treatment. The average age was 53.5 years; six African American, the rest Caucasian; eight were on tamoxifen, nine were on aromatase inhibitors, and 14 were on anti-depressants. Seventeen patients escalated the magnesium dose. Hot flash frequency/week was reduced from 52.2 (standard error (SE), 13.7) to 27.7 (SE, 5.7), a 41.4% reduction, p = 0.02, two-sided paired t test. Hot flash score was reduced from 109.8 (SE, 40.9) to 47.8 (SE, 13.8), a 50.4% reduction, p = 0.04. Of 25 patients, 14 (56%) had a >50% reduction in hot flash score, and 19 (76%) had a >25% reduction. Fatigue, sweating, and distress were all significantly reduced. Side effects were minor: two women stopped the drug including one each with headache and nausea, and two women had grade 1 diarrhea. Compliance was excellent, and many patients continued treatment after the trial.Conclusions: Oral magnesium appears to have helped more than half of the patients and was well tolerated. Side effects and cost ($0.02/tablet) were minimal. A randomized placebo-controlled trial is planned.
Keywords: Breast Neoplasms -- Drug Therapy; Hot Flashes -- Drug Therapy; Magnesium Compounds -- Therapeutic Use; Menopause; Adult; Aged; Breast Neoplasms -- Complications; Clinical Trials; Female; Health Care Costs; Hot Flashes -- Etiology; Human; Medication Compliance; Middle Age; Pilot Studies; Prospective Studies; Severity of Illness Indices

A pilot program in collaboration with African American churches successfully increases awareness of the importance of cancer research and participation in cancer translational research studies among African Americans. - Colon-Otero, Gerardo; Albertie, Monica; Lesperance, Mary; Weis, Jennifer; Coles, Alton; Smith, Nina; Mills, Lynette; Woodward, Timothy; Aspitia, Alvaro; Vishnu, Prakash; Willis, Floyd; Isley, Amber; et al. (Journal of Cancer Education, 2012)
African Americans are underrepresented in cancer research. We evaluate whether collaboration with African American churches can improve cancer awareness and increase participation in translational research protocols among African Americans. From February to April 2010, the Mayo Clinic partnered with African American Jacksonville churches to provide educational programs focused on cancer research and healthy behaviors. Education on multiple myeloma and on-site access to a translational cancer research pilot project evaluating the prevalence of monoclonal gammopathies and t(14,18) in African Americans was offered. Seventy-four percent, 236 out of 318 participants, returned the questionnaires. The majority of participants had never received information on multiple myeloma (67%), had never received clinical research study information (57%), and were enrolled in the translational research studies (55%). Partnerships with African American churches in community education projects that bring research to church venues are effective in improving cancer awareness and in increasing research participation among African Americans.
Keywords: Black Persons; Churches; Clinical Research; Collaboration; Health Education; Multiple Myeloma -- Education; Research Subject Recruitment; Adult; Aged; Body Mass Index; Cancer Care Facilities; Clergy; Descriptive Statistics; Female; Florida; Funding Source; Health Behavior; Health Knowledge; Health Promotion; Human; Insurance, Health; Interinstitutional Relations; Male; Middle Age; Pilot Studies; Questionnaires; Surveys

A pilot randomized controlled trial of a commercial diet and exercise weight loss program in minority breast cancer survivors. - Greenlee, Heather A; Crew, Katherine D; Mata, Jennie M; McKinley, Paula S; Rundle, Andrew G; Zhang, Wenfei; Liao, Yuyan; Tsai, Wei Y; Hershman, Dawn L (Obesity (19307381), 2013)
Objective: Obesity is associated with poorer breast cancer outcomes and losing weight postdiagnosis may improve survival. As Hispanic and black women have poorer breast cancer prognosis than non-Hispanic whites diagnosed at similar age and stage, and have higher rates of obesity, effective weight loss strategies are needed. We piloted a randomized, waitlist-controlled, crossover study to examine the effects and feasibility of the commercial Curves weight loss program among Hispanic, African American and Afro-Caribbean breast cancer survivors.Design and Methods: Women with stage 0-IIIa breast cancer ≥ 6 months posttreatment, sedentary, and BMI ≥ 25 kg/m(2) were randomized to the immediate arm (IA): 6 months of the Curves program followed by 6 months of observation; or the waitlist control arm (WCA): 6 months of observation followed by 6 months of the Curves program. The Curves program uses a 30-min exercise circuit and a high-vegetable/low-fat/calorie-restricted diet.Results: A total of 42 women enrolled (79% Hispanic, 21% black), mean age 51 (range 32-69) and mean BMI 33.2(± 5.9) kg/m(2); 91% were retained at month 12. At month 6, women in the IA lost an average 3.3% (± 3.5%) of body weight (range: 1.7% gain to 10.6% loss), as compared with 1.8% (± 2.9%) weight loss in the WCA (P = 0.04). At month 12, on average women in the IA regained some but not all of the weight lost during the first 6 months (P = 0.02).Conclusions: Minority breast cancer survivors were recruited and retained in a weight loss study. Six months of the Curves program resulted in moderate weight loss, but weight loss was not maintained postintervention. Future interventions should identify methods to increase uptake and maintenance of weight loss behaviors.
Keywords: Breast Neoplasms -- Complications; Diet, Reducing; Exercise; Minority Groups; Obesity -- Therapy; Survivors; Weight Reduction Programs; Adult; Black Persons; Aged; Body Mass Index; Breast Neoplasms -- Ethnology; Diet Therapy; Dietary Fats -- Administration and Dosage; Female; Hispanic Americans; Human; Middle Age; Obesity -- Complications; Obesity -- Diet Therapy; Obesity -- Ethnology; Pilot Studies; Weight Gain

A pilot trial of decision aids to give truthful prognostic and treatment information to chemotherapy patients with advanced cancer. - Smith TJ; Dow LA; Virago EA; Khatcheressian J; Matsuyama R; Lyckholm LJ (Journal of Supportive Oncology, 2011)
Most cancer patients do not have an explicit discussion about prognosis and treatment despite documented adverse outcomes. Few decision aids have been developed to assist the difficult discussions of palliative management. We developed decision aids for people with advanced in curable breast, colorectal, lung, and hormone-refractory prostate cancers facing first-, second-, third-, and fourth-line chemotherapy. We recruited patients from our urban oncology clinic after gaining the permission of their treating oncologist. We measured knowledge of curability and treatment benefit before and after the intervention. Twenty-six of 27 (96%) patients completed the aids, with ameanage of 63, 56% female, 56% married, 56% African American, and 67% with a high school education or more. Most patients (14/27, 52%) thought a person with their advanced cancer could be cured, which was reduced (to 8/26, 31%, P = 0.15) after the decision aid. Nearly all overestimated the effect of palliative chemotherapy. No distress was noted, and hope did not change. The majority (20/27, 74%) found the information helpful to them, and almost all (25/27, 93%) wanted to share the information with their family and physicians. It is possible to give incurable patients their prognosis, treatment options, and options for improving end-of-life care without causing distress or lack of hope. Almost all find the information helpful and want to share it with doctors and family. Research is needed to test the findings in a larger sample and measure the outcomes of truthful information on quality of life, quality of care, and costs.
Keywords: Decision Support Techniques; Neoplasms -- Drug Therapy; Aged; Female; Human; Male; Middle Age; Pilot Studies; Prognosis

A pilot trial of spirituality counseling for weight loss maintenance in African American breast cancer survivors. - Djuric Z; Mirasolo J; Kimbrough L; Brown DR; Heilbrun LK; Canar L; Venkatranamamoorthy R; Simon MS; Djuric, Zora; Mirasolo, Josephine; Kimbrough, LaVern; Brown, Diane R; et al. (Journal of the National Medical Association, 2009)
A continuing challenge in weight loss treatment is attaining maintenance of weight loss. The goal of this study was to develop a counseling method that would assist African American breast cancer survivors with weight loss maintenance. In this pilot study, 31 obese breast cancer survivors were recruited. Individualized, dietitian-led counseling by telephone and free Weight Watchers coupons were provided to all participants for 18 months. At the 6-month time point, women were randomized to receive spirituality counseling or not in addition to the standard program. The spirituality counseling was delivered via telephone using an 8-step framework. Subjects were asked to utilize daily meditation or prayer, daily readings, and the recording of thoughts in a journal. Mean weight loss from baseline to 6 months was a modest 2.0% of baseline weight. From 6 to 18 months, there was no further weight change in the spirituality arm and a gain of 0.7% in the dietitian-only arm. Despite little effect on weight loss, it did appear that spirituality counseling positively affected spiritual well-being (FACIT-Sp) scores and dietary quality. The spirituality counseling framework therefore may be further refined and useful for other health promotion studies with African American populations.
Keywords: Black Persons; Breast Neoplasms -- Psychosocial Factors; Counseling; Religion and Psychology; Weight Loss; Body Mass Index; Breast Neoplasms -- Mortality; Diet Records; Female; Human; Middle Age; Motor Activity; Obesity -- Complications; Obesity -- Diet Therapy; Obesity -- Psychosocial Factors; Pilot Studies; Quality of Life; Questionnaires; Survival Analysis; Survivors; United States; Clinical Trials

A Prospective Pilot Study Evaluating Feasibility and Preliminary Effects of Breathe Easier : A Mindfulness-based Intervention for Survivors of Lung Cancer and Their Family Members (Dyads). - McDonnell, Karen Kane; Gallerani, David G.; Newsome, Brandi R.; Owens, Otis L.; Beer, Jenay; Myren-Bennett, Amanda R.; Regan, Elizabeth; Hardin, James W.; Webb, Lisa A. (Integrative Cancer Therapies, 2020)
Objective: Symptom burden remains a distressing problem for survivors with non-small-cell lung cancer (stages I-IIIa). This pilot study evaluated feasibility and preliminary effects of a tailored mindfulness-based intervention, Breathe Easier, which encompasses meditation, 2 levels of mindful hatha yoga, breathing exercises, and participant interaction. Methods: Participants were recruited from 2 cancer programs in the US Southeast. A family member was required for participation. Sixty-two participants enrolled (20% recruitment) and 49 completed the intervention (79% retention). Participants chose level 1 yoga (basic) or level 2 (more advanced). Of the completers, survivors were 39% male and 65% Black. A community-based participatory research framework helped identify the specific needs and interests of potential participants and foreseeable barriers to implementation. A 2-month prospective, 1-group, pre-post design evaluated feasibility. Intervention dosage was measured using written protocols. Attendance and completion of daily home assignments measured adherence. Acceptability was assessed using a 10-item questionnaire, completed at three time points. Preliminary outcome data collected pre- and post-intervention tested the hypothesis that participants who received the 8-week intervention Breathe Easier would, post-intervention, demonstrate (a) less dyspnea, (b) less fatigue, (c) less stress, (d) improved sleep, (e) improved anxiety and depression, and (f) improved functional exercise capacity. Exit interviews were conducted, transcribed verbatim, and analyzed for content using descriptive statistics. Results: Quantitative and qualitative measures indicated strong feasibility. Over time, level 1 participants had statistically less dyspnea, fatigue and improved exercise capacity, as well as improved sleep, and stress scores. Level 2 participants experienced slightly increased dyspnea and fatigue but improved sleep, stress, and exercise capacity. All participants experienced anxiety and depression within normal limits pre- and post-intervention. Five major themes emerged out of exit interviews: Learning to Breathe Easier; Interacting with Others as a Personal Benefit; Stretching, Releasing Tension, and Feeling Energized; Enhancing Closeness with Committed Partners; Refocusing on Living; and Sustaining New Skills as a Decision. Conclusions: The study offers insight into the feasibility of an 8-week in-person mindfulness-based intervention with a unique subset of understudied survivors of lung cancer and family members. Outcome data interpretation is limited by the 1-group design and sample size.
Keywords: Mindfulness; Lung Neoplasms -- Therapy; Family Therapy; Cancer Survivors; Extended Family; Treatment Outcomes; Human; Pilot Studies; Meditation; Yoga; Breathing Exercises; Southeastern United States; Male; Female; Descriptive Statistics; Prospective Studies; Pretest-Posttest Design; Questionnaires; Interviews; Thematic Analysis; Functional Status; Dyspnea; Sleep; Stress, Psychological; Cancer Fatigue; Anxiety; Depression; Content Analysis

A randomized controlled trial of a multicomponent, targeted, low-literacy educational intervention compared with a nontargeted intervention to boost colorectal cancer screening with fecal immunochemical testing in community clinics. - Davis, Stacy N; Christy, Shannon M; Chavarria, Enmanuel A; Abdulla, Rania; Sutton, Steven K; Schmidt, Alyssa R; Vadaparampil, Susan T; Quinn, Gwendolyn P; Simmons, Vani N; Ufondu, Chukwudi B; Ravindra, Chitra; Schultz, Ida; et al. (Cancer (0008543X), 2016)
Background: The objective of the current study was to improve colorectal cancer (CRC) screening uptake with the fecal immunochemical test (FIT). The current study investigated the differential impact of a multicomponent, targeted, low-literacy educational intervention compared with a standard, nontargeted educational intervention.Methods: Patients aged 50 to 75 years who were of average CRC risk and not up-to-date with CRC screening were recruited from either a federally qualified health center or a primary care community health clinic. Patients were randomized to the intervention condition (targeted photonovella booklet/DVD plus FIT kit) or comparison condition (standard Centers for Disease Control and Prevention brochure plus FIT kit). The main outcome was screening with FIT within 180 days of delivery of the intervention.Results: Of the 416 participants, 54% were female; the participants were racially and ethnically diverse (66% white, 10% Hispanic, and 28% African American), predominantly of low income, and insured (the majority had county health insurance). Overall, the FIT completion rate was 81%, with 78.1% of participants in the intervention versus 83.5% of those in the comparison condition completing FIT (P =  .17). In multivariate analysis, having health insurance was found to be the primary factor predicting a lack of FIT screening (adjusted odds ratio, 2.10; 95% confidence interval, 1.04-4.26 [P =  .04]).Conclusions: The multicomponent, targeted, low-literacy materials were not found to be significantly different or more effective in increasing FIT uptake compared with the nontargeted materials. Provision of a FIT test plus education may provide a key impetus to improve the completion of CRC screening. The type of educational material (targeted vs nontargeted) may matter less. The findings of the current study provide a unique opportunity for clinics to adopt FIT and to choose the type of patient education materials based on clinic, provider, and patient preferences. Cancer 2017;123:1390-1400. © 2016 American Cancer Society.
Keywords: Patient Education; Feces; Colorectal Neoplasms -- Epidemiology; Colorectal Neoplasms -- Diagnosis; Early Detection of Cancer; Health Screening; Risk Factors; Odds Ratio; Aged; Male; Middle Age; Human; Female; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Impact of Events Scale

A randomized controlled trial using patient navigation to increase colonoscopy screening among low-income minorities. - Christie J; Itzkowitz S; Lihau-Nkanza I; Castillo A; Redd W; Jandorf L; Christie, Jennifer; Itzkowitz, Steven; Lihau-Nkanza, Irene; Castillo, Anabella; Redd, William; Jandorf, Lina (Journal of the National Medical Association, 2008)
Organizational barriers play a key role in colorectal cancer (CRC) screening disparities in low-income minorities. This is a prospective, randomized trial to determine whether a patient navigator (PN) can help overcome the organizational barriers low-income minorities face in trying to obtain screening colonoscopy. Patients of average risk for CRC were referred by their primary care physician for screening colonoscopy. After the PN received the referral, patients were randomly assigned to either receive navigation (PN+) to screening colonoscopy or not receive navigation (PN-). We hypothesized that a PN would increase patient compliance with screening colonoscopy. A total of 21 patients were enrolled in the pilot study (PN+ = 13, PN- = 8); 54% of navigated patients completed screening colonoscopy versus 13% of nonnavigated patients (p = 0.058). Eighty-six percent of navigated patients had an excellent or very good colon prep; however, there was no difference in prep quality between groups ( p = 0.10). One-hundred percent of navigated patients were very satisfied with navigation services. A PN improves compliance with screening colonoscopy in low-income minorities. Larger studies are needed to evaluate what features of navigation are most effective in facilitating completion of screening colonoscopy.
Keywords: Colonoscopy -- Utilization; Colorectal Neoplasms -- Diagnosis; Health Screening -- Utilization; Health Services Accessibility; Patient Attitudes; Poverty; Appointments and Schedules; Attitude to Health; Black Persons; Randomized Controlled Trials; Colonoscopy -- Statistics and Numerical Data; Colorectal Neoplasms -- Ethnology; Colorectal Neoplasms -- Prevention and Control; Female; Health Behavior; Health Screening -- Statistics and Numerical Data; Hispanic Americans; Male; Middle Age; Patient Education; Patient Satisfaction; Prospective Studies; Reminder Systems; Socioeconomic Factors; United States; Human

A randomized trial comparing web-based decision aids on prostate cancer knowledge for African-American men. - Ellison GL; Weinrich SP; Lou M; Xu H; Powell IJ; Baquet CR; Ellison, Gary L; Weinrich, Sally P; Lou, Mimi; Xu, Hongyan; Powell, Isaac J; Baquet, Claudia R (Journal of the National Medical Association, 2008)
Objectives: Few decision aids are tailored for African-American men. We sought to determine if web-based decision aids increased knowledge of prostate cancer screening among African men.Methods: This postintervention, quasiexperimental research measured knowledge of prostate cancer screening among African-American men following receipt of 1 of 2 web-based decision aids: enhanced or usual care. Men ages 40-65 were recruited at the annual convention of the Prince Hall Masons in the summer of 2007, which was attended by 1170 masons. The primary outcome was knowledge of prostate cancer screening.Results: There were 87 participants in the sample with a mean age of 52 years (standard deviation = 6.9). Forty-six masons were randomized to the enhanced decision aid, and 41 masons were randomized to the usual care decision aid. Knowledge scores were statistically significantly higher among the men receiving the enhanced decision aid compared to the usual care decision aid after simultaneously adjusting for age, educational level, marital status, family history, previous prostate specific antigen test and digital rectal exam (p = 0.01).Conclusion: We found evidence that the enhanced web decision aid was significantly more effective than the usual care decision aid in promoting knowledge of the benefits, limitations and risks of prostate cancer screening. Web-based sites may be effective in facilitating discussions about screening between patients and health care providers.
Keywords: Attitude to Health; Black Persons; Internet; Prostatic Neoplasms; Adult; Aged; Clinical Trials; Decision Making, Computer Assisted; Funding Source; Male; Middle Age; United States; Human

A randomized, double-blind, placebo-controlled study of oral coenzyme Q10 to relieve self-reported treatment-related fatigue in newly diagnosed patients with breast cancer. - Lesser, Glenn J; Case, Doug; Stark, Nancy; Williford, Susan; Giguere, Jeff; Garino, L Astrid; Naughton, Michelle J; Vitolins, Mara Z; Lively, Mark O; Shaw, Edward G (Journal of Supportive Oncology, 2013)
BACKGROUND: Coenzyme Q10 (CoQ10) is a common antioxidant supplement with known cardioprotective effects and potential anticancer benefits. OBJECTIVES: We performed a randomized, double-blind, placebo-controlled study of oral CoQ10 in female breast cancer patients with the primary objective of determining CoQ10's effects on self-reported fatigue, depression, and quality of life (QOL). Methods Eligible women with newly diagnosed breast cancer and planned adjuvant chemotherapy were randomized to oral supplements of 300 mg CoQ10 or placebo, each combined with 300 IU vitamin E, divided into 3 daily doses. Treatment was continued for 24 weeks. Blood tests, QOL measures, and levels of plasma CoQ10 and vitamin E were obtained at baseline and at 8, 16, and 24 weeks. Mixed-effects models were used to assess treatment differences in outcomes over time. RESULTS: Between September 2004 and March 2009, 236 women were enrolled. Treatment arms were well balanced with respect to age (range, 28-85 years), pathologic stage (stage 0, 91%; stage 1, 8%; stage II, 1%), ethnicity (white, 87%; black, 11%; Hispanic, 2%), and planned therapy. Baseline CoQ10 levels in the CoQ10 and placebo arms were 0.70 and 0.73 microg/mL, respectively; the 24-week CoQ10 levels were 1.83 and 0.79 microg/mL, respectively. There were no significant differences between the CoQ10 and placebo arms at 24 weeks for scores on the Profile of Mood States-Fatigue questionnaire (least squares means, 7.08 vs 8.24, P = .257), the Functional Assessment of Chronic Illness Therapy-Fatigue tool (37.6 vs 37.6, P = .965), the Functional Assessment of Cancer Therapy-Breast Cancer instrument (111.9 vs 110.4, P = .577), or the Center for Epidemiologic Studies-Depression scale (11.6 vs 12.3, P = .632). CONCLUSIONS: Supplementation with conventional doses of CoQ10 led to sustained increases in plasma CoQ10 levels but did not result in improved self-reported fatigue or QOL after 24 weeks of treatment.
Keywords: Antineoplastic Agents -- Adverse Effects; Breast Neoplasms -- Complications; Coenzyme Q; Fatigue -- Drug Therapy; Outcome Assessment; Self Report -- Utilization; Vitamins -- Administration and Dosage; Administration, Oral; Adult; Aged; Aged, 80 and Over; Breast Neoplasms -- Diagnosis; Breast Neoplasms -- Drug Therapy; Center for Epidemiological Studies Depression Scale; Coenzyme Q -- Administration and Dosage; Consumer Participation; Dietary Supplements; Double-Blind Studies; Fatigue -- Chemically Induced; Female; Human; Middle Age; Prognosis; Prospective Studies; Psychological Tests; Quality of Life; Questionnaires; Scales

A Randomized, Placebo Controlled Trial of Oral Zinc for Chemotherapy-Related Taste and Smell Disorders. - Lyckholm, Laurel; Heddinger, Steven P.; Parker, Gwendolyn; Coyne, Patrick J.; Ramakrishnan, Viswanathan; Smith, Thomas J.; Henkin, Robert I. (Journal of Pain & Palliative Care Pharmacotherapy, 2012)
Abnormalities in taste and smell are commonly reported in patients receiving chemotherapy and may hinder appetite, dietary intake, nutritional well-being, and quality of life. Oral zinc has been used to treat taste and smell abnormalities in several altered physiologic states, including renal failure, liver disease, head trauma, and pregnancy, with varying results. The authors conducted a double-blinded, placebo-controlled randomized clinic trial over 3 months. Eligible patients were those taking chemotherapy that had alterations in taste and/or smell. The measurement of the primary end point, improvement in altered taste and smell, was made using a 0-100 scale (100 describing no loss or distortion in taste and smell, and 0 describing the worst distortion or loss of taste and smell). Twenty-nine subjects were enrolled in each treatment group, of whom 31 were white, 26 African American, and 1 Native American. Forty-one patients were female. A wide range of cancer types was represented, with breast the most common (21 patients). The zinc dose was 220 mg orally twice daily (equivalent of 50 mg elemental zinc twice daily). There was no statistically significant improvement in loss or distortion of taste or smell with the addition of zinc. There was a trend toward improvement over time in all groups, except in the zinc group where there was a nonsignificant worsening in loss of smell over time. Zinc at standard doses did not provide significant benefit to taste or smell in patients receiving chemotherapy.
Keywords: Zinc -- Administration and Dosage; Administration, Oral; Chemotherapy, Cancer -- Adverse Effects; Taste Disorders -- Drug Therapy; Olfaction Disorders -- Drug Therapy; Neoplasms -- Drug Therapy; Treatment Outcomes; Human; Male; Female; Middle Age; Repeated Measures; Questionnaires; Analysis of Variance; Data Analysis Software; Pilot Studies

A review of intervention studies that seek to increase colorectal cancer screening among African-Americans. - Powe BD; Faulkenberry R; Harmond L; Powe, Barbara D; Faulkenberry, Rachel; Harmond, Lokie (American Journal of Health Promotion, 2010)
Objective: The purpose of this paper is to critically review intervention studies that aimed to increase African-Americans' participation in colorectal cancer (CRC) screening.Data Source: Potential studies were identified using a combination of key words in five computerized databases.Study Inclusion and Exclusion Criteria: Articles were selected if they met all of the inclusion criteria: (1) The study's purpose was to test an intervention to increase CRC screening. (2) At least 50% of the sample was African-American. (3) The study focused on individuals 50 years and older. (4) The study was published between 2000 and 2008.Data Extraction: Abstracts and reference lists were scanned to determine relevance and a copy of the article was obtained.Data Synthesis: Data from each study were extracted and placed in a matrix for synthesis.Results: Interventions focused on recruitment from health care centers, churches, housing projects, and senior centers. Both direct and indirect strategies were used to identify the barriers to CRC screening.Conclusions: Findings suggest that interventions are most successful when they target individuals or communities, address known barriers to screening, deliver tailored messages, use multiple methods of message delivery, and are delivered over multiple time points.
Keywords: Black Persons -- Psychosocial Factors; Colorectal Neoplasms -- Diagnosis; Colorectal Neoplasms -- Ethnology; Health Promotion -- Methods; Colorectal Neoplasms -- Prevention and Control; Community-Institutional Relations; Consumer Participation; Early Detection of Cancer -- Methods; Early Detection of Cancer -- Psychosocial Factors; Human; Experimental Studies; Middle Age; United States

A single mathematical model predicts physicians' recommendations and postmenopausal women's decisions to participate in a clinical trial to prevent breast cancer or coronary heart disease. - Veit CT (Medical Decision Making, 2004)
Few eligible postmenopausal women participate in clinical trial research to prevent breast cancer or coronary heart disease, making it impossible to adequately assess the efficacy of tested interventions for this vulnerable group. To elucidate the causal factors and decision model underlying participation behavior, 180 white, African American, and Hispanic postmenopausal women judged their likelihood of participation in a breast cancer or coronary heart disease prevention clinical trial in scenarios with varied cost/remuneration, perceived risk, doctor's recommendation, and expected toxicity. In addition, 293 white, African American, and Hispanic male and female physicians judged the strength of their participation recommendation in scenarios with varied cost/remuneration, expected toxicity, patient's age, and the source of the information about the clinical trial. An additive and constant-weight-averaging model were rejected. The same configural-weight-range model accounted for judgments in both breast cancer and coronary heart disease scenarios, with different parameter values for each group. According to this model, white and Hispanic women under 70 years of age are most likely to participate, even under somewhat adverse conditions; costs and high toxicity levels act as severe barriers to physicians' positive recommendations and women's participation. Perceived risk was the most important factor for women, yet only 8% and 15% reported ever having received risk information from their doctor for breast cancer and coronary heart disease, respectively. For these two diseases, respectively, 75% and 48% of women rated their risk of the disease as low and 76% and 88% reported they had never heard of a randomized clinical trial or of a prevention clinical trial being conducted. These results have implications for education, information dissemination, and prevention clinical-trial planners.
Keywords: Breast Neoplasms -- Prevention and Control; Cardiovascular Diseases -- Prevention and Control; Decision Making, Patient; Models, Statistical; Physician-Patient Relations; Research Subject Recruitment; Adult; Aged; Aged, 80 and Over; Analysis of Variance; Black Persons; California; Clinical Trials -- Economics; Experimental Studies; Female; Hispanic Americans; Middle Age; Research Instruments; White Persons; Funding Source; Human

A six-month crossover chemoprevention clinical trial of tea in smokers and non-smokers: methodological issues in a feasibility study. - Dash, Chiranjeev; Fung-Lung Chung; Phillips Rohan, Joy Ann; Greenspan, Emily; Christopher, Patrick D.; Makambi, Kepher; Yukihiko Hara; Newkirk, Kenneth; Davidson, Bruce; Adams-Campbell, Lucile L. (BMC Complementary & Alternative Medicine, 2012)
Background: Chemoprevention crossover trials of tea can be more efficient than parallel designs but the attrition and compliance rates with such trials are unknown. Methods: Attrition (dropouts) and compliance with treatment were assessed in a 25-week randomized, placebo controlled, crossover, feasibility clinical trial of four tea treatments to investigate the effect of tea on oral cancer biomarkers. Each treatment lasted 4 weeks with 2 weeks of washout in between. Participants were 32 smokers and 33 non-smokers without any evidence of premalignant oral lesions. The interventions consisted of packets of green tea, black tea, caffeinated water, or placebo. Participants were assigned to each treatment for four weeks, and were instructed to drink five packets per day while on the treatment. Dropout from the trial and compliance (consumption of 85% of the prescribed treatment packets) are the main outcome measures reported. Results: There was a high rate of dropout (51%) from the study, and the rates were significantly higher among smokers (64%) than non-smokers (36%). Among participants who completed the study the rate of compliance was 72%. The highest rates of dropouts occurred between the first and second treatment visits in both smokers (38% dropout) and non-smokers (18% dropout). Throughout the study smokers were more likely to dropout than non-smokers. Black tea treatment was associated with the highest rates of dropout among smokers (37%), but was associated with the lowest rate of dropout among non-smokers (4%). Conclusions: In a study conducted to test the feasibility of a four-treatment crossover tea trial, a high rate of dropout among smokers and non-smokers was observed. Multi-arm crossover tea trials might pose a higher burden on participants and research is needed to improve adherence and treatment compliance in such trials. Trial registration number: ISRCTN70410203
Keywords: Chemoprevention; Tea -- Therapeutic Use; Smoking; Neoplasms -- Symptoms; Biological Markers; Human; Pilot Studies; Crossover Design; Randomized Controlled Trials; Random Assignment; Research Dropouts; Patient Compliance; Descriptive Statistics; Academic Medical Centers; Male; Female; Adolescence; Adult; Middle Age; District of Columbia; Chi Square Test; Fisher's Exact Test; Models, Statistical; Funding Source

A targeted decision aid for the elderly to decide whether to undergo colorectal cancer screening: development and results of an uncontrolled trial. - Lewis CL; Golin CE; DeLeon C; Griffith JM; Ivey J; Trevena L; Pignone M; Lewis, Carmen L; Golin, Carol E; DeLeon, Chris; Griffith, Jennifer M; Ivey, Jena; et al. (BMC Medical Informatics & Decision Making, 2010)
Background: Competing causes of mortality in the elderly decrease the potential net benefit from colorectal cancer screening and increase the likelihood of potential harms. Individualized decision making has been recommended, so that the elderly can decide whether or not to undergo colorectal cancer (CRC) screening. The objective is to develop and test a decision aid designed to promote individualized colorectal cancer screening decision making for adults age 75 and over.Methods: We used formative research and cognitive testing to develop and refine the decision aid. We then tested the decision aid in an uncontrolled trial. The primary outcome was the proportion of patients who were prepared to make an individualized decision, defined a priori as having adequate knowledge (10/15 questions correct) and clear values (25 or less on values clarity subscale of decisional conflict scale). Secondary outcomes included overall score on the decisional conflict scale, and preferences for undergoing screening.Results: We enrolled 46 adults in the trial. The decision aid increased the proportion of participants with adequate knowledge from 4% to 52% (p < 0.01) and the proportion prepared to make an individualized decision from 4% to 41% (p < 0.01). The proportion that preferred to undergo CRC screening decreased from 67% to 61% (p = 0. 76); 7 participants (15%) changed screening preference (5 against screening, 2 in favor of screening)Conclusion: In an uncontrolled trial, the elderly participants appeared better prepared to make an individualized decision about whether or not to undergo CRC screening after using the decision aid.
Keywords: Colonoscopy -- Psychosocial Factors; Colorectal Neoplasms -- Diagnosis; Decision Support Techniques; Health Screening -- Psychosocial Factors; Aged; Aged, 80 and Over; Black Persons -- Psychosocial Factors; Black Persons -- Statistics and Numerical Data; Clinical Trials; Colorectal Neoplasms -- Ethnology; Consent; Disabled -- Psychosocial Factors; Disabled -- Statistics and Numerical Data; Educational Status; Female; Human; Information Literacy; Male; Patient Education; Patient Selection; White Persons -- Psychosocial Factors; White Persons -- Statistics and Numerical Data

A theoretical approach to understanding black men's health-seeking behavior. - Plowden KO (Journal of Theory Construction & Testing, 2003)
Black men are suffering disproportionately from most illnesses. Action is needed to decrease the current health disparity. An important step in decreasing this disparity is to understand social factors that act as motivators and barriers to seeking care. This article examines how social factors influence health-seeking behaviors of Black men using two theoretical frameworks: Leininger's Culture Care Diversity and Universality Theory and the Health Belief Models. By understanding the impact of social factors on health seeking behaviors, nurses can develop appropriate behavioral interventions for Black men.
Keywords: Black Persons; Health Belief Model; Help Seeking Behavior; Leininger's Theory of Culture Care Diversity and Universality; Men's Health; Attitude to Health; Clinical Trials; Health Services Accessibility; Male; Motivation; Prostatic Neoplasms; Research Subjects; Self-Efficacy; Socioeconomic Factors

A trial of 3 interventions to promote colorectal cancer screening in African Americans. - Blumenthal DS; Smith SA; Majett CD; Alema-Mensah E; Blumenthal, Daniel S; Smith, Selina A; Majett, Charlye D; Alema-Mensah, Ernest (Cancer (0008543X), 2010)
Background: Colorectal cancer (CRC) is the second leading cause of cancer death in the United States. CRC incidence and mortality rates are higher among blacks than among whites, and screening rates are lower in blacks than in whites. For the current study, the authors tested 3 interventions that were intended to increase the rate of CRC screening among African Americans.Methods: The following interventions were chosen to address evidence gaps in the Centers for Disease Control and Prevention's Guide to Community Preventive Services: one-on-one education, group education, and reducing out-of-pocket costs. Three hundred sixty-nine African-American men and women aged > or =50 years were enrolled in this randomized, controlled community intervention trial. The main outcome measures were postintervention increase in CRC knowledge and obtaining a screening test within 6 months.Results: There was substantial attrition: Two hundred fifty-seven participants completed the intervention and were available for follow-up 3 months to 6 months later. Among completers, there were significant increases in knowledge in both educational cohorts but in neither of the other 2 cohorts. By the 6-month follow-up, 17.7% (11 of 62 participants) of the Control cohort reported having undergone screening compared with 33.9% (22 of 65 participants) of the Group Education cohort (P = .039). Screening rate increases in the other 2 cohorts were not statistically significant.Conclusions: The current results indicated that group education could increase CRC cancer screening rates among African Americans. The screening rate of <35% in a group of individuals who participated in an educational program through multiple sessions over a period of several weeks indicated that there still are barriers to overcome.
Keywords: Black Persons; Colorectal Neoplasms -- Diagnosis; Colorectal Neoplasms -- Ethnology; Early Detection of Cancer; Patient Education; Aged; Colorectal Neoplasms -- Economics; Continuity of Patient Care; Female; Financing, Organized; Human; Male; Middle Age; Outcome Assessment; Clinical Trials

Accept me for myself: African American women's issues after breast cancer. - Wilmoth MC; Sanders LD (Oncology Nursing Forum, 2001)
PURPOSE/OBJECTIVES: To identify the personal issues and concerns of African American women who are breast cancer survivors. DESIGN: Exploratory. SETTING: Southeastern United States; urban community. SAMPLE: A total of 24 women were recruited from churches and the community; 16 women participated in focus groups. METHODS: Two focus group sessions were held in a community library. Audiotaped interviews were transcribed and analyzed for themes that described issues the women had to deal with after treatment for breast cancer. MAIN RESEARCH VARIABLE: Women's perceptions of the impact breast cancer had placed on their personal lives, including sexuality. FINDINGS: Five themes emerged-body appearance, social support, health activism, menopause, and learning to live with a chronic illness. CONCLUSIONS: African American women have concerns that are similar to, but different from, those of Caucasian women. Further research is needed to identify culturally appropriate care. IMPLICATIONS FOR NURSING PRACTICE: Assess the effects of treatment on women's personal lives. Know where women can purchase prostheses that match their skin tones. Refer minority women to support groups specifically designed for them.
Keywords: Breast Neoplasms -- Psychosocial Factors; Black Persons -- Southeastern United States; Exploratory Research; Southeastern United States; Focus Groups; Thematic Analysis; Research Subject Recruitment; Content Analysis; Cancer Patients; Pilot Studies; Adult; Middle Age; Aged; Female; Funding Source; Human

Accreditation and quality assurance for Radiation Therapy Oncology Group: Multicenter clinical trials using Stereotactic Body Radiation Therapy in lung cancer. - Timmerman R; Galvin J; Michalski J; Straube W; Ibbott G; Martin E; Abdulrahman R; Swann S; Fowler J; Choy H (Acta Oncologica, 2006)
Starting in 2002, the Radiation Therapy Oncology Group in North America began the process of developing multicenter prospective trials in lung cancer using Stereotactic Body Radiation Therapy (SBRT). Much of the work was based on the prospective single institution trials from Indiana University that had been presented and published. In late 2004, RTOG 0236 using SBRT for medically inoperable patients with clinical stage I non-small cell lung cancer (NSCLC) was activated for accrual. Prior to activation, representatives from the Lung, Image-Guided Therapy, Physics, and Radiobiology Committees met on regular occasions to design the multicenter study and quality assurance measures. SBRT is not a black box, and the essence of the therapy had to be distilled via guidelines. Issues related to patient selection, method of dosimetry construction, equipment requirements, motion assessments and control, site accreditation, data exchange, and follow-up policies were worked out by compromise and consensus. RTOG 0236 has nearly completed its accrual. The Lung Committee has initiated the development of several other trials, each building on the last, to investigate the therapy in central tumors, in combinations with systemic therapy, in operable patients, and in lung metastases patients. The guidelines developed for RTOG 0236 will be refined to take advantage of more modern innovations including heterogeneity corrections and intensity modulation when appropriate. The development of RTOG 0618 using SBRT in operable patients with early stage NSCLC is a testament to both the enthusiasm from already published works and prospective multicenter clinical testing using SBRT techniques.
Keywords: Accreditation -- Administration; Carcinoma -- Surgery; Clinical Trials -- Methods; Lung Neoplasms -- Surgery; Multicenter Studies -- Methods; Oncology; Quality Assurance -- Administration; Radiosurgery -- Methods; Carcinoma -- Pathology; Lung Neoplasms -- Pathology; Motion; Phantoms, Imaging; Radiation Dosage; Radiometry; Radiotherapy -- Methods

Addressing Breast Cancer Health Disparities in the Mississippi Delta Through an Innovative Partnership for Education, Detection, and Screening. - Mayfield-Johnson, Susan; Fastring, Danielle; Fortune, Melody; White-Johnson, Freddie (Journal of Community Health, 2016)
Projects to reduce disparities in cancer treatment and research include collaborative partnerships and multiple strategies to promote community awareness, education, and engagement. This is especially needed in underserved areas such as the Mississippi Delta where more women are diagnosed at regional and distant stages of breast cancer. The purpose for this project was to increase the relatively low screening rate for African American women in the Mississippi Delta through a partnership between the Mississippi Network for Cancer Control and Prevention at The University of Southern Mississippi, The Fannie Lou Hamer Cancer Foundation and the Mississippi State Department of Health to decrease health disparities in breast cancer through increased awareness on self-early detection methods, leveraging resources to provide mammography screenings, and adequate follow-up with services and treatment for abnormal findings. Through this collaborative effort, over 500 women in three rural Mississippi Delta counties were identified, provided community education on early self-detection, and given appointments for mammography screenings within one fiscal year.
Keywords: Healthcare Disparities -- Mississippi; Medically Underserved Area -- Mississippi; Breast Neoplasms -- Prevention and Control -- Mississippi; Cancer Screening -- Mississippi; Black Persons -- Mississippi; Community Health Workers -- Mississippi; Health Education -- Mississippi; Human; Mississippi; Foundations; Interinstitutional Relations; Research Subject Recruitment; Female; Adult; Middle Age; Questionnaires; Descriptive Statistics; Mammography -- Utilization; Health Knowledge -- Evaluation; Health Services Accessibility; Socioeconomic Factors; Convenience Sample; Collaboration; Experimental Studies; Funding Source

Addressing Patient Emotional and Existential Needs During Serious Illness: Results of the Outlook Randomized Controlled Trial. - Stechuchak, Karen M.; Zervakis, Jennifer; Steinhauser, Karen E.; Olsen, Maren K.; Tulsky, James A.; Alexander, Stewart; Ammarell, Natalie; Byock, Ira (Journal of Pain & Symptom Management, 2017)
Context: Few interventions exist to address patients' existential needs.Objectives: Determine whether an intervention to address seriously ill patients' existential concerns improves preparation, completion (elements of quality of life [QOL] at end of life), and reduces anxiety and depression.Methods: A randomized controlled trial comparing outlook intervention, relaxation meditation (RM), and usual care (UC). Measures included primary-a validated measure of QOL at the end of life and secondary-Functional Assessment of Cancer Therapy-General, anxiety (Profile of Mood States), depression (Center for Epidemiological Studies-Depression Scale), and spiritual well-being (Functional Assessment of Chronic Illness Therapy-Spiritual Well-Being). Qualitative interviews assessed outlook intervention acceptability. Enrolled patients were nonhospice eligible veterans with advanced cancer, congestive heart failure, chronic obstructive pulmonary disease, end-stage renal disease, or end-stage liver disease.Results: Patients (n = 221) were randomly assigned 1:1:1 to outlook, RM, and UC. Patients were 96% males, 46% with cancer, 58.4% married, and 43.9% of African American origin. Compared with UC, outlook participants had higher preparation (a validated measure of QOL at the end of life) (mean difference 1.1; 95% CI 0.2, 2.0; P = 0.02) and mean completion (1.6; 95% CI 0.05, 3.1; P = 0.04) at the first but not second postassessment. Compared with RM, outlook participants did not show significant differences over time. Exploratory analyses indicated that in subgroups with cancer and low sense of peace, outlook participants had improved preparation at first and not second postassessment, as compared with UC (mean difference 1.4; 95% CI 0.03, 2.7; P = 0.04) (mean difference = 1.8; 95% CI 0.3, 3.3; P = 0.02), respectively.Conclusion: Outlook had an impact on social well-being and preparation compared with UC. The lack of impact on anxiety and depression differs from previous results among hospice patients. Results suggest that outlook is not demonstratively effective in populations not experiencing existential or emotional distress.
Keywords: Critical Illness -- Psychosocial Factors; Emotions; Palliative Care -- Methods; Philosophy; Interviews; Female; Aged; Prospective Studies; Relaxation Techniques; Anxiety; Spirituality; Human; Male; Quality of Life; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Clinical Assessment Tools; Center for Epidemiological Studies Depression Scale; Scales; Psychological Tests

Addressing social determinants of health to improve access to early breast cancer detection: results of the Boston REACH 2010 Breast and Cervical Cancer Coalition Women's Health Demonstration Project. - Clark CR; Baril N; Kunicki M; Johnson N; Soukup J; Ferguson K; Lipsitz S; Bigby J (Journal of Women's Health (15409996), 2009)
BACKGROUND: The Boston Racial and Ethnic Approaches to Community Health (REACH) 2010 Breast and Cervical Cancer Coalition developed a case management intervention for women of African descent to identify and reduce medical and social obstacles to breast cancer screening and following up abnormal results. METHODS: We targeted black women at high risk for inadequate cancer screening and follow-up as evidenced by a prior pattern of missed clinic appointments and frequent urgent care use. Case managers provided referrals to address patient-identified social concerns (e.g., transportation, housing, language barriers), as well as navigation to prompt screening and follow-up of abnormal tests. We recruited 437 black women aged 40-75, who received care at participating primary care sites. The study was conducted as a prospective cohort study rather than as a controlled trial and evaluated intervention effects on mammography uptake and longitudinal screening rates via logistic regression and timely follow-up of abnormal tests via Cox proportional hazards models. RESULTS: A significant increase in screening uptake was found (OR 1.53, 95% CI 1.13-2.08). Housing concerns (p < 0.05) and lacking a regular provider (p < 0.01) predicted poor mammography uptake. Years of participation in the intervention increased odds of obtaining recommended screening by 20% (OR 1.20, 95% CI 1.02-1.40), but this effect was attenuated by covariates (p = 0.53). Timely follow-up for abnormal results was achieved by most women (85%) but could not be attributed to the intervention (HR 0.95, 95% CI 0.50-1.80). CONCLUSIONS: Case management was successful at promoting mammography screening uptake, although no change in longitudinal patterns was found. Housing concerns and lacking a regular provider should be addressed to promote mammography uptake. Future research should provide social assessment and address social obstacles in a randomized controlled setting to confirm the efficacy of social determinant approaches to improve mammography use.
Keywords: Cancer Screening; Case Management -- Utilization; Patient Compliance; Socioeconomic Factors; Women's Health Services -- Massachusetts; Adult; Aged; Black Persons; Breast Neoplasms -- Prevention and Control; Chi Square Test; Coalition; Confidence Intervals; Correlational Studies; Cox Proportional Hazards Model; Descriptive Statistics; Fisher's Exact Test; Funding Source; Health Services Accessibility; Housing; Linear Regression; Logistic Regression; Mammography -- Utilization; Massachusetts; Middle Age; Odds Ratio; Outcomes Research; Primary Health Care; Prospective Studies; Questionnaires; Record Review; Rescreening; Human

Adherence to American Cancer Society and American Institute of Cancer Research dietary guidelines in overweight African American breast cancer survivors. - Springfield, Sparkle; Odoms-Young, Angela; Tussing-Humphreys, Lisa; Freels, Sally; Stolley, Melinda (Journal of Cancer Survivorship, 2019)
Purpose: The American Cancer Society (ACS) and the American Institute for Cancer Research (AICR) each created dietary and physical activity guidelines to improve cancer survivorship. Despite African American breast cancer survivors (AABCS) having the lowest survival rates of any racial or ethnic group, limited information exists on their adherence to cancer-specific lifestyle recommendations. The study's purpose was to measure adherence to ACS/AICR dietary recommendations in AABCS.Methods: Two hundred ten AABCS enrolled in the Moving Forward intervention trial, a randomized, community-based, 6-month weight loss study, were assessed for socio-demographics, dietary intake (via food frequency questionnaire), and related health factors at baseline. We operationalized the dietary recommendations put forth by ACS/AICR and created component and total adherence index scores. Descriptive statistics were used to calculate the proportion of women who met recommendations. Student's t test and χ2 tests were used to compare participant characteristics by median adherence scores.Results: The mean total ACS/AICR score was 12.7 ± 2.5 out of 21 points (median, 13; range, 5 to 21). Over 90% were moderately or completely adherent to limiting alcohol and red & processed meat consumption, but the majority failed to meet the other recommendations to eat whole grains, legumes, fruits, vegetables, and avoid added sugars. Women with total scores below the median were younger, with higher BMI, had fewer years of education, and lower income levels.Implications For Cancer Survivors: The present study extends the literature on AABCS adherence to cancer survivor-specific dietary guidelines. Findings will inform future dietary lifestyle interventions in this population.
Keywords: Black Persons -- Statistics and Numerical Data; Breast Neoplasms -- Rehabilitation; Obesity -- Diet Therapy; Nutrition Policy; Patient Compliance; Breast Neoplasms -- Complications; Obesity -- Complications; Human; Breast Neoplasms -- Diet Therapy; Life Style; Obesity -- Ethnology; American Cancer Society; Middle Age; Aged; Breast Neoplasms -- Ethnology; Weight Reduction Programs -- Standards; Exercise; Behavior; Diet; Medical Organizations -- Standards; Female; United States; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Questionnaires

Adherence to screening guidelines for breast and cervical cancer in postmenopausal women with coronary heart disease: an ancillary study of volunteers for HERS. - Castellano PZ; Wenger NK; Graves WL (Journal of Women's Health & Gender-Based Medicine, 2001)
Postmenopausal women with coronary heart disease (CHD) who volunteered for the Heart and Estrogen/Progestin Replacement Study (HERS) randomized clinical trial had high rates of gynecological abnormalities. We examined compliance with gynecological cancer screening and factors affecting this behavior. Women who met inclusion criteria for HERS and were seen for screening by the study gynecologist were considered eligible for this study. Data were abstracted from study records, and additional information was obtained by telephone questionnaire. Adherence to mammography, breast examination, pelvic examination, and Pap smear recommendations was assessed. Provider behavior and its effect on compliance were assessed. Compliance rates were 59.1% for monthly breast self-examination (BSE), 67.2% for yearly mammography, 73% for yearly Pap smear and pelvic examination, and 75.7% for provider breast examination. Over 50% of patients had most of their screening tests done within the last year. Provider behavior was significantly related to patient screening compliance for mammography, breast examination, Pap smear, and pelvic examination. Provider gender was not significantly related to adherence. There were no significant differences in compliance rates based on the type of most recent coronary event. Compliance rates did not differ significantly between patients with and without gynecological abnormalities, except for mammography (78.3% versus 48.3%, p = 0.02). The majority of patients were compliant with gynecological screening. Among patients with gynecological abnormalities, mammography compliance was significantly lower. Provider behavior was an important factor in influencing women to obtain preventive screening. There were no significant differences in compliance based on provider gender or type of coronary event preceding HERS enrollment.
Keywords: Breast Neoplasms -- Prevention and Control; Cervix Neoplasms -- Prevention and Control; Coronary Disease; Health Behavior; Patient Compliance; Postmenopause; Female; Male; Middle Age; Aged; Breast Self-Examination; Georgia; Mammography; Medical Records; Questionnaires; Cervical Smears; Women's Health; Data Analysis Software; Clinical Trials; T-Tests; Chi Square Test; Descriptive Statistics; Black Persons; White Persons; Funding Source; Human

Adherence to World Cancer Research Fund/American Institute for Cancer Research Lifestyle Recommendations Reduces Prostate Cancer Aggressiveness Among African and Caucasian Americans. - Arab, Lenore; Su, Joseph; Steck, Susan E.; Ang, Alfonso; Fontham, Elizabeth T. H.; Bensen, Jeannette T.; Mohler, James L. (Nutrition & Cancer, 2013)
The effect of adherence to the World Cancer Research Fund (WCRF) lifestyle recommendations on cancer aggressiveness is unknown. We examined associations between adherence to recommendations and risk of highly aggressive prostate cancer in research subjects enrolled in the North Carolina-Louisiana Prostate Cancer Project (PCaP). We examined associations between adherence to WCRF recommendations and risk of highly aggressive prostate cancer among 2212 newly diagnosed African Americans (AA) or Caucasian Americans (CA) aged 40–70 years in PCaP. Prostate cancer aggressiveness was based on Gleason scores, serum prostate-specific antigens, and TNM stage. Adherence to WCRF recommendations was based on point scores and odds ratios estimated. Results showed that adherence to recommendations was significantly and negatively associated with risk of a highly aggressive prostate cancer. Each additional point in the total adherence score corresponded to a 13% risk reduction. Total adherence score <4 predicted increased risk in both AA (OR = 1.36; 95% CI = 1.01–1.85) and CA (OR = 1.41; 95% CI = 1.01–1.98). Consumption of <500 g red meat per week or ≤125 total kcal/100 g solid food per day is a statistically significant protective factor in the overall cohort. Recommendations aimed at preventing all cancers also may reduce risk of highly aggressive prostate cancer.
Keywords: Practice Guidelines; Medical Organizations; Prostatic Neoplasms -- Prevention and Control; Nutrition; Africa; Black Persons; White Persons; Race Factors; Academic Medical Centers; Life Style Changes; Reports; Patient Selection; Consent; Food Intake -- Evaluation; Body Mass Index -- Evaluation; Demography; Male; Data Analysis; T-Tests; Patient Compliance; Middle Age; Education; Descriptive Statistics; Smoking -- Evaluation; Diet -- Evaluation; Human

Adoption, reach, and implementation of a cancer education intervention in African American churches. - Santos, Sherie Lou Zara; Tagai, Erin K.; Scheirer, Mary Ann; Bowie, Janice; Haider, Muhiuddin; Slade, Jimmie; Min Qi Wang; Holt, Cheryl L.; Wang, Min Qi (Implementation Science, 2017)
Background: Use of technology is increasing in health promotion and has continued growth potential in intervention research. Guided by the Reach, Effectiveness, Adoption, Implementation, ﻿and Maintenance (RE-AIM) framework, this paper reports on the adoption, reach, and implementation of Project HEAL (Health through Early Awareness and Learning)-a community-based implementation trial of a cancer educational intervention in 14 African American churches. We compare adoption, reach, and implementation at the organizational and participant level for churches in which lay peer community health advisors (CHAs) were trained using traditional classroom didactic methods compared with a new online system.Methods: Fifteen churches were randomized to one of two study groups in which two CHAs per church were trained through either classroom ("Traditional"; n = 16 CHAs in 8 churches) or web-based ("Technology"; n = 14 CHAs in 7 churches) training methods. Once trained and certified, all CHAs conducted a series of three group educational workshops in their churches on cancer early detection (breast, prostate, and colorectal). Adoption, reach, and implementation were assessed using multiple data sources including church-level data, participant engagement in the workshops, and study staff observations of CHA performance.Results: The project had a 41% overall adoption rate at the church level. In terms of reach, a total of 375 participants enrolled in Project HEAL-226 participants in the Traditional group (43% reach) and 149 in the Technology group (21% reach; p < .10). Implementation was evaluated in terms of adherence, dosage, and quality. All churches fully completed the three workshops; however, the Traditional churches took somewhat longer (M = 84 days) to complete the workshop series than churches in the Technology group (M = 64 days). Other implementation outcomes were comparable between both the Traditional and Technology groups (p > .05).Conclusions: Overall, the Project HEAL intervention had reasonable adoption, though reach could have been better. Implementation was strong across both study groups, suggesting the promise of using web-based methods to disseminate and implement evidence-based interventions in faith-based settings and other areas where community health educators work to eliminate health disparities.
Keywords: Health Education -- Methods; Health Promotion -- Methods; Neoplasms -- Therapy; Neoplasms -- Prevention and Control; Religion and Medicine; Black Persons; Female; Male; Neoplasms -- Diagnosis; Attitude to Health; Cluster Analysis; Aged; Adult; Middle Age; Human; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Funding Source

African American couples merging strengths to successfully cope with breast cancer. - Morgan PD; Fogel J; Rose L; Barnett K; Mock V; Davis BL; Gaskins M; Brown-Davis C (Oncology Nursing Forum, 2005)
PURPOSE/OBJECTIVES: To explore the process of coping with breast cancer among African American women and their spouses. DESIGN: Exploratory, qualitative study using grounded theory methods. SETTING: Large metropolitan area in the mid-Atlantic United States. SAMPLE: 12 African American couples (N = 24). METHODS: African American women and their spouses were asked to complete a background data sheet and participate in a face-to-face semistructured interview. Qualitative data were audiotaped and transcribed verbatim. Themes were identified using the constant comparative method. Quantitative data were analyzed with descriptive statistics. MAIN RESEARCH VARIABLES: The process of coping with breast cancer among African American couples. FINDINGS: The basic social concern was living through and beyond a breast cancer diagnosis. The core variable was merging strengths to cope with and survive a breast cancer diagnosis. Six main categories emerged to describe how African American couples actively worked together to cope with a breast cancer diagnosis: walking together, praying together, seeking together, trusting together, adjusting together, and being together. CONCLUSIONS: African American couples described the importance of combining their strengths and working together as a couple to cope with a breast cancer diagnosis. IMPLICATIONS FOR NURSING: Nurses must understand the importance of developing culturally sensitive and culturally relevant interventions to assist African American couples with effectively coping with a breast cancer diagnosis. When providing care to African American couples, nurses should incorporate the six categories of walking, praying, seeking, trusting, adjusting, and being together to help couples cope with the various phases of the breast cancer experience.
Keywords: Black Persons -- Mid Atlantic Region; Breast Neoplasms -- Psychosocial Factors; Cancer Patients -- Psychosocial Factors; Family Coping; Marriage; Spouses -- Psychosocial Factors; Audiorecording; Coding; Constant Comparative Method; Data Analysis Software; Descriptive Statistics; Exploratory Research; Female; Funding Source; Grounded Theory; Interview Guides; Male; Mid Atlantic Region; Middle Age; Purposive Sample; Qualitative Studies; Research Subject Recruitment; Semi-Structured Interview; Spirituality; Support, Psychosocial; Thematic Analysis; Theoretical Sample; Trust; Uncertainty; Human

African American women's breast memories, cancer beliefs, and screening behaviors. - Thomas EC (Cancer Nursing, 2004)
African American women experience higher breast cancer mortality and lower survival rates compared with white women of comparable age and cancer stage. The literature is lacking in studies that address the influence of past events on current health behaviors among women of diverse cultural groups. This qualitative exploratory study used participant narratives to examine associations between women's memories and feelings concerning their breasts and current breast cancer screening behaviors. Twelve professional African American women, aged 42 to 64 years, shared stories about memories and feelings regarding their breasts. Codes grouped together with related patterns and recurrences revealed categories that encompassed the language and culture of the participants. The categories identified were Seasons of Breast Awareness, Womanhood, Self-Portraits, Breast Cancer and Cancer Beliefs, Breast Cancer Screening Experiences, and Participants' Advice for Change. These categories provide direction for further exploration of barriers to health promotion practices among African American women and women in general.
Keywords: Black Persons -- United States; Breast Neoplasms -- Diagnosis; Cancer Screening; Health Behavior -- Evaluation; Health Beliefs -- Evaluation; Adult; Audiorecording; Culture; Data Analysis Software; Diaries; Exploratory Research; Female; Feminist Critique; Field Notes; Focus Groups; Funding Source; Interviews; Language; Memory; Middle Age; Midwestern United States; Narratives -- Evaluation; Patient Attitudes -- Evaluation; Purposive Sample; Qualitative Studies; Research Subject Recruitment; Sociological Theory; Thematic Analysis; United States; Human

African American Women's Perspectives on Donating Healthy Breast Tissue for Research: Implications for Recruitment. - Ridley-Merriweather, Katherine E.; Head, Katharine J. (Health Communication, 2017)
African American women die of breast cancer at a higher rate than any other racial group. The Komen Tissue Bank (KTB) is an ongoing clinical trial that collects healthy breast tissue from women of all racial groups to use as controls in research and represents a critical tool in efforts to treat and prevent breast cancer; however, African Americans display reticence toward donating breast tissue to the KTB. Through the lens of the Integrated Behavioral Model, this study recruited African American women to share their perspectives on donating breast tissue for research purposes. Seventy-one (N = 71) eligible Black women who were previous tissue donors to the KTB responded to an online questionnaire. Findings revealed that (a) participants had positive instrumental attitudes or reasons for donating; (b) participants felt generally supported in their decision to donate, but revealed that the lack of Black women participating in the KTB meant that they themselves were setting the norm for others; and (c) their race was an important element in their donation decision. While acknowledging the negative history of African Americans in medical research, they offered their perceptions regarding the importance of involving themselves in medical research, and suggested that health communication strategies to recruit African Americans into research should embrace race as part of the message. The findings from this study have important implications for other those who work in applied clinical settings and are interested in addressing racial disparities in medical research through more effective and targeted recruitment messaging.
Keywords: Black Persons; Consumer Attitudes; Breast Neoplasms -- Prevention and Control; Living Donors; Human; Female; Models, Theoretical; Questionnaires; World Wide Web; Race Factors; Research, Medical; Data Analysis Software; Coding; Constant Comparative Method; Qualitative Studies; Thematic Analysis; Accountability

African American Women's Recollected Experiences of Adherence to Breast Cancer Treatment. - Heiney, Sue P.; Messias, DeAnne K. Hilfinger; Felder, Tisha M.; Phelps, Kenneth W.; Quinn, Jada C. (Oncology Nursing Forum, 2017)
Purpose/Objectives: To explore African American women's recollected experiences of breast cancer treatment. Research Approach: Qualitative description and narrative analysis. Setting: South Carolina Oncology Associates, an outpatient oncology clinic serving rural and urban populations. Participants: 16 African American women with breast cancer previously enrolled in the control arm (n = 93) of a completed randomized, controlled trial. Methodologic Approach: Feminist narrative analysis of in-depth individual interviews. Findings: The authors identified three themes within the African American breast cancer survivors' recollected experiences of treatment adherence: Embarking With Trust, Moving on Down the Road, and Being Actively Involved in Decision Making. Interpretation: Although little evidence was presented of shared decision making with providers, patients were committed to completing the prescribed therapies. The narratives highlighted the value of in-depth examination of patients' perspectives, particularly among minority and underserved groups. With the exception of voicing personal choice of surgical treatment, the women trusted providers' recommendations with a resolve to "just do it." Although trust may enhance treatment adherence, it may also reflect power differentials based on gender, race, education, and culture. Implications for Nursing: Nurses should listen to patients describe their experience with cancer treatment and compare the themes from this study with their patients' story. This comparison will help nurses support patients through various aspect of diagnosis and treatment.
Keywords: Black Persons -- United States; Cancer Patients; Patient Compliance; Breast Neoplasms -- Therapy; Qualitative Studies; Narratives -- Evaluation; Decision Making; Feminist Critique; Human; Semi-Structured Interview; Thematic Analysis; Trust; Rural Population; South Carolina; Survivors; Professional-Patient Relations; Urban Population; Interview Guides; United States; Descriptive Research; Patient Attitudes -- Evaluation; Multidisciplinary Care Team; Research Subject Recruitment; Female; Adult; Middle Age; Aged; Field Notes; Funding Source

African-American breast cancer survivors' preferences for various types of physical activity interventions: a Sisters Network Inc. web-based survey. - Paxton, Raheem J; Nayak, Pratibha; Taylor, Wendell C; Chang, Shine; Courneya, Kerry S; Schover, Leslie; Hodges, Kelly; Jones, Lovell A (Journal of Cancer Survivorship, 2014)
Background: Needs assessments are essential to developing lifestyle interventions for minority populations. To our knowledge, no physical activity (PA) needs assessment studies have been conducted for African-American (AA) breast cancer survivors. The purpose of this study was to determine the PA intervention preferences of AA breast cancer survivors and determine whether these preferences differ according to medical and sociodemographic factors.Methods: AA breast cancer survivors (n = 475, mean age = 54 years) were recruited using ads sent via email and social media sites. Preferences for the mode of intervention delivery were assessed via web-based questionnaires. Descriptive statistics were used to characterize their interests in PA interventions, and subgroup differences were assessed.Results: About 49 % (142 out of 291) of the participants who completed the survey were obese and 54 % did not meet the recommended guidelines for PA. Most (90 %) participants reported that they could participate in PA, and many (67 %) indicated that they were interested in receiving program materials. Participants expressed the greatest interest in email (50 %)-, web (48 %)-, or mail-based (45 %) over group (39 %), and telephone (10 %). Women also expressed the greatest interest in participating in studies that promoted walking and resistance or strength training. Intervention preferences did not differ significantly (P > 0.05) across sociodemographic or medical factors.Conclusion: Most AA breast cancer survivors can participate in PA, and many are interested in interventions that promoted walking and resistance training and were delivered via the email or web. The development of culturally sensitive interventions that provide activities consistent with preferences can assist AA breast cancer survivors to adopt and maintain a healthy lifestyle.Implications For Cancer Survivors: Despite evidence that AA breast cancer survivors are at increased risk for poor breast cancer-specific outcomes, they are underrepresented in clinical trials promoting positive health behaviors. In this study, we propose to assess their exercise preferences and receptivity to a culturally appropriate PA intervention developed in collaboration with the Sisters Network Inc. Health promotion programs developed in collaboration with a community-based organization may aid in the development of research tools and resources that AA breast cancer survivors are receptive to using.
Keywords: Black Persons -- Psychosocial Factors; Breast Neoplasms -- Psychosocial Factors; Health Services Needs and Demand; Motor Activity; Patient Education -- Methods; Patient Satisfaction; Survivors -- Psychosocial Factors; Adult; Aged; Breast Neoplasms -- Therapy; CD ROM; Comorbidity; Data Collection; Email; Female; Habits; Human; Internet; Life Style; Middle Age; Obesity -- Epidemiology; Obesity -- Psychosocial Factors; Pamphlets; Practice Guidelines; Quality of Life; Questionnaires; Resistance Training; Life Style, Sedentary; Telephone; Texas

African-American women's perspectives on research participation. - Lillington L; Johnson I; Chlebowski R (Medicine of the Americas, 2000)
Eight focus groups (N=45) led by an experienced investigator were used to explore African-American women's beliefs and attitudes about breast health, breast cancer, breast cancer prevention, medical research and ways to communicate information about research to the African-American community. Content analysis of session transcripts revealed at least six emerging themes concerning research participation: 1) importance of informed consent; 2) lack of understanding regarding the placebo concept, which was viewed as 'unfair' treatment; 3) distrust of the research process; 4) importance of medical research as a way to help others and increase knowledge 'if used properly;' 5) importance of reimbursing participants for their time and costs; and 6) the perception that research is for people who have the disease, not for healthy people, with participation possibly leading to development of the disease.Major themes related to breast cancer prevention included: 1) awareness of breast cancer risk factors limited to family history; 2) confusion about the difference between screening and prevention; 3) perceived low susceptibility to breast cancer; and 4) fatalistic view of breast cancer outcome.These results identify unique aspects of the African-American view of medical research and breast cancer prevention that have important implications for developing culturally relevant strategies to increase recruitment in cancer prevention trials and participation in breast cancer risk reduction.
Keywords: Research Subjects; Breast Neoplasms -- Psychosocial Factors; Black Persons; Focus Groups; Female; Adult; Middle Age; Aged; Aged, 80 and Over; Health Beliefs; Audiorecording; Videorecording; Content Analysis; Health Knowledge; Research Subject Recruitment; Denial (Psychology); Funding Source; Human

An evaluation of a community-academic-clinical partnership to reduce prostate cancer disparities in the South. - Friedman, Daniela B; Owens, Otis L; Jackson, Dawnyea D; Johnson, Kim M; Gansauer, Lucy; Dickey, Joe; Miller, Ron; Payne, Johnny; Bearden, James D; Hebert, James R (Journal of Cancer Education, 2014)
Engaging partners in the planning, implementation, and evaluation of cancer education programs is critical for improving the health of our communities. A 2-year pilot education intervention on prostate cancer decision making and participation in medical research was funded by the National Cancer Institute. The partnership involving community members and clinical staff at a cancer center was used to develop recruitment strategies and plan for the implementation of the intervention with African-American middle-age and older men and female family members. We assessed partners' perceptions of this community-academic-clinical research collaboration. In year 2, eight project advisory council members were selected among existing partners and year 1 participants to serve as a formal committee. Council members were required to participate in telephone and in person meetings and actively support recruitment/implementation efforts. At the conclusion of the project, 20 individuals (all clinical and community partners, including the eight advisory council members) were invited to complete a survey to assess their perceived impact of the collaboration on the community and provide suggestions for future collaborations. Most partners agreed that their organization benefitted from the collaboration and that various aspects of the advisory council process (e.g., both formal and informal communication) worked well. The most noted accomplishment of the partnership related to leveraging the collaboration to make men more knowledgeable about prostate cancer decision making. Suggested improvements for future collaborations included distributing more frequent updates regarding project successes. Evaluating partners' perceptions of this collaboration provided important recommendations for future planning, implementation, and evaluation of community-based cancer education programs.
Keywords: Academic Medical Centers -- Administration; Community Networks -- Administration; Cooperative Behavior; Health Education; Health Services Accessibility; Healthcare Disparities; Prostatic Neoplasms -- Prevention and Control; Human; Male; Pilot Studies; Prognosis; Prostatic Neoplasms -- Ethnology; South Carolina

Association of Sociodemographic and Health-Related Factors With Receipt of Nondefinitive Therapy Among Younger Men With High-Risk Prostate Cancer. - Bagley, Alexander F.; Anscher, Mitchell S.; Choi, Seungtaek; Frank, Steven J.; Hoffman, Karen E.; Kuban, Deborah A.; McGuire, Sean E.; Nguyen, Quynh-Nhu; Chapin, Brian; Aparicio, Ana; Pezzi, Todd A.; Smith, Grace L.; et al. (JAMA Network Open, 2020)
Key Points: Question: What factors are associated with the receipt of nondefinitive therapy and survival among patients aged 70 years and younger who are diagnosed with high-risk prostate cancer? Findings: In this cohort study of 72 036 patients aged 70 years and younger with high-risk prostate cancer entered in the National Cancer Database, we found that 7.3% of patients received nondefinitive therapy; moreover, receipt of nondefinitive therapy was associated with inferior overall survival. Insurance status and race/ethnicity were independently associated with receipt of nondefinitive therapy. Meaning: The findings of this study suggest that significant barriers to life-extending treatment options for younger patients with high-risk prostate cancer remain. This cohort study identifies sociodemographic and health-related factors associated with receipt of nondefinitive therapy among patients aged 70 years and younger with high-risk prostate cancer. Importance: Multiple randomized clinical trials have shown that definitive therapy improves overall survival among patients with high-risk prostate cancer. However, many patients do not receive definitive therapy because of sociodemographic and health-related factors. Objective: To identify factors associated with receipt of nondefinitive therapy (NDT) among patients aged 70 years and younger with high-risk prostate cancer. Design, Setting, and Participants: This cohort study identified 72 036 patients aged 70 years and younger with high-risk prostate cancer and Charlson Comorbidity Index scores of 2 or less who were entered in the National Cancer Database between January 2004 and December 2014. Data analysis was conducted from November 2018 to December 2019. Exposure: Receipt of NDT as an initial treatment approach. Main Outcomes and Measures: Survival rates were compared based on receipt of definitive therapy or NDT, and sociodemographic and health-related factors were associated with the type of therapy received. Residual life expectancy was estimated from the National Center for Health Statistics to calculate person-years of life lost. Results: A total of 72 036 men with a median (range) age of 63 (30-70) years, Charlson Comorbidity Index scores of 2 or less, and high-risk prostate cancer without regional lymph node or distant metastatic disease were analyzed. Among eligible patients, 5252 (7.3%) received NDT as an initial therapeutic strategy. On univariate and multivariate analyses, NDT was associated with worse overall survival (univariate analysis hazard ratio, 2.54; 95% CI, 2.40-2.69; P <.001; multivariate analysis hazard ratio, 2.40; 95% CI, 2.26-2.56; P <.001). Compared with patients with private insurance or managed care, those with no insurance, Medicaid, or Medicare were more likely to receive systemic therapy only (no insurance: odds ratio [OR], 3.34; 95% CI, 2.81-3.98; P <.001; Medicaid: OR, 2.92; 95% CI, 2.48-3.43; P <.001; Medicare: OR, 1.36; 95% CI, 1.20-1.53; P <.001) or no treatment (no insurance: OR, 2.63; 95% CI, 2.24-3.08; P <.001; Medicaid: OR, 1.71; 95% CI, 1.45-2.01; P <.001; Medicare: OR, 1.14; 95% CI, 1.04-1.24; P =.004). Compared with white patients, black patients were more likely to receive systemic therapy only (OR, 1.93; 95% CI, 1.74-2.14; P <.001) or no treatment (OR, 1.46; 95% CI, 1.32-1.61; P <.001), and Hispanic patients were more likely to receive systemic therapy only (OR, 1.36; 95% CI, 1.13-1.64; P =.001) or no treatment (OR, 1.36; 95% CI, 1.14-1.60; P <.001). Between 2004 and 2014, patients without insurance or enrolled in Medicaid had 1.83-fold greater person-years of life lost compared with patients with private insurance (area under the curve, 77 600 vs 42 300 person-years of life lost). Conclusions and Relevance: In this study, receipt of NDT was associated with insurance status and race/ethnicity. While treatment decisions should be individualized for every patient, younger men with high-risk prostate cancer and minimal comorbidities should be encouraged to receive definitive local therapy regardless of other factors. These data suggest that significant barriers to life-extending treatment options for patients with prostate cancer remain.
Keywords: Men's Health; Prostatic Neoplasms -- Therapy; Prostatic Neoplasms -- Psychosocial Factors; Social Determinants of Health; Insurance, Health; Human; Male; Aged; Prospective Studies; Clinical Assessment Tools; Survival Analysis; Adult; Middle Age; Descriptive Statistics; Univariate Statistics; Multivariate Analysis; Confidence Intervals; Odds Ratio; Logistic Regression; Cox Proportional Hazards Model; Kaplan-Meier Estimator; Data Analysis Software; Two-Tailed Test; Medicaid; Medicare

At What Cost to Clinical Trial Enrollment? A Retrospective Study of Patient Travel Burden in Cancer Clinical Trials. - Borno, Hala T.; Zhang, Li; Siegel, Adam; Chang, Emily; Ryan, Charles J. (Oncologist, 2018)
Background: Recent literature suggests that living in a rural setting may be associated with adverse cancer outcomes. This study examines the burden of travel from home to cancer center for clinical trial (CT) enrollees. Materials and Methods: Patients from the University of California San Francisco Clinical Trial Management System database who enrolled in a cancer CT for a breast, genitourinary, or gastrointestinal malignancy between 1993 and 2014 were included. Cancer type, household zip code, race/ethnicity, phase of study, study sponsor, and year of signed consent were exported. Distance traveled from home to center was calculated using a GoogleMaps application programming interface. The relationships of distance with phase of CT, household income, and race/ethnicity were examined. Results: A total of 1,600 patients were enrolled in breast (55.8%), genitourinary (29.4%), or gastrointestinal (14.9%) cancer CTs. The overall median unidirectional distance traveled from home to study site was 25.8 miles (interquartile range [IQR] 11.5–75.3). Of the trial sponsors examined, principal investigator (56.4%), industry (22.2%), cooperative group (11.6%), and National Institutes of Health (NIH; 9.8%), the longest distance traveled was for NIH‐sponsored trials, with a median of 39.4 miles (p < .001). Phase I (8.4%) studies had the longest distance traveled, with a median of 41.2 miles (IQR 14.5–101.0 miles; p = .001). White patients (83%) traveled longer compared with black patients (4.4%), with median distances of 29.9 and 13.9 miles, respectively (p < .001). Patients from lower‐income areas (n = 799) traveled longer distances compared with patients from higher‐income areas (n = 773; 58.3 vs. 17.8 miles, respectively; p < .001). A multivariable linear model where log10 (distance) was the outcome and adjusting for the exported variables and income revealed that cancer type, year of consent, race/ethnicity, and income were significantly associated with distance traveled. Conclusion: This study found that the burden of travel is highest among patients enrolled in NIH‐sponsored trials, phase I studies, or living in low‐income areas. These data suggest that travel burden for cancer CT participants may be significant. Implications for Practice: This study is one of the first to measure travel distance for patients in cancer clinical trials using a real‐world GoogleMaps calculator. Out‐of‐pocket expenses such as travel are not typically covered by health care payers; therefore, patients may face considerable cost to attend each study visit. Using a single‐center clinical trials enrollment database, this study found that the burden of travel is highest for patients enrolled in National Institutes of Health‐sponsored trials and phase I studies, as well as for patients living in low‐income areas. Results suggest that a significant proportion of patients enrolled in clinical trials face a substantial travel burden. Several barriers to clinical trial participation exist; however, the burden of cost and time associated with travel to visits may contribute to disparities in care. This analysis may inform ways that health care payers and systems can reduce the burden to encourage equitable recruitment and retention in cancer clinical trials.
Keywords: Clinical Trials -- Economics; Costs and Cost Analysis; Travel; Cancer Patients; Cancer Care Facilities; Home Environment; Human; Retrospective Design; Academic Medical Centers -- California; California; Tomography, X-Ray Computed -- Methods; Breast Neoplasms -- Radiography; Urogenital Neoplasms -- Radiography; Gastrointestinal Neoplasms -- Radiography; Income; Race Factors; Ethnic Groups; National Institutes of Health (U.S.); Black Persons; Poverty; Multiple Linear Regression; Consent

Attitudes of African-Americans regarding prostate cancer clinical trials. - Robinson SB; Ashley M; Haynes MA (Journal of Community Health, 1996)
The purpose of this study was to qualitatively assess attitudes associated with the willingness of African-Americans to participate in prostate cancer clinical trials. Fifty-six African-American males, 40 years of age and older, were recruited from South Central Los Angeles. Respondents were divided into lower or middle socio-economic groups based on education and occupation. Focus group discussions were conducted to assess their knowledge about prostate cancer and willingness to participate in prostate cancer clinical trials. In addition, information was obtained to identify their incentives and barriers toward participating in prostate cancer research. Middle socio-economic respondents expressed a greater willingness to participate in prostate cancer clinical trials than did men of lower socio-economic status. Many indicated that they would be more likely to participate if they were encouraged to do so by a physician or researcher who was viewed as being competent and compassionate. Barriers to participation in prostate cancer clinical trials included concerns about drug toxicity, medical experimentation and distrust of the medical establishment. Endeavors aimed at increasing minority representation in prostate cancer clinical studies should address these issues.
Keywords: Prostatic Neoplasms -- Prevention and Control; Black Persons; Attitude to Illness; Clinical Trials -- Utilization; Funding Source; California; Qualitative Studies; Focus Groups; Socioeconomic Factors; Health Beliefs; Health Knowledge; Male; Consumer Attitudes; Human

Attitudes toward participation in breast cancer randomized clinical trials in the African American community: a focus group study. - Linden HM; Reisch LM; Hart A Jr.; Harrington MA; Nakano C; Jackson JC; Elmore JG (Cancer Nursing, 2007)
Participation of African Americans in research trials is low. Understanding the perspectives of African American patients toward participation in clinical trials is essential to understanding the disparities in participation rates compared with whites. A qualitative study was conducted to discover attitudes of the African American community regarding willingness to participate in breast cancer screening and randomized clinical trials. Six focus groups consisting of 8 to 11 African American women (N = 58), aged 30 to 65, were recruited from local churches. Focus group sessions involved a 2-hour audio-taped discussion facilitated by 2 moderators. A breast cancer randomized clinical trial involving an experimental breast cancer treatment was discussed to identify the issues related to willingness to participate in such research studies. Six themes surrounding willingness to participate in randomized clinical trials were identified: (1) Significance of the research topic to the individual and/or community; (2) level of trust in the system; (3) understanding of the elements of the trial; (4) preference for 'natural treatments' or 'religious intervention' over medical care; (5) cost-benefit analysis of incentives and barriers; and (6) openness to risk versus a preference for proven treatments. The majority (80%) expressed willingness or open-mindedness to the idea of participating in the hypothetical trial. Lessons learned from this study support the selection of a culturally diverse research staff and can guide the development of research protocols, recruitment efforts, and clinical procedures that are culturally sensitive and relevant.
Keywords: Attitude -- Evaluation; Black Persons; Breast Neoplasms; Clinical Trials; Research Subjects; Adult; Antineoplastic Agents; Audiorecording; Chemotherapy, Adjuvant; Convenience Sample; Descriptive Statistics; Female; Focus Groups; Funding Source; Interview Guides; Middle Age; Qualitative Studies; Research Subject Recruitment; Thematic Analysis; Trust; Human

Barriers and Strategies to Participation in Tissue Research Among African-American Men. - Drake, Bettina; Boyd, Danielle; Carter, Kimberly; Gehlert, Sarah; Thompson, Vetta; Drake, Bettina F; Thompson, Vetta Sanders (Journal of Cancer Education, 2017)
Before the burgeoning field of biospecimen collection can advance prevention and treatment methods, researchers must access diverse molecular data samples. However, minorities, especially African-American men, remain reticent to join these studies. This study, using theory-based approaches, investigated African-American men's barriers to participating in biorepository research. Fourteen focus groups were conducted among 70 African-American men (ages 40 to 80). The groups were stratified by prostate cancer history and educational attainment background. Participants identified perceived factors that promoted or hindered study participation when questioned about their knowledge and attitudes about biospecimen research. Ninety-four percent of participants indicated never participating in a study that collected biological samples. Barriers to their participation included lack of knowledge and understanding regarding biospecimen research practices and uses. In addition, they extensively cited a prevalent mistrust of the medical community and discomfort with study recruitment practices. African-American males were more willing to participate in biorepository studies with physician endorsement or if they understood that participation could benefit future generations. Men also wanted more recruitment and advertising done in familiar places.
Keywords: Patient Selection; Black Persons -- Statistics and Numerical Data; Prostatic Neoplasms -- Therapy; Middle Age; Aged, 80 and Over; Prostatic Neoplasms -- Prevention and Control; Aged; Research, Medical; Specimen Handling -- Methods; Adult; Male; Focus Groups; United States; Attitude to Health; Funding Source; Human

Barriers to Recruitment and Adherence in a Randomized Controlled Diet and Exercise Weight Loss Intervention Among Minority Breast Cancer Survivors. - Aycinena, A.; Valdovinos, Cristina; Crew, Katherine; Tsai, Wei; Mata, Jennie; Sandoval, Rossy; Hershman, Dawn; Greenlee, Heather (Journal of Immigrant & Minority Health, 2017)
Minority recruitment to cancer trials is low and there are limited data on minority adherence to lifestyle modification interventions. We examined factors related to recruitment and adherence to a pilot weight loss intervention among Hispanic and black breast cancer survivors. Participants completed a detailed screening interview to assess barriers to enrollment. An index was created to assess adherence at 6 months. 112 potentially eligible women were identified; 66 consented and completed a screening interview. After screening, 9 were ineligible; 15 opted to not enroll; and 42 were randomized. Among eligible women, earlier stage at diagnosis, treatment type, and negative beliefs related to exercise and diet after diagnosis were negatively associated with study enrollment ( P < 0.05). Self-reported barriers to adherence included fatigue, family responsibilities, illness, work, transportation, and negative perceptions of exercise and diet. Results from this study emphasize the need to adapt recruitment and adherence strategies to address these factors.
Keywords: Breast Neoplasms; Health Services; Diet; Weight Loss; Exercise; Black Persons; Fatigue; Female; Hispanic Americans; Human; Life Style; Quality of Life; Minority Groups; Survivors; Questionnaires; Paired T-Tests; Chi Square Test; Logistic Regression; Middle Age; Adult

Biases in Recommendations for and Acceptance of Prostate Biopsy Significantly Affect Assessment of Prostate Cancer Risk Factors: Results From Two Large Randomized Clinical Trials. - Tangen, Catherine M.; Goodman, Phyllis J.; Till, Cathee; Schenk, Jeannette M.; Lucia, M. Scott; Thompson Jr, Ian M.; Thompson, Ian M Jr (Journal of Clinical Oncology, 2016)
Purpose To identify factors related to who undergoes a prostate biopsy in a screened population and to estimate the impact of biopsy verification on risk factor-prostate cancer associations. Patients and Methods Men who were screened regularly from the placebo arms of two large prostate cancer prevention trials (Prostate Cancer Prevention Trial [PCPT] and Selenium and Vitamin E Cancer Prevention Trial [SELECT]) were examined to define incident prostate cancer cohorts. Because PCPT had an end-of-study biopsy, prostate cancer cases were categorized by a preceding prostate-specific antigen/digital rectal examination prompt (yes/no) and noncases by biopsy-proven negative status (yes v no). We estimated the association of risk factors (age, ethnicity, family history, body mass index, medication use) with prostate cancer and quantified differences in risk associations across cohorts. Results Men 60 to 69 years of age, those with benign prostatic hyperplasia, and those with a family history of prostate cancer were more likely, and those with a higher body mass index (≥ 25), diabetes, or a smoking history were less likely, to undergo biopsy, adjusting for age and longitudinal prostate-specific antigen and digital rectal examination. Medication use, education, and marital status also influenced who underwent biopsy. Some risk factor estimates for prostate cancer varied substantially across cohorts. Black ( v other ethnicities) had odds ratios (ORs) that varied from 1.20 for SELECT (community screening standards, epidemiologic-like cohort) to 1.83 for PCPT (end-of-study biopsy supplemented with imputed end points). Statin use in SELECT provided an OR of 0.65 and statin use in in PCPT provided an OR of 0.99, a relative difference of 34%. Conclusion Among screened men enrolled in prostate cancer prevention trials, differences in risk factor estimates for prostate cancer likely underestimate the magnitude of bias found in other cohorts with varying screening and biopsy recommendations and acceptance. Risk factors for prostate cancer derived from epidemiologic studies not only may be erroneous but may lead to misdirected research efforts.

Biospecimen donation among black and white breast cancer survivors: opportunities to promote precision medicine. - Sheppard, Vanessa B.; Hurtado-de-Mendoza, Alejandra; Zheng, Yun-Ling; Wang, Ying; Graves, Kristi D.; Lobo, Tania; Xu, Hanfei; Jennings, Yvonne; Tolsma, Dennis; Trout, Martha; Robinson, Brandi E.; McKinnon, Brittany; et al. (Journal of Cancer Survivorship, 2018)
Purpose: Advances in precision medicine (PM) have potential to reduce and/or eliminate breast cancer disparities in both treatment and survivorship. However, compared to white Americans, black Americans are often underrepresented in genetic research. This report assessed factors that influence receipt of buccal cells via saliva kits.Methods: This prospective study recruited women with confirmed hormonal-positive (HR+) breast cancer (BC). A standardized telephone survey collected sociodemographic, socio-cultural (e.g., religiosity), and healthcare process factors. Clinical information was abstracted from medical records. After the baseline survey, return postage-paid envelopes and mouthwash collection kits were mailed. Univariate and adjusted logistic regression models estimated the probability of biospecimen donation.Results: Seventy percent of the sample provided buccal cells which were of good quality. No differences were noted by race or other demographic factors. In the multivariable logistic model, time spent with providers (OR 1.61 per 1-point increase; 95% CI 1.242, 2.088) and religiosity (OR 0.957 per 1-point increase; 95% CI 0.931, 0.984) remained associated with biospecimen provision. Women with lower-stage cancer (vs. higher stage III+) were more likely to donate biospecimens (p < 0.05).Conclusions: Cancer care experiences predicted specimen donation. Understanding the contextual reasons for lower receipt among women with higher religiosity scores and higher stage warrants further examination.Implications For Cancer Survivors: PM is relevant to cancer survivors because of its potential to inform targeted therapies, understand disease resistance, and aide in prediction of toxicity and/or recurrence. Future efforts to launch precision medicine trials with BC survivors may benefit from engaging medical oncologists and/or leveraging patient-provider encounters for trial participation.
Keywords: Black Persons -- Statistics and Numerical Data; Tissue Banks -- Standards; Breast Neoplasms -- Pathology; White Persons -- Statistics and Numerical Data; Breast Neoplasms -- Ethnology; Adult; Aged; Breast Neoplasms -- Therapy; Breast Neoplasms -- Mortality; Female; Middle Age; Specimen Handling -- Methods; Aged, 80 and Over; Human; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Ferrans and Powers Quality of Life Index; Scales

Body mass index and mortality among blacks and whites adults in the Prostate, Lung, Colorectal, and Ovarian (PLCO) cancer screening trial. - Xiao, Qian; Hsing, Ann W; Park, Yikyung; Moore, Steven C; Matthews, Charles E; de González, Amy Berrington; Kitahara, Cari M (Obesity (19307381), 2014)
Objective: In a large prospective cohort, we examined the relationship of body mass index (BMI) with mortality among blacks and compared the results to those among whites in this population.Design and Methods: The study population consisted of 7,446 non-Hispanic black and 130,598 white participants, ages 49-78 at enrollment, in the Prostate, Lung, Colorectal and Ovarian (PLCO) Cancer Screening Trial. BMI at baseline, BMI at age 20, and BMI change were calculated using self-reported and recalled height and weight. Relative risks were stratified by race and sex and adjusted for age, education, marital status, and smoking.Results: During follow-up, 1,495 black and 18,236 white participants died (mean = 13 years). Clear J-shaped associations between BMI and mortality were observed among white men and women. Among black men and women, the bottoms of these curves were flatter, and increasing risks of death with greater BMI were observed only at higher BMI levels (≥35.0). Associations for BMI at age 20 and BMI change also appeared to be stronger in magnitude in whites versus blacks, and these racial differences appeared to be more pronounced among women.Conclusion: Our results suggest that BMI may be more weakly associated with mortality in blacks, particularly black women, than in whites.
Keywords: Body Mass Index; Mortality; Black Persons; Aged; Colorectal Neoplasms -- Diagnosis; White Persons; Female; Prospective Studies; Human; Lung Neoplasms -- Diagnosis; Male; Middle Age; Ovarian Neoplasms -- Diagnosis; Prostatic Neoplasms -- Diagnosis; Questionnaires; Clinical Trials; Risk Factors; Socioeconomic Factors

Breast cancer and cervical cancer control program enrollees inform the kin keeper curriculum. - Williams KP; Mabiso A; Jackson TL; Lawshe DC; Maurer J; Williams, Karen Patricia; Mabiso, Athur; Jackson, Tedra L; Lawshe, Dorothy C; Maurer, Joel (Journal of Cancer Education, 2009)
Background: The purpose of this study is to present the methodology of developing the Kin Keeper Cancer Prevention Curriculum Guide and Workbook through participatory engagement of women from underserved communities.Methods: It was developed to cross train community health workers (CHWs) from public health programs to deliver cancer education. Data collection included review of existing educational materials, a 10-minute telephone survey of 146 women enrolled in a Breast and Cervical Cancer Control Program and a pair of pre-post training assessments of 31 African American, Latina, and Arab CHWs.Results: The enrollees adequately informed the curriculum and the CHWs increased their scores by 7% (14%) in breast (cervical) cancer literacy; P-values <0.01.Conclusion: The methodology was validated; the curriculum was well-informed and CHWs were effectively cross trained using the curriculum.
Keywords: Breast Neoplasms -- Prevention and Control; Cervix Neoplasms -- Prevention and Control; Community Health Services; Curriculum Development; Health Education; Health Knowledge; Adult; Arabs; Black Persons; Cancer Screening; Cervical Smears; Confidence Intervals; Descriptive Statistics; Educational Measurement; Educational Status; Female; Funding Source; Hispanic Americans; Income; Interviews; Medicaid; Medically Underserved Area; Michigan; Middle Age; P-Value; Paired T-Tests; Pretest-Posttest Design; Seminars and Workshops; Surveys; Teaching Materials

Breast cancer patients' attitudes toward clinical trials in the radiation oncology clinic versus those searching for trial information on the Internet. - Dolinsky CM; Wei SJ; Hampshire MK; Metz JM (Breast Journal, 2006)
Web-based clinical trials matching systems including breast cancer patients are expanding rapidly. However, limited data exist regarding the demographics and attitudes of breast cancer patients using the Internet to search for clinical trials information. Biases in patient populations could be introduced by recruiting patients to trials through the Internet. This study was designed to compare breast cancer patients in the radiation oncology clinic to those using the Internet to search for clinical trials information. A piloted questionnaire assessing demographics and attitudes regarding clinical trials was offered through the radiation oncology clinic at the University of Pennsylvania and on the OncoLink website (http://www.oncolink.org). The questionnaire consisted of 18 questions and was answered by a total of 157 patients with breast cancer. Breast cancer patients using the Web were more likely to be interested in clinical trials testing new drugs or therapies (71 [53%] versus 4 [17%], p = 0.002). More clinic patients indicated they would need a greater than 50% chance of benefiting from a trial (12 [52%] versus 33 [25%], p = 0.01) and a less than 10% potential for serious toxicity from a trial (15 [65%] versus 51 [38%], p = 0.02) for consideration of enrollment. African Americans were more likely than other races to have never used the Internet to search for cancer-related information (4 [40%] versus 18 [12%], p = 0.01), more likely to indicate that they need a greater than 50% chance of benefit to enroll in clinical trials (8 [80%] versus 37 [25%], p = 0.001), and less likely to be interested in clinical trials testing new drugs or therapies (1 [10%] versus 73 [50%], p = 0.01). Breast cancer patients have different attitudes regarding clinical trials based on race, Internet usage, and previous trial enrollment. Biases may be introduced with recruitment for clinical trials through the Internet. Radiation oncologists must consider these issues when offering clinical trials information through the Internet.
Keywords: Breast Neoplasms; Clinical Trials; Internet; Patient Satisfaction -- Ethnology; Patient Selection; Female; Male; Middle Age; Pennsylvania; Pilot Studies; Prospective Studies; Human

Breast Cancer Screening in Women at Higher-Than-Average Risk: Recommendations From the ACR. - Monticciolo, Debra L.; Newell, Mary S.; Moy, Linda; Niell, Bethany; Monsees, Barbara; Sickles, Edward A. (Journal of the American College of Radiology, 2018)
Early detection decreases breast cancer mortality. The ACR recommends annual mammographic screening beginning at age 40 for women of average risk. Higher-risk women should start mammographic screening earlier and may benefit from supplemental screening modalities. For women with genetics-based increased risk (and their untested first-degree relatives), with a calculated lifetime risk of 20% or more or a history of chest or mantle radiation therapy at a young age, supplemental screening with contrast-enhanced breast MRI is recommended. Breast MRI is also recommended for women with personal histories of breast cancer and dense tissue, or those diagnosed by age 50. Others with histories of breast cancer and those with atypia at biopsy should consider additional surveillance with MRI, especially if other risk factors are present. Ultrasound can be considered for those who qualify for but cannot undergo MRI. All women, especially black women and those of Ashkenazi Jewish descent, should be evaluated for breast cancer risk no later than age 30, so that those at higher risk can be identified and can benefit from supplemental screening.
Keywords: Patient Selection; Early Detection of Cancer; Breast Neoplasms; Risk Factors; Neoplasm Recurrence, Local; Risk Assessment; Mammography; Breast Neoplasms -- Pathology; Age Factors; Adult; Models, Statistical; Magnetic Resonance Imaging; Breast Neoplasms -- Ethnology; Ultrasonography; Female; Neoplasms, Radiation-Induced; Disease Susceptibility; Personal Resource Questionnaire

Breast cancer survivors willingness to participate in an acupuncture clinical trial: a qualitative study. - Schapira, Marilyn M; Mackenzie, Elizabeth R; Lam, Regina; Casarett, David; Seluzicki, Christina M; Barg, Frances K; Mao, Jun J (Supportive Care in Cancer, 2014)
Purpose: Acupuncture is a complementary and alternative medicine (CAM) modality that shows promise as a component of supportive breast cancer care. Lack of robust recruitment for clinical trial entry has limited the evidence base for acupuncture as a treatment modality among breast cancer survivors. The objective of this study is to identify key decision-making factors among breast cancer survivors considering entry into an acupuncture clinical trial for treatment of symptoms.Methods: Semistructured interviews were conducted among African-American (n=12) and Caucasian (n=13) breast cancer survivors. Verbatim transcripts were made and analyzed by two or more independent coders using NVivo software. Major recurring themes were identified and a theoretical framework developed.Results: Six themes emerged reflecting key attributes of the decision to enter a clinical trial: (1) symptom appraisal, (2) practical barriers (e.g., distance and travel), (3) beliefs about the interventions (e.g., fear of needles and dislike of medications), (4) comfort with elements of clinical trial design (e.g., randomization, the nature of the control intervention, and blinding), (5) trust, and (6) altruism. African-American and Caucasian women weighed similar attributes but differed in the information sources sought regarding clinical trial entry and in concerns regarding the use of a placebo in a clinical trial.Conclusions: Our findings contribute to the development of a theoretical model of decision making for breast cancer survivors considering participation in a CAM clinical trial. Insights regarding the decision making process can inform interventions to support informed decision making and robust recruitment to CAM trials among cancer survivors.
Keywords: Acupuncture -- Psychosocial Factors; Breast Neoplasms -- Psychosocial Factors; Breast Neoplasms -- Therapy; Patient Attitudes; Acupuncture -- Methods; Adult; Aged; Black Persons -- Psychosocial Factors; Breast Neoplasms -- Ethnology; Breast Neoplasms -- Pathology; Decision Making; Female; Human; Middle Age; Neoplasm Recurrence, Local -- Ethnology; Neoplasm Recurrence, Local -- Psychosocial Factors; Neoplasm Recurrence, Local -- Therapy; Neoplasm Staging; Patient Attitudes -- Ethnology; Survivors -- Psychosocial Factors; White Persons -- Psychosocial Factors

Breast cancer treatment of older women in integrated health care settings. - Enger SM; Thwin SS; Buist DS; Field T; Frost F; Geiger AM; Lash TL; Prout M; Yood MU; Wei F; Silliman RA; Enger, Shelley M; et al. (Journal of Clinical Oncology, 2006)
Purpose: A substantial literature describes age-dependent variations in breast cancer treatment, showing that older women are less likely to receive standard treatment than younger women. We sought to identify patient and tumor characteristics associated with the nonreceipt of standard primary tumor and systemic adjuvant therapies.Patients and Methods: We studied 1,859 women age 65 years or older with stage I and II breast cancer diagnosed between 1990 and 1994 who were cared for in six geographically dispersed community-based health care systems. We collected demographic, tumor, treatment, and comorbidity data from electronic data sources, including cancer registry, administrative, and clinical databases, and from subjects' medical records.Results: Women 75 years of age or older and women with higher comorbidity indices were more likely to receive nonstandard primary tumor therapy, to not receive axillary lymph node dissection, and to not receive radiation therapy after breast-conserving surgery (BCS). Asian women were less likely to receive BCS, and African American women were less likely to be prescribed tamoxifen. Although nonreceipt of most therapies was associated with a lower baseline risk of recurrence, an important minority of high-risk women (16% to 30%) did not receive guideline therapies.Conclusion: Age is an independent risk factor for nonreceipt of effective cancer therapies, even when comorbidity and risk of recurrence are taken into account. Information regarding treatment effectiveness in this age group and tools that allow physicians and patients to estimate the benefits versus the risks of therapies, taking into account age and comorbidity burden, are critically needed.
Keywords: Breast Neoplasms -- Epidemiology; Breast Neoplasms -- Therapy; Health Care Delivery, Integrated; Patient Selection; Black Persons; Age Factors; Aged; Aged, 80 and Over; Antineoplastic Agents, Hormonal -- Administration and Dosage; Antineoplastic Agents, Combined -- Administration and Dosage; Asians; Breast Neoplasms -- Drug Therapy; Breast Neoplasms -- Pathology; Breast Neoplasms -- Radiotherapy; Breast Neoplasms -- Surgery; Chemotherapy, Adjuvant; Comorbidity; Female; Managed Care Programs; Mastectomy -- Methods; Mastectomy; Medical Records; Odds Ratio; Radiotherapy, Adjuvant; Retrospective Design; Risk Assessment; Risk Factors; Tamoxifen -- Administration and Dosage; Treatment Outcomes; United States; Human

Bridging the Gap: Racial concordance as a strategy to increase African American participation in breast cancer research. - Frierson, Georita M; Pinto, Bernardine M; Denman, Deanna C; Leon, Pierre A; Jaffe, Alex D (Journal of Health Psychology, 2019)
Lack of African American females in breast cancer research has been receiving substantial attention. This study seeks to identify research perceptions and motivating factors needed to increase racial/ethnic minority participation in breast cancer research. A total of 57 African American women (Σ = 47.8 years), from Rhode Island and Texas, completed a questionnaire and focus group. While many participants were not breast cancer survivors, they reported knowledge of their racial group's risk for breast cancer. One major finding that could be seen as both a facilitator and barrier is racial concordance between participant and researcher. Cultural sensitivity and trust building is recommended to increase minority participation.
Keywords: Race Factors; Black Persons -- Psychosocial Factors; Consumer Participation -- Psychosocial Factors; Research Subject Recruitment; Breast Neoplasms; Research, Medical; Health Behavior; Human; Female; Adult; Middle Age; Aged; Rhode Island; Texas; Questionnaires; Focus Groups; Health Status Disparities; Health Knowledge; Culture; Qualitative Studies; Descriptive Statistics

Brief report. Adoption of breast self-examination among socioeconomically disadvantaged women: the importance of frequent caregiver contact. - Russ CR; Winett RA (Journal of Gender, Culture, & Health, 1996)
The utility of breast self-examination (BSE) as an adjunctive and economical means of early detection for breast cancer has been well documented. This preliminary study examined the efficacy of an intervention promoting BSE through standard face-to-face training, written prompts, self-management, personalized feedback, and supplementary training among a sample of women recruited from a federally subsidized housing development. The sample (n = 28) was largely African-American (87%), ranged in age from 20 to 57 (M = 35 years), and had a mean educational attainment of 10th grade. Women reported low levels of BSE frequency, quality, and knowledge at baseline. Analyses of variance revealed a significant effect of the intervention on reported BSE frequency (p < 0.01) and number of BSE records returned (p < 0.05); however, BSE quality was not significantly improved. Continual contacts with participants appeared to be the most important factor in BSE adoption. While this intervention has potential to increase BSE frequency among low SES women, suggestions for improving examination proficiency are also provided.
Keywords: Breast Self-Examination -- Education -- Virginia; Women; Poverty; P-Value; Pretest-Posttest Design; Analysis of Variance; Female; Adult; Black Persons; Multidimensional Health Locus of Control Scales; Comparative Studies; Virginia; Prospective Studies; Questionnaires; One-Way Analysis of Variance; Chi Square Test; Multiple Regression; Dependent Variable; Residence Characteristics; Human

Can Women Facilitate Men's Prostate Cancer Screening Informed Decision-Making? The M-PACT Trial. - Holt, Cheryl L.; Le, Daisy; Slade, Jimmie L.; Muwwakkil, Bettye; Saunders, Darlene R.; Williams, Ralph; Atkinson, Nancy L.; Naslund, Michael (Journal of Health Communication, 2017)
The M-PACT study compared an all-male with a mixed-sex intervention to increase informed decision-making for prostate cancer screening among African-American men in church settings. We recruited 262 men in 18 churches randomized to the two intervention approaches. Trained and certified lay peer community health advisors in each church led a series of four men’s health workshops on informed decision-making for prostate cancer screening. African-American male workshop participants completed baseline, post-workshop, and 12-month follow-up surveys. Contrary to our expectations, including women in the workshops did not result in increased intervention efficacy for the informed decision-making outcomes as both groups showed significant improvement over time in several study outcomes including stage of decision-making for prostate cancer screening, preference for role in decision-making, prostate cancer knowledge, and self-reports of prostate specific antigen testing. Finally, men who attended multiple workshops had better informed decision-making outcomes on several indicators. The current findings suggest mixed results from including women in this men’s health educational intervention. Future work should consider optimal ways of providing family support for African-American men’s health promotion.

Cancer mortality in German carbon black workers 1976-98. - Wellmann J; Weiland SK; Neiteler G; Klein G; Straif K (Occupational & Environmental Medicine, 2006)
BACKGROUND: Few studies have investigated cancer risks in carbon black workers and the findings were inconclusive. METHODS: The current study explores the mortality of a cohort of 1535 male German blue-collar workers employed at a carbon black manufacturing plant for at least one year between 1960 and 1998. Vital status and causes of death were assessed for the period 1976-98. Occupational histories and information on smoking were abstracted from company records. Standardised mortality ratios (SMR) and Poisson regression models were calculated. RESULTS: The SMRs for all cause mortality (observed deaths (obs) 332, SMR 120, 95% CI 108 to 134), and mortality from lung cancer (obs 50, SMR 218, 95% CI 161 to 287) were increased using national rates as reference. Comparisons to regional rates from the federal state gave SMRs of 120 (95% CI 107 to 133) and 183 (95% CI 136 to 241), respectively. However, there was no apparent dose response relationship between lung cancer mortality and several indicators of occupational exposure, including years of employment and carbon black exposure. CONCLUSIONS: The mortality from lung cancer among German carbon black workers was increased. The high lung cancer SMR can not fully be explained by selection, smoking, or other occupational risk factors, but the results also provide little evidence for an effect of carbon black exposure.
Keywords: Carbon; Neoplasms -- Mortality; Occupational Diseases -- Mortality; Adult; Aged; Aged, 80 and Over; Cause of Death; Confidence Intervals; Data Analysis Software; Descriptive Statistics; Epidemiological Research; Female; Germany; Industry; Male; Middle Age; Occupational Exposure; Occupational Exposure -- Adverse Effects; Regression; Relative Risk; Research Subject Recruitment; Risk Factors; Smoking -- Mortality; Human

Cancer Screening Behaviors of African American Women Enrolled in a Community-Based Cancer Prevention Trial. - Reiter, Paul L.; Linnan, Laura A. (Journal of Women's Health (15409996), 2011)
Background: African American women have increased mortality rates for cervical, breast, and colorectal cancers, yet not all receive the recommended screening tests for these cancers. We characterized the cancer screening behaviors of African American women enrolled in a community-based cancer prevention trial. Methods: We examined cross-sectional data from 1123 African American customers aged ≥18 years from 37 beauty salons in North Carolina who completed the North Carolina BEAUTY and Health Project baseline survey. Mixed logistic regression models were used to identify correlates of receiving cervical, breast, and colorectal cancer screening tests within recommended screening guidelines. Results: Overall, 94% (1026 of 1089) of women aged ≥18 years reported receiving a Pap smear test within the last 3 years, 70% (298 of 425) of women aged ≥40 years reported receiving a mammography within the last year, and 64% (116 of 180) of women aged ≥50 years were considered to be within recommended screening guidelines for colorectal cancer. Age was correlated with recent Pap smear testing and mammography. Women who reported receiving a recent Pap smear test were more likely to report a mammogram in the last year, and women with a recent mammogram were more likely to be within recommended screening guidelines for colorectal cancer. Many women reported multiple barriers to getting recommended cancer screening tests. Conclusions: Almost all women reported receiving a Pap smear test within the last 3 years. Future interventions should focus on increasing breast and colorectal cancer screening among African American women.
Keywords: Cancer Screening; Black Persons; Health Behavior; Patient Compliance; Human; Funding Source; Female; Cross Sectional Studies; Adult; Grooming -- Organizations -- North Carolina; North Carolina; Cervical Smears; Mammography; Age Factors; Middle Age; Colorectal Neoplasms -- Prevention and Control; Health Services Accessibility; Secondary Analysis; Questionnaires; Logistic Regression; Bivariate Statistics; Correlational Studies; Predictive Validity; Descriptive Statistics; Odds Ratio; Confidence Intervals

Cancer screening intervention among Black women in inner-city Atlanta -- design of a study. - Sung JFC; Coates RJ; Williams JE; Liff JM; Greenberg RS; McGrady GA; Avery BY; Blumenthal DS (Public Health Reports, 1992)
This experimental study attempts to determine if an in-home educational intervention conducted by lay health workers (LHWs) can increase adherence among low-income, inner-city black women to schedules for screening for breast cancer and cervical cancer, as well as increase the women's knowledge and change their attitudes regarding these cancers. This paper is a description of the purposes, hypotheses, design, subject recruitment, intervention, and evaluation of the study conducted by Morehouse School of Medicine. Subjects were recruited from a variety of sources, including patients seen in a community health center, women referred by the National Black Women's Health Project (NBWHP), residents of public and senior citizen housing projects, and persons identified in various community settings. Fewer than half of those asked to participate agreed to do so. The 321 women who were recruited were demographically diverse. Overall, about half of these volunteer subjects self-reported at least one Papanicolaou (Pap) smear and one breast examination within a year before enrollment in the study. There was little variation by source of recruitment in compliance with screening recommendations, except that referrals from NBWHP were more likely (P < 0.01) to have had a Pap test and breast self-examination, while residents of public housing projects were somewhat less likely to have done so. About 35 percent of participants ages 35 and older had a mammogram within an appropriate interval. Participants were randomly assigned to intervention and control groups. Women in the intervention group were visited in their homes by LHWs on three occasions; the LHWs provided education on cancer and reproductive health. The groups were comparable in their baseline sociodemographic status and previous screening history.
Keywords: Breast Neoplasms -- Epidemiology; Cancer Screening -- Methods; Health Education -- Methods; Women's Health; Attitude to Health; Cervix Neoplasms -- Epidemiology; Black Persons; Georgia; Epidemiological Research; Breast Neoplasms -- Diagnosis; Cervix Neoplasms -- Diagnosis; Urban Areas; Cervical Smears; Prospective Studies; Poverty; Convenience Sample; Adolescence; Adult; Middle Age; Aged; Female; Human

Capturing the Experience. - Haga Gripsrud, Birgitta; Brassil, Kelly J.; Summers, Barbara; Søiland, Havard; Kronowitz, Steven; Lode, Kirsten (Cancer Nursing, 2016)
Background: Expressive writing has been shown to improve quality of life, fatigue, and posttraumatic stress among breast cancer patients across cultures. Understanding how and why the method may be beneficial to patients can increase awareness of the psychosocial impact of breast cancer and enhance interventional work within this population. Qualitative research on experiential aspects of interventions may inform the theoretical understanding and generate hypotheses for future studies. Aim: The aim of the study was to explore and describe the experience and feasibility of expressive writing among women with breast cancer following mastectomy and immediate or delayed reconstructive surgery. Methods: Seven participants enrolled to undertake 4 episodes of expressive writing at home, with semistructured interviews conducted afterward and analyzed using experiential thematic analysis. Results: Three themes emerged through analysis: writing as process, writing as therapeutic, and writing as a means to help others. Conclusions: Findings illuminate experiential variations in expressive writing and how storytelling encourages a release of cognitive and emotional strains, surrendering these to reside in the text. The method was said to process feelings and capture experiences tied to a new and overwhelming illness situation, as impressions became expressions through writing. Expressive writing, therefore, is a valuable tool for healthcare providers to introduce into the plan of care for patients with breast cancer and potentially other cancer patient groups. Implications for Practice: This study augments existing evidence to support the appropriateness of expressive writing as an intervention after a breast cancer diagnosis. Further studies should evaluate its feasibility at different time points in survivorship.
Keywords: Breast Neoplasms -- Therapy; Cancer Patients -- Psychosocial Factors; Women -- Psychosocial Factors; Writing -- Utilization; Life Experiences; Human; Semi-Structured Interview; Thematic Analysis; Prospective Studies; Comparative Studies; Descriptive Research; United States; Audiorecording; Phenomenology; Storytelling; Adult; Aged; Middle Age; Female; White Persons; Black Persons; Asians; Funding Source; Experimental Studies; Emotions; Narratives; Stress Disorders, Post-Traumatic; Norway

Casting a Wider Net: Engaging Community Health Worker Clients and Their Families in Cancer Prevention. - Roman, Lee Anne; Zambrana, Ruth Enid; Ford, Sabrina; Meghea, Cristian; Williams, Karen Patricia (Preventing Chronic Disease, 2016)

Cause-specific mortality by race in low-income Black and White people with Type 2 diabetes. - Conway, B. N.; May, M. E.; Fischl, A.; Frisbee, J.; Han, X.; Blot, W. J. (Diabetic Medicine, 2015)
Keywords: Income -- Evaluation; Diabetes Mellitus, Type 2 -- Mortality; Race Factors; Ethnic Groups; Black Persons; White Persons; Socioeconomic Factors; After Care; United States; Middle Age; Poverty; Research Subject Recruitment; Prospective Studies; Ambulatory Care Facilities; Geographic Locations; Data Analysis; Human; Cox Proportional Hazards Model; Confidence Intervals; Mortality; Diabetes Mellitus, Type 2 -- Physiopathology; Male; Female; Disease Duration; Body Mass Index -- Evaluation; Insulin -- Administration and Dosage; Hypoglycemic Agents -- Administration and Dosage; Administration, Oral; Lipids -- Analysis; Comorbidity; Heart Diseases -- Mortality; Lung Diseases -- Mortality; Kidney Failure, Chronic; Neoplasms; Sepsis

Challenges and opportunities using online portals to recruit diverse patients to behavioral trials. - Tabriz, Amir Alishahi; Fleming, Patrice Jordan; Shin, Yongyun; Resnicow, Ken; Jones, Resa M; Flocke, Susan A; Shires, Deirdre A; Hawley, Sarah T; Willens, David; Lafata, Jennifer Elston; Alishahi Tabriz, Amir (Journal of the American Medical Informatics Association, 2019)
We describe the use of an online patient portal to recruit and enroll primary care patients in a randomized trial testing the effectiveness of a colorectal cancer (CRC) screening decision support program. We use multiple logistic regression to identify patient characteristics associated with trial recruitment, enrollment, and engagement. We found that compared to Whites, Blacks had lower odds of viewing the portal message (OR = 0.46, 95% CI = 0.37-0.57), opening the attached link containing the study material (OR = 0.75, 95% CI = 0.62-0.92), and consenting to participate in the trial (OR = 0.85, 95% CI = 0.67-0.93). We also found that compared to Whites, Asians had lower odds of viewing the portal message (OR = 0.53, 95% CI = 0.33-0.64), opening the attached link containing the study material (OR = 0.76, 95% CI = 0.54-0.97), consenting to participate in the trial (OR = 0.68, 95% CI = 0.53-0.95), and completing the trial's baseline questionnaire (OR = 0.59, 95% CI = 0.36-0.90). While portals offer an opportunity to mitigate human bias in trial invitations, because of racial disparities-not only in who has a portal account, but in how they interact with trial recruitment and enrollment material within the portal-using portals alone for trial recruitment may generate study samples that are not racially diverse.
Keywords: Colorectal Neoplasms -- Diagnosis; Patient Selection; Early Detection of Cancer; Female; Randomized Controlled Trials; Health Status Disparities; Primary Health Care; Human; Middle Age; Logistic Regression; Patient Attitudes -- Ethnology; Colorectal Neoplasms -- Ethnology; Selection Bias; Population; Male; Aged; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Challenges unique to the design of a comprehensive questionnaire assessing breast cancer risk factors among women in sub-Saharan Africa. - Deming SL; Egbuji A; Smith J; Gociu A; Young J; Carter C Jr.; Barnes F; Oduma J; Kimende K; Onayade A; Durosinmi M; Lawal OO; et al. (Journal of Health Care for the Poor & Underserved, 2010)
We assessed the efficacy of a pilot questionnaire designed to elicit information about external risk factors for breast cancer in sub-Saharan African women. Preliminary analysis identified areas of the questionnaire and interviewing process that required modification, as well as socioeconomic factors that contribute to reduced participation among these understudied populations.
Keywords: Breast Neoplasms -- Risk Factors; Questionnaires; Adult; Black Persons; Case Control Studies; Female; Human; Instrument Construction; Interviews; Kenya; Life Style; Middle Age; Nigeria; Pilot Studies; Research Methodology; Research Subject Retention; Socioeconomic Factors

Changes in Risk Perceptions in Relation to Self-Reported Colorectal Cancer Screening Among First-Degree Relatives of Colorectal Cancer Cases Enrolled in a Randomized Trial. - Glenn, Beth A.; Herrmann, Alison K.; Crespi, Catherine M.; Mojica, Cynthia M.; Chang, L. Cindy; Maxwell, Annette F.; Bastani, Roshan (Health Psychology, 2011)
Objective: This secondary data analysis was conducted to evaluate the applicability of the Risk Reappraisal Hypothesis, which has been proposed to explain the influence of performing a health behavior on perceived risk. Data were collected in the context of a randomized trial, which found that an individually tailored, multicomponent intervention was successful in increasing colorectal cancer (CRC) screening among first-degree relatives of CRC cases. Method: The ethnically diverse study sample (N = 841; 29% Latino, 21% African American, 20% Asian) consisted of adult siblings and children (40-80 years) of CRC cases, identified through the California Cancer Registry. Data were collected at baseline and at 6- and 12-month follow-up. Changes in self-reported risk perception (perceived likelihood of developing CRC) were examined over the study period in relation to study condition and screening status. Results: Greater increases in perceived risk were observed among intervention versus control-group participants over the study period, but increases were limited to intervention participants who had not been screened. We also examined trajectories of perceived risk in relation to timing of screening receipt (e.g., before 6 months, 6-12 months, never). Continued upward shifts in risk were observed during the study period among intervention participants not screened during the study. In contrast, participants screened by 6 months displayed a reduction or leveling off in perceived risk between 6- and 12-month follow-up. Conclusion: Results provide support for the applicability of the Risk Reappraisal Hypothesis within a high-risk sample enrolled in a CRC screening promotion trial. Future research is needed to explore the impact of short-term risk reductions on future CRC screening behavior.
Keywords: Attitude to Risk; Colorectal Neoplasms -- Prevention and Control; Cancer Screening; Family -- Psychosocial Factors; Health Behavior; Human; Self Report; Secondary Analysis; Family Attitudes; Adult; Middle Age; Aged; Aged, 80 and Over; Interviews; California; Male; Female; Descriptive Statistics; Chi Square Test; Odds Ratio; P-Value; Confidence Intervals; Prospective Studies; Randomized Controlled Trials

Chemobrain in Underserved African American Breast Cancer Survivors. - Rust, Connie; Davis, Cindy (Clinical Journal of Oncology Nursing, 2013)
Although research has been conducted to address specific medical and psychosocial needs of breast cancer survivors, little has been done to address needs along the entire trajectory of care. One such need is chemobrain, a phenomenon recognized as an identifiable psychosocial cognitive change in breast cancer survivors. The purpose of this article is to present the findings of a qualitative study conducted with two focus groups of underserved African American breast cancer survivors. Four themes emerged from the transcribed interviews: the concept of chemobrain, variability among individuals, the stigma of chemobrain, and methods of coping. In addition, findings revealed that health professionals were not used by the participants as a resource to address the issues of chemobrain, which holds significant implications for practice. That fact highlights the implications for oncology nursing with respect to providing education and support for patients experiencing chemobrain. Nursing professionals are in a position to be a frontline resource for breast cancer survivors, providing information, education, and coping methods to help improve their quality of life.
Keywords: Cognition Disorders -- Chemically Induced; Antineoplastic Agents -- Adverse Effects; Breast Neoplasms; Cancer Survivors; Black Persons -- Tennessee; Medically Underserved; Human; Female; Convenience Sample; Qualitative Studies; Thematic Analysis; Focus Groups; Stigma; Coping; Exploratory Research; Tennessee; Audiorecording; Adult; Middle Age; Aged; Support Groups; Research Subject Recruitment

Chemobrain in Underserved African American Breast Cancer Survivors: A Qualitative Study. - Rust, Connie; Davis, Cindy (Clinical Journal of Oncology Nursing, 2013)
Although research has been conducted to address specific medical and psychosocial needs of breast cancer survivors, little has been done to address needs along the entire trajectory of care. One such need is chemobrain, a phenomenon recognized as an identifiable psychosocial cognitive change in breast cancer survivors. The purpose of this article is to present the findings of a qualitative study conducted with two focus groups of underserved African American breast cancer survivors. Four themes emerged from the transcribed interviews: the concept of chemobrain, variability among individuals, the stigma of chemobrain, and methods of coping. In addition, findings revealed that health professionals were not used by the participants as a resource to address the issues of chemobrain, which holds significant implications for practice. That fact highlights the implications for oncology nursing with respect to providing education and support for patients experiencing chemobrain. Nursing professionals are in a position to be a frontline resource for breast cancer survivors, providing information, education, and coping methods to help improve their quality of life.
Keywords: Cognition Disorders -- Chemically Induced; Antineoplastic Agents -- Adverse Effects; Breast Neoplasms; Cancer Survivors; Black Persons -- Tennessee; Medically Underserved; Human; Female; Convenience Sample; Qualitative Studies; Thematic Analysis; Focus Groups; Stigma; Coping; Exploratory Research; Tennessee; Audiorecording; Adult; Middle Age; Aged; Support Groups; Research Subject Recruitment

Chemoprevention of breast cancer with selective estrogen receptor modulators: views from broadly diverse focus groups of women with elevated risk for breast cancer. - Cyrus-David MS; Strom SS; Cyrus-David, M S; Strom, S S (Psycho-Oncology, 2001)
Selective estrogen receptor modulators (SERMs) are anti-estrogens that selectively antagonize the proliferative effects of estrogens on breast cells, thereby inhibiting or reversing neoplastic progression to clinical breast cancer. The goal is to administer these agents to healthy women with an elevated risk for breast cancer. The study reported here assessed the knowledge and attitude of 26 broadly selected women with an elevated risk for breast cancer who participated in three focus groups (eight to ten per group) that discussed the use of SERMs, such as tamoxifen and raloxifen. Data were analyzed by cross-case procedure using variable-oriented strategies. Acceptance of breast cancer chemoprevention treatment with SERMs was found to be influenced by various factors, including a knowledge of breast cancer risk factors, the perception of personal risk for breast cancer, and the perception of barriers and benefits to receiving chemoprevention treatment. The issues involved in making the decision to accept treatment with SERMs are discussed. Most of the participants in the groups indicated they were unlikely to accept breast cancer chemoprevention treatment with SERMs.
Keywords: Breast Neoplasms; Estrogen Antagonists -- Administration and Dosage; Patient Attitudes; Chemoprevention; Focus Groups; Research Subject Recruitment; Qualitative Studies; Descriptive Statistics; Patient Attitudes -- Evaluation; White Persons; Black Persons; Health Knowledge -- Evaluation; Adult; Middle Age; Aged; Female; Funding Source; Human

Clinical Efficacy of Enzalutamide vs Bicalutamide Combined With Androgen Deprivation Therapy in Men With Metastatic Hormone-Sensitive Prostate Cancer: A Randomized Clinical Trial. - Vaishampayan, Ulka N.; Heilbrun, Lance K.; Monk III, Paul; Tejwani, Sheela; Sonpavde, Guru; Hwang, Clara; Smith, Daryn; Jasti, Pallavi; Dobson, Kimberlee; Dickow, Brenda; Heath, Elisabeth I.; Semaan, Louie; et al. (JAMA Network Open, 2021)
Key Points: Question: Is enzalutamide combined with androgen deprivation therapy associated with better outcomes than treatment with bicalutamide in Black men with metastatic hormone-sensitive prostate cancer (mHSPC)? Findings: In a randomized clinical trial of 71 men with mHSPC, the 7-month prostate-specific antigen response rate was significantly improved with enzalutamide vs bicalutamide among Black patients but not among non-Black patients. Meaning: These findings suggest that treatment with enzalutamide is associated with improved outcomes vs bicalutamide in Black men with mHSPC, and incorporation of enzalutamide in the mHSPC treatment plan should be strongly considered. This randomized clinical trial examines the efficacy of enzalutamide vs bicalutamide in combination with androgen deprivation therapy (ADT) in men with metastatic hormone-sensitive prostate cancer. Importance: Black patients have been underrepresented in prospective clinical trials of advanced prostate cancer. This study evaluated the efficacy of enzalutamide compared with bicalutamide, with planned subset analysis of Black patients with metastatic hormone-sensitive prostate cancer (mHSPC), which is a disease state responsive to androgen deprivation therapy (ADT). Objective: To compare the efficacy of enzalutamide vs bicalutamide in combination with ADT in men with mHSPC, with a subset analysis of Black patients. Design, Setting, and Participants: In this randomized clinical trial, a phase 2 screening design enabled a nondefinitive comparison of the primary outcome by treatment. Patients were stratified by race (Black or other) and bone pain (present or absent). Accrual of at least 30% Black patients was required. This multicenter trial was conducted at 4 centers in the US. Men with mHSPC with no history of seizures and adequate marrow, renal, and liver function were eligible. Data analysis was performed from February 2019 to March 2020. Interventions: Participants were randomized 1:1 to receive oral enzalutamide (160 mg daily) or bicalutamide (50 mg daily) in addition to ADT. Main Outcomes and Measures: The primary end point was the 7-month prostate-specific antigen (PSA) response (SMPR) rate, a previously accepted surrogate for overall survival (OS) outcome. Secondary end points included adverse reactions, time to PSA progression, and OS. Results: A total of 71 men (median [range] age, 65 [51-86] years) were enrolled; 29 (41%) were Black, 41 (58%) were White, and 1 (1%) was Asian. Thirty-six patients were randomized to receive enzalutamide, and 35 were randomized to receive bicalutamide. Twenty-six patients (37%) had bone pain and 37 patients (52%) had extensive disease. SMPR was achieved in 30 of 32 patients (94%; 95% CI, 80%-98%) taking enzalutamide and 17 of 26 patients (65%; 95% CI, 46%-81%) taking bicalutamide (P =.008) (difference, 29%; 95% CI, 5%-50%). Among Black patients, the SMPR was 93% (95% CI, 69%-99%) among those taking enzalutamide and 42% (95% CI, 19%-68%) among those taking bicalutamide (P =.009); among non-Black patients, the SMPR was 94% (95% CI, 74%-99%) among those taking enzalutamide and 86% (95% CI, 60%-96%) among those taking bicalutamide. The 12-month PSA response rates were 84% with enzalutamide and 34% with bicalutamide. Conclusions and Relevance: The findings of this randomized clinical trial comparing enzalutamide with bicalutamide suggest that enzalutamide is associated with improved outcomes compared with bicalutamide, in terms of the rate and duration of PSA response, in Black patients with mHSPC. Trial Registration: ClinicalTrials.gov Identifier: NCT02058706
Keywords: Prostatic Neoplasms -- Drug Therapy; Neoplasm Metastasis -- Drug Therapy; Androgen Antagonists -- Administration and Dosage; Bicalutamide -- Administration and Dosage; Drug Efficacy; Hormone Therapy; Men's Health; Outcomes (Health Care); Human; Randomized Controlled Trials; Random Assignment; Black Persons; Multicenter Studies; Middle Age; Aged; Aged, 80 and Over; Confidence Intervals; Survival; Immunohistochemistry; Gene Expression; Kaplan-Meier Estimator; Log-Rank Test; Cox Proportional Hazards Model; Data Analysis Software; Chi Square Test; Funding Source; Fisher's Exact Test

Clinical trial resources on the internet must be designed to reach underrepresented minorities. - Wilson JJ; Mick R; Wei SJ; Rustgi AK; Markowitz SD; Hampshire M; Metz JM; Wilson, John J; Mick, Rosemarie; Wei, S Jack; Rustgi, Anil K; Markowitz, Sanford D; et al. (Cancer Journal, 2006)
Purpose: Internet-based clinical trial information services are being developed to increase recruitment to studies. However, there are limited data that evaluate their ability to reach elderly and underrepresented minority populations. This study was designed to evaluate the ability of an established clinical trials registry to reach these populations based on expected Internet use.Patients and Methods: This study compares general Internet users to participants who enrolled in an Internet based colorectal cancer clinical trials registry established by OncoLink (www.oncolink.org) and the National Colorectal Cancer Research Alliance. Observed rates of demographic groupings were compared to those established for general Internet users.Results: Two thousand, four hundred and thirty-seven participants from the continental United States used the Internet to register for the database. New England, the Mid-Atlantic region, and the Southeast had the highest relative frequency of participation in the database, whereas the Upper Midwest, California, and the South had the lowest rates. Compared to general Internet users, there was an overrepresentation of women (73% vs. 50%) and participants over 55 years old (27% vs. 14%). However, there was an underrepresentation of minorities (10.3% vs. 22%), particularly African Americans (3.1% vs. 8%) and Hispanics (2.8% vs. 9%).Discussion: The Internet is a growing medium for registry into clinical trials databases. However, even taking into account the selection bias of Internet accessibility, there are still widely disparate demographics between general Internet users and those registering for clinical trials, particularly the underrepresentation of minorities. Internet-based educational and recruitment services for clinical trials must be designed to reach these underrepresented minorities to avoid selection biases in future clinical trials.
Keywords: Clinical Trials; Internet; Minority Groups; Research Subject Recruitment; Black Persons; Female; Funding Source; Hispanic Americans; Male; Middle Age; Human

Cluster Randomized Trial of a Church-Based Peer Counselor and Tailored Newsletter Intervention to Promote Colorectal Cancer Screening and Physical Activity Among Older African Americans. - Leone, Lucia A.; Allicock, Marlyn; Pignone, Michael P.; Walsh, Joan F.; Johnson, La-Shell; Armstrong-Brown, Janelle; Carr, Carol C.; Langford, Aisha; Ni, Andy; Resnicow, Ken; Campbell, Marci K. (Health Education & Behavior, 2016)
Action Through Churches in Time to Save Lives (ACTS) of Wellness was a cluster randomized controlled trial developed to promote colorectal cancer screening and physical activity (PA) within urban African American churches. Churches were recruited from North Carolina (n = 12) and Michigan (n = 7) and were randomized to intervention (n = 10) or comparison (n = 9). Intervention participants received three mailed tailored newsletters addressing colorectal cancer screening and PA behaviors over approximately 6 months. Individuals who were not up-to-date for screening at baseline could also receive motivational calls from a peer counselor. The main outcomes were up-to-date colorectal cancer screening and Metabolic Equivalency Task (MET)-hours/week of moderate–vigorous PA. Multivariate analyses examined changes in the main outcomes controlling for church cluster, gender, marital status, weight, and baseline values. Baseline screening was high in both intervention (75.9%, n = 374) and comparison groups (73.7%, n = 338). Screening increased at follow-up: +6.4 and +4.7 percentage points for intervention and comparison, respectively (p = .25). Baseline MET-hours/week of PA was 7.8 (95% confidence interval [6.8, 8.7]) for intervention and 8.7 (95% confidence interval [7.6, 9.8]) for the comparison group. There were no significant changes (p = .15) in PA for intervention (−0.30 MET-hours/week) compared with the comparison (−0.05 MET-hours/week). Among intervention participants, PA increased more for those who participated in church exercise programs, and screening improved more for those who spoke with a peer counselor or recalled the newsletters. Overall, the intervention did not improve PA or screening in an urban church population. These findings support previous research indicating that structured PA opportunities are necessary to promote change in PA and churches need more support to initiate effective peer counselor programs.
Keywords: Counseling; Newsletters -- Utilization; Colorectal Neoplasms -- Prevention and Control -- In Old Age; Cancer Screening -- In Old Age; Black Persons -- In Old Age; Human; Randomized Controlled Trials; Peer Group; Churches; Physical Activity; North Carolina; Urban Areas; Multivariate Analysis; Outcomes (Health Care); Confidence Intervals; Counselors; Female; Male; Aged; Random Assignment; Michigan; Middle Age; Surveys; Social Learning Theory; Data Analysis Software; Prospective Studies; Funding Source

Coaching Intervention As a Strategy for Minority Recruitment to Cancer Clinical Trials. - Fracasso, Paula M.; Goodner, Sherry A.; Creekmore, Allison N.; Morgan, Helen P.; Foster, Denise M.; Hardmon, Angela A.; Engel, Seth J.; Springer, Brian C.; Mathews, Katherine J.; Fisher, Edwin B.; Walker, Mark S. (Journal of Oncology Practice, 2013)
Purpose: Lack of trust and rapport with health care providers has been identified in the under-representation of racial/ethnic minorities within clinical trials. Our study used a coach to promote trust among minority patients with advanced cancer. Patients and Methods: Minority patients with advanced breast, colorectal, lung, or prostate carcinoma were randomly assigned to receive a coach Intervention (CI) or usual care (UC). All patients completed baseline and 6-month telephone interviews to assess demographics, trust in health care providers, attitudes toward clinical trials, and quality of life. Patients randomly assigned to CI were assigned a coach, who made biweekly contacts for 6 months to address general issues, progress or development in cancer care, and available resources. Patients randomly assigned to UC received the standard of care, without this intervention. Clinical trial enrollment was assessed. Results: Over 21 months, we screened 268 patients and enrolled 73 African Americans and two Asian Americans. Patients were randomly assigned to CI (n = 38) or to UC (n = 37). Longitudinal analyses were conducted on 69 patients who completed the 6-month follow-up assessment. Trial enrollment was 16 and 13 patients for the CI and UC groups, respectively. This difference was not significant (P = .351). Higher quality of life (1-point odds ratio on Functional Assessment of Cancer Treatment- General = 1.033, P = .036) and positive attitudes toward trials predicted enrollment. There was no significant difference between these groups in quality of life, attitudes toward clinical trials, perceptions of racism, trust in doctors, or depression. Conclusions: Quality of life and positive attitude toward trials predicted trial enrollment, regardless of assignment to CI or UC.
Keywords: Minority Groups; Cancer Patients; Research Subject Recruitment; Human; Male; Female; Random Assignment; Questionnaires; Prospective Studies; Odds Ratio; Fisher's Exact Test; Adult; Middle Age; Aged; Aged, 80 and Over; Confidence Intervals; Funding Source

Collaborative breast health intervention for African American women of lower socioeconomic status. - Fowler BA; Rodney M; Roberts S; Broadus L (Oncology Nursing Forum, 2005)
PURPOSE/OBJECTIVES: To describe all phases of a collaborative breast health intervention delivered by paraprofessionals or specially trained community health advisors (CHAs) for African American women designed to increase mammography screening. DESIGN: Collaborative pretest, post-test breast health intervention. SETTING: Large city in Ohio. SAMPLE: 68 African American women with a median age of 57.8 (SD = 5.28) obtained mammography screening and participated in the breast health intervention. METHODS: Specially trained CHAs used aggressive recruitment strategies to increase mammography screening and knowledge of breast health and mammography screening in African American women aged 50 and older. MAIN RESEARCH VARIABLES: Knowledge scores of breast health and mammography screening. FINDINGS: Ninety women (81%) met the inclusion criteria and were recruited into the intervention, but only 68 (76%) obtained mammography screening. The women demonstrated increased knowledge by change in pre- to post-test scores. Several questions were statistically significant. CONCLUSIONS: Collaborative breast health interventions delivered by trained CHAs are effective in increasing screenings as well as knowledge of breast health and mammography screening in African American women. The unique role of the CHA is especially important in recruitment of hard-to-reach women and was vital to the success of the educational intervention. Most importantly, the women valued the individualized attention to their breast health and agreed to share the information with significant others. Further collaborative interventions designed to increase screenings and increase knowledge of breast health and mammography screening are needed to reduce the health disparities of later-stage detection and poorer survival of breast cancer in African American women. IMPLICATIONS FOR NURSING: Oncology nurses should build on the findings and deliver further outreach programs to increase mammography screening and knowledge of breast health in a larger number of women of lower socioeconomic status. Future research is needed to determine the influence of reminder phone calls for mammography screening. Oncology nurses should incorporate evaluation strategies at baseline and periodically throughout an intervention to provide more comprehensive data and enhance the credibility of findings. To maximize success, oncology nurses should work collaboratively with other healthcare professionals such as certified x-ray technicians and influential people in the community to increase knowledge of breast health and mammography screening.
Keywords: Black Persons; Breast Neoplasms -- Prevention and Control; Community Health Services; Health Promotion; Mammography -- Utilization; Poverty; Community Health Workers -- Education; Convenience Sample; Cost Benefit Analysis; Descriptive Statistics; Experimental Studies; Female; Health Education; Health Knowledge -- Evaluation; Middle Age; Ohio; Oncologic Nursing; Paired T-Tests; Pretest-Posttest Design; Purposive Sample; Questionnaires; Research Subject Recruitment; Socioeconomic Factors; Human

Colorectal cancer knowledge, perceptions, and behaviors in African Americans. - Green PM; Kelly BA (Cancer Nursing, 2004)
Disparities in healthcare among racial and ethnic minorities are associated with poor outcomes. African Americans have the highest incidence of colorectal cancer (CRC) among all racial groups. Using a nonrandom sample of 100 African American men and women, 50 years of age and older, the authors explored CRC knowledge, perceptions, and screening behaviors of African American men and women who resided or worked in an urban low-income housing residence. The extent to which screening may be attributed to demographic, sociopsychological, and structural variables was also investigated. Respondents demonstrated inadequate knowledge of CRC, with a significant difference in mean scores between males and females. Self-report of participation in CRC screening was above the national average, with almost half of the sample reporting fecal occult blood home kit use and more than half of the sample reporting completion of sigmoid and colonoscopy exams and double contrast barium enema exam. A majority perceived CRC as a threat. A very high percentage perceived numerous benefits to CRC screening in preventing CRC susceptibility. Perceived barriers of nearly half of the sample included screening may be painful and afraid to find out something is wrong if I have CRC screening, while more than half did not know how to schedule screening. Barriers and threat were correlated with grade school education. Barriers were negatively correlated with secondary education and post-secondary education and moderately correlated with threat. Predictor variables found in the Health Belief Model accounted for a significant amount of the variance in screening behavior, barriers, and threat. Older African American men and women need more information about CRC in order to increase their awareness of CRC and the importance of screening. There is a need to educate healthcare professionals about the causes, prevention, and detection of CRC and the importance of screening.
Keywords: Attitude to Illness -- Evaluation; Black Persons -- United States; Cancer Screening -- Utilization; Colorectal Neoplasms; Health Knowledge -- Evaluation; Aged; Bias (Research); Coefficient Alpha; Conceptual Framework; Convenience Sample; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Education, Continuing (Credit); Educational Status; Female; Funding Source; Health Belief Model; Health Services Accessibility; Independent Variable; Male; Middle Age; Poverty; Questionnaires; Race Factors; Regression; Research Subject Recruitment; Sex Factors; Spearman's Rank Correlation Coefficient; Summated Rating Scaling; T-Tests; United States; Urban Areas; Human

Colorectal Cancer Screening in Vulnerable Patients: Promoting Informed and Shared Decisions. - Brenner, Alison T.; Hoffman, Richard; McWilliams, Andrew; Pignone, Michael P.; Rhyne, Robert L.; Tapp, Hazel; Weaver, Mark A.; Callan, Danelle; de Hernandez, Brisa Urquieta; Harbi, Khalil; Reuland, Daniel S. (American Journal of Preventive Medicine, 2016)
Introduction: Low-income, low-literacy, limited English-proficient populations have low colorectal cancer (CRC) screening rates and experience poor patient-provider communication and decision-making processes around screening. The purpose of this study was to test the effect of a CRC screening decision aid on screening-related communication and decision making in primary care visits.Study Design: RCT with data collected from patients at baseline and immediately after the provider encounter.Setting/participants: Patients aged 50-75 years, due for CRC screening, were recruited from two safety net clinics in North Carolina and New Mexico (data collection, January 2014-September 2015; analysis, 2015).Intervention: Participants viewed a CRC screening decision aid or a food safety (control) video immediately before their provider encounter.Main Outcome Measures: CRC screening-related knowledge, discussion, intent, test preferences, and test ordering.Results: The study population (N=262) had a mean age of 58.3 years and was 66% female, 61% Latino, 17% non-Latino black, and 16% non-Latino white. Among Latino participants, 71% preferred Spanish. Compared with controls, intervention participants had greater screening-related knowledge (on average 4.6 vs 2.8 of six knowledge items correct, adjusted difference [AD]=1.8, 95% CI=1.5, 2.1) and were more likely to report screening discussion (71.0% vs 45.0%, AD=26.1%, 95% CI=14.3%, 38.0%) and high screening intent (93.1% vs 84.7%, AD=9.0%, 95% CI=2.0%, 16.0%). Intervention participants were more likely to indicate a specific screening test preference (93.1% vs 68.0%, AD=26.5%, 95% CI=17.2%, 35.8%) and to report having a test ordered (56.5% vs 32.1%, AD=25.8%, 95% CI=14.4%, 37.2%).Conclusions: Viewing a CRC screening decision aid before a primary care encounter improves knowledge and shared decision making around screening in a racially, ethnically, and linguistically diverse safety net clinic population.Trial Registration: This study is registered at www.clinicaltrials.gov NCT02054598.
Keywords: Health Screening -- Psychosocial Factors; Special Populations -- Psychosocial Factors; Colorectal Neoplasms -- Diagnosis; Decision Making; Decision Support Techniques; Middle Age; Aged; Male; Female; Special Populations; Human; Randomized Controlled Trials; Random Assignment

Combating breast cancer using combination therapy with 3 phytochemicals: Piperine, sulforaphane, and thymoquinone. - Aumeeruddy, M. Zakariyyah; Mahomoodally, M. Fawzi (Cancer (0008543X), 2019)
Despite the significant advances in screening methods for early diagnosis, breast cancer remains a global threat and continues to be the leading cancer diagnosed in women, requiring effective therapy. Currently, combination therapy has become the hallmark of breast cancer treatment due to the high incidence of tumor recurrence and disease progression after monotherapeutic treatments, including surgery, radiotherapy, endocrine therapy, and chemotherapy. Over the past decades, there has been considerable interest in studying the anticancer effect of bioactive phytochemicals from medicinal plants combined with these conventional therapies. The rationale for this type of therapy is to use combinations of drugs that work by different mechanisms, thereby decreasing the likelihood that cancer cells will develop resistance, and also reduce the therapeutic dose and toxicity of single treatments. Three agents have received great attention with regard to their anticancer properties: 1) piperine, a dietary phytochemical isolated from black pepper (Piper nigrum L.) and long pepper (Piper longum L.); 2) sulforaphane, an isothiocyanate mainly derived from cruciferous vegetables; and 3) thymoquinone, the active compound from black seed (Nigella sativa L.). This review focused on the combined effect of these 3 compounds on conventional cancer therapy with the objective of observing enhanced efficacy compared with single treatments. This review also highlights the importance of the nanoformulation of such bioactive phytochemicals that could enhance their bioavailability by providing an efficient targeted delivery system with a reduced systemic dose while resulting in a more efficient dosing at the target site.
Keywords: Benzoquinones -- Administration and Dosage; Heterocyclic Compounds -- Administration and Dosage; Medicine, Herbal -- Methods; Breast Neoplasms -- Drug Therapy; Alkaloids -- Administration and Dosage; Piperidines -- Administration and Dosage; Amides -- Administration and Dosage; Phytochemicals -- Administration and Dosage; Combined Modality Therapy; Patient Selection; In Vitro Studies; Sensitivity and Specificity; Breast Neoplasms -- Pathology; Cell Line, Tumor -- Drug Effects; Antineoplastic Agents -- Administration and Dosage; Chemotherapy, Adjuvant; Female; Breast Neoplasms -- Mortality; Radiotherapy, Adjuvant; Scales

Comparative Effectiveness Research: The Impact of Biologic Agents in Ethnic Minorities With Metastatic Colorectal Cancer. - Goel, Sanjay; Negassa, Abdissa; Khot, Ashish; Goyal, Dharmendra; Shuang Guo; Nandikolla, Amara; Bakirhan, Kamila; Polineni, Rahul; Shah, Umang; Chaudhary, Imran; Ghalib, Mohammad H.; Rajdev, Lakshmi; et al. (Clinical Colorectal Cancer, 2017)
Background: Biologic agents have improved the outcomes of patients with metastatic colorectal cancer (mCRC). However, the clinical trials included a predominately white population (85%), with Hispanic and black patients underrepresented. Thus, the real world benefit for the latter remains unknown. Comparative effectiveness research is a tool allowing for this exploration.Patients and Methods: The demographic and clinical characteristics of patients treated for mCRC from 2000 to 2011 were extracted from the medical records of Montefiore Medical Center. A semiparametric accelerated failure time model was used to assess the survival differences between patients receiving chemotherapy (CT) alone versus CT plus biologic agents (CBT).Results: Of the 290 patients (black, 45.9%; Hispanic, 26.2%; and white, 27.9%), 53.8% received biologic agents. The median overall survival was 15.2 months in the CT-alone group and 25.6 months in CBT group (P = .004). On univariate analysis, a lower number of metastatic sites, carcinoembryonic antigen < 41 ng/mL, and more lines of CT were associated with improved overall survival. In a propensity score-based analysis of the entire cohort, CBT offered a survival benefit compared with CT alone (increased median survival, 1.44-fold; 95% confidence interval [CI], 1.11-1.86; P = .038). The results of the subgroup analysis suggested a survival benefit for white patients (2.01; 95% CI, 1.26-3.23; P = .031) but not for Hispanic (1.42; 95% CI, 0.91-2.20; P = .370) or black (1.12; 95% CI, 0.76-1.66; P = .596) patients.Conclusion: In the present cohort, CBT was associated with longer survival, with the effect mainly driven by the outcomes for white patients, with black patients not appearing to benefit. These data are provocative and warrant further confirmation. Efforts to increase ethnic minority patients' enrollment in clinical trials is required to prospectively define the benefit from novel therapies.
Keywords: Models, Theoretical; Antineoplastic Agents, Combined -- Therapeutic Use; Colorectal Neoplasms -- Drug Therapy; Biological Factors -- Administration and Dosage; Aged; Female; Health Services Research; Aged, 80 and Over; Black Persons -- Statistics and Numerical Data; Prospective Studies; Hispanic Americans -- Statistics and Numerical Data; Adult; Treatment Outcomes; Survival; White Persons -- Statistics and Numerical Data; Middle Age; Antigens, Tumor -- Blood; Male; Human; Antineoplastic Agents, Combined -- Administration and Dosage; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Comparing knowledge of colorectal and prostate cancer among African American and Hispanic men. - Powe BD; Cooper DL; Harmond L; Ross L; Mercado FE; Faulkenberry R (Cancer Nursing, 2009)
African American and Hispanic men are less likely to participate in prostate and colorectal cancer screening and have poorer outcomes from these diseases. Guided by the Patient/Provider/System Theoretical Model for Cancer Screening, this study compares the relationships among knowledge of prostate and colorectal cancer, perceptions of cancer fatalism, common sources of cancer information, and awareness of cancer resources screening between African American (n = 72) and Hispanic (n = 47) men who attend federally qualified health centers and a hospital-based primary care clinic in a southern state. African American men were older, had higher levels of education, and were more knowledgeable about cancer than Hispanic men were. However, Hispanic men were more fatalistic about cancer. Most men in both groups were more likely to get cancer information from the television and/or radio, with few accessing the Internet for this information. The men were not aware of many of the leading cancer-related organizations and programs. Nurses continue to play a critical role in patient education and enhancing screening rates. These findings suggest that culturally and educationally appropriate intervention strategies are needed to enhance knowledge and that the television/radio may be an effective medium for delivering these strategies.
Keywords: Black Persons -- United States; Colorectal Neoplasms; Health Knowledge; Hispanic Americans -- United States; Prostatic Neoplasms; Adult; Aged; Aged, 80 and Over; Attitude to Illness -- Evaluation; Cancer Screening; Chi Square Test; Comparative Studies; Conceptual Framework; Convenience Sample; Descriptive Research; Descriptive Statistics; Effect Size; Health Knowledge -- Evaluation; Male; Middle Age; Models, Theoretical; Pearson's Correlation Coefficient; Quantitative Studies; Questionnaires; Race Factors; Research Subject Recruitment; T-Tests; United States; Human

Complications and outcomes after spinal cord tumor resection in the United States from 1993 to 2002. - Patil CG; Patil TS; Lad SP; Boakye M (Spinal Cord, 2008)
STUDY DESIGN: Retrospective cohort study. OBJECTIVE: Data on patient outcomes after surgery for spinal cord tumors have been derived from single-institution series. The objective of this study is to report inpatient complications, mortality and outcomes on a national level. SETTING: United States, national inpatient care database. METHODS: The National Inpatient Sample (NIS) was used to identify 19,017 admissions for resection of a spinal cord tumor in the United States from 1993 to 2002. The effects of patient and hospital characteristics on inpatient outcomes were analyzed using logistic regression. RESULTS: The in-hospital mortality rate and the complication rate were 0.55 and 17.5%, respectively. Urinary and renal complications (3.7%), postoperative hemorrhages or hematomas (2.5%) and pulmonary complications (2.4%) were the most common complications reported. A single postoperative complication increased the length of stay by 4 days, increased the mortality rate by sixfold and added over $10,000 to hospital charges. Multivariate analysis showed that complications were more likely in African Americans and patients with multiple comorbidities. The odds of an adverse outcome increased significantly with age greater than 64, multiple comorbidities and postoperative complications. CONCLUSION: A national perspective on inpatient outcomes after resection of spinal cord tumors has been provided. The significant negative impact of postoperative complications on mortality and resource utilization has been demonstrated. We have identified advanced age and multiple comorbidities as risk factors that predict adverse outcome. Furthermore, this study highlights the importance of avoidance, recognition and prompt management of nonneurologic complications.
Keywords: Neurosurgery -- Adverse Effects; Postoperative Complications; Spinal Cord Neoplasms -- Complications; Spinal Cord Neoplasms -- Surgery; Adolescence; Adult; Age Factors; Aged; Aged, 80 and Over; Chi Square Test; Child; Child, Preschool; Comorbidity; Confidence Intervals; Data Analysis Software; Female; Infant; Infant, Newborn; Kidney Diseases; Logistic Regression; Lung Diseases; Male; Middle Age; Multivariate Analysis; Odds Ratio; Outcomes (Health Care); Patient Selection; Prospective Studies; Registries, Disease; Retrospective Design; Spinal Cord Neoplasms -- Mortality; Statistical Significance; Human

Confusion about mammography: prevalence and consequences. - Rimer BK; Halabi S; Strigo TS; Crawford Y; Lipkus IM (Journal of Women's Health & Gender-Based Medicine, 1999)
Over the last decade, there has been significant controversy about the schedule on which women, particularly women in their 40s, should have mammograms. The purpose of the analysis reported here was to assess whether women in their 40s and 50s were confused as a result of the controversy following the January 1997 National Institutes of Health Consensus Development Conference on Breast Cancer Screening For Women Ages 40-49. We also examined if confusion was related to being off schedule for mammography. The study sample included 1287 women recruited from a random sample of 2165 Blue Cross/Blue Shield of North Carolina members. The data described in this analysis were derived from a baseline telephone interview conducted as part of a larger intervention trial. Study measures included a variety of sociodemographic, medical, belief, and behavioral variables. Overall, 28% of women were confused, and 35% were off schedule. Although a higher proportion of women in their 40s than 50s were confused, more women in their 50s were off schedule. Confusion was a significant predictor for the outcome being off schedule. Predictors of confusion included several belief variables, risk perceptions, age (40s), whether the woman had a regular physician, and whether she had enough information about mammography. Healthcare providers should ask some simple questions to determine if women are confused and then seek to meet their information needs.
Keywords: Mammography -- Psychosocial Factors; Appointments and Schedules; Confusion -- Epidemiology; Health Knowledge; Evaluation Research; Epidemiological Research; Mammography -- Utilization; Attitude to Health; Attitude Measures; Stratified Random Sample; Female; Adult; Middle Age; Insurance, Health; Telephone; Interviews; Surveys; Questionnaires; Breast Neoplasms -- Prevention and Control; Cancer Screening; Psychological Tests; Pearson's Correlation Coefficient; Chi Square Test; T-Tests; Coefficient Alpha; Logistic Regression; P-Value; Odds Ratio; Confidence Intervals; Independent Variable; Goodness of Fit Chi Square Test; Descriptive Statistics; White Persons; Black Persons; Demography; Health Beliefs; Women's Health; Human

Contemporary prostate cancer treatment choices in multidisciplinary clinics referenced to national trends. - Tang, Chad; Hoffman, Karen E.; Allen, Pamela K.; Gabel, Molly; Schreiber, David; Choi, Seungtaek; Chapin, Brian F.; Nguyen, Quynh‐Nhu; Davis, John W.; Corn, Paul; Logothetis, Christopher; Ward, John; et al. (Cancer (0008543X), 2020)
Background: The purpose of this study was to assess treatment choices among men with prostate cancer who presented at The University of Texas MD Anderson Cancer Center multidisciplinary (MultiD) clinic compared with nationwide trends.Methods: In total, 4451 men with prostate cancer who presented at the MultiD clinic from 2004 to 2016 were analyzed. To assess nationwide trends, the authors analyzed 392,710 men with prostate cancer who were diagnosed between 2004 and 2015 from the Surveillance, Epidemiology, and End Results (SEER) database. The primary endpoint was treatment choice as a function of pretreatment demographics.Results: Univariate analyses revealed similar treatment trends in the MultiD and SEER cohorts. The use of procedural forms of definitive therapy decreased with age, including brachytherapy and prostatectomy (all P < .05). Later year of diagnosis/clinic visit was associated with decreased use of definitive treatments, whereas higher risk grouping was associated with increased use (all P < .001). Patients with low-risk disease treated at the MultiD clinic were more likely to receive nondefinitive therapy than patients in SEER, whereas the opposite trend was observed for patients with high-risk disease, with a substantial portion of high-risk patients in SEER not receiving definitive therapy. In the MultiD clinic, African American men with intermediate-risk and high-risk disease were more likely to receive definitive therapy than white men, but for SEER the opposite was true.Conclusions: Presentation at a MultiD clinic facilitates the appropriate disposition of patients with low-risk disease to nondefinitive strategies of patients with high-risk disease to definitive treatment, and it may obviate the influence of race.
Keywords: Prostatic Neoplasms -- Therapy; Prostatic Neoplasms -- Epidemiology; Male; Middle Age; Prostate-Specific Antigen -- Blood; Black Persons; Brachytherapy -- Trends; Registries, Disease; White Persons; United States; Aged; Patient Selection; Prostatectomy -- Trends; Human; Prostatic Neoplasms -- Blood; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Coping and distress among women under treatment for early stage breast cancer: comparing African Americans, Hispanics, and non-Hispanic whites. - Culver JL; Arena PL; Antoni MH; Carver CS (Psycho-Oncology, 2002)
Keywords: Breast Neoplasms -- Psychosocial Factors; Coping -- Ethnology; Race Factors; Stress, Psychological -- Ethnology; Adult; Aged; Analysis of Variance; Black Persons; Center for Epidemiological Studies Depression Scale; Comparative Studies; Psychological Tests; Scales; Descriptive Statistics; Female; Hispanic Americans; Interviews; Middle Age; Prospective Studies; Research Subject Recruitment; White Persons; Funding Source; Human

Coping strategies among African American women with breast cancer. - Henderson PD; Fogel J; Edwards QT (Southern Online Journal of Nursing Research, 2003)
Although coping strategies have proven vital in assisting women to adapt to a diagnosis of breast cancer, few researchers have focused on coping strategies used by African American women with breast cancer. The objectives of this study were to determine the coping strategies used by African American women with breast cancer and to explore sociodemographic variables such as age, income, education, marital status, and length of time since diagnosis on coping strategies among African American women with breast cancer. A cross-sectional design was used to study relationships among these variables. The sample consisted of 86 African American women with a diagnosis of breast cancer living in the southeastern United States. Participants were surveyed with a demographic data sheet and the Ways of Coping Questionnaire (WCQ). Data were analyzed with descriptive statistics and multiple linear regression analyses. Results indicated that positive reappraisal and seeking social support are the most commonly used coping strategies among African American women with breast cancer. No significant relationships were found among sociodemographic variables and coping strategies among African American women. Also, a comparison of our mean coping strategy scores among African American women with breast cancer are higher than the mean coping strategy scores from a previous study of mostly Caucasian women with breast cancer. Further research is needed to explore coping strategies of positive reappraisal and seeking social support as these may be important factors in how African American women survive breast cancer.
Keywords: Black Persons -- United States; Breast Neoplasms; Cancer Patients -- Psychosocial Factors; Coping; Adult; Aged; Coefficient Alpha; Conceptual Framework; Confidence Intervals; Convenience Sample; Cross Sectional Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Female; Middle Age; Multiple Linear Regression; Power Analysis; Questionnaires; Research Subject Recruitment; Roy Adaptation Model; Socioeconomic Factors; Southeastern United States; Support, Psychosocial; T-Tests; United States; Ways of Coping Questionnaire; Human

Correlates of Patient Intent and Preference on Colorectal Cancer Screening. - Jimbo, Masahito; Sen, Ananda; Plegue, Melissa A.; Hawley, Sarah T.; Kelly-Blake, Karen; Rapai, Mary; Zhang, Minling; Zhang, Yuhong; IVRuffin, Mack T.; Ruffin, Mack T 4th (American Journal of Preventive Medicine, 2017)
Introduction: Information is limited on patient characteristics that influence their preference among screening options and intent to be screened for colorectal cancer (CRC). A mechanistic pathway to intent and preference was examined through a formal mediation analysis.Methods: From 2012 to 2014, a total of 570 adults aged 50-75 years were recruited from 15 primary care practices in Metro Detroit for a trial on decision aids for CRC screening. Confirmatory factor, regression, and mediation analyses were performed in 2015-2016 on baseline cross-sectional data. Main outcomes were patient intent and preference. Perceived risk and self-efficacy were secondary outcomes. Covariates included demographic information, health status, previous CRC screening experience, patient attitudes, and knowledge.Results: Mean age was 57.7 years, 56.1% were women, and 55.1% white and 36.6% black. Women had 32% and 41% lower odds than men of perceiving CRC to be high/moderate risk (OR=0.68, 95% CI=0.47, 0.97, p=0.03) and having high self-efficacy (OR=0.59, 95% CI=0.42, 0.85, p=0.006), respectively. Whites had 63% and 47% lower odds than blacks of having high self-efficacy (OR=0.37, 95% CI=0.25, 0.57, p<0.001) and intent to undergo CRC screening (OR=0.53, 95% CI=0.34, 0.84, p=0.007), respectively. Younger age, higher knowledge, lower level of test worries, and medium/high versus low self-efficacy increased the odds of intent of being screened. Self-efficacy, but not perceived risk, significantly mediated the association between race, attitude, and test worries and patient screening intent.Conclusions: Self-efficacy mediated the association between race, attitude, and test worries and patient intent.
Keywords: Colorectal Neoplasms -- Diagnosis; Intention; Health Screening -- Psychosocial Factors; Decision Support Techniques; Patient Satisfaction; Human; Cross Sectional Studies; Male; Middle Age; Female; Colorectal Neoplasms -- Psychosocial Factors; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Funding Source

Correlates of quality of life among african american and white cancer survivors. - Matthews, Alicia K; Tejeda, Silvia; Johnson, Timothy P; Berbaum, Michael L; Manfredi, Clara (Cancer Nursing, 2012)
BACKGROUND: : African Americans continue to suffer disproportionately from cancer morbidity and mortality, with emerging evidence suggesting potential quality of life (QOL) disparities in the survivorship period. OBJECTIVE: : The objective of the study was to assess sociodemographic, clinical, and psychosocial factors associated with physical and mental health QOL (PHQOL and MHQOL) among African American and white cancer survivors. METHODS: : Patients were recruited from tumor registries. Telephone interviews were conducted with 248 African American and 244 white respondents with a history of breast, prostate, or colorectal cancers. Multivariate regression models were used to assess what factors were associated with PHQOL and MHQOL. RESULTS: : Key racial differences in adjusted analyses included poorer MHQOL scores among African Americans compared with white survivors. Furthermore, race moderated the relationship between perceived social support and MHQOL, where higher social support levels were associated with increased MHQOL among African Americans. Other correlates of QOL impacted racial groups similarly. For example, factors associated with PHQOL scores included being unemployed, being uninsured, the presence of medical comorbidities, a longer time since diagnosis, and higher levels of cancer-related stress appraisals. Factors associated with MHQOL scores included being unemployed, higher levels of daily stress, higher levels of stress associated with the diagnosis, higher levels of education, higher levels of perceived social support, and higher levels of spirituality. CONCLUSION: : Interventions aimed at increasing social support may have important implications for improving QOL outcomes among African Americans. IMPLICATIONS FOR PRACTICE: : Measuring and understanding factors associated with QOL have important implications for patient adjustment and clinical decision making.
Keywords: Black Persons; Cancer Survivors; Health Status; Mental Health; Quality of Life; Race Factors; White Persons; Adult; Aged; Breast Neoplasms; Chi Square Test; Colorectal Neoplasms; Comorbidity; Comparative Studies; Descriptive Research; Descriptive Statistics; Educational Status; Employment Status; Funding Source; Human; Illinois; Income; Interviews; Medically Uninsured; Middle Age; Multiple Regression; Prostatic Neoplasms; Quality of Life -- Evaluation; Registries, Disease; Research Subject Recruitment; Rural Areas; Scales; Short Form-36 Health Survey (SF-36); Spirituality -- Evaluation; Support, Psychosocial; T-Tests; Telephone; Urban Areas

Correlates of quality of life in overweight or obese breast cancer survivors at enrollment into a weight loss trial. - Pakiz, Bilgé; Ganz, Patricia A.; Sedjo, Rebecca L.; Flatt, Shirley W.; Demark‐Wahnefried, Wendy; Liu, Jingxia; Wolin, Kathleen Y.; Rock, Cheryl L. (Psycho-Oncology, 2016)
Objective: The purpose of this analysis was to examine the correlates of the physical and psychosocial domains of quality of life (QOL) in a cohort of breast cancer survivors participating in a weight loss intervention trial.Methods: Correlates of QOL and psychosocial functioning were examined in 692 overweight or obese breast cancer survivors at entry into a weight loss trial. QOL was explored with three measures: Short-form 36 (SF-36), Impact of Cancer scale (IOC), and the Breast Cancer Prevention Trial (BCPT) symptom scales. Available data included information on weight and physical activity, as well as demographic and medical characteristics. Multivariate analyses were used to identify associations adjusted for other characteristics.Results: In multivariate analysis, younger age was associated with higher negative impact scores (p < 0.0001). Hispanic, African-American, and Asian women had higher positive IOC impact scores compared with White non-Hispanic women (p < 0.01). Increased number of comorbidities was associated with lower physical and mental QOL scores (p < 0.01). Body mass index was not independently associated with QOL measures. Physical activity was directly associated with physical and mental QOL and IOC positive impact, and inversely related to IOC negative impact and Breast Cancer Prevention Trial symptom scales.Conclusions: Quality-of-life measures in breast cancer survivors are differentially associated with demographic and other characteristics. When adjusted for these characteristics, degree of adiposity among overweight or obese women does not appear to be independently associated with QOL. Among overweight or obese breast cancer survivors, higher level of physical activity is associated with higher QOL across various scales and dimensions.
Keywords: Obesity -- Therapy; Breast Neoplasms -- Psychosocial Factors; Weight Loss; Obesity -- Psychosocial Factors; Quality of Life -- Psychosocial Factors; Survivors -- Psychosocial Factors; Aged; Middle Age; Female; Adult; Body Weight; Human; Body Mass Index; Obesity -- Complications; Ethnic Groups; Clinical Trials; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Short Form-36 Health Survey (SF-36); Funding Source; Scales

Cost analysis of a patient navigation system to increase screening colonoscopy adherence among urban minorities. - Jandorf L; Stossel LM; Cooperman JL; Graff Zivin J; Ladabaum U; Hall D; Thélémaque LD; Redd W; Itzkowitz SH; Jandorf, Lina; Stossel, Lauren M; Cooperman, Julia L; et al. (Cancer (0008543X), 2013)
Background: Patient navigation (PN) is being used increasingly to help patients complete screening colonoscopy (SC) to prevent colorectal cancer. At their large, urban academic medical center with an open-access endoscopy system, the authors previously demonstrated that PN programs produced a colonoscopy completion rate of 78.5% in a cohort of 503 patients (predominantly African Americans and Latinos with public health insurance). Very little is known about the direct costs of implementing PN programs. The objective of the current study was to perform a detailed cost analysis of PN programs at the authors' institution from an institutional perspective.Methods: In 2 randomized controlled trials, average-risk patients who were referred for SC by primary care providers were recruited for PN between May 2008 and May 2010. Patients were randomized to 1 of 4 PN groups. The cost of PN and net income to the institution were determined in a cost analysis.Results: Among 395 patients who completed colonoscopy, 53.4% underwent SC alone, 30.1% underwent colonoscopy with biopsy, and 16.5% underwent snare polypectomy. Accounting for the average contribution margins of each procedure type, the total revenue was $95,266.00. The total cost of PN was $14,027.30. Net income was $81,238.70. In a model sample of 1000 patients, net incomes for the institutional completion rate (approximately 80%), the historic PN program (approximately 65%), and the national average (approximately 50%) were compared. The current PN program generated additional net incomes of $35,035.50 and $44,956.00, respectively.Conclusions: PN among minority patients with mostly public health insurance generated additional income to the institution, mainly because of increased colonoscopy completion rates.
Keywords: Colonoscopy -- Utilization; Health Screening -- Utilization; Minority Groups -- Statistics and Numerical Data; Patient Compliance; Urban Population -- Economics; Aged; Aged, 80 and Over; Black Persons -- Statistics and Numerical Data; Carcinoma -- Diagnosis; Carcinoma -- Economics; Carcinoma -- Epidemiology; Carcinoma -- Prevention and Control; Colonoscopy -- Economics; Colonoscopy -- Psychosocial Factors; Colorectal Neoplasms -- Diagnosis; Colorectal Neoplasms -- Economics; Colorectal Neoplasms -- Epidemiology; Colorectal Neoplasms -- Prevention and Control; Costs and Cost Analysis; Female; Health Screening -- Economics; Health Screening -- Psychosocial Factors; Hispanic Americans -- Statistics and Numerical Data; Human; Male; Middle Age; Minority Groups -- Psychosocial Factors; Occult Blood; Randomized Controlled Trials

Currently recommended lung cancer screening guidelines may be insufficient for high-risk minorities. - Printz, Carrie (Cancer (0008543X), 2019)
The article discusses how inadequate screening guidelines for under-served populations has led to racial disparities in lung cancer outcomes. A team of researchers compared patients in a Chicago-based lung cancer screening program with those enrolled in the National Lung Screening Trial (NLST), a large-scale study of current and former smokers sponsored by the NCI. The Chicago screening program reportedly resulted in double the frequency of positive scans.
Keywords: Lung Neoplasms -- Ethnology; Early Detection of Cancer -- Methods; Lung Neoplasms -- Diagnosis; Human; Female; Black Persons -- Statistics and Numerical Data; Male; Illinois -- Ethnology; Clinical Trials; Early Detection of Cancer -- Statistics and Numerical Data; Health Screening; Middle Age; Hispanic Americans -- Statistics and Numerical Data; White Persons -- Statistics and Numerical Data; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Decisional conflict in economically disadvantaged men with newly diagnosed prostate cancer: baseline results from a shared decision-making trial. - Kaplan, Alan L; Crespi, Catherine M; Saucedo, Josemanuel D; Connor, Sarah E; Litwin, Mark S; Saigal, Christopher S (Cancer (0008543X), 2014)
Background: Decisional conflict is a source of anxiety and stress for men diagnosed with prostate cancer given uncertainty surrounding myriad treatment options. Few data exist to help clinicians identify which patients are at risk for decisional conflict. The purpose of this study was to examine factors associated with decisional conflict in economically disadvantaged men diagnosed with prostate cancer before any treatment choices were made.Methods: A total of 70 men were surveyed at a Veterans Administration clinic with newly diagnosed localized prostate cancer enrolled in a randomized trial testing a novel shared decision-making tool. Baseline demographic, clinical, and functional data were collected. Independent variables included age, race, education, comorbidity, relationship status, urinary/sexual dysfunction, and prostate cancer knowledge. Tested outcomes were Decisional Conflict Scale, Uncertainty Subscale, and Perceived Effectiveness Subscale. Multiple linear regression modeling was used to identify factors associated with decisional conflict.Results: Mean age was 63 years, 49% were African American, and 70% reported an income less than $30,000. Poor prostate cancer knowledge was associated with increased decisional conflict and higher uncertainty (P < .001 and P = 0.001, respectively). Poor knowledge was also associated with lower perceived effectiveness (P = 0.003) whereas being in a relationship was associated with higher decisional conflict (P = 0.03).Conclusions: Decreased patient knowledge about prostate cancer is associated with increased decisional conflict and lower perceived effective decision-making. Interventions to increase comprehension of prostate cancer and its treatments may reduce decisional conflict. Further work is needed to better characterize this relationship and identify effective targeted interventions.
Keywords: Dissent and Disputes; Prostatic Neoplasms -- Therapy; Aged; Decision Making; Cross Sectional Studies; Attitude to Health; Human; Income; Male; Middle Age; Prostatic Neoplasms -- Diagnosis; Prostatic Neoplasms -- Economics; Special Populations

Defining the role of antioxidants in the prevention of prostate cancer. - Pathak HR; Singh BP (Indian Journal of Urology, 2009)
This is the largest individually randomized, multicenter cancer prevention trial conducted that has maintained high rates of adherence and retention for 4 to 7 years. This trial recruited 35,533 men who were randomly assigned to four groups (selenium, vitamin E, selenium + vitamin E, and placebo) in a double-blind fashion between 2001 and 2004. Eligibility included age 50 years or older (African American men) or 55 years or older (all other men), a serum prostate-specific antigen level of ≤4 ng/ml, and a digital rectal examination not suspicious for prostate cancer. Antioxidant formulations used were oral selenium (200 µg/d from L-selenomethionine) and matched vitamin E placebo, vitamin E (400 IU/d of all rac-α-tocopheryl acetate), and matched selenium placebo, selenium + vitamin E, or placebo + placebo for a follow-up of minimum of 7 years and a maximum of 12 years. The primary outcome was prostate cancer and prespecified secondary outcomes were lung, colorectal, and overall primary cancer. At median overall follow-up of 5.46 years (range: 4.17.7.33 years), hazard ratios for prostate cancer were 1.13 (99% CI, 0.95-1.35; n = 473) for vitamin E, 1.04 (99% CI, 0.87-1.24; n = 432) for selenium, and 1.05 (99% CI, 0.88-1.25; n = 437) for selenium + vitamin E vs. 1.00 (n = 416) for placebo. No significant differences (all were p > 0.15) were seen in any other prespecified cancer endpoints. There were statistically non significant increased risks of prostate cancer in the vitamin E group (p = 0.06) and Type 2 diabetes mellitus in the selenium group (relative risk, 1.07; 99% CI, 0.94-1.22; p = 0.16), but not in the selenium + vitamin E group. This study concluded that selenium or vitamin E alone or in combination at the doses and formulations used did not prevent prostate cancer in this population of relatively healthy men.
Keywords: Antioxidants; Prostatic Neoplasms -- Prevention and Control; Role; Beta Carotene; Neoplasms -- Mortality; Prostatic Neoplasms -- Risk Factors; Selenium; Vitamin E

Design and Development of a Prostate Cancer Survivor Self-Reported Registry. - Davis, Kimberly E.; Richards, Antoine; Gooden, Reginald O. (Journal of Oncology Navigation & Survivorship, 2018)
Background: Prostate cancer (PCa) incidence and survival rates continue to rise among African American men. An estimated 161,360 new cases were expected to occur in 2017. With increased survival rates, individuals are living longer, thus increasing the risk of experiencing adverse physical and psychosocial longterm effects of the cancer and its treatment. This study explores how minorities affected by PCa can become more informed and active in the decision-making process in the context of a support community. Methods: An online registry was created by researchers from the Center for Cancer Research & Therapeutic Development. The registry captures participants' demographics and clinical disease information throughout the PCa continuum. The registry was made available online at www.pcregistry.cau.edu, required registration and informed consent, and included mechanisms to maintain confidentiality. A voluntary response sample was utilized. Conceptual framework from Andersen's version of the Behavioral Model of Health Services Utilization and Wilson and Cleary's Model of Health-Related Quality of Life were used as the basis for the survey. Key consultants were engaged as community relations advisory board members. Comprehensive recruitment strategies were employed yielding a response rate of over 1000 registered survivors, surpassing the goal of 500. Conclusion: The PCa registry targets a specific group of survivors, exploring subsets that may be underserved or high-risk for distress. The registry is not linked to treatment location, thus respondents are more compelled to share their experience. A comprehensive database system provides ongoing information on health and issues facing ethnic PCa survivors and identifies gaps to determine areas of future research while developing a consensus on implications survivors may face.
Keywords: Database Design; Prostatic Neoplasms -- Therapy; Cancer Survivors -- Psychosocial Factors; Self Report; Registries, Disease; Human; Education, Continuing (Credit); Conceptual Framework; Cancer Screening; Medically Underserved; Minority Groups; Race Factors; Ethnic Groups; Survivorship -- Psychosocial Factors; Stress, Psychological; Oncologic Care; Questionnaires; Support, Psychosocial; Funding Source

Determinants of prostate cancer screening in a sample of African American military servicemen. - Joseph HJ; Joseph, Hyacinth J (Military Medicine, 2006)
This descriptive/cross-sectional study assessed determinants of prostate cancer screening in a sample of African American military servicemen who were age 45 years and older. Data were collected using the Edwards Prostate Perception Survey, a 52-item questionnaire that assessed knowledge, beliefs, self-efficacy, health-related practices, and demographic variables. Despite reporting high knowledge and positive belief about prostate cancer and screening, 43% of the respondents indicated they had never been screened with the prostate-specific antigen blood test, and 27% reported that health care providers had not recommended screening. Respondents were more likely to be screened if they had more knowledge of the prostate-specific antigen test, were retired, older, and when health care providers recommended it. The younger active duty servicemen in the 45 to 50 age group reported the lowest rates of screening.
Keywords: Black Persons; Cancer Screening; Military Personnel -- United States; Prostatic Neoplasms -- Prevention and Control; Coefficient Alpha; Cross Sectional Studies; Data Analysis Software; Demography; Descriptive Research; Hawaii; Middle Age; Questionnaires; Reliability; Research Question; Research Subject Recruitment; Scales; Summated Rating Scaling; Surveys; United States; Funding Source; Human

Developing partnerships and recruiting dyads for a prostate cancer informed decision making program: lessons learned from a community-academic-clinical team. - Friedman, Daniela; Johnson, Kim; Owens, Otis; Thomas, Tracey; Dawkins, DeLisa; Gansauer, Lucy; Bartelt, Sharon; Waddell, Nancy; Talley, Pastor; Bearden, James; Hébert, James; Friedman, Daniela B; et al. (Journal of Cancer Education, 2012)
Prostate cancer (PrCA) is the most commonly diagnosed non-skin cancer among men. PrCA mortality in African-American (AA) men in South Carolina is ~50% higher than for AAs in the U.S as a whole. AA men also have low rates of participation in cancer research. This paper describes partnership development and recruitment efforts of a Community-Academic-Clinical research team for a PrCA education intervention with AA men and women that was designed to address the discordance between high rates of PrCA mortality and limited participation in cancer research. Guided by Vesey's framework on recruitment and retention of minority groups in research, recruitment strategies were selected and implemented following multiple brainstorming sessions with partners having established community relationships. Based on findings from these sessions culturally appropriate strategies are recommended for recruiting AA men and women for PrCA education research. Community-based research recruitment challenges and lessons learned are presented.
Keywords: Black Persons; Health Education; Oncologic Care; Prostatic Neoplasms -- Education; Prostatic Neoplasms -- Ethnology; Research Subject Recruitment; Action Research; Brainstorming; Cancer Screening; Community-Institutional Relations; Female; Focus Groups; Funding Source; Human; Male; Middle Age; Multimedia; Oncologic Nursing; Pilot Studies; Pretest-Posttest Design; Prostatic Neoplasms -- Mortality; Prostatic Neoplasms -- Nursing; Prostatic Neoplasms -- Prevention and Control; Questionnaires; Scales; South Carolina; Summated Rating Scaling; Surveys

Development and Evaluation of a Technology-Enhanced Interdisciplinary Navigation Program for Low-Income Breast Cancer Patients. - Helzlsouer, Kathy J.; Appling, Susan E.; Scarvalone, Susan; Manocheh, Shannon; MacDonald, Ryan; Gallicchio, Lisa; Henninger, Dawn; Varanasi, Arti P. (Journal of Oncology Navigation & Survivorship, 2016)
Background: Navigators have the potential to help overcome barriers that interfere with cancer treatment adherence, but their widespread use is economically challenging, especially in rural and low-resource communities. A centrally located interdisciplinary navigator team using technology to extend the navigators' reach holds promise to efficiently improve treatment outcomes. Objectives: To develop and evaluate a centralized "virtual" navigation program to support breast cancer patients through their adjuvant treatment. Methods: The technology-enhanced navigator program was developed in collaboration with patient advisors and evaluated in a randomized clinical trial comparing use of the web-based navigation application with and without a navigator team (N = 98). A usability assessment was conducted at 3 months after enrollment. Comparisons by study arm were conducted using independent samples t tests for continuous measures and chi-square tests for proportions. Results: Of the participants, 67% were minorities, mostly African American. Slightly more of the group randomized to the navigator team reported that the application was easy to use (77.6% vs 71.4%) and with higher confidence (71.4% vs 67.3%), but these differences were not statistically significant. Discussion: A web-based interactive navigation program was developed in collaboration with breast cancer patients. Evaluation of the program demonstrated ease of use even among those with no prior computer experience. Conclusions: A "virtual" interdisciplinary navigator program was confidently and easily used by low-income breast cancer patients who had a wide range in age, education levels, and prior computer experience.
Keywords: Breast Neoplasms; Program Development; Cancer Patients; Patient Navigation; Multidisciplinary Care Team; Socioeconomic Factors; Program Evaluation; Internet; Human; Randomized Controlled Trials; Random Assignment; Patient Compliance; Female; Adult; Middle Age; T-Tests; Chi Square Test

Development of Wagle Health-Specific Religiousness scale. - Wagle AM; Champion VL; Russell KM; Rawl SM (Cancer Nursing, 2009)
African American women have a lower rate of regular mammography screening, resulting in higher incidence of advanced-stage breast cancer at diagnosis and a lower 5-year survival rate as compared with white women. Researchers have demonstrated that several health beliefs relate to mammography screening in African American women, but little attention has been paid to the importance of religiousness. Although some authors have attempted to determine a link between religiousness and health, we lack a valid and reliable instrument to measure religiousness that can be found in the context of health behaviors. The purpose of this article is to describe the development and psychometric testing of the Wagle Health-Specific Religiousness (WHSR) scale, an instrument used to measure religious beliefs and the influence of those beliefs on mammography screening for African American women. A sample of 344 low-income African American women who were nonadherent to mammography at accrual participating in a randomized trial completed the WHSR. Data from this trial were used to determine the validity and reliability of the WHSR. The 19-item WHSR scale had a Cronbach alpha of. 94. Construct validity was supported via factor analysis and analysis of theoretical relationships. Although further testing is warranted, this analysis indicates that the concept of religiousness is an important component of mammography behavior in African American women.
Keywords: Black Persons -- Midwestern United States; Breast Neoplasms -- Prevention and Control; Health Beliefs; Instrument Construction; Instrument Validation; Mammography; Religion and Religions; Adult; Aged; Clinical Trials; Coefficient Alpha; Conceptual Framework; Construct Validity; Factor Analysis; Female; Linear Regression; Logistic Regression; Middle Age; Midwestern United States; Poverty; Scales; Secondary Analysis; Self-Efficacy -- Evaluation; Summated Rating Scaling; Human

Diagnostic accuracy of the Gail model in the Black Women's Health Study. - Adams-Campbell LL; Makambi KH; Palmer JR; Rosenberg L (Breast Journal, 2007)
The Gail model is used to predict the risk of breast cancer in women of diverse race/ethnic groups for clinical trial protocols. However, this model has only been validated in US white women. Using a nested case-control study design, we evaluated the diagnostic accuracy of the original Gail model (GM) and that of the revised Gail model algorithm for blacks/African-Americans (GM-B) in the Black Women's Health Study (BWHS). Risk profiles were derived via a self reported questionnaire at the time of enrollment into the BWHS in 1995. Biennial questionnaires were obtained from the participants to determine the incident cases of breast cancer. The study of 725 breast cancer cases and 725 controls revealed that the 5-year risk of breast cancer based on the GM ranged from 0.2% to 15.4% among cases and 0.2% to 13.6% among the controls. Based on the GM-B, the 5-year risk of breast cancer ranged from 0.2% to 8.7% among cases and 0.2% to 7.2% among the controls. The sensitivities of the GM and GM-B model with the standard cutoff of 1.7% were 17.9% (95% CI: 15.9-19.9%) and 4.1% (95% CI: 3.0-5.2), respectively. Both the original and the modified version of the Gail model underestimate the risk of developing breast cancer in African-American women. More importantly, the modified Gail Model (GM-B) does a worse job at predicting the development of breast cancer for blacks than the original model (GM).
Keywords: Black Persons; Breast Neoplasms -- Etiology; Models, Statistical; Risk Assessment -- Methods; Women's Health; Adult; Aged; Algorithms; Breast Neoplasms; Case Control Studies; Female; Maternal Age; Middle Age; Postmenopause; Predictive Value of Tests; Premenopause; Risk Assessment -- Standards; ROC Curve; Human

Diet-Related Colorectal Cancer Prevention Beliefs and Dietary Intakes in an Urban Minority Population. - Zaharek-Girgasky, Margot; Wolf, Randi; Zybert, Patricia; Basch, Corey; Basch, Charles (Journal of Community Health, 2015)
In the United States, colorectal cancer (CRC) is the third leading cause of cancer-related death and third most commonly diagnosed cancer among adults. This study is the first to examine the relationship between diet-related beliefs for colorectal cancer prevention and dietary intake among an urban, predominantly Black population (n = 169). More than two-thirds reported diet-related CRC prevention beliefs. Those with diet-related CRC prevention beliefs had healthier intakes for dietary fiber ( p = .005), fruit, vegetable, bean ( p = .027), red meat ( p = .032), vitamin C ( p = .039), and cholesterol ( p = .045). Most people may already have diet-related CRC prevention beliefs and having them is associated with a more healthful dietary intake.
Keywords: Minority Groups; Diet -- Evaluation; Colorectal Neoplasms -- Prevention and Control; Health Beliefs; Food Intake -- Evaluation; Community Health Services; Human; United States; Colorectal Neoplasms -- Mortality; Colorectal Neoplasms -- Diagnosis; Life Style, Sedentary; Urban Areas; Black Persons; Race Factors; Insurance Coverage; Data Collection; Language; Colonoscopy; Patient Selection -- Methods; Crohn Disease -- Diagnosis; Crohn Disease -- Complications; Colitis, Ulcerative -- Diagnosis; Colitis, Ulcerative -- Complications; Male; Female; West Indies; Obesity -- Diagnosis; Middle Age; Ethnic Groups; Income; Education; Birth Place; Body Mass Index; Data Analysis; Data Analysis Software; Vegetables; Dietary Fiber; Fruit; Meat; Water; Fish; Alcohol Drinking; Dairy Products

Differences in Stage of Cancer at Diagnosis, Treatment, and Survival by Race and Ethnicity Among Leading Cancer Types. - Zhang, Chenyue; Zhang, Chenxing; Wang, Qingliang; Li, Zhenxiang; Lin, Jiamao; Wang, Haiyong (JAMA Network Open, 2020)
Key Points: Question: Do stage of cancer at diagnosis, use of definitive therapy, and survival differ by race/ethnicity among patients with 1 of the most common cancers? Findings: In this cohort study of 950 377 patients with cancer, stage at diagnosis, treatment, and survival varied by race and ethnicity. Overall, compared with Asian patients, black patients were more likely to have metastatic disease at diagnosis, black and Hispanic patients were less likely to receive definitive treatment, and white, black, and Hispanic patients had worse odds of cancer-specific and overall survival. Meaning: The findings of this study may lead to different management strategies based on race and ethnicity to improve outcomes. This cohort study assesses the stage of cancer at diagnosis, use of therapy, overall survival, and cancer-specific survival among patients with cancer from different racial/ethnic groups. Importance: Information about stage of cancer at diagnosis, use of therapy, and survival among patients from different racial/ethnic groups with 1 of the most common cancers is lacking. Objective: To assess stage of cancer at diagnosis, use of therapy, overall survival (OS), and cancer-specific survival (CSS) in patients with cancer from different racial/ethnic groups. Design, Setting, and Participants: This cohort study included 950 377 Asian, black, white, and Hispanic patients who were diagnosed with prostate, ovarian, breast, stomach, pancreatic, lung, liver, esophageal, or colorectal cancers from January 2004 to December 2010. Data were collected using the Surveillance, Epidemiology, and End Results (SEER) database, and patients were observed for more than 5 years. Data analysis was conducted in July 2018. Main Outcomes and Measures: Multivariable logistic and Cox regression were used to evaluate the differences in stage of cancer at diagnosis, treatment, and survival among patients from different racial/ethnic groups. Results: A total of 950 377 patients (499 070 [52.5%] men) were included in the study, with 681 251 white patients (71.7%; mean [SD] age, 65 [12] years), 116 015 black patients (12.2%; mean [SD] age, 62 [12] years), 65 718 Asian patients (6.9%; mean [SD] age, 63 [13] years), and 87 393 Hispanic patients (9.2%; mean [SD] age, 61 [13] years). Compared with Asian patients, black patients were more likely to have metastatic disease at diagnosis (odds ratio [OR], 1.144; 95% CI, 1.109-1.180; P <.001). Black and Hispanic patients were less likely to receive definitive treatment than Asian patients (black: adjusted OR, 0.630; 95% CI, 0.609-0.653; P <.001; Hispanic: adjusted OR, 0.751; 95% CI, 0.724-0.780; P <.001). White, black, and Hispanic patients were more likely to have poorer CSS and OS than Asian patients (CSS, white: adjusted HR, 1.310; 95% CI, 1.283-1.338; P <.001; black: adjusted HR, 1.645; 95% CI, 1.605-1.685; P <.001; Hispanic: adjusted HR, 1.300; 95% CI, 1.266-1.334; P <.001; OS, white: adjusted HR, 1.333; 95% CI, 1.310-1.357; P <.001; black: adjusted HR, 1.754; 95% CI, 1.719-1.789; P <.001; Hispanic: adjusted HR, 1.279; 95% CI, 1.269-1.326; P <.001). Conclusions and Relevance: In this study of patients with 1 of 9 leading cancers, stage at diagnosis, treatment, and survival were different by race and ethnicity. These findings may help to optimize treatment and improve outcomes.
Keywords: Neoplasm Staging -- Evaluation; Neoplasms -- Therapy; Survival Analysis -- Evaluation; Cancer Patients -- Psychosocial Factors; Ethnic Groups; Human; Prospective Studies; Asians; Black Persons; White Persons; Hispanic Americans; Databases; Multivariate Analysis; Logistic Regression; Cox Proportional Hazards Model; Male; Female; Middle Age; Aged; Odds Ratio; Confidence Intervals; Descriptive Statistics; Patient Selection; Data Analysis Software; T-Tests; Chi Square Test; Neoplasm Metastasis

Diminutive polyps among black and Latino populations undergoing screening colonoscopy: evidence supporting a resect and discard approach. - Lee, Kristen K.; Jandorf, Lina; Itzkowitz, Steven H. (Gastrointestinal Endoscopy, 2015)
Background A resect and discard strategy for diminutive (≤5 mm) colon polyps has been proposed to save costs of screening colonoscopy (SC). Prior studies on neoplasia prevalence based on polyp size have involved mostly white patients. Objective To determine the prevalence of adenomas and advanced histologic features by size among primarily black and Latino patients enrolled in a prospective SC study. Design Retrospective analysis of data from a prospective clinical trial. Setting Urban academic medical center. Patients Average risk, asymptomatic, minority patients aged ≥50 years undergoing SC. Interventions Screening colonoscopy. Main Outcome Measurements Rates of neoplasia and advanced histologic features (villous histology, high-grade dysplasia, or cancer) by polyp size and location. Results A total of 566 polyps from 295 patients were analyzed. Diminutive polyps and small (6-9 mm) polyps had lower prevalence of ≥1 advanced feature compared with large (≥10 mm) polyps (0.9% and 2.7%, respectively, vs 13.6%; P < .001 for both comparisons). Distal polyps were less likely to be neoplastic (31.7% vs 61.4%; P < .001) than proximal polyps in all size categories ( P < .001 for all comparisons). After adjusting for sex, ethnicity, age, and location, large polyps were more likely to have ≥1 advanced feature than diminutive polyps (adjusted odds ratio [OR] 19.5; 95% CI, 4.4-85.6) or small polyps (adjusted OR 6.1; 95% CI, 2.2-16.9). Limitations Use of pathology reports for polyp size. Conclusion Among a cohort of minority patients, advanced histologic features were very rare in diminutive polyps. Distal polyps were less likely to be neoplastic than proximal polyps in all size categories. This supports a resect and discard strategy for diminutive polyps, especially in the distal colon.
Keywords: Colonoscopy -- Utilization; Health Screening -- Methods; Colonic Neoplasms -- Prevention and Control; Human; Academic Medical Centers; Black Persons; Hispanic Americans; Prospective Studies; Retrospective Design; Record Review; Odds Ratio; Confidence Intervals

Discussions about clinical trials among patients with newly diagnosed lung and colorectal cancer. - Kehl, Kenneth L; Arora, Neeraj K; Schrag, Deborah; Ayanian, John Z; Clauser, Steven B; Klabunde, Carrie N; Kahn, Katherine L; Fletcher, Robert H; Keating, Nancy L (JNCI: Journal of the National Cancer Institute, 2014)
Background: Clinical trials are essential to establish the effectiveness of new cancer therapies, but less than 5% of adults with cancer enroll in trials. In addition to ineligibility or lack of available trials, barriers to enrollment may include limited patient awareness about the option of participation.Methods: We surveyed a multiregional cohort of patients with lung or colorectal cancer (or their surrogates) three to six months after diagnosis. We assessed whether respondents reported learning that clinical trial participation might be an option, and, if so, with whom they discussed trials. We used logistic regression to assess the association of patient characteristics with discussing trial participation and enrolling in trials. All statistical tests were two-sided.Results: Of 7887 respondents, 1114 (14.1%) reported discussing the possibility of clinical trial participation; most learned about trials from their physicians, and 287 patients (3.6% of all patients, 25.8% of trial discussants) enrolled. Among 2173 patients who received chemotherapy for advanced (stage III/IV lung or stage IV colorectal) cancer, 25.7% discussed trials, and 7.6% (29.5% of trial discussants) enrolled. Discussions were less frequent among older patients, African American or Asian vs white patients, and those with lower incomes and more comorbidity. Enrollment was higher among patients reporting shared vs physician-driven decisions (all P < .05).Conclusions: In this population-based cohort, only 14% of patients discussed participation in clinical trials. Discussions were more frequent among advanced cancer patients but were still reported by a minority of patients. Strategies to expand access to trials and facilitate patient-provider communication about participation may accelerate development of better cancer therapeutics.
Keywords: Colorectal Neoplasms -- Diagnosis; Communication; Decision Making; Lung Neoplasms -- Diagnosis; Patient Selection; Age Factors; Aged; Aged, 80 and Over; Asians -- Statistics and Numerical Data; Black Persons -- Statistics and Numerical Data; Clinical Trials; Colorectal Neoplasms -- Pathology; Colorectal Neoplasms -- Therapy; Comorbidity; Consumer Participation; Female; Human; Income; Information Seeking Behavior; Lung Neoplasms -- Pathology; Lung Neoplasms -- Therapy; Male; Middle Age; Neoplasm Staging; Prospective Studies; Questionnaires; United States; White Persons -- Statistics and Numerical Data

Disease-Free and Overall Survival Among Patients With Operable HER2-Positive Breast Cancer Treated With Sequential vs Concurrent Chemotherapy: The ACOSOG Z1041 (Alliance) Randomized Clinical Trial. - Buzdar, Aman U.; Suman, Vera J.; Meric-Bernstam, Funda; Leitch, Ann Marilyn; Ellis, Matthew J.; Boughey, Judy C.; Unzeitig, Gary W.; Royce, Melanie E.; Hunt, Kelly K. (JAMA Oncology, 2019)
Key Points: Question: What are the long-term outcomes associated with 2 different approaches to administering trastuzumab with neoadjuvant chemotherapy in patients with HER2-positive breast cancer? Findings: Analysis of the ACOSOG Z1041 (Alliance) study of 280 patients revealed no difference in disease-free or overall survival for patients given a regimen of paclitaxel plus trastuzumab followed by fluorouracil, epirubicin, and cyclophosphamide plus trastuzumab compared with a regimen of fluorouracil, epirubicin, and cyclophosphamide followed by paclitaxel plus trastuzumab. Meaning: Across a median follow-up of 5 years, no differences were found in disease-free or overall survival between the 2 approaches of administering trastuzumab with neoadjuvant chemotherapy in patients with HER2-positive breast cancer. Importance: Pathologic complete response rate (pCR), the primary end point of the ACOSOG (American College of Surgeons Oncology Group) Z1041 (Alliance) trial, and disease-free survival (DFS) and overall survival (OS) in women with operable HER2-positive breast cancer are similar between treatment regimens. Objective: To assess DFS and OS for patients treated with sequential vs concurrent anthracycline plus trastuzumab. Design, Setting, and Participants: Phase 3 randomized clinical trial conducted at 36 centers in the continental United States and Puerto Rico. Women 18 years or older with invasive operable HER2-positive breast cancer were enrolled from September 15, 2007, to December 15, 2011, and randomized to 1 of 2 treatment arms. The analysis data set was locked on October 15, 2017, and analysis was completed on December 15, 2017. Interventions: Patients randomized to arm 1 received 500 mg/m2 of fluorouracil, 75 mg/m2 of epirubicin, and 500 mg/m2 of cyclophosphamide (FEC) every 3 weeks for 12 weeks followed by the combination of 80 mg/m2 of paclitaxel and 2 mg/kg (except initial dose of 4 mg/kg) of trastuzumab weekly for 12 weeks. Patients randomized to arm 2 received the same combination of paclitaxel with trastuzumab weekly for 12 weeks followed by FEC every 3 weeks with weekly trastuzumab for 12 weeks. Women with hormone receptor–positive disease received endocrine therapy, and radiotherapy was delivered at physician discretion. Main Outcomes and Measures: The primary outcomes were DFS and OS and pCR in the breast and nodes. Results: Two hundred eighty-two women with HER2-positive breast cancer were enrolled in the trial, and 2 withdrew consent before treatment. Among the remaining 280 women, the median age was 50 years (range, 28-76 years), 232 (82.9%) were white, 29 (10.3%) were black, 8 (2.9%) were Asian, 4 (1.4%) were American Indian or Alaskan Native, and 7 (2.5%) did not report race/ethnicity. There were 22 disease events in arm 1 and 27 in arm 2. Disease-free survival rates did not differ with respect to treatment arm (stratified log-rank P =.96; stratified hazard ratio [HR] [arm 2 to arm 1], 1.02; 95% CI, 0.56-1.83). Overall survival did not differ with respect to treatment arm (stratified log-rank P =.73; stratified HR [arm 2 to arm 1], 1.17; 95% CI, 0.48-2.88). Conclusions and Relevance: Across a median follow-up of 5.1 years (range, 26 days to 6.2 years), pCR, DFS, and OS did not differ with respect to sequential or concurrent administration of FEC with trastuzumab. Trial Registration: ClinicalTrials.gov identifier: NCT00513292 This phase 3 randomized clinical trial compares disease-free and overall survival among patients with operable HER2-positive breast cancer who received concurrent vs sequential administration of neoadjuvant chemotherapy.
Keywords: Breast Neoplasms -- Surgery; Breast Neoplasms -- Drug Therapy; Chemotherapy, Adjuvant; HER-2-neu Oncogene; Survival Analysis -- Methods; Anthracyclines -- Therapeutic Use; Trastuzumab -- Therapeutic Use; Combined Modality Therapy; Human; Puerto Rico; United States; Randomized Controlled Trials; Fluorouracil -- Administration and Dosage; Epirubicin -- Administration and Dosage; Cyclophosphamide -- Administration and Dosage; Paclitaxel -- Administration and Dosage; Trastuzumab -- Administration and Dosage; Antineoplastic Agents, Combined -- Therapeutic Use; Female; Adult; Middle Age; Aged; Confidence Intervals; Receptors, Cell Surface; Log-Rank Test; Data Analysis Software; Treatment Outcomes; Funding Source

Disparities among Cancer Patients Seen in gaps in Clinical Trial Participation. - NEWITT, VALERIE NEFF (Oncology Times, 2020)
Keywords: Healthcare Disparities; Cancer Patients; Clinical Trials; Research Subject Recruitment; Black Persons -- Psychosocial Factors; Prostatic Neoplasms; Socioeconomic Factors; Health Services Accessibility; Financial Support; Abiraterone Acetate -- Therapeutic Use; Career Planning and Development

Distrust, predisposition to use health services and breast cancer screening: results from a multicultural community-based survey. - Katapodi MC; Pierce PF; Facione NC (International Journal of Nursing Studies, 2010)
PURPOSE: To examine whether and how distrust of the health system and predisposition to use healthcare services influence frequency of mammograms and Clinical Breast Exams (CBEs). METHODS: A community-based survey recruited 184 women (age 47+/-12); 49% were college-educated, 77% had health insurance, and 57% were non-white. Distrust was measured with a four-item scale (Cronbach alpha=0.71); predisposition to use health services with an 11-item scale (Cronbach alpha=0.84). Ordinal regression analysis was used to test two models examining 'time since last mammogram' and 'time since last CBE.' The later model had a better goodness-of-fit, as indicated by a non-significant, Pearson coefficient. FINDINGS: Distrust to the health system was significantly correlated with age (r=-0.19*), income (r=-0.16*), and predisposition to use health services (r=-0.26**). Distrust predicted time since last CBE (B: 0.37, SE: 0.19*), which in turn was significantly correlated with time since last mammogram (r=0.44**). Predisposition to use health services predicted time since last CBE (B: -0.78, SE: 0.19**) and time since last mammogram (B: -0.47, SE: 0.22**). Insurance predicted time since last CBE (B: -0.94, SE: 0.44*), while age (B: -0.21, SE: 0.03**) and income (B: -0.19, SE: 0.09*) predicted time since last mammogram. CONCLUSION: Distrust of the healthcare system and predisposition to use health services influence breast cancer screening directly. Distrust interferes with behavioral patterns that favor recurrent breast cancer screening. PRACTICE IMPLICATIONS: Trustworthiness in the healthcare system and positive attitudes for the use of, health services enhance routine breast cancer screening. *p<0.05, **p<0.001.
Keywords: Breast Neoplasms -- Prevention and Control; Cancer Screening; Consumer Attitudes; Health Resource Utilization; Trust; Adult; Age Factors; Asians; Black Persons; Breast Examination; Coefficient Alpha; Consumer Attitudes -- Evaluation; Convenience Sample; Cross Sectional Studies; Descriptive Research; Descriptive Statistics; Female; Funding Source; Hispanic Americans; Human; Income; Middle Age; Pearson's Correlation Coefficient; Questionnaires; Regression; Research Subject Recruitment; Scales; Summated Rating Scaling; United States; White Persons

Do Patients and Oncologists Discuss the Cost of Cancer Treatment? An Observational Study of Clinical Interactions Between African American Patients and Their Oncologists. - Hamel, Lauren M.; Penner, Louis A.; Eggly, Susan; Chapman, Robert; Klamerus, Justin F.; Simon, MichaelS.; Stanton, Sarah C. E.; Albrecht, Terrance L. (Journal of Oncology Practice, 2017)
Purpose Financial toxicity negatively affects patients with cancer, especially racial/ethnic minorities. Patient-oncologist discussions about treatment-related costs may reduce financial toxicity by factoring costs into treatment decisions. This study investigated the frequency and nature of cost discussions during clinical interactions between African American patients and oncologists and examined whether cost discussions were affected by patient sociodemographic characteristics and social support, a known buffer to perceived financial stress. Methods Video recorded patient-oncologist clinical interactions (n = 103) from outpatient clinics of two urban cancer hospitals (including a National Cancer Institute-designated comprehensive cancer center) were analyzed. Coders studied the videos for the presence and duration of cost discussions and then determined the initiator, topic, oncologist response to the patient's concerns, and the patient's reaction to the oncologist's response. Results Cost discussions occurred in 45% of clinical interactions. Patients initiated 63% of discussions; oncologists initiated 36%. The most frequent topics were concern about time off from work for treatment (initiated by patients) and insurance (initiated by oncologists). Younger patients and patients with more perceived social support satisfaction were more likely to discuss cost. Patient age interacted with amount of social support to affect frequency of cost discussions within interactions. Younger patients with more social support had more cost discussions; older patients with more social support had fewer cost discussions. Conclusion Cost discussions occurred in fewer than one half of the interactions and most commonly focused on the impact of the diagnosis on patients' opportunity costs rather than treatment costs. Implications for ASCO's Value Framework and design of interventions to improve cost discussions are discussed.
Keywords: Health Care Costs; Oncologists; Physician-Patient Relations -- Evaluation; Cancer Care Facilities; Human; Minority Groups; National Cancer Institute (U.S.); Neoplasms; Oncology; Physicians; Support, Psychosocial; United States; Videorecording; Black Persons; Race Factors; Cancer Patients -- Evaluation; Ethnic Groups; Health Services Accessibility -- Evaluation; Outpatient Service; Patient Satisfaction; Neoplasms -- Economics; Data Collection; Communication; Research Subject Recruitment; Socioeconomic Factors; Multivariate Analysis; Regression; Data Analysis Software; Male; Female; Education; Income; Breast Neoplasms -- Diagnosis; Colorectal Neoplasms; Lung Neoplasms

Do preparation and life completion discussions improve functioning and quality of life in seriously ill patients? Pilot randomized control trial. - Steinhauser KE; Alexander SC; Byock IR; George LK; Olsen MK; Tulsky JA (Journal of Palliative Medicine, 2008)
BACKGROUND: Significant palliative care intervention has focused on physical pain and symptom control; yet less empirical evidence supports efforts to address the psychosocial and spiritual dimensions of experience. OBJECTIVE: To evaluate the impact of an intervention (Outlook) that promotes discussions of end-of-life preparation and completion on health outcomes in dying persons, including pain and symptoms, physical function, emotional function (anxiety and depression), spiritual well-being, and quality of life at the end of life. DESIGN: A three-arm pilot randomized control trial. Subjects were recruited from inpatient and outpatient hospital, palliative care, and hospice settings. Intervention subjects met with a facilitator three times and discussed issues related to life review, forgiveness, and heritage and legacy. Attention control subjects met with a facilitator three times and listened to a nonguided relaxation CD. True control subjects received no intervention. MEASUREMENTS: Preoutcomes and postoutcomes included the Memorial Symptom Assessment Scale, QUAL-E, Rosow-Breslau ADL Scale, Profile of Mood States anxiety sub-scale, the CESD short version, and the Daily Spiritual Experience Scale. RESULTS: Eighty-two hospice eligible patients enrolled in the study; 38 were women, 35 were African American. Participants' primary diagnoses included cancer (48), heart disease (5) lung disease (10), and other (19) Ages ranged from 28-96. Participants in the active discussion intervention showed improvements in functional status, anxiety, depression, and preparation for end of life. CONCLUSIONS: The Outlook intervention was acceptable to patients from a variety of educational and ethnic backgrounds and offers a brief, manualized, intervention for emotional and spiritual concerns.
Keywords: Death Education; Patient Attitudes; Quality of Life; Spiritual Care; Terminally Ill Patients; Adult; Aged; Aged, 80 and Over; Center for Epidemiological Studies Depression Scale; Clinical Assessment Tools; Clinical Trials; Female; Male; Middle Age; Random Assignment; Scales; Human

Does a community-based stress management intervention affect psychological adaptation among underserved black breast cancer survivors? - Lechner, Suzanne C; Whitehead, Nicole E; Vargas, Sara; Annane, Debra W; Robertson, Belinda R; Carver, Charles S; Kobetz, Erin; Antoni, Michael H (JNCI Monographs, 2014)
Background: In this randomized trial, Project CARE, we examined whether participation in a cognitive-behavioral stress management and breast cancer wellness and education program improved psychological outcomes among a sample of underserved black breast cancer survivors.Methods: Both complementary medicine interventions were 10-sessions, manualized, group-based, and were culturally adapted for black women in the community from evidence-based interventions. Participants were 114 black women (mean age = 51.1, 27-77 years) who had completed breast cancer treatment 0-12 months before enrollment (stages 0-IV, mean time since cancer diagnosis = 14.1 months). Women were enrolled upon completion of curative treatment (ie, surgical, chemotherapy, radiation oncology) and randomized to receive cognitive-behavioral stress management or cancer wellness and education program.Results: There was a remarkable 95% retention rate from baseline to 6-month follow-up. Participants in both conditions showed statistically significant improvement on indices of psychological well-being, including overall quality of life (Functional Assessment of Cancer Therapy-Breast), intrusive thoughts (Impact of Event Scale-Revised), depressive symptoms (Center for Epidemiologic Studies-Depression), and stress levels (Perceived Stress Scale) over the 6-month postintervention follow-up (all repeated measures analysis of variance within-subjects time effects: P < .05, except for overall mood; Profile of Mood States-Short Version). Contrary to hypotheses, however, condition × time effects were not statistically significant.Conclusions: Findings suggest that improvements in multiple measures over time may have been due to intensive training in stress management, extensive provision of breast cancer information, or participation in an ongoing supportive group of individuals from a similar racial background. Implications bear on decisions about appropriate control groups, the timing of intervention delivery during the treatment trajectory, and perceived support from the research team.

Editorial comment. - Ellimoottil, Chandy; Gupta, Gopal N; Quek, Marcus L (Urology, 2015)
Keywords: Black Persons; White Persons; Patient Selection; Prostatectomy; Prostatic Neoplasms -- Surgery; Outcomes (Health Care); Male

Educational Colonoscopy Video Enhances Bowel Preparation Quality and Comprehension in an Inner City Population. - Pillai, Ajish; Menon, Radha; Oustecky, David; Ahmad, Asyia (Journal of Clinical Gastroenterology, 2018)
Background: Quality of bowel preparation and patient knowledge remains a major barrier for completing colorectal cancer screening. Few studies have tested unique ways to impact patient understanding centering on interactive computer programs, pictures, and brochures. Two studies explored instructional videos but focused on patient compliance and anxiety as endpoints. Furthermore, excessive video length and content may limit their impact on a broad patient population. No study so far has studied a video's impact on preparation quality and patient understanding of the colonoscopy procedure.Methods: We conducted a single blinded prospective study of inner city patients presenting for a first time screening colonoscopy. During their initial visit patients were randomized to watch an instructional colonoscopy video or a video discussing gastroesophageal reflux disease (GERD). All patients watched a 6 minutes long video with the same spokesperson, completed a demographic questionnaire (Supplemental Digital Content 1, http://links.lww.com/JCG/A352) and were enrolled only if screened within 30 days of their visit. On the day of the colonoscopy, patients completed a 14 question quiz of their knowledge. Blinded endoscopist graded patient preparations based on the Ottawa scale. All authors had access to the study data and reviewed and approved the final manuscript.Results: Among the 104 subjects enrolled in the study, 56 were in the colonoscopy video group, 48 were in GERD video group, and 12 were excluded. Overall, 48% were male and 52% female; 90% of patients had less than a high school education, 76% were African American, and 67% used a 4 L split-dose preparation. There were no differences between either video group with regard to any of the above categories. Comparisons between the 2 groups revealed that the colonoscopy video group had significantly better Ottawa bowel preparation score (4.77 vs. 6.85; P=0.01) than the GERD video group. The colonoscopy video group also had less-inadequate repeat bowel preparations versus the GERD video group (9% vs. 23%; P<0.01). The overall score on the knowledge questionnaire (Supplemental Digital Content 1, http://links.lww.com/JCG/A352) was significantly higher in the colonoscopy video group as compared with the GERD video group (12.77 vs. 11.08; P<0.001. In all patients the overall quiz score positively correlated with preparation quality (odds ratio, 2.31; confidence interval, 1.35-3.94; P<0.001).Conclusions: Our unique population represented an overwhelmingly under-educated (85% had a high school education or less) and minority group (76% African American). They are one of the most at risk of having multiple barriers such as comprehension and reading difficulties resulting in poor preparation examinations and no shows to procedures. Our instructional video proved to be high yield in this population. The patients assigned to watch the colonoscopy video showed a significant increase in "excellent" grade adequate bowel preparation quality by >23% and a significant decrease in "inadequate" bowel preparations by almost 50%. Our study proves that an educational video can improve both comprehension with regard to all aspects of colonoscopy. ClinicalTrials.gov number, NCT02906969.
Keywords: Colonoscopy -- Education; Colorectal Neoplasms -- Pathology; Early Detection of Cancer -- Methods; Cathartics -- Therapeutic Use; Urban Health Services; Videorecording; Attitude to Health; Patient Education -- Methods; Therapeutic Irrigation -- Methods; Colonoscopy -- Methods; Pennsylvania; Human; Cathartics -- Adverse Effects; Readability; Communication; Single-Blind Studies; Prospective Studies; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Questionnaires

Effect of a Patient Decision Aid on Lung Cancer Screening Decision-Making by Persons Who Smoke: A Randomized Clinical Trial. - Volk, Robert J.; Lowenstein, Lisa M.; Leal, Viola B.; Escoto, Kamisha H.; Cantor, Scott B.; Munden, Reginald F.; Rabius, Vance A.; Bailey, Linda; Cinciripini, Paul M.; Lin, Heather; Housten, Ashley J.; Luckett, Pamela Graef; et al. (JAMA Network Open, 2020)
This randomized clinical trial compares the effect of a patient decision aid on lung cancer screening vs standard educational information on decision-making outcomes among persons who smoke. Key Points: Question: Does providing a lung cancer screening decision aid through tobacco quitlines improve informed decision-making about lung cancer screening among persons who smoke? Findings: In this randomized clinical trial of 516 smokers, use of a patient decision aid compared with standard educational information led to better preparedness to decide about screening, higher reports of feeling informed and clear about screening choices, and greater knowledge of screening benefits and harms. Meaning: The findings suggest that decision aids about lung cancer screening can reach large numbers of smokers who are eligible for screening through tobacco quitlines, can inform them about lung cancer screening, and can promote high-quality screening decisions. Importance: Lung cancer screening with low-dose computed tomography lowers lung cancer mortality but has potential harms. Current guidelines support patients receiving information about the benefits and harms of lung cancer screening during decision-making. Objective: To examine the effect of a patient decision aid (PDA) about lung cancer screening compared with a standard educational material (EDU) on decision-making outcomes among smokers. Design, Setting, and Participants: This randomized clinical trial was conducted using 13 state tobacco quitlines. Current and recent tobacco quitline clients who met age and smoking history eligibility for lung cancer screening were enrolled from March 30, 2015, to September 12, 2016, and followed up for 6 months until May 5, 2017. Data analysis was conducted between May 5, 2017, and September 30, 2018. Interventions: Participants were randomized to the PDA video Lung Cancer Screening: Is It Right for Me? (n = 259) or to EDU (n = 257). Main Outcomes and Measures: The primary outcomes were preparation for decision-making and decisional conflict measured at 1 week. Secondary outcomes included knowledge, intentions, and completion of screening within 6 months of receiving the intervention measured by patient report. Results: Of 516 quit line clients enrolled, 370 (71.7%) were younger than 65 years, 320 (62.0%) were female, 138 (26.7%) identified as black, 47 (9.1%) did not have health insurance, and 226 (43.8%) had a high school or lower educational level. Of participants using the PDA, 153 of 227 (67.4%) were well prepared to make a screening decision compared with 108 of 224 participants (48.2%) using EDU (odds ratio [OR], 2.31; 95% CI, 1.56-3.44; P <.001). Feeling informed about their screening choice was reported by 117 of 234 participants (50.0%) using a PDA compared with 66 of 233 participants (28.3%) using EDU (OR, 2.56; 95% CI, 1.72-3.79; P <.001); 159 of 234 participants (68.0%) using a PDA compared with 110 of 232 (47.4%) participants using EDU reported being clear about their values related to the harms and benefits of screening (OR, 2.37; 95% CI, 1.60-3.51; P <.001). Participants using a PDA were more knowledgeable about lung cancer screening than participants using EDU at each follow-up assessment. Intentions to be screened and screening behaviors did not differ between groups. Conclusions and Relevance: In this study, a PDA delivered to clients of tobacco quit lines improved informed decision-making about lung cancer screening. Many smokers eligible for lung cancer screening can be reached through tobacco quit lines. Trial Registration: ClinicalTrials.gov identifier: NCT02286713
Keywords: Decision Making, Patient; Lung Neoplasms -- Prevention and Control; Cancer Screening -- Education; Patient Education; Smoking; Audiovisuals; Pamphlets; Human; Male; Female; Adolescence; Adult; Middle Age; Aged; Randomized Controlled Trials; Smoking Cessation Programs; Health Knowledge; Intention; Patient Attitudes; Descriptive Statistics; Odds Ratio; Confidence Intervals; Tomography, X-Ray Computed; Outcomes of Education; Post Hoc Analysis; T-Tests; Data Analysis Software; Logistic Regression; Scales; Funding Source

Effect of Combined Patient Decision Aid and Patient Navigation vs Usual Care for Colorectal Cancer Screening in a Vulnerable Patient Population: A Randomized Clinical Trial. - Reuland, Daniel S.; Brenner, Alison T.; Hoffman, Richard; McWilliams, Andrew; Rhyne, Robert L.; Getrich, Christina; Tapp, Hazel; Weaver, Mark A.; Callan, Danelle; Cubillos, Laura; de Hernandez, Brisa Urquieta; Pignone, Michael P.; et al. (JAMA Internal Medicine, 2017)
Importance: Colorectal cancer (CRC) screening is underused, especially among vulnerable populations. Decision aids and patient navigation are potentially complementary interventions for improving CRC screening rates, but their combined effect on screening completion is unknown.Objective: To determine the combined effect of a CRC screening decision aid and patient navigation compared with usual care on CRC screening completion.Design, Setting, and Participants: In this randomized clinical trial, data were collected from January 2014 to March 2016 at 2 community health center practices, 1 in North Carolina and 1 in New Mexico, serving vulnerable populations. Patients ages 50 to 75 years who had average CRC risk, spoke English or Spanish, were not current with recommended CRC screening, and were attending primary care visits were recruited and randomized 1:1 to intervention or control arms.Interventions: Intervention participants viewed a CRC screening decision aid in English or Spanish immediately before their clinician encounter. The decision aid promoted screening and presented colonoscopy and fecal occult blood testing as screening options. After the clinician encounter, intervention patients received support for screening completion from a bilingual patient navigator. Control participants viewed a food safety video before the encounter and otherwise received usual care.Main Outcomes and Measures: The primary outcome was CRC screening completion within 6 months of the index study visit assessed by blinded medical record review.Results: Characteristics of the 265 participants were as follows: their mean age was 58 years; 173 (65%) were female, 164 (62%) were Latino; 40 (15%) were white non-Latino; 61 (23%) were black or of mixed race; 191 (78%) had a household income of less than $20 000; 101 (38%) had low literacy; 75 (28%) were on Medicaid; and 91 (34%) were uninsured. Intervention participants were more likely to complete CRC screening within 6 months (68% vs 27%); adjusted-difference, 40 percentage points (95% CI, 29-51 percentage points). The intervention was more effective in women than in men (50 vs 21 percentage point increase, interaction P = .02). No effect modification was observed across other subgroups.Conclusions and Relevance: A patient decision aid plus patient navigation increased the rate of CRC screening completion in compared with usual care invulnerable primary care patients.Trial Registration: clinicaltrials.gov Identifier: NCT02054598.
Keywords: Patient Navigation -- Methods; Colorectal Neoplasms -- Epidemiology; Early Detection of Cancer -- Psychosocial Factors; Early Detection of Cancer -- Methods; Colorectal Neoplasms -- Diagnosis; Colorectal Neoplasms -- Psychosocial Factors; Decision Support Techniques; Occult Blood; Colonoscopy -- Methods; North Carolina; Primary Health Care -- Methods; Decision Making; Colonoscopy -- Psychosocial Factors; Special Populations; Female; Middle Age; New Mexico; Human; Aged; Black Persons; Medical Records -- Statistics and Numerical Data; Hispanic Americans; Primary Health Care -- Statistics and Numerical Data; Male; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Funding Source

Effect of comorbid conditions on adherence to colorectal cancer screening. - Lukin, Dana; Jandorf, Lina; Dhulkifl, Rayhana; Thélémaque, Linda; Christie, Jennifer; Itzkowitz, Steven; DuHamel, Katherine; Lukin, Dana J; Jandorf, Lina H; Dhulkifl, Rayhana J; Thélémaque, Linda D; Christie, Jennifer A; et al. (Journal of Cancer Education, 2012)
Potential barriers to colorectal cancer (CRC) screening include preexisting medical conditions (comorbidities), physician recommendation, psychosocial factors, and screening preparedness. This study's purpose was to investigate the impact of comorbid conditions on CRC screening among African Americans. A stage-matched randomized clinical trial was performed. Asymptomatic African Americans over age 50, with a primary care physician, and eligible for CRC screening were recruited at The Mount Sinai Hospital from 2005 to 2008. One hundred sixty-one patients were assessed for referral for, and completion of, CRC screening, comorbid conditions, "readiness to change," and number of physician visits within the observation period. Data was compared to a pretrial index to predict the likely effect of comorbid conditions on CRC screening. One hundred fifty-nine patients completed the study; 108 (68.9%) were referred for and 34 (21.2%) completed CRC screening. No demographic characteristics were associated with CRC screening completion. CRC screening referrals were similar for all patients, regardless of comorbidities or clinical visits. Comorbidities rated as having extreme influence on CRC screening showed a trend toward lower screening rates. There was a significant increase in screening rates among participants in advanced stages of readiness at enrollment. These data suggest that while comorbidities did not predict colonoscopy completion, they may play a role in concert with other factors. This is the only study to assess the effect of screening colonoscopy in an African American primary care setting. We must continue to explore interventions to narrow the disparate gap in screening and mortality rates.
Keywords: Black Persons; Cancer Screening; Colonoscopy -- Utilization; Colorectal Neoplasms -- Prevention and Control; Comorbidity; Patient Compliance; Aged; Behavioral Changes; Data Analysis Software; Descriptive Statistics; Educational Status; Employment Status; Female; Funding Source; Human; Income; Insurance, Health; Interviews; Male; Marital Status; Middle Age; New York; Occult Blood; Odds Ratio; Outpatients; P-Value; Primary Health Care; Prospective Studies; Randomized Controlled Trials; Record Review; Referral and Consultation

Effect of Erlotinib Plus Bevacizumab vs Erlotinib Alone on Progression-Free Survival in Patients With Advanced EGFR-Mutant Non–Small Cell Lung Cancer: A Phase 2 Randomized Clinical Trial. - Stinchcombe, Thomas E.; Jänne, Pasi A.; Wang, Xiaofei; Bertino, Erin M.; Weiss, Jared; Bazhenova, Lyudmila; Gu, Lin; Lau, Christie; Paweletz, Cloud; Jaslowski, Anthony; Gerstner, Gregory J.; Baggstrom, Maria Q.; et al. (JAMA Oncology, 2019)
Key Points: Question: Is the combination of erlotinib and bevacizumab superior to erlotinib alone to treat epidermal growth factor receptor (EGFR)–mutant non–small cell lung cancer? Findings: This phase 2 randomized clinical trial found that compared with erlotinib alone, the combination of erlotinib and bevacizumab did not result in superior progression-free survival. Meaning: The combination of erlotinib and bevacizumab does not have superior efficacy compared with erlotinib alone. This phase 2 multicenter randomized clinical trial including 88 patients compares progression-free survival, and secondarily overall survival, overall response rate, and adverse events, in patients with stage 4 EGFR-mutant non–small cell lung cancer treated with erlotinib plus bevacizumab vs erlotinib alone. Importance: Erlotinib is a standard first-line therapy for patients with epidermal growth factor receptor (EGFR)–mutant non–small cell lung cancer (NSCLC). Median progression-free survival (PFS) with erlotinib is approximately 10 months. Objective: To determine whether adding bevacizumab to erlotinib treatment results in superior progression-free survival compared with erlotinib alone. Design, Setting, and Participants: This phase 2 randomized clinical trial compared erlotinib plus bevacizumab with erlotinib alone in EGFR-mutant NSCLC. The trial was conducted in 17 US academic and community medical centers among 88 patients with EGFR exon 19 deletion or exon 21 L858R mutation based on local testing and stage 4 NSCLC who were eligible for bevacizumab. Patients were enrolled between November 2, 2012, and August 22, 2016, and followed up for a median (range) of 33 (0.7-62.5) months. Data were analyzed on August 28, 2018, and included data from November 2, 2012, to August 20, 2018. Interventions: Patients were randomized with equal allocation to 150 mg of oral erlotinib daily alone or with 15 mg/kg of intravenous bevacizumab every 3 weeks. Study therapy continued until disease progression, unacceptable adverse event, or withdrawal of consent. Main Outcomes and Measures: The primary outcome was PFS as assessed by the investigator; secondary outcomes were objective response rate (ORR), adverse events, and overall survival (OS). Analysis was designed to detect a hazard ratio (HR) of 0.667 for PFS (an improvement from a median PFS of 10 to 15 months). Results: Among 88 patients enrolled, the median (range) age was 63 (31-84) years; 62 patients (70%) were female; 75 (85%) were white, 8 (9%) were African American, 3 (3%) were Asian, and for 2 (2%), data on race were not available. Forty-eight patients (55%) were never smokers, 45 patients (51%) were of Eastern Cooperative Oncology Group performance status 1, and 59 patients (67%) had EGFR exon 19 deletion. Compared with erlotinib, the combination did not result in a significant difference in PFS (HR, 0.81; 95% CI, 0.50-1.31; P =.39; median PFS 17.9 [combination] and 13.5 months [erlotinib]), ORR (81% vs 83%; P =.81), and OS (HR, 1.41; 95% CI, 0.71-2.81; P =.33; median OS, 32.4 months [combination] and 50.6 months [erlotinib]). Adverse events of grade 3 or higher observed in 5 or more patients in the combination and erlotinib arms were skin eruption in 11 (26%) vs 7 (16%) patients, diarrhea in 4 (9%) vs 6 (13%) patients, hypertension in 17 (40%) vs 9 (20%) patients, and proteinuria in 5 (12%) vs 0 (0%) patients. Conclusions and Relevance: Erlotinib plus bevacizumab compared with erlotinib did not result in a significant improvement in PFS in EGFR-mutant NSCLC. Trial Registration: ClinicalTrials.gov identifier: NCT01532089.
Keywords: Carcinoma, Non-Small-Cell Lung -- Drug Therapy; Erlotinib -- Therapeutic Use; Bevacizumab -- Therapeutic Use; Antineoplastic Agents, Combined -- Therapeutic Use; Epidermal Growth Factors; Mutation; Treatment Outcomes -- Evaluation; Survival; Human; Male; Female; Adult; Middle Age; Aged; Aged, 80 and Over; Randomized Controlled Trials; Random Assignment; Multicenter Studies; Antineoplastic Agents, Combined -- Adverse Effects; Confidence Intervals; Kaplan-Meier Estimator; Chi Square Test; Data Analysis Software; Cox Proportional Hazards Model; Erlotinib -- Administration and Dosage; Bevacizumab -- Administration and Dosage; Cell-Free Nucleic Acids -- Analysis; Sex Factors; Functional Status; Clinical Assessment Tools; Funding Source

Effect of Patient Navigation on Breast Cancer Screening Among African American Medicare Beneficiaries: A Randomized Controlled Trial. - Marshall, Jessie; Mbah, Olive; Ford, Jean; Phelan-Emrick, Darcy; Ahmed, Saifuddin; Bone, Lee; Wenzel, Jennifer; Shapiro, Gary; Howerton, Mollie; Johnson, Lawrence; Brown, Qiana; Ewing, Altovise; et al. (JGIM: Journal of General Internal Medicine, 2016)
Background: There is growing evidence that patient navigation improves breast cancer screening rates; however, there are limited efficacy studies of its effect among African American older adult women.Objective: To evaluate the effect of patient navigation on screening mammography among African American female Medicare beneficiaries in Baltimore, MD.Design: The Cancer Prevention and Treatment Demonstration (CPTD), a multi-site study, was a randomized controlled trial conducted from April 2006 through December 2010.Setting: Community-based and clinical setting.Participants: The CPTD Screening Trial enrolled 1905 community-dwelling African American female Medicare beneficiaries who were ≥65 years of age and resided in Baltimore, MD. Participants were recruited from health clinics, community centers, health fairs, mailings using Medicare rosters, and phone calls.Interventions: Participants were randomized to either: printed educational materials on cancer screening (control group) or printed educational materials + patient navigation services designed to help participants overcome barriers to cancer screening (intervention group).Main Measure: Self-reported receipt of mammography screening within 2 years of the end of the study.Key Results: The median follow-up period for participants in this analysis was 17.8 months. In weighted multivariable logistic regression analyses, women in the intervention group had significantly higher odds of being up to date on mammography screening at the end of the follow-up period compared to women in the control group (odds ratio [OR] 2.26, 95 % confidence interval [CI]1.59-3.22). The effect of the intervention was stronger among women who were not up to date with mammography screening at enrollment (OR 3.63, 95 % CI 2.09-6.38).Conclusion: Patient navigation among urban African American Medicare beneficiaries increased self-reported mammography utilization. The results suggest that patient navigation for mammography screening should focus on women who are not up to date on their screening.
Keywords: Patient Education -- Methods; Guideline Adherence; Breast Neoplasms -- Ethnology; Patient Navigation -- Economics; Early Detection of Cancer -- Economics; Black Persons; Medicare -- Economics; Human; Breast Neoplasms -- Prevention and Control; Attitude to Health; Female; Mammography -- Economics; Aged; United States; Breast Neoplasms -- Economics; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Funding Source

Effect of simvastatin on the pharmacokinetics of anastrozole. - Bao, T; Slater, S A; Blackford, A; Jeter, S C; Wright, L; Rudek, M A; Desta, Z; Stearns, V (Journal of Clinical Oncology, 2009)
1517 Background: When used in the adjuvant setting, aromatase inhibitors (AIs) reduce the incidence of contralateral breast cancer and are therefore under investigation for primary breast cancer prevention. Statins hold promise for chemoprevention based on preclinical and epidemiological data. Adding statin to AI has the potential to enhance breast cancer prevention and to protect women from AI-related side effects. Prior to initiating a chemoprevention trial of combination therapy, we evaluated the potential for pharmacokinetic drug-drug interaction between anastrozole and simvastatin in postmenopausal women taking adjuvant anastrozole to ensure that the combination will not influence anastrozole concentration or affect its ability to reduce estrogen.Methods: Postmenopausal women with hormone receptor-positive, stage 0-III breast cancer who had been on adjuvant anastrozole (1 mg/day) for at least 30 days were prescribed 14 days of simvastatin (40 mg/day). We collected serum at baseline (anastrozole alone) and after 14 days of simvastatin initiation (combination therapy). Anastrozole and hydroxyanastrozole, its hydroxylated metabolite, concentrations were determined using liquid chromatography-tandem mass spectrometry assay. Estrogen concentrations will be determined using radio-immunoassay. Significant change in anastrozole was predetermined to be greater than a 30% decrease in concentrations. Percent changes from baseline in anastrozole and hydroxyanastrozole were evaluated using Wilcoxon signed-rank tests.Results: From December 2006 to September 2008, 11 women (10 Caucasian, 1 Black, all reported non-Hispanic with a mean age of 60 yrs [range 51-69]) were enrolled in the study. Of these women, nine had evaluable anastrozole concentrations. After 14 days of simvastatin, there were nonsignificant changes in anastrozole (median percentage difference = 10.1% [-13.5%, 38.4%], p = 0.36) and hydroxyanastrozole (median percentage difference = -3.0% [-19.1%, 11.2%], p = 0.65). Estrogen data will be available for presentation.Conclusions: Simvastatin is unlikely to alter the pharmacokinetics of anastrozole in a clinically meaningful way. Combination studies to assess chemopreventive properties of the combination are planned. [Table: see text].

Effect of socioeconomic status as measured by education level on survival in breast cancer clinical trials. - Herndon JE 2nd; Kornblith AB; Holland JC; Paskett ED; Herndon, James E 2nd; Kornblith, Alice B; Holland, Jimmie C; Paskett, Electra D (Psycho-Oncology, 2013)
Objectives: This paper aims to investigate the effect of socioeconomic status, as measured by education, on the survival of breast cancer patients treated on 10 studies conducted by the Cancer and Leukemia Group B.Methods: Sociodemographic data, including education, were reported by the patient at trial enrollment. Cox proportional hazards model stratified by treatment arm/study was used to examine the effect of education on survival among patients with early stage and metastatic breast cancer, after adjustment for known prognostic factors.Results: The patient population included 1020 patients with metastatic disease and 5146 patients with early stage disease. Among metastatic patients, factors associated with poorer survival in the final multivariable model included African American race, never married, negative estrogen receptor status, prior hormonal therapy, visceral involvement, and bone involvement. Among early stage patients, significant factors associated with poorer survival included African American race, separated/widowed, post/perimenopausal, negative/unknown estrogen receptor status, negative progesterone receptor status, >4 positive nodes, tumor diameter >2 cm, and education. Having not completed high school was associated with poorer survival among early stage patients. Among metastatic patients, non-African American women who lacked a high school degree had poorer survival than other non-African American women, and African American women who lacked a high school education had better survival than educated African American women.Conclusions: Having less than a high school education is a risk factor for death among patients with early stage breast cancer who participated in a clinical trial, with its impact among metastatic patients being less clear. Post-trial survivorship plans need to focus on women with low social status, as measured by education.
Keywords: Breast Neoplasms -- Mortality; Social Class; Adult; Aged; Black Persons -- Statistics and Numerical Data; Breast Neoplasms -- Ethnology; Clinical Trials; Cox Proportional Hazards Model; Educational Status; Female; Human; Middle Age; Multivariate Analysis; Risk Factors; Survival; United States

Effect of Supplementation With Marine ω-3 Fatty Acid on Risk of Colorectal Adenomas and Serrated Polyps in the US General Population: A Prespecified Ancillary Study of a Randomized Clinical Trial. - Song, Mingyang; Lee, I-Min; Manson, JoAnn E.; Buring, Julie E.; Dushkes, Rimma; Gordon, David; Walter, Joseph; Wu, Kana; Chan, Andrew T.; Ogino, Shuji; Fuchs, Charles S.; Meyerhardt, Jeffrey A.; et al. (JAMA Oncology, 2020)
Key Points: Question: Does marine ω-3 fatty acid supplementation reduce risk of colorectal cancer precursors in the US general population? Findings: In this randomized clinical trial that included 25 871 adults, daily supplementation of marine ω-3 fatty acid, 1 g, did not reduce risk of conventional adenomas or serrated polyps. A suggestive beneficial association was observed among individuals with low plasma levels of ω-3 fatty acid at baseline and among African American persons. Meaning: Daily supplementation with marine ω-3 fatty acids, 1 g, appears not to reduce the risk of colorectal premalignant lesions in the average-risk US population; however, individuals with low plasma levels of ω-3 or African American persons may benefit. Importance: Marine ω-3 fatty acid has been suggested to protect against colorectal cancer. Objective: To assess the effect of daily marine ω-3 fatty acid supplementation on the risk of colorectal cancer precursors, including conventional adenomas and serrated polyps. Design, Setting, and Participants: This study was a prespecified ancillary study of the placebo-controlled randomized clinical trial VITAL (Vitamin D and Omega-3 Trial). An intention-to-treat analysis was used to examine the effect of daily marine ω-3 supplements among 25 871 adults in the US general population (including 5106 African American persons) free of cancer and cardiovascular disease at enrollment. Randomization was from November 2011 to March 2014, and intervention ended as planned on December 31, 2017. Interventions: Marine ω-3 fatty acid, 1 g daily (which included eicosapentaenoic acid, 460 mg, and docosahexaenoic acid, 380 mg) and vitamin D3 (2000 IU daily) supplements. Main Outcomes and Measures: Risk of conventional adenomas (including tubular adenoma, tubulovillous adenoma, villous adenoma, and adenoma with high-grade dysplasia) or serrated polyps (including hyperplastic polyp, traditional serrated adenoma, and sessile serrated polyp). In a subset of participants who reported receiving a diagnosis of polyp on follow-up questionnaires, endoscopic and pathologic records were obtained to confirm the diagnosis. Odds ratios (ORs) and 95% CIs were calculated using logistic regression, after adjusting for age, sex, vitamin D treatment assignment, and use of endoscopy. Secondary analyses were performed according to polyp features and participants' characteristics. Results: The demographic characteristics of participants at randomization were well balanced between the treatment and placebo groups; for example, 50.6% vs 50.5% were women, and 19.7% vs 19.8% were African American persons were included in each group. The mean (SD) age was 67.1 (7.1) years in the placebo group and 67.2 (7.1) in the ω-3 treatment group. During a median follow-up of 5.3 years (range, 3.8-6.1 years), 294 cases of conventional adenomas were documented in the ω-3 group and 301 in the control group (multivariable OR, 0.98; 95% CI, 0.83-1.15) (1:1 ratio between number of cases and number of participants). In addition, 174 cases of serrated polyps were documented in the ω-3 group and 167 in the control group (OR, 1.05; 95% CI, 0.84-1.29). Null associations were found for polyp subgroups according to size, location, multiplicity, or histology. In secondary analyses, marine ω-3 treatment appeared to be associated with lower risk of conventional adenomas among individuals with low plasma levels of ω-3 index at baseline (OR, 0.76; 95% CI, 0.57-1.02; P =.03 for interaction by ω-3 index). A beneficial association of supplementation was also noted in the African American population (OR, 0.59; 95% CI, 0.35-1.00) but not in other racial/ethnic groups (P =.11 for interaction). Conclusions and Relevance: Supplementation with marine ω-3 fatty acids, 1 g per day, was not associated with reduced risk of colorectal cancer precursors. A potential benefit of this supplementation for individuals with low baseline ω-3 levels or for African American persons requires further confirmation. Trial Registration: ClinicalTrials.gov identifier: NCT01169259 This prespecified ancillary study of a randomized clinical trial compares the effects of daily marine ω-3 fatty acid supplementation vs placebo on risk of colorectal cancer precursors, including conventional adenomas and serrated polyps, in an average-risk US population.
Keywords: Colorectal Neoplasms -- Risk Factors -- United States; Adenoma -- Risk Factors -- United States; Colonic Polyps -- Risk Factors; Fatty Acids, Omega-3 -- Administration and Dosage; Dietary Supplementation -- In Adulthood; Human; United States; Female; Male; Adult; Eicosapentaenoic Acid -- Administration and Dosage; Docosahexaenoic Acids -- Administration and Dosage; Cholecalciferol -- Administration and Dosage; Randomized Controlled Trials; Random Assignment; Control Group; Black Persons; Placebos; Consent (Research); Questionnaires; Fatty Acids, Omega-3 -- Adverse Effects; Descriptive Statistics; Logistic Regression; Treatment Outcomes; Odds Ratio; Confidence Intervals; Colonoscopy; Sigmoidoscopy; Age Factors; Sex Factors; Ethnic Groups; Body Mass Index; Data Analysis Software; Statistical Significance; Middle Age; Aged; Funding Source

Effect of Text Messaging on Bowel Preparation and Appointment Attendance for Outpatient Colonoscopy: A Randomized Clinical Trial. - Mahmud, Nadim; Asch, David A.; Sung, Jessica; Reitz, Catherine; Coniglio, Mary S.; McDonald, Caitlin; Bernard, Donna; Mehta, Shivan J. (JAMA Network Open, 2021)
Key Points: Question: Do automated text messages improve outpatient colonoscopy attendance rate and bowel preparation quality? Findings: In this randomized clinical trial including 753 patients, usual care patient instructions were compared with an automated text messaging intervention in the week prior to outpatient colonoscopy. There was no significant difference between groups in appointment attendance rate or bowel preparation quality. Meaning: This randomized clinical trial found that automated text message reminders and instructions did not improve outpatient colonoscopy adherence, although future studies may identify patient subgroups that benefit from this approach. This randomized clinical trial examines the effectiveness of information and reminders via automated text message vs usual care for coloscopy attendance and preparation. Importance: Outpatient colonoscopy is important for colorectal cancer screening. However, nonadherence and poor bowel preparation are common. Objective: To determine if an automated text messaging intervention with a focus on informational and reminder functions could improve attendance rates and bowel preparation quality for outpatient colonoscopy. Design, Setting, and Participants: This randomized clinical trial was conducted in an endoscopy center at an urban academic medical center. Adult patients scheduled for outpatient colonoscopy between January and September 2019 were enrolled by telephone call (early phase) or by automated text message (late phase). Data were analyzed from October 2019 to January 2020. Interventions: After enrollment, patients were randomized in a 1:1 ratio to usual care (ie, written instructions and nurse telephone call) or to the intervention (ie, usual care plus an automated series of 9 educational or reminder text messages in the week prior to scheduled colonoscopy). Main Outcomes and Measures: The primary outcome was appointment attendance rate with good or excellent bowel preparation. Secondary outcomes included appointment attendance rate, bowel preparation quality (poor or inadequate, fair or adequate, and good or excellent), and cancellation lead time (in days). Results: Among 753 patients included and randomized in the trial (median [interquartile range] age, 56 [49-64] years; 364 [48.3%] men; 429 [57.2%] Black), 367 patients were randomized to the intervention group and 386 patients were randomized to the control group. There was no significant difference in the primary outcome between groups (patients attending appointments with good or excellent bowel preparation: intervention, 195 patients [53.1%]; control, 210 patients [54.4%]; P =.73), including when stratified by early or late phase enrollment groups. Similarly, there were no significant differences in secondary outcomes. Conclusions and Relevance: This randomized clinical trial found no significant difference in appointment attendance or bowel preparation quality with an automated text messaging intervention compared with the usual care control. Future work could optimize the content and delivery of text message interventions or identify patient subgroups that may benefit from this approach. Trial Registration: ClinicalTrials.gov Identifier: NCT03710213
Keywords: Text Messaging; Bowel Preparation; Appointments and Schedules; Outpatients; Colonoscopy; Patient Compliance; Outcomes (Health Care); Human; Randomized Controlled Trials; Health Information; Urban Areas; Academic Medical Centers; Middle Age; Aged; Control Group; Quality Improvement; Pilot Studies; Young Adult; Adult; Aged, 80 and Over; Wilcoxon Rank Sum Test; Chi Square Test; Data Analysis Software; Male

Effect of Vitamin D Supplementation on Breast Cancer Biomarkers: CALGB 70806 (Alliance) Study Design and Baseline Data. - Apoe, Ogheneruona; Sin-Ho Jung; Heshan Liu; Seisler, Drew K.; Charlamb, Jayne; Zekan, Patricia; Lili X. Wang; Unzeitig, Gary W.; Garber, Judy; Marshall, James; Wood, Marie (American Journal of Hematology/Oncology, 2016)
One in eight women will develop breast cancer over their lifetime with 230,000 women diagnosed in 2015. For this reason, breast cancer prevention efforts are essential. Vitamin D, with anticancer properties, may have a role in prevention of some cancers, including breast cancer. This report discusses the rationale, study protocol, and baseline data for a clinical trial of vitamin D and its effects on breast cancer biomarkers. This study was a randomized controlled trial designed to evaluate the effect of a fixed dose of vitamin D on specific breast cancer biomarkers. Study participants were randomized to take either vitamin D or placebo for a period of one year. All participants had mammograms and blood drawn for serum biomarkers. A subset of participants underwent random periareolar fine needle aspiration to draw tissue for biomarkers. From January 2011 to December 2013, 300 premenopausal women, aged 59 or younger, were recruited from 41 institutions across the United States. A total of 102 women underwent random periareolar fine needle aspiration. The last subject completed the trial in January 2015. Baseline vitamin D levels for all participants ranged from 4 to 72 ng/mL, with 62% of participants being vitamin-D deficient at enrollment (≥30 ng/mL or ≥75 nmol/L). The mean body mass index (BMI) was 27.0 kg/m² (range 15.1-53.6 kg/m²). 14% and 11.7% of participants were Hispanic or African American, respectively. Accrual and enrollment of participants is feasible for this type of multicenter prevention trial, and it can readily be carried out in a cooperative group setting.
Keywords: Treatment Outcomes -- Evaluation; Vitamin D -- Therapeutic Use; Dietary Supplementation; Breast Neoplasms -- Drug Therapy; Biological Markers; Human; Randomized Controlled Trials; Random Assignment; Study Design; Vitamin D -- Administration and Dosage; Placebos; Mammography; Biopsy, Needle; Middle Age; Research Subject Recruitment; Descriptive Statistics; Body Mass Index; Hispanic Americans; Black Persons; Breast Neoplasms -- Prevention and Control

Effectiveness of a web-based colorectal cancer screening patient decision aid: a randomized controlled trial in a mixed-literacy population. - Miller DP Jr; Spangler JG; Case LD; Goff DC Jr; Singh S; Pignone MP; Miller, David P Jr; Spangler, John G; Case, L Doug; Goff, David C Jr; Singh, Sonal; Pignone, Michael P (American Journal of Preventive Medicine, 2011)
Background: Colorectal cancer (CRC) screening reduces mortality yet remains underutilized. Low health literacy may contribute to this underutilization by interfering with patients' ability to understand and receive preventive health services.Purpose: To determine if a web-based multimedia CRC screening patient decision aid, developed for a mixed-literacy audience, could increase CRC screening.Design: RCT. Patients aged 50-74 years and overdue for CRC screening were randomized to the web-based decision aid or a control program seen immediately before a scheduled primary care appointment.Setting/participants: A large community-based, university-affiliated internal medicine practice serving a socioeconomically disadvantaged population.Main Outcome Measures: Patients completed surveys to determine their ability to state a screening test preference and their readiness to receive screening. Charts were abstracted by masked observers to determine if screening tests were ordered and completed.Results: Between November 2007 and September 2008, a total of 264 patients enrolled in the study. Data collection was completed in 2009, and data analysis was completed in 2010. A majority of participants (mean age=57.8 years) were female (67%), African-American (74%), had annual household incomes of <$20,000 (76%), and had limited health literacy (56%). When compared to control participants, more decision-aid participants had a CRC screening preference (84% vs 55%, p<0.0001) and an increase in readiness to receive screening (52% vs 20%, p=0.0001). More decision-aid participants had CRC screening tests ordered (30% vs 21%) and completed (19% vs 14%), but no statistically significant differences were seen (AOR=1.6, 95% CI=0.97, 2.8, and AOR=1.7, 95% CI=0.88, 3.2, respectively). Similar results were found across literacy levels.Conclusions: The web-based decision aid increased patients' ability to form a test preference and their intent to receive screening, regardless of literacy level. Further study should examine ways the decision aid can be combined with additional system changes to increase CRC screening.
Keywords: Colorectal Neoplasms -- Diagnosis; Decision Support Techniques; Health Screening -- Methods; Internet; Aged; Female; Human; Information Literacy; Male; Middle Age; Patient Satisfaction; Primary Health Care -- Methods; Randomized Controlled Trials; Socioeconomic Factors

Effects of dialogue and therapeutic touch on preoperative and postoperative experiences of breast cancer surgery: an exploratory study. - Samarel N; Fawcett J; Davis MM; Ryan FM (Oncology Nursing Forum, 1998)
Purpose/Objectives: To obtain preliminary data and determine the feasibility of a large-scale experimental study to test the efficacy of the Rogerian Science of Unitary Human Beings-based intervention of dialogue and therapeutic touch (TT) on pre- and postoperative anxiety and mood and postoperative pain from breast cancer surgery. Design: Experimental. Setting: Mid-Atlantic region; ambulatory. Sample: 29 Caucasian and 2 African American English-speaking women with positive breast cancer biopsy (experimental, n = 14, control, n = 17), ranging in age from 31-84 years old (F = 55.6). Methods: Treatments administered in subjects' homes within seven days prior to surgery and 24 hours after hospital discharge. Experimental treatment consisted of 10 minutes of TT and 20 minutes of dialogue. Control treatment consisted of 10 minutes of quiet time and 20 minutes of dialogue. Data (Spielberger State-Trait Anxiety Inventory, Affects Balance Scale, and Visual Analog Scale-Pain) were collected at the conclusion of each home visit. Main Research Variables: Anxiety, mood, and pain. Findings: The experimental group had lower preoperative state anxiety than the control groups (p = 0.008). No difference was found for preoperative mood. No differences were found for any postoperative measure. Conclusions: A large-scale study of dialogue and TT would require changes in design and recruitment strategies. Implications for Nursing Practice: Nurses may provide more comprehensive care by incorporating dialogue and TT or quiet time into their pre- and postoperative care, Additional research, however, is recommended to determine the differential effects of dialogue, TT, and quiet time on women's experiences with breast cancer prior to incorporating these noninvasive modalities into clinical practice.
Keywords: Therapeutic Touch; Preoperative Care; Postoperative Care; Breast Neoplasms -- Surgery; Oncologic Nursing; Nurse-Patient Relations; Funding Source; Experimental Studies; Mid Atlantic Region; Rogers Science of Unitary Human Beings; Cancer Patients; Anxiety; Postoperative Pain; Research Subject Recruitment; Descriptive Statistics; Visual Analog Scaling; Research Instruments; Data Analysis Software; Multivariate Analysis of Variance; Affect; Exploratory Research; Correlation Coefficient; Adult; Middle Age; Aged; Aged, 80 and Over; Outpatients; Female; Human

Efficacy to effectiveness transition of an Educational Program to Increase Colorectal Cancer Screening (EPICS): study protocol of a cluster randomized controlled trial. - Smith, Selina A; Blumenthal, Daniel S (Implementation Science, 2013)
Background: African Americans have the highest incidence and mortality and are less likely than whites to have been screened for colorectal cancer (CRC). Many interventions have been shown to increase CRC screening in research settings, but few have been evaluated specifically for use in African-American communities in real world settings. This study aims to identify the most efficacious approach to disseminate an evidence-based intervention in promoting colorectal screening in African Americans and to identify the factors associated with its efficacy.Methods/design: In this study, investigators will recruit 20 community coalitions and 7,200 African-Americans age 50 to 74 to test passive and active approaches to disseminating the Educational Program to Increase Colorectal Cancer Screening (EPICS); to measure the extent to which EPICS is accepted and the fidelity of implementation in various settings and to estimate the potential translatability and public health impact of EPICS. This four-arm cluster randomized trial compares the following implementation strategies: passive arms, (web access to facilitator training materials and toolkits without technical assistance (TA) and (web access, but with technical assistance (TA); active arms, (in-person access to facilitator training materials and toolkits without TA and (in-person access with TA). Primary outcome measures are the reach (the proportion of representative community coalitions and individuals participating) and efficacy (post-intervention changes in CRC screening rates). Secondary outcomes include adoption (percentage of community coalitions implementing the EPICS sessions) and implementation (quality and consistency of the intervention delivery). The extent to which community coalitions continue to implement EPICS post-implementation (maintenance) will also be measured. Cost-effectiveness analysis will be conducted.Discussion: Implementing EPICS in partnership with community coalitions, we hypothesized, will result in more rapid adoption than traditional top-down approaches, and resulting changes in community CRC screening practices are more likely to be sustainable over time. With its national reach, this study has the potential to enhance our understanding of barriers and enablers to the uptake of educational programs aimed at eliminating cancer disparities.Trial Registration: http://www.ClinicalTrials.gov NCT01805622.
Keywords: Colorectal Neoplasms -- Prevention and Control; Patient Education -- Methods; Black Persons; Aged; Cluster Analysis; Colorectal Neoplasms -- Ethnology; Early Detection of Cancer; Female; Health Promotion -- Administration; Health Status Disparities; Human; Male; Middle Age; Treatment Outcomes

End-of-Life Care in Patients with Metastatic Lung Cancer Harboring Epidermal Growth Factor Receptor Mutations. - Bauman, Jessica R.; Piotrowska, Zofia; Muzikansky, Alona; Gallagher, Emily; Scribner, Emily; Temel, Brandon; Sequist, Lecia V.; Heist, Rebecca S.; Temel, Jennifer S. (Journal of Palliative Medicine, 2016)
Background/Objective: Patients with metastatic nonsmall cell lung cancer (NSCLC) harboring epidermal growth factor receptor (EGFR) mutations benefit from improved survival and quality of life with EGFR-directed therapy. We sought to explore if these improvements in cancer care impacted the delivery of end-of-life (EOL) care in this population. Design: We retrospectively reviewed medical records of patients cared for at our institution with the diagnosis of metastatic EGFR-mutant NSCLC who died by January 2015. Results: Sixty-one patients were included. The majority of patients were female (68%), white or Asian (97%), and never or minimal smokers (76%). Forty-two out of fifty-eight patients (72%) received chemotherapy within 30 days of death. Forty-one out of sixty-one patients (67%) had a hospital admission within 30 days of death. EOL outcomes were known for 53 patients. Of these, 34 (64%) patients enrolled on hospice. The median length of stay on hospice was 6 days (range 0-206). Thirty-three (62%) patients died at home with hospice services or at an inpatient hospice facility. Eighteen patients (34%) died in the hospital. Conclusion: Patients with metastatic NSCLC harboring EGFR mutations had high rates of chemotherapy use and hospital admissions in the last month of life, and many died in the hospital. Hospital admissions near the EOL and short admissions to hospice are indicators of poor quality EOL care and are likely a result of prolonged chemotherapy administration in this population. Thus, current healthcare delivery models may be insufficient to provide comprehensive EOL care for patients with EGFR mutations.
Keywords: Terminally Ill Patients; Lung Neoplasms -- Diagnosis; Neoplasm Metastasis; Epidermal Growth Factors -- Physiology; Mutation; Human; Carcinoma, Non-Small-Cell Lung -- Mortality; Cancer Patients -- Evaluation; Survival; Patient Selection; Male; Female; Race Factors; Ethnic Groups; White Persons; Asians; Chemotherapy, Cancer; Patient Admission; Death -- Evaluation; Hospice Care; Length of Stay; Health Care Delivery; Quality of Health Care -- Evaluation; Retrospective Design; Record Review; Descriptive Statistics; Data Analysis Software; Black Persons; Smoking -- Evaluation

Engaging African American breast cancer survivors in an intervention trial: culture, responsiveness and community. - Germino BB; Mishel MH; Alexander GR; Jenerette C; Blyler D; Baker C; Vines AI; Green M; Long DG; Germino, Barbara B; Mishel, Merle H; Alexander, G Rumay; et al. (Journal of Cancer Survivorship, 2011)
Introduction: Younger breast cancer survivors often lead extremely busy lives with multiple demands and responsibilities, making them difficult to recruit into clinical trials. African American women are even more difficult to recruit because of additional historical and cultural barriers. In a randomized clinical trial of an intervention, we successfully used culturally informed, population-specific recruitment and retention strategies to engage younger African-American breast cancer survivors.Methods: Caucasian and African American breast cancer survivors were recruited from multiple communities and sites. A variety of planned recruitment and retention strategies addressed cultural and population-specific barriers and were guided by three key principals: increasing familiarity with the study in the communities of interest; increasing the availability and accessibility of study information and study participation; and using cultural brokers.Results: Accrual of younger African-American breast cancer survivors increased by 373% in 11 months. The steepest rise in the numbers of African-American women recruited came when all strategies were in place and operating simultaneously. Retention rates were 87% for both Caucasian and African American women. DISCUSSSION/CONCLUSIONS: To successfully recruit busy, younger African American cancer survivors, it is important to use a multifaceted approach, addressing cultural and racial/ethnic barriers to research participation; bridging gaps across cultures and communities; including the role of faith and beliefs in considering research participation; recognizing the demands of different life stages and economic situations and the place of research in the larger picture of peoples' lives. Designs for recruitment and retention need to be broadly conceptualized and specifically applied.Implications For Cancer Survivors: For busy cancer survivors, willingness to participate in and complete research participation is enhanced by strategies that address barriers but also acknowledge the many demands on their time by making research familiar, available, accessible and credible.
Keywords: Black Persons -- Psychosocial Factors; Breast Neoplasms -- Therapy; Carcinoma -- Therapy; Culture; Patient Selection; Clinical Trials; Survivors -- Psychosocial Factors; Black Persons -- Statistics and Numerical Data; Breast Neoplasms -- Ethnology; Breast Neoplasms -- Psychosocial Factors; Breast Neoplasms -- Rehabilitation; Carcinoma -- Ethnology; Carcinoma -- Psychosocial Factors; Carcinoma -- Rehabilitation; Communication Barriers; Counseling -- Methods; Fear; Female; Health Services Accessibility; Human; Patient Attitudes; Psychotherapy -- Methods; Recurrence; Residence Characteristics

Enrolling older persons in cancer trials: the effect of sociodemographic, protocol, and recruitment center characteristics. - Gross CP; Herrin J; Wong N; Krumholz HM (Journal of Clinical Oncology, 2005)
PURPOSE: To determine the effect of patient, protocol, geographic, and institutional factors on enrollment of older persons onto cancer trials. METHODS: We conducted a cross-sectional analysis of patients enrolled onto National Cancer Institute-sponsored lung, breast, colorectal, and prostate cancer trials during 1996 to 2002. We used a cross-classified logistic multilevel model to examine the associations between patient, hospital, county, and protocol characteristics, and the likelihood of participants being elderly (>or= 65 years old). RESULTS: The final study sample consisted of 36,167 patients enrolled onto 33 trials. After accounting for cancer type, only 6% of the variation in elderly enrollment onto cancer trials was at the protocol level. In contrast, more than 55% of the variation in elderly enrollment was attributable to patient level variation. In multivariate analysis, nonwhite patients were significantly less likely to be elderly than whites (odds ratio [OR] for blacks, 0.51; 95% CI, 0.44 to 0.58; and OR for Hispanics, 0.49; 95% CI, 0.40 to 0.59 v whites). Participants living less than 7 miles from their recruitment center were significantly more likely to be elderly (OR, 1.31; 95% CI, 1.24 to 1.38). Among the 910 recruitment centers, the median adjusted proportion of patients who were elderly was 24.9% (interquartile range, 24.0% to 26.9%). There were a significantly higher number of outlier centers (<or= 20.8% or >or= 29.3% elderly) than would be expected by a normal distribution (68 observed v six expected; P < .0001). CONCLUSION: Race and proximity to trial enrollment centers were significantly related to age of trial participants after adjusting for protocol factors. Additional work should explore why some recruitment centers were outliers regarding enrollment of older persons.
Keywords: Research Subject Recruitment -- In Old Age; Geographic Factors; Socioeconomic Factors; Neoplasms -- Therapy; Cross Sectional Studies; Chi Square Test; Odds Ratio; Confidence Intervals; Multivariate Analysis; Aged; Funding Source; Human

Enrollment and biospecimen collection in a multiethnic family cohort: the Northern California site of the Breast Cancer Family Registry. - John, Esther M.; Sangaramoorthy, Meera; Koo, Jocelyn; Whittemore, Alice S.; West, Dee W. (Cancer Causes & Control, 2019)
Purpose: Racial/ethnic minorities are often assumed to be less willing to participate in and provide biospecimens for biomedical research. We examined racial/ethnic differences in enrollment of women with breast cancer (probands) and their first-degree relatives in the Northern California site of the Breast Cancer Family Registry from 1996 to 2011.Methods: We evaluated participation in several study components, including biospecimen collection, for probands and relatives by race/ethnicity, cancer history, and other factors.Results: Of 4,780 eligible probands, 76% enrolled in the family registry by completing the family history and risk factor questionnaires and 68% also provided a blood or mouthwash sample. Enrollment was highest (81%) for non-Hispanic whites (NHWs) and intermediate (73-76%) for Hispanics, African Americans, and all Asian American subgroups, except Filipina women (66%). Of 4,279 eligible relatives, 77% enrolled in the family registry, and 65% also provided a biospecimen sample. Enrollment was highest for NHWs (87%) and lowest for Chinese (68%) and Filipinas (67%). Among those enrolled, biospecimen collection rates were similar for NHW, Hispanic, and African American women, both for probands (92-95%) and relatives (82-87%), but lower for some Asian-American subgroups (probands: 72-88%; relatives: 71-88%), foreign-born Asian Americans, and probands those who were more recent immigrants or had low English language proficiency.Conclusions: These results show that racial/ethnic minority populations are willing to provide biospecimen samples for research, although some Asian American subgroups in particular may need more directed recruitment methods. To address long-standing and well-documented cancer health disparities, minority populations need equal opportunities to contribute to biomedical research.
Keywords: Population; Breast Neoplasms -- Epidemiology; California; Risk Factors; Young Adult; Breast Neoplasms -- Ethnology; Middle Age; White Persons -- Statistics and Numerical Data; Asians -- Statistics and Numerical Data; Adult; Data Collection; Adolescence; Black Persons -- Statistics and Numerical Data; Female; Hispanic Americans -- Statistics and Numerical Data; Funding Source; Human

Enrollment of lung cancer patients on clinical trials at an NCI comprehensive cancer center. - Keedy, V L; Horn, L; Hayes, A; Spencer, B; Garcia, G; Campbell, N; Sandler, A; Carbone, D; Johnson, D H (Journal of Clinical Oncology, 2009)
6633 Background: Enrollment of cancer patients (pt) in clinical trials is considered essential in order to improve cancer care. However, cancer clinical trials participation remains low. Understanding barriers to pt enrollment is necessary to overcome this problem. Previous reports have identified pt age, race, and ethnicity, disease stage, performance status (PS) and relationship with their health care provider as factors that can influence the enrollment of pts in clinical trials.Methods: We conducted a retrospective review of the charts of all lung cancer pts seen in the Thoracic Oncology Clinic at Vanderbilt Ingram Cancer Center between November 2005 and November 2008. A total of 1075 lung cancer pts were seen.Results: 577 charts (of a planned 1075) have been audited to date. Pt demographics: median age = 64 yrs; male = 54%; Caucasian = 92%, African American = 4%, and Asian = 1%; NSCLC = 80%, SCLC = 17%. Male pts were more likely than females to be eligible for a clinical trial (p = 0.056). A study protocol was available for 57% of pts; 52% of pts proved eligible; 36% were entered into a study (11% total population). Significantly more protocols were available for NSCLC pts compared to pts with SCLC (p ≤ 0.001); there was also a non-significant trend towards higher enrollment of eligible NSCLC pts. There was no difference in eligibility between ethnicity; the percentage of eligible pts enrolling on trials was similar between Caucasian & African American pts (46% and 43%); no Asian pts were enrolled. The most common reasons for not enrolling included a preference for treatment closer to home (29%), patient refusal (19%), PS (19%), and co-morbidities (17%). The distance pts traveled was inversely correlated with likelihood of study participation.Conclusions: A total of 11% of lung cancer pt evaluated in our Thoracic Oncology Clinic were enrolled in clinical trials. Our data suggest additional strategies are needed to attract minority groups, increase enrollment of women and pts with comorbidities and poor PS. Travel distances influence pt willingness to participate in clinical trials. Strategies are needed to overcome this factor. No significant financial relationships to disclose.

Enrollment of racial and ethnic minorities in the Prostate, Lung, Colorectal and Ovarian Cancer Screening Trial. - Pinsky PF; Ford M; Gamito E; Higgins D; Jenkins V; Lamerato L; Tenorio S; Marcus PM; Gohagan JK; Pinsky, Paul F; Ford, Marvella; Gamito, Eduard; et al. (Journal of the National Medical Association, 2008)
Background: Minority populations in the United States, especially blacks and Hispanics, are generally underrepresented among participants in clinical trials. Here, we report the experience of enrolling ethnic minorities in a large cancer screening trial.Methods: The Prostate, Colorectal, Lung and Ovarian (PLCO) Cancer Screening Trial is a multicenter randomized trial designed to evaluate the effectiveness of screening for the PLCO cancers. Subjects were recruited at 10 U.S. centers between 1993 and 2001. One screening center had a major special recruitment effort for blacks and another center had a major special recruitment effort for Hispanics.Results: Among almost 155,000 subjects enrolled in PLCO, minority enrollment was as follows: black (5.0%), Hispanic (1.8%) and Asian (3.6%). This compares to an age-eligible population in the combined catchment areas of the PLCO centers that was 14.0% black, 2.9% Hispanic and 5.4% Asian, and an age-eligible population across the U.S. that was 9.5% black, 6.5% Hispanic and 3.0% Asian. About half (45%) of Hispanics were recruited at the center with the special Hispanic recruitment effort. Seventy percent of blacks were recruited at two centers; the one with the major special recruitment effort and a center in Detroit whose catchment area was 20% black among age-eligibles. Blacks, Hispanics and (non-Hispanic) whites were all more highly educated, less likely to currently smoke and more likely to get regular exercise than their counterparts in the general population.Conclusion: Significant efforts were made to recruit racial/ ethnic minorities into PLCO, and these efforts resulted in enrollment levels that were comparable to those seen in many recent cancer screening or prevention trials. Blacks and Hispanics were nonetheless underrepresented in PLCO compared to their levels among age-eligibles in the overall U.S. population or in the aggregate PLCO catchment areas.
Keywords: Colorectal Neoplasms -- Diagnosis; Ethnic Groups -- Statistics and Numerical Data; Health Screening; Lung Neoplasms -- Diagnosis; Ovarian Neoplasms -- Diagnosis; Patient Selection; Prostatic Neoplasms -- Diagnosis; Aged; Asians -- Statistics and Numerical Data; Attitude to Health; Black Persons -- Statistics and Numerical Data; Clinical Trials; Colorectal Neoplasms -- Epidemiology; Female; Hispanic Americans -- Statistics and Numerical Data; Lung Neoplasms -- Epidemiology; Male; Middle Age; Ovarian Neoplasms -- Epidemiology; Patient Attitudes; Patient Satisfaction; Prostatic Neoplasms -- Epidemiology; United States; White Persons -- Statistics and Numerical Data; Human

Enrollment Trends and Disparity Among Patients With Lung Cancer in National Clinical Trials, 1990 to 2012. - Pang, Herbert H.; Xiaofei Wang; Stinchcombe, Thomas E.; Wong, Melisa L.; Perry Cheng; Ganti, Apar Kishor; Sargent, Daniel J.; Ying Zhang; Chen Hu; Mandrekar, Sumithra J.; Redman, Mary W.; Manola, Judith B.; et al. (Journal of Clinical Oncology, 2016)
Purpose Under-representation of elderly, women, and racial/ethnic minority patients with cancer in clinical trials is of national concern. The goal of this study was to characterize enrollment trends and disparities by age, sex, and race/ethnicity in lung cancer trials. Methods We analyzed data for 23,006 National Cancer Institute cooperative group lung cancer trial participants and 578,476 patients with lung cancer from the SEER registry from 1990 to 2012. The enrollment disparity difference (EDD) and enrollment disparity ratio (EDR) were calculated on the basis of the proportion of each subgroup in the trial population and the US lung cancer population. Annual percentage changes (APCs) in the subgroup proportions in each population were compared over time. Results Enrollment disparity for patients ≥ 70 years of age with non-small-cell lung cancer improved from 1990 to 2012 (test of parallelism, P = .020), with a remaining EDD of 0.22 (95% CI, 0.19 to 0.25) and EDR of 1.65 (95% CI, 1.51 to 1.82) in 2010 to 2012. No improvement was seen for elderly patients with small-cell lung cancer (SCLC), with an APC of 0.20 ( P = .714) among trial participants, despite a rising proportion of elderly patients with SCLC in the US population (APC, 0.32; P = .020). Enrollment disparity for women with lung cancer improved overall, with the gap closing by 2012 (EDD, 0.03 [95% CI, 0.00 to 0.06]; EDR, 1.07 [95% CI, 1.00 to 1.16]). Enrollment disparities persisted without significant improvement for elderly women, blacks, Asians/Pacific Islanders, and Hispanics. Conclusion Under-representation in lung cancer trials improved significantly from 1990 to 2012 for elderly patients with non-small-cell lung cancer and for women, but ongoing efforts to improve the enrollment of elderly patients with SCLC and minorities are needed. Our study highlights the importance of addressing enrollment disparities by demographic and disease subgroups to better target under-represented groups of patients with lung cancer.
Keywords: Healthcare Disparities -- Statistics and Numerical Data; Carcinoma, Non-Small-Cell Lung -- Epidemiology; Lung Neoplasms -- Therapy; Clinical Trials; Carcinoma, Non-Small-Cell Lung -- Therapy; Lung Neoplasms -- Epidemiology; Lung Neoplasms -- Ethnology; Male; Patient Selection; United States; Socioeconomic Factors; Registries, Disease; Age Factors; Aged; Female; Sex Factors; Human; Funding Source

Establishing a Minority-Based Community Clinical Oncology Program: The University of Medicine and Dentistry of New Jersey, New Jersey Medical School-University Hospital Cancer Center Experience. - Wieder, Robert; Teal, Randall; Saunders, Tracie; Weiner, Bryan J. (Journal of Oncology Practice, 2013)
The Minority-Based Community Clinical Oncology Program (MB-CCOP) at University of Medicine and Dentistry of New Jersey, New Jersey Medical School-University Hospital Cancer Center was established to serve an unmet need in a medically, educationally, and socioeconomically underserved community of primarily African American and Latino patients in Newark and Essex County, New Jersey. The MB-CCOP was built on an existing infrastructure of multidisciplinary teams of cancer specialists who collaborated in patient care and an existing clinical research program, which included multilingual staff and a breast cancer navigator. This article highlights some of the unique opportunities and challenges involved in the startup of an MBCCOP specifically relevant to an academic setting. We present a guide to the necessary infrastructure and institutional support that must be in place before considering such a program and some of the steps an institution can take to overcome barriers preventing successful enrollment of patients onto clinical trials.
Keywords: Research Subject Recruitment -- Methods; Clinical Trials; Oncology; Minority Groups; Program Development -- Methods -- New Jersey; New Jersey; Academic Medical Centers; Community Health Services

Establishment of a Southern Breast Cancer Cohort. - Bondurant, Kristina L.; Harvey, Sarah; Klimberg, Suzanne; Kadlubar, Susan; Phillips, Martha M. (Breast Journal, 2011)
Breast cancer continues to be among the most common cancers affecting women in the United States. Researchers investigating the area are turning their attention to novel prevention, detection, and treatment options. Recent molecular epidemiology research has highlighted the effects of both genetic and environmental exposures on an individual's risk of developing breast cancer and predicted response to treatment. Cohort designs are a potentially powerful tool that researchers can utilize to investigate the genetic and environmental factors affecting breast cancer risk and treatment options. This paper describes the recruitment of a community-based cohort of women in a southern state. The Spit for the Cure Cohort (SFCC), being developed by researchers at the University of Arkansas for Medical Sciences (Little Rock, AR), is designed to be representative of the female population of the state with oversampling of women with a history of breast cancer and women of color. To date, the SFCC includes more than 14,000 women recruited from all 75 counties of Arkansas and six neighboring states. Methods used to recruit and maintain the cohort and collect both questionnaire data and genetic material are described, as are the demographic characteristics of the cohort as it currently exists. The recruitment methods utilized for the SFCC are rapidly building a breast cancer cohort and providing a large biorepository for molecular epidemiology research.
Keywords: Breast Neoplasms -- Epidemiology; Research Subject Recruitment; Funding Source; Human; Female; Prospective Studies; Arkansas; Breast Neoplasms -- Familial and Genetic; Adult; Middle Age; Aged; Aged, 80 and Over; Questionnaires; Black Persons; White Persons; Descriptive Statistics

Evaluation of conceptual framework for recruitment of African American patients with breast cancer. - Heiney SP; Adams SA; Wells LM; Johnson H (Oncology Nursing Forum, 2010)
Purpose/Objectives: To describe the Heiney-Adams Recruitment Framework (H-ARF); to delineate a recruitment plan for a randomized, behavioral trial (RBT) based on H-ARF; and to provide evaluation data on its implementation.Data Sources: All data for this investigation originated from a recruitment database created for an RBT designed to test the effectiveness of a therapeutic group convened via teleconference for African American women with breast cancer.Data Synthesis: Major H-ARF concepts include social marketing and relationship building. The majority of social marketing strategies yielded 100% participant recruitment. Greater absolute numbers were recruited via Health Insurance Portability and Accountability Act waivers. Using H-ARF yielded a high recruitment rate (66%).Conclusions: Application of H-ARF led to successful recruitment in an RBT. The findings highlight three areas that researchers should consider when devising recruitment plans: absolute numbers versus recruitment rate, cost, and efficiency with institutional review board-approved access to protected health information.Implications for Nursing: H-ARF may be applied to any clinical or population-based research setting because it provides direction for researchers to develop a recruitment plan based on the target audience and cultural attributes that may hinder or help recruitment.
Keywords: Black Persons; Breast Neoplasms; Conceptual Framework -- Evaluation; Research Subject Recruitment; Databases; Marketing; Models, Theoretical; Professional-Patient Relations; Referral and Consultation; Research Subject Recruitment -- Methods

Examining opportunity for cancer clinical trial participation among under-represented groups. - Rearden, Jessica Rose (Examining Opportunity for Cancer Clinical Trial Participation Among Under-represented Groups, 2014)
Recent evidence suggests racial/ethnic minorities, older adults and the economically disadvantaged are willing to participate in cancer clinical trials (CCTs) but may lack the opportunity to do so. We define opportunity for participation as an offer from a healthcare provider or researcher for screening and/or enrollment in a CCT. A barrier/promoter of opportunity for participation is eligibility, or the key attributes/characteristics a person must have in order to participate in a CCT. We have limited understanding of the roles of opportunity and eligibility for participation in CCTs and how this may contribute to under-representation. The primary objective of this dissertation was to examine whether opportunity and eligibility for cancer clinical trial participation differs between under-represented and well-represented groups based on socio-demographic and disease characteristics. Using Ford's conceptual framework for examining participation of under-represented groups in CCTs, we performed a cross-sectional matched cohort study in a large academic comprehensive cancer center. We enrolled 88 new cancer patients (44 Black or Hispanic, 44 Non-Hispanic White), matched on age (+/- 5 years) and cancer type (breast, lung, kidney or leukemia). We collected information on opportunity, eligibility, socio-demographic/disease characteristics and reasons for exclusion via a participant questionnaire, and with participant permission, a retrospective electronic medical record (EMR) review. We examined differences using Fisher's exact tests, t-tests and ANOVA. Most of the sample reported no opportunity for CCT participation (79%) and were ineligible for accruing trials (84%). Those with Stage III/IV disease were significantly more likely to have opportunity (p=.001) and be eligible for participation (p=<.001). Differences in opportunity and eligibility were predominantly associated with disease characteristics, as opposed to socio-demographic characteristics. Common reasons for exclusion included 'other' (a combination of categories primarily suggesting advanced disease), prior therapy, and lack of required therapy (per study eligibility criteria). Results suggest lack of available trials, poor patient-trial fit and stringent eligibility criteria limit opportunity across populations. Opportunity and eligibility likely vary based on complex intersections between race, ethnicity, age, SES and disease characteristics, as well as differences in the healthcare setting. Future research should explore these intersections and how they influence under-representation in opportunity for CCT participation.
Keywords: Clinical Trials; Ethnic Groups; Minority Groups; Oncology; Research Subjects; Analysis of Variance; Black Persons; Cancer Care Facilities; Cross Sectional Studies; Descriptive Statistics; Fisher's Exact Test; Hispanic Americans; Human; Matched Case Control; Neoplasm Staging; Prospective Studies; Questionnaires; Record Review; T-Tests; White Persons

Exploratory Subset Analysis of African Americans From the PointBreak Study: Pemetrexed-Carboplatin-Bevacizumab Followed by Maintenance Pemetrexed-Bevacizumab Versus Paclitaxel-Carboplatin-Bevacizumab Followed by Maintenance Bevacizumab in Patients With Stage IIIB/IV Nonsquamous Non-Small-Cell Lung Cancer. - Reynolds, Craig H; Patel, Jyoti D; Garon, Edward B; Olsen, Mark R; Bonomi, Philip; Govindan, Ramaswamy; Pennella, Eduardo J; Liu, Jingyi; Guba, Susan C; Li, Shi; Spigel, David R; Hermann, Robert C; et al. (Clinical Lung Cancer, 2015)
Introduction: African Americans have a greater incidence of lung cancer than whites and have been underrepresented in clinical trials. In the PointBreak trial (pemetrexed-carboplatin-bevacizumab and maintenance pemetrexed-bevacizumab [PemCBev] vs. paclitaxel-carboplatin-bevacizumab and maintenance bevacizumab [PacCBev]), 10% of the patients were African American. PointBreak had negative findings; PemCBev did not demonstrate superior overall survival (OS).Materials and Methods: PointBreak subgroup efficacy and safety data were retrospectively analyzed: African Americans versus whites for PemCBev; PemCBev versus PacCBev in African Americans; and academic versus community settings for African Americans. Hazard ratios (HRs) and P values were derived from a multivariate Cox proportional hazards model after adjusting for covariates.Results: Of 939 intent-to-treat (ITT) patients, 94 were African American and 805 were white. African-American enrollment was uniform across the study sites (median, 1 African American per site). In the PemCBev arm, OS (HR, 1.125; P = .525), progression-free survival (PFS) (HR, 1.229; P = .251), response (P = .607), and toxicity profiles were similar in African Americans versus whites. For African Americans, OS (HR, 1.375; P = .209), PFS (HR, 0.902; P = .670), response (P = 1.000), and toxicity profiles were similar in the PemCBev versus PacCBev arm. For African Americans, no significant differences were seen in OS (HR, 0.661; P = .191) or PFS (HR, 0.969; P = .915) in academic versus community practice settings.Conclusion: In the PemCBev arm, this exploratory analysis showed no significant differences between African Americans and whites for the efficacy outcomes or toxicity profiles. Consistent with the ITT population negative trial result, for African Americans, the median OS was not superior for either arm. For African Americans, PFS and OS were similar in the academic and community settings. Additional outcomes data for African Americans should be collected in lung cancer studies.

Exploring the financial impact of breast cancer for African American medically underserved women: a qualitative study. - Darby K; Davis C; Likes W; Bell J (Journal of Health Care for the Poor & Underserved, 2009)
In addition to the physical suffering experienced by cancer survivors, there are considerable financial hardships and access barriers to quality health care. The current study explored the financial burden of breast cancer on African American medically underserved women. Four focus groups were conducted in three major cities across Tennessee. Research participants (N=36) were recruited by the staff of cancer support and treatment programs in the area. Findings revealed that participants' lack of insurance or inadequate insurance resulted in missed, delayed, or fewer treatment opportunities. The financial burden of cancer was not limited to the acute treatment phase. The women in the current study reported extreme economic hardship resulting from this disease into long-term survivorship. This exploratory study confirms the importance of providing care across the continuum to address the complex needs of low-income cancer survivors.
Keywords: Black Persons; Breast Neoplasms -- Economics; Medically Underserved Area -- Tennessee; Women; Continuity of Patient Care -- Economics; Exploratory Research; Female; Focus Groups; Funding Source; Health Services Accessibility; Medically Uninsured; Qualitative Studies; Tennessee; Thematic Analysis; Treatment Delay; Human

Exploring the influence of demographic and medical characteristics of African-American and Latinas on enrollment in a behavioral intervention study for breast cancer survivors. - Ashing, Kimlin; Rosales, Monica; Fernandez, Alejandro (Quality of Life Research, 2015)
Purpose: To better understand research participation among hard-to-reach populations, this exploratory investigation examined characteristics of enrollees and non-enrollees from a population-based longitudinal study with African-American and Latina-American breast cancer survivors.Methods: A mixed-method recruitment approach was utilized to enroll participants from cancer registries and community groups who were 1-6 years post-diagnosis.Results: Four hundred and sixty-eight participants agreed to participate constituting an 81% participation rate; 65 and 55% completed Time-1, and both Time-1 and Time-2 assessments, respectively. African-Americans were more likely to agree to participate and complete the T1 assessment (73%) than Latinas (62%) (p < 0.05). Participation was influenced by educational attainment and comorbidities (p < 0.05) for African-Americans. Among Latinas, language proficiency, comorbidities and psychological difficulties (p < 0.01) influenced participation.Conclusions: Our findings suggest that enrollment in research studies may be influenced by complex and multi-dimensional factors stemming from subjects' characteristics including ethnicity, culture, language proficiency and literary, and socioeconomic status, as well as medical characteristics including co-occurring chronic illness and psychological status. Thus, comprehensive, multi-method research studies are urgently needed to better understand and address the challenge of minority recruitment in biomedical research. To increase research participation among cancer survivors, it is imperative to implement focused strategies that will support and encourage individuals' enrollment and continued participation in studies.
Keywords: Black Persons -- Psychosocial Factors; Breast Neoplasms -- Ethnology; Health Behavior -- Ethnology; Hispanic Americans -- Psychosocial Factors; Patient Selection; Survivors -- Psychosocial Factors; Adult; Aged; Breast Neoplasms -- Psychosocial Factors; Breast Neoplasms -- Therapy; Comorbidity; Culture; Female; Human; Logistic Regression; Prospective Studies; Middle Age; Questionnaires; United States

Factors affecting older african american women's decisions to join the PLCO Cancer Screening Trial. - Trauth JM; Jernigan JC; Siminoff LA; Musa D; Neal-Ferguson D; Weissfeld J (Journal of Clinical Oncology, 2005)
PURPOSE: The purpose of this study is to describe the factors associated with the decisions of older African American women to join the PLCO (Prostate, Lung, Colorectal and Ovarian) Cancer Screening Trial when recruited. METHODS: African American women between ages 55 and 74 years who were never diagnosed with a PLCO cancer were eligible for our study. Two methods of recruitment were used. First, mailings were sent to a random sample of women describing the PLCO followed by a telephone call to determine interest in the PLCO. If women were not interested in PLCO but consented to participate in our study, they were interviewed immediately. Second, we followed up with African American women who responded to mass mailings sent out before the start of our study by the Pittsburgh PLCO office. Women completed an interview about their cancer and clinical trial knowledge, attitudes, beliefs, and behaviors. The responses of women who joined the PLCO Trial are contrasted with the responses of women who did not join. RESULTS: Numerous factors were associated with the decision of older African American women to join the PLCO, including perceptions of cancer prevention and detection, the experience of having a loved one with cancer, knowledge of and experience with clinical trials, and beliefs regarding the benefits and risks of clinical trial participation. CONCLUSION: Minority recruitment to cancer clinical trials could be increased by designing interventions focused on individual, organizational, and community needs.
Keywords: Black Persons -- Psychosocial Factors; Decision Making; Health Screening -- Psychosocial Factors; Multicenter Studies; Neoplasms -- Diagnosis; Clinical Trials; Aged; Colorectal Neoplasms -- Diagnosis; Colorectal Neoplasms -- Ethnology; Colorectal Neoplasms -- Prevention and Control; Female; Attitude to Health; Lung Neoplasms -- Diagnosis; Lung Neoplasms -- Ethnology; Lung Neoplasms -- Prevention and Control; Male; Health Screening -- Methods; Middle Age; Neoplasms -- Ethnology; Neoplasms -- Prevention and Control; Ovarian Neoplasms -- Diagnosis; Ovarian Neoplasms -- Ethnology; Ovarian Neoplasms -- Prevention and Control; Pennsylvania; Prostatic Neoplasms -- Diagnosis; Prostatic Neoplasms -- Ethnology; Prostatic Neoplasms -- Prevention and Control; Study Design; Human

Factors affecting participation in a breast cancer risk reduction telephone survey among women from four racial/ethnic groups. - Des Jarlais G; Kaplan CP; Haas JS; Gregorich SE; Pérez-Stable EJ; Kerlikowske K; Des Jarlais, Genevieve; Kaplan, Celia Patricia; Haas, Jennifer S; Gregorich, Steven E; Pérez-Stable, Eliseo J; Kerlikowske, Karla (Preventive Medicine, 2005)
Background: Little is known about the participation of minorities in health behavior research. This manuscript assesses factors associated with participation among women in four racial/ethnic groups. Methods: A total of 2800 Asian/Pacific Islander (API), Black, Latina, and non-Latina White women recruited through the San Francisco Mammography Registry was invited in 2002 and 2003 to participate in a telephone survey about breast cancer prevention. Results: Minorities participated at lower rates (49% for APIs, 60% for Latinas, and 64% for Blacks) than Whites (77%). Increased participation was associated with younger age for Latinas (OR = 1.90, 95% CI 1.05-3.44) and Whites (OR = 1.77, CI 1.08-2.91), and with a family history of breast cancer for APIs (OR = 2.09, CI 1.24-3.52). Decreased participation was associated with having less than a high school education for APIs (OR = 0.47, CI 0.26-0.86), Blacks (OR = 0.29, CI 0.11-0.78), and Latinas (OR = 0.51, CI 0.28-0.94). Conclusions: Results suggest minorities' participation in health behavior research does not match Whites' and should be enhanced.
Keywords: Breast Neoplasms -- Risk Factors; Race Factors; Research Subject Recruitment; Adult; Age Factors; Aged; Asians; Black Persons; California; Confidence Intervals; Data Analysis Software; Data Analysis, Statistical; Descriptive Statistics; Educational Status; Family History; Female; Hispanic Americans; Logistic Regression; Middle Age; Odds Ratio; P-Value; Self Report; Survey Research; White Persons; Funding Source; Human

Factors associated with attendance in a voluntary nutrition education program...including commentary by Glanz K - Damron D; Langenberg P; Anliker J; Ballesteros M; Feldman R; Havas S; Damron, D; Langenberg, P; Anliker, J; Ballesteros, M; Feldman, R; Havas, S (American Journal of Health Promotion, 1999)
Purpose: This paper examines factors associated with attendance in a National Cancer Institute-funded randomized trial of nutrition education to increase fruit and vegetable consumption among women served by the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC).Setting: The study took place at 16 WIC sites in Maryland.Subjects: The participants were 1528 women who were enrolled in WIC or who had children enrolled in WIC, were > or = 18 years of age, and planned to continue enrollment at that WIC site for at least 6 months (68% of eligible women approached agreed to participate).Intervention: Women received personal invitations, letters, and telephone reminders from peer educators encouraging their attendance at three bimonthly nutrition sessions.Measures: Demographic data were collected in a baseline survey. Attendance data and telephone and address changes were also collected. The postintervention survey included a question regarding reasons for nonattendance. Focus groups were also held to ascertain reasons for attendance or nonattendance. Chi-square tests of trend and multiple logistic regression, adjusted for within-site correlation, were used in statistical analyses.Results: Fifty-four percent of enrollees attended at least one session. Multiple logistic regression analysis showed increased odds of attending with higher age, breast-feeding, and/or knowledge of the recommendation to eat five or more servings of fruits and vegetables daily. There were decreased odds of attending for pregnant women who already had children. There were nonsignificant trends toward decreased attendance among unmarried women compared with married women and among blacks compared with nonblacks. Reasons given for nonattendance included withdrawal from WIC, moving, conflicting activities, negative feelings about nutrition education, and lack of transportation or child care.Conclusions: The results suggest that numerous barriers hinder participation in nutrition programs aimed at low-income women. These barriers should be considered by health care professionals when planning intervention programs. Overcoming these barriers presents a major challenge.
Keywords: Nutrition Education -- In Adulthood; Infant Nutrition; Child Nutrition; Nutrition Education -- In Infancy and Childhood; Consumer Participation; Child; Funding Source; Focus Groups; Fruit; Vegetables; Survey Research; Questionnaires; Pretest-Posttest Design; Mantel-Haenszel Test; Multiple Logistic Regression; P-Value; Odds Ratio; Confidence Intervals; Data Analysis, Statistical; Data Analysis Software; Prospective Studies; Adolescence; Adult; Middle Age; Aged; Female; Human

Factors associated with breast cancer clinical trials participation and enrollment at a large academic medical center. - Simon MS; Du W; Flaherty L; Philip PA; Lorusso P; Miree C; Smith D; Brown DR (Journal of Clinical Oncology, 2004)
PURPOSE: The practice patterns of medical oncologists at a large National Cancer Institute Comprehensive Cancer Center in Detroit, MI were evaluated to better understand factors associated with accrual to breast cancer clinical trials.PATIENTS AND METHODS: From 1996 to 1997, physicians completed surveys on 319 of 344 newly evaluated female breast cancer patients. The 19-item survey included clinical data, whether patients were offered clinical trial (CT) participation and enrollment, and when applicable, reasons why they were not. Multivariate analyses using logistic regression were performed to evaluate predictors of an offer and enrollment.RESULTS: The patients were 57% white, 32% black, and 11% other/unknown race. One hundred six (33%) were offered participation and 36 (34%) were enrolled. In multivariate analysis, CTs were less likely offered to older women (mean age, 52 years for those offered v 57 years for those not offered; P = .0005) and black women (21% of blacks offered v 42% of whites; P = .0009). Women with stage 1 disease, poor performance status, and those who were previously diagnosed were also less likely to be offered trials. None of these factors were significant predictors of enrollment. Women were not offered trials because of ineligibility (57%), lack of available trials (41%), and noncompliance (2%). Reasons for failed enrollment included patient refusal (88%) and failed eligibility (12%).CONCLUSION: It is important for cooperative groups to design studies that will accommodate a broader spectrum of patients. Further work is needed to assess ways to improve communication about breast cancer CT participation to all eligible women.
Keywords: Breast Neoplasms; Clinical Trials; Health Services Accessibility; Minority Groups; Research Subject Recruitment; Academic Medical Centers; Surveys; Data Analysis Software; T-Tests; Fisher's Exact Test; Logistic Regression; Questionnaires; Multiple Logistic Regression; Middle Age; Female; Funding Source; Human

Factors predicting the use of complementary therapies in a multi-ethnic sample of early-stage breast cancer patients. - Alferi SM; Antoni MH; Ironson G; Kilbourn KM; Carver CS (Journal of the American Medical Women's Association, 2001)
Objectives: to examine predictors of use of complementary therapies reported by women who had also received standard medical treatment for early-stage breast cancer. Methods: A volunteer sample of 231 black, Hispanic, and non-Hispanic white patients with early-stage breast cancer (diagnosed within the preceding year) reported their use of complementary therapies. We examined predictors of the use of each therapy from among a set of demographic and quality of life measures. Results: Most women reported using 1 complementary therapy or more, most commonly psychotherapy, support groups, meditation, and spiritual healing. Use of psychotherapy related to age, education, and elevated distress. Use of other complementary therapies was not related to distress. More black than Hispanic or nonHispanic white patients used herbal therapies and spiritual healing. Use of complementary therapies did not relate to expectation of recurrence, dissatisfaction with medical care, or (among relevant patients) concerns about the consequences of chemotherapy. Conclusions: Use of healing therapies that do not replace medical treatment should be viewed as attempts to increase potential benefit and not as signs of distress or dissatisfaction. Use of complementary therapies also varies across racial and ethnic groups.
Keywords: Breast Neoplasms -- Therapy; Combined Modality Therapy; Alternative Therapies; Attitude to Illness; Black Persons; Hispanic Americans; White Persons; Demography; Adult; Middle Age; Aged; Chi Square Test; T-Tests; Logistic Regression; Center for Epidemiological Studies Depression Scale; Psychological Tests; Psychosocial Adjustment to Illness Scale; Research Subject Recruitment; Attitude Measures; Scales; Descriptive Statistics; Religion and Religions; Time Factors; Funding Source; Human

Faith among low-income, African American/Black men treated for prostate cancer. - Maliski, Sally L; Connor, Sarah E; Williams, Lindsay; Litwin, Mark S (Cancer Nursing, 2010)
BACKGROUND: Understanding how low-income, uninsured African American/black men use faith to cope with prostate cancer provides a foundation for the design of culturally appropriate interventions to assist underserved men cope with the disease and its treatment. Previous studies have shown spirituality to be a factor related to health and quality of life, but the process by which faith, as a promoter of action, supports coping merits exploration. OBJECTIVE: Our purpose was to describe the use of faith by low-income, uninsured African American/black men in coping with prostate cancer and its treatment and adverse effects. METHODS: We analyzed data from a qualitative study that used in-depth individual interviews involving 18 African American men ranging in ages from 53 to 81 years. Our analysis used grounded theory techniques. RESULTS: Faith was used by African American men to overcome fear and shock engendered by their initial perceptions of cancer. Faith was placed in God, health care providers, self, and family. Men came to see their prostate cancer experience a new beginning that was achieved through purposeful acceptance or resignation. CONCLUSIONS: Faith was a motivator of and source for action. Faith empowered men to be active participants in their treatment and incorporate treatment outcomes into their lives meaningfully. IMPLICATION: By understanding faith as a source of empowerment for active participation in care, oncology nurses can use men's faith to facilitate reframing of cancer perceptions and to acknowledge the role of men's higher being as part of the team. Studies are needed to determine if this model is relevant across various beliefs and cultures.
Keywords: Black Persons -- Psychosocial Factors -- California; Cancer Patients -- Psychosocial Factors; Coping; Poverty; Spirituality; Aged; Aged, 80 and Over; Attitude to Illness -- Evaluation; Audiorecording; California; Culture; Descriptive Research; Empowerment; Funding Source; Grounded Theory; Human; Male; Medically Uninsured; Middle Age; Patient Attitudes -- Evaluation; Research Subject Recruitment; Semi-Structured Interview; Socioeconomic Factors; Thematic Analysis

Familial pancreatic cancer in South Louisiana. - Price TF; Payne RL; Oberleitner MG (Cancer Nursing, 1996)
Previous researchers have found high mortality and incidence rates for pancreatic cancer in the Acadiana region of southern Louisiana. While lifestyle practices such as pork and alcohol consumption and a familial trend have been linked to pancreatic cancer, cigarette smoking is the only established risk factor for pancreatic cancer. Therefore, a retrospective, descriptive study was conducted to explore lifestyle risk factors and the familial trend in pancreatic cancer. The Familial Pancreatic Cancer Questionnaire (FPCQ) was used to collect data on demographics, tobacco and alcohol use, dietary history, and medical history. A surrogate respondent (family member) for 3I pancreatic cancer subjects completed the FPCQ. Race and gender specific incidence rates (IR) for pancreatic cancer in Acadiana were calculated. Results showed that mean IRs for pancreatic cancer for Caucasian and African-American males and females were higher than national SEER rates. Pancreatic cancer and lung cancer were the most frequently reported cancers among subjects' first degree relatives. The majority (65%) of the subjects smoked. A positive family history for pancreatic cancer was found in this study with five (16%) of the pancreatic cancer subjects having one or more first degree relatives with pancreatic cancer. This percent is twice that found by previous researchers.
Keywords: Pancreatic Neoplasms -- Epidemiology; Ethnic Groups -- Louisiana; Family Health; Louisiana; Retrospective Design; Descriptive Research; Race Factors; Sex Factors; Descriptive Statistics; Risk Factors; Questionnaires; Content Validity; Research Subject Recruitment; Data Analysis Software; Research Instruments; Demography; Health Behavior; Male; Female; Human

Fear of Cancer Recurrence in Young Breast Cancer Survivors: Impact on Surveillance Behaviors. - Pattison, Kelley Hempsall (Fear of Cancer Recurrence in Young Breast Cancer Survivors: Impact on Surveillance Behaviors, 2014)
Introduction: Fear of recurrence (FOR) has been studied in various populations of patients with cancer e.g. colon, prostate, and breast. Breast cancer survivors are often faced with the lingering fear that the cancer may reoccur. It is estimated over 232,000 women diagnosed with breast cancer in 2014 FOR has the possibility to impact the lives of thousands of women. Yet, little is known about FOR in women diagnosed with breast cancer at a young age and are young breast cancer survivors (YBCS). These cancer survivors need additional support, as the probability they will develop another cancer is high.Purpose: The purposes of this study were to 1) describe FOR in a large, statewide sample of YBCS 2) to explore predictors of FOR and 3) to determine if FOR is a mediator for breast cancer surveillance, namely mammograms and clinical breast exams (CBE).Methods: This secondary data analysis examines baseline data collected for an efficacy trial, aiming to increase breast cancer surveillance and use of cancer genetic services among YBCS and their high risk family members. Fear of recurrence was examined in 863 YBCS identified and recruited through the Michigan cancer registry. Participants completed a survey including instruments that measured FOR, quality of life (mental and physical), self-efficacy in managing breast cancer, perceived breast cancer risk, knowledge of breast cancer risk factors, family support, and current breast cancer surveillance practices.Findings: Results of this study suggest predictors of FOR in young breast cancer survivors include African American race, lower level of education, belief that cancer development is by chance, and increased level of anxiety. The strongest predictor of FOR was low level of self-efficacy in managing breast cancer. Being negative for the BRCA1 genetic marker was found not to be associated with FOR in this population. FOR did not mediate surveillance mammograms or clinical breast exams.Conclusion: Knowing what predicts young breast cancer survivors to experience FOR is important in lessening FOR. Employing screening measures to determine patients at risk for experiencing FOR may lessen this problem.
Keywords: Breast Neoplasms -- Psychosocial Factors; Cancer Survivors -- Psychosocial Factors; Health Behavior; Neoplasm Recurrence, Local -- Psychosocial Factors; Breast Examination; Clinical Trials; Fear; Human; Mammography; Michigan; Quality of Life; Secondary Analysis; Self-Efficacy

Feasibility and clinical impact of sharing patient-reported symptom toxicities and performance status with clinical investigators during a phase 2 cancer treatment trial. - Basch, Ethan; Wood, William A.; Schrag, Deborah; Sima, Camelia S.; Shaw, Mary; Rogak, Lauren J.; Kris, Mark G.; Shouery, Marwan; Bennett, Antonia; Atkinson, Thomas; Pietanza, M. Catherine (Clinical Trials, 2016)
Background: Clinicians can miss up to half of patients’ symptomatic toxicities in cancer clinical trials and routine practice. Although patient-reported outcome questionnaires have been developed to capture this information, it is unclear whether clinicians will make use of patient-reported outcomes to inform their own toxicity documentation, or to prompt symptom management activities. Methods: 44 lung cancer patients that participated in a phase 2 treatment trial self-reported 13 symptomatic toxicities derived from the National Cancer Institute’s Common Terminology Criteria for Adverse Events and Karnofsky Performance Status via tablet computers in waiting areas immediately preceding scheduled visits. During visits, clinicians viewed patients’ self-reported toxicity and performance status ratings on a computer interface and could agree or disagree/reassign grades (“shared” reporting). Agreement of clinicians with patient-reported grades was tabulated, and compared using weighted kappa statistics. Clinical actions in response to patient-reported severe (grade 3/4) toxicities were measured (e.g. treatment discontinuation, dose reduction, supportive medications). For comparison, 45 non-trial patients with lung cancer being treated in the same clinic by the same physicians were simultaneously enrolled in a parallel cohort study in which patients also self-reported toxicity grades but reports were not shared with clinicians (“non-shared” reporting). Results: Toxicities and performance status were reported by patients and reviewed by clinicians at (780/782) 99.7% of study visits in the phase 2 trial which used “shared” reporting. Clinicians agreed with patients 93% of the time with kappas 0.82–0.92. Clinical actions were taken in response to 67% of severe patient-reported toxicities. In the “non-shared” reporting comparison group, clinicians agreed with patients 56% of the time with kappas 0.04–0.48 (significantly worse than shared reporting for all symptoms), and clinical actions were taken in response to 44% of severe patient-reported toxicities. Conclusion: Clinicians will frequently agree with patient-reported symptoms and performance status, and will use this information to guide documentation and symptom management. (ClinicalTrials.gov: NCT00807573).
Keywords: Adverse Drug Event; Cancer Patients; Randomized Controlled Trials; Access to Information; Human; Lung Neoplasms; Self Report; Treatment Outcomes; Antineoplastic Agents -- Adverse Effects; Kappa Statistic; Female; Male; Adult; Middle Age; Aged; Aged, 80 and Over; White Persons; Black Persons; Pilot Studies; Funding Source

Feasibility Test of a Community-Relevant Intervention Designed to Promote African American Participation in Translational, Breast Cancer Disparities Research: Know About Health Options for Women (Know HOW). - Yeary, Karen Hye-cheon Kim; Moore, Page; Turner, Jerome; Dawson, Leah; Heo, Seongkum; Greene, Paul (Journal of Cancer Education, 2018)
There are marked racial differences in breast cancer, the second leading cause of death among US women. Understanding the causes of these differences is essential to eliminate breast cancer inequities. More prevalent in African American than in Caucasian women, metabolic syndrome has been associated with breast cancer outcomes. Further research is needed to understand metabolic syndrome's role in breast cancer disparities, thus novel strategies to increase minority participation in research are important. We embedded two approaches (comprehensive, focused) to increase African American participation in breast cancer research in a state-wide service program and pilot tested both approaches in rural African American women. We conducted three comprehensive and three focused outreach programs (n = 48) and assessed research participation through consent and actual provision of data for four types of data: survey, anthropometric, blood, and mammography records. The majority of participants provided written consent for all data collection procedures (96 % survey; 92 % anthropometric; 94 %, blood; 100 % mammography). There were no between group differences in consent rates. There was variation in the overall proportion of participants who provided data (96 % survey; 92 % anthropometric; 73 % blood; 40 % mammography). Women in the comprehensive approach were less likely to return for a scheduled mammogram than women in the focused approach (19 % vs 64 %, p = 0.0236). Both outreach programs promoted African American engagement in research. Differences in the provision of data by type may have been due to participant burden (i.e., time required to provide data). Study designs that embed research in service programs have promise to increase minority research participation.
Keywords: Attitude to Health -- Ethnology; Black Persons; Breast Neoplasms -- Ethnology; Health Status Disparities; Patient Selection; Mammography -- Statistics and Numerical Data; Female; Health Promotion; Rural Population; Adult; Research, Medical; Pilot Studies; United States; Minority Groups; Middle Age; Aged

Feasibility, acceptability, and preliminary efficacy of a technology-assisted psychosocial intervention for racially diverse men with advanced prostate cancer. - Yanez, Betina; McGinty, Heather L.; Mohr, David C.; Begale, Mark J.; Dahn, Jason R.; Flury, Sarah C.; Perry, Kent T.; Penedo, Frank J. (Cancer (0008543X), 2015)
Background: The utility of psychosocial interventions in reducing symptom burden and improving health-related quality of life (HRQOL) for men with localized prostate cancer has been demonstrated. However, studies have yet to demonstrate the efficacy of interventions in advanced prostate cancer (APC). This study examined the feasibility, acceptability, and preliminary efficacy of a technology-assisted, 10-week, group-based psychosocial intervention for diverse men with APC.Methods: The participants were 74 men (mean age, 68.84 years; non-Hispanic white, 57%; black, 40.5%) who were randomized to a cognitive-behavioral stress management (CBSM) treatment or health promotion (HP) attention-control condition. The participants were assessed at the baseline, weekly throughout the 10-week program, and 6 months after the baseline. Outcomes were assessed with the Patient-Reported Outcomes Measurement Information System along with established measures of HRQOL, CBSM intervention targets (eg, relaxation skills), and patient-reported acceptability.Results: Feasibility was demonstrated through good retention rates (>85%) and acceptable average attendance rates (>70%), and acceptability was demonstrated through very favorable weekly session evaluations (mean score, 4/5) and exit surveys (mean score, 3.6/4). Men randomized to the CBSM condition reported significant reductions (P < .05) in depressive symptoms and improvements in relaxation self-efficacy (P < .05) at the 6-month follow-up. CBSM participants reported trends for improvement in distress and functional well-being (P < .08) in comparison with those in the HP condition. Effect sizes ranged from medium (0.54) to large (1.87) and, in some instances, were clinically meaningful.Conclusions: Technology-based CBSM interventions among diverse men with APC may be feasible, acceptable, and efficacious.
Keywords: Stress, Psychological -- Therapy; Therapy, Computer Assisted -- Methods; Quality of Life; Cognitive Therapy -- Methods; Patient Attitudes; Depression -- Therapy; Prostatic Neoplasms -- Psychosocial Factors; Middle Age; Prostatic Neoplasms -- Pathology; Pilot Studies; Stress, Psychological -- Psychosocial Factors; Aged; White Persons -- Psychosocial Factors; Neoplasm Staging; Black Persons -- Psychosocial Factors; Self-Efficacy; Depression -- Psychosocial Factors; Male; Aged, 80 and Over; Patient Satisfaction; Treatment Outcomes; Human; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Scales; Funding Source; Questionnaires

Follow-up approaches to a health literacy intervention to increase colorectal cancer screening in rural community clinics: A randomized controlled trial. - Arnold, Connie L.; Rademaker, Alfred W.; Morris, James D.; Ferguson, Laurie Anne; Wiltz, Gary; Davis, Terry C. (Cancer (0008543X), 2019)
Background: Significant disparities exist in colorectal cancer (CRC) screening rates among those of low socioeconomic status, with fewer years of education, lacking health insurance, or living in rural areas.Methods: A randomized controlled trial was conducted to compare the effectiveness of 2 follow-up approaches to a health literacy intervention to improve CRC screening: automated telephone call or personal call. Patients aged 50 to 75 years residing in 4 rural community clinics in Louisiana were given a structured interview that assessed demographic, health literacy and CRC screening barriers, knowledge, and attitudes. All were given health literacy-informed CRC education, a patient-friendly CRC screening pamphlet, simplified fecal immunochemical test (FIT) instructions, and a FIT kit, and a "teach-back" method was used to confirm understanding. Patients were randomized to 1 of 2 telephone follow-up arms. If they did not mail their FIT kit within 4 weeks, they received a reminder call and were called again at 8 weeks if the test still was not received.Results: A total of 620 patients were enrolled. Approximately 55% were female, 66% were African American, and 40% had limited literacy. The overall FIT completion rate was 68%: 69.2% in the automated telephone call arm and 67% in the personal call arm. Greater than one-half of the patients (range, 58%-60%) returned the FIT kit without receiving a telephone call. There was no difference noted with regard to the effectiveness of the follow-up calls; each increased the return rate by 9%.Conclusions: Providing FIT kits and literacy-appropriate education at regularly scheduled clinic visits with a follow-up telephone call when needed was found to increase CRC screening among low-income, rural patients. The lower cost automated call was just as effective as the personal call.
Keywords: Early Detection of Cancer; Colorectal Neoplasms -- Diagnosis; Rural Population; Health Screening -- Methods; Human; Male; Feces; Prospective Studies; Louisiana; Colorectal Neoplasms -- Blood; Information Literacy; Health Education -- Statistics and Numerical Data; Middle Age; Ambulatory Care Facilities; Female; Colorectal Neoplasms -- Epidemiology; Telephone; Aged; Colorectal Neoplasms -- Pathology; Occult Blood; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Personal Resource Questionnaire; Questionnaires

Genetic Testing and Surveillance of Young Breast Cancer Survivors and Blood Relatives: A Cluster Randomized Trial. - Katapodi, Maria C.; Ming, Chang; Northouse, Laurel L.; Duffy, Sonia A.; Duquette, Debra; Mendelsohn-Victor, Kari E.; Milliron, Kara J.; Merajver, Sofia D.; Dinov, Ivo D.; Janz, Nancy K. (Cancers, 2020)
Simple Summary: Identifying breast cancer patients with pathogenic mutations that run in their families may improve the follow-up care they receive and breast cancer screening of their close relatives. In this study we identified breast cancer patients with high chances of having a pathogenic mutation and their close female relatives. We developed and tested two different kinds of letters and booklets that presented either personalized or generic information about screening and breast cancer that runs in families, and we encouraged participants to seek genetic evaluation. We found that both types of letters worked equally well for breast cancer patients and for relatives, regardless of their racial background. The personalized letters had slightly better outcomes. Some breast cancer patients and their relatives used genetic services and improved their screening practices. Black patients and their relatives were more satisfied with the booklets than other participants. We compared a tailored and a targeted intervention designed to increase genetic testing, clinical breast exam (CBE), and mammography in young breast cancer survivors (YBCS) (diagnosed <45 years old) and their blood relatives. A two-arm cluster randomized trial recruited a random sample of YBCS from the Michigan cancer registry and up to two of their blood relatives. Participants were stratified according to race and randomly assigned as family units to the tailored (n = 637) or the targeted (n = 595) intervention. Approximately 40% of participants were Black. Based on intention-to-treat analyses, YBCS in the tailored arm reported higher self-efficacy for genetic services (p = 0.0205) at 8-months follow-up. Genetic testing increased approximately 5% for YBCS in the tailored and the targeted arm (p ≤ 0.001; p < 0.001) and for Black and White/Other YBCS (p < 0.001; p < 0.001). CBEs and mammograms increased significantly in both arms, 5% for YBCS and 10% for relatives and were similar for Blacks and White/Others. YBCS and relatives needing less support from providers reported significantly higher self-efficacy and intention for genetic testing and surveillance. Black participants reported significantly higher satisfaction and acceptability. Effects of these two low-resource interventions were comparable to previous studies. Materials are suitable for Black women at risk for hereditary breast/ovarian cancer (HBOC).
Keywords: Genetic Screening; Disease Surveillance; Breast Neoplasms -- Familial and Genetic; Cancer Survivors; Extended Family; Human; Mammography; Randomized Controlled Trials; Random Sample; Black Persons; Cluster Analysis; Sex Factors

Geographic recruitment of breast cancer survivors into community-based exercise interventions. - Rogerino A; Grant LL; Wilcox H III; Schmitz KH (Medicine & Science in Sports & Exercise, 2009)
PURPOSE:: There is increased interest in developing and disseminating health behavior interventions for cancer survivors. Challenges in these efforts include participant burden in traveling to central intervention sites and sustainability. The purpose of this article is to report various methods used to recruit breast cancer survivors into an exercise intervention that attempts to address both of these challenges. METHODS:: Letters were mailed within specific zip codes near community-based intervention sites in cooperation with state cancer registries. Additional recruitment methods included flyers at breast care clinics and support groups, mass media, and conferences. RESULTS:: Of the 3200 women who responded, 82% (n = 2625) identified having heard about the study through state or hospital registry and 8% (n = 243) through print and broadcast media. Thirty-five percent (n = 103) of randomized women self-identified as having a minority racial background and 31.9% (n = 94) self-identified as African American. Comparisons of participant age and racial distribution to state cancer registries indicate similar age distribution but greater racial diversity among participants. CONCLUSION:: These results support the use of population-based cancer registries to recruit survivors into community-based interventions and clinical trials.
Keywords: Breast Neoplasms -- Complications; Cancer Survivors; Community Programs; Exercise; Neoplasm Recurrence, Local -- Prevention and Control; Female; Funding Source; Health Promotion; Mail; Pamphlets; Patient Selection; Registries, Disease; Human

"Hard to reach, but not out of reach": Barriers and facilitators to recruiting Black African and Black Caribbean men with prostate cancer and their partners into qualitative research. - Bamidele, Olufikayo O.; E. McGarvey, Helen; Lagan, Briege M.; Chinegwundoh, Frank; Ali, Nasreen; McCaughan, Eilis (European Journal of Cancer Care, 2019)
Access and recruitment barriers may have contributed to the underrepresentation of Black African/Caribbean men and their partners in current psychosocial research related to prostate cancer survivors. Whilst some studies have explored recruitment barriers and facilitators from participants' perspectives, little is known from researchers' point of view. This paper aimed to address this gap in the literature. Recruitment strategies included the following: cancer support groups, researchers' networks, media advertisement, religious organisations, National Health Service hospitals and snowball sampling. Thirty‐six eligible participants (men = 25, partners = 11) were recruited into the study. Recruitment barriers comprised of gate‐keeping and advertisement issues and the stigma associated with prostate cancer disclosure. Facilitators which aided recruitment included collaborating with National Health Service hospitals, snowball sampling, flexible data collection, building rapport with participants to gain their trust and researcher's attributes. Findings highlight that "hard to reach" Black African/Caribbean populations may be more accessible if researchers adopt flexible but strategic and culturally sensitive recruitment approaches. Such approaches should consider perceptions of stigma associated with prostate cancer within these communities and the influence gatekeepers can have in controlling access to potential participants. Increased engagement with healthcare professionals and gatekeepers could facilitate better access to Black African/Caribbean populations so that their voices can be heard and their specific needs addressed within the healthcare agenda.
Keywords: Health Services Accessibility; Prostatic Neoplasms; Cancer Survivors; Research Subject Recruitment; Spouses; Black Persons; Human; Support Groups; Qualitative Studies; Social Media; Advertising; Religion and Religions -- Organizations; National Health Programs; Snowball Sample; Male; Female; Collaboration; Grounded Theory; Convenience Sample; Internet -- Utilization

Health Beliefs of African American Women on Breast Self-Exam. - Registe, Marlaine; Porterfield, Susan Padham (Journal for Nurse Practitioners, 2012)
Abstract: Purpose: Investigate the relationship between African American women''s health beliefs in regard to breast cancer screening behaviors. Data sources: A sample of 131 African American women, age 20–65, from a family practice clinic and 3 rural churches in Southeast. Conclusions: One-hundred and nine of the participants reported practicing breast self-exam (BSE) within the past 12 months. However, 21 women had never practiced BSE. Fear of not doing it correctly was a main barrier. Implication for practice: Steps should be taken to increase confidence and resolve barriers of African American women through the development of culturally sensitive educational training on BSE and cancer prevention.
Keywords: Health Beliefs; Black Persons -- United States; Breast Self-Examination; Human; United States; Health Beliefs -- Evaluation; Female; Adult; Middle Age; Southeastern United States; Descriptive Research; Correlational Studies; Health Knowledge -- Evaluation; Research Subject Recruitment; Convenience Sample; Scales; Summated Rating Scaling; Correlation Coefficient

Health disadvantages in colorectal cancer screening among African Americans: considering the cultural context of narrative health promotion. - Robillard AG; Larkey L (Journal of Health Care for the Poor & Underserved, 2009)
African Americans are more likely than any other racial or ethnic group to develop colorectal cancer (CRC) and to die as a result. Factors such as age, family history, income, knowledge, attitudes and beliefs regarding screening are important predictors of risk, and multiple factors may contribute to poor CRC outcomes for African Americans. Although screening is not the only factor associated with CRC outcomes, it may be one of the more important and modifiable risk factors for African Americans. Few programs have utilized narrative approaches to promote cancer screening among African Americans. None have focused on CRC screening. The purpose of this discussion is to review factors associated with CRC incidence, late detection and mortality among African Americans with emphasis on screening to improve CRC-related outcomes, and to discuss narrative health promotion as a culturally appropriate means for eliminating the disparities in CRC-related outcomes between African Americans and other racial/ethnic groups.
Keywords: Black Persons; Cancer Screening; Colorectal Neoplasms -- Prevention and Control; Colorectal Neoplasms -- Risk Factors; American Cancer Society; Clinical Trials; Colorectal Neoplasms -- Epidemiology; Culture; Family History; Female; Health Beliefs; Health Knowledge; Health Promotion; Incidence; Male; Morbidity; Narratives; Nutrition; Physical Activity; Practice Guidelines; Research Subject Recruitment; Socioeconomic Factors

Health parties for African American study recruitment. - Sadler GR; York C; Madlensky L; Gibson K; Wasserman L; Rosenthal E; Barbier L; Newman VA; Tso C (Journal of Cancer Education, 2006)
Innovative strategies are needed to increase minorities' research participation. Using existing social networks within the African American community, 'home health parties' were tested as a way to recruit African American women to a breast cancer control study. Parties included social, educational, and recruitment components. All women attending health parties consented, completed a survey, and received the study's preliminary breast cancer risk assessment. There were no differences in rates of participation for subsequent study components between women recruited via parties versus other methods. Health parties are viable recruitment strategies, reduce barriers to participation, provide a supportive environment, and are relatively inexpensive.
Keywords: Black Persons; Research Subject Recruitment -- Methods; Research Subjects; Social Networks; Adult; Asians; Breast Examination; Breast Neoplasms -- Prevention and Control; California; Cancer Screening; Chi Square Test; Clinical Assessment Tools; Comparative Studies; Culture; Data Analysis Software; Descriptive Statistics; Educational Status; Female; Funding Source; Genetic Counseling; Health Education; Hispanic Americans; Middle Age; Nutrition Education; Pilot Studies; Risk Assessment; Surveys; White Persons; Human

High Baseline Anal HPV and Abnormal Anal Cytology in a Phase 3 Trial of the Quadrivalent HPV Vaccine in HIV-infected individuals over 26 years old: ACTG 5298. - Cranston, Ross D.; Cespedes, Michelle S.; Paczuski, Pawel; Ming Yang; Coombs, Robert W.; Dragavon, Joan; Saah, Alfred; Godfrey, Catherine; Webster-Cyriaque, Jennifer Y.; Chiao, Elizabeth Y.; Bastow, Barbara; Wilkin, Timothy; et al. (Sexually Transmitted Diseases, 2018)
Background: The quadrivalent human papillomavirus (HPV) vaccine (qHPV; types 6, 11, 16, 18) is indicated for men and women 9-26 years to prevent HPV associated anogenital high grade squamous intraepithelial lesions (HSIL) and cancer. ACTG 5298 was a randomized placebo controlled Phase 3 study in HIV-infected men who have sex with men (MSM), and women of qHPV to prevent persistent anal HPV infection. Baseline data is presented here.Methods: HIV-infected MSM, and women ≥ 27 years without previous anogenital or oral cancer were enrolled. Baseline anal cytology, high resolution anoscopy and collection of anal, oral, and vaginal specimens for HPV genotyping were performed and acceptability assessed.Results: 575 participants were enrolled (82% male and 18% female). Median age was 47 years. Race/ethnicity was 46% White, 31% Black, and 20% Hispanic. Plasma HIV-1 RNA was <50 copies/mL in 83% and median CD4 T count was 602 cells/μL. Abnormal anal cytology was detected in 62%, with corresponding HSIL on biopsy (bHSIL) in 33%. Anal HPV 6, 11, 16 and 18 were detected in 25%, 13%, 32%, and 18% of participants respectively. Prevalence of 0, 1, 2, 3, and 4 qHPV types was 40%, 38%, 17%, 4%, and 1%, respectively. Oral infection with ≥ 1 qHPV type was detected in 10% of participants. Study procedures were generally acceptable.Conclusions: At study baseline, there was a high prevalence of abnormal anal cytology, bHSIL, and HPV infection. Sixty percent of participants had anal infection with preventable qHPV types.

How African American men decide whether or not to get prostate cancer screening. - Jones RA; Steeves R; Williams I (Cancer Nursing, 2009)
Prostate cancer is the most commonly diagnosed cancer in men in the United States and affects African Americans disproportionately when compared to other ethnic groups. There are unclear reasons for this disparity, but several factors may include race, nutrition, family history of cancer, and screening. With early detection of prostate cancer, survival is much better; thus, screening may be helpful, especially for high-risk individuals. Prostate cancer screening continues to be controversial. A paucity of data exists on what prostate cancer screening means to African Americans, particularly in rural areas, and how they make the decision whether or not to undergo prostate cancer screening. This study interviewed 17 African American men to explore how and when they decided about prostate cancer screening. Most of the men (n = 9) said that they had prostate cancer screening. Three themes emerged from the data: (1) these men had information on prostate cancer; (2) family and friends played an important role in the men's decision-making process; and (3) for screening, it was necessary for the men to have a trusting relationship with their healthcare provider. These findings confirm that the decision-making process is not a simple process. The study's results can help healthcare providers understand some of the important decision-making factors in prostate cancer screening for African American men.
Keywords: Black Persons -- United States; Cancer Screening; Decision Making; Prostatic Neoplasms -- Prevention and Control; Adult; Aged; Audiorecording; Constant Comparative Method; Convenience Sample; Descriptive Statistics; Family Role; Field Notes; Funding Source; Health Education; Male; Middle Age; Patient Attitudes -- Evaluation; Phenomenological Research; Professional-Patient Relations; Research Subject Recruitment; Rural Areas; Semi-Structured Interview; Thematic Analysis; Trust; United States; Human

Identifying problems faced by spouses and partners of patients with prostate cancer. - Hawes SM; Malcarne VL; Ko CM; Sadler GR; Banthia R; Sherman SA; Varni JW; Schmidt J (Oncology Nursing Forum, 2006)
PURPOSE/OBJECTIVES: To describe problems chosen as targets of problem-solving therapy by spouses and partners of patients with prostate cancer. DESIGN: Descriptive, cross-sectional. SETTING: Spouses' and partners' homes. SAMPLE: Spouses and partners (N = 66) aged 32-79 years (mean = 60 years). The sample was predominantly Caucasian (82%) and African American (8%). METHODS: As part of a randomized clinical trial, women received problem-solving therapy to help manage issues related to their husbands' or partners' prostate cancer. The issues they chose to address during therapy and the categorization of the issues fell into four groups: treatment and side-effect issues, patient issues, family issues, and spouse issues. Scores on the Social Problem-Solving Inventory-Revised, which measures everyday problem-solving skills, and the Profile of Mood States, which measures mood disturbance, were contrasted with the problems women chose to address. MAIN RESEARCH VARIABLES: Problems faced by spouses and partners of patients with prostate cancer. FINDINGS: The most frequently reported categories were spouse issues (e.g., women's emotional wellness, balancing their medical concerns with their husbands' condition) and patient issues (e.g., men's lack of communication, fear, or depression). CONCLUSIONS: Findings of this study alert nurses to a variety of key problem areas for spouses and partners of patients with prostate cancer. IMPLICATIONS FOR NURSING: Spouses and partners play a critical role when their loved ones have cancer. Understanding the problems spouses and partners face can help nurses design optimal supportive care interventions.
Keywords: Problem Identification; Prostatic Neoplasms; Spouses -- Psychosocial Factors; Adult; Aged; California; Chi Square Test; Coding; Communication; Cross Sectional Studies; Decision Making; Descriptive Research; Descriptive Statistics; Experimental Studies; Female; Funding Source; Interrater Reliability; Kappa Statistic; Male; Middle Age; Multivariate Analysis of Variance; Nonparametric Statistics; Problem Solving -- Education; Psychological Tests; Psychological Well-Being; Questionnaires; Record Review; Research Subject Recruitment; Secondary Analysis; Summated Rating Scaling; Thematic Analysis; Human

Impact of pretest on posttest knowledge scores with a Solomon Four research design. - Weinrich SP; Seger R; Curtsinger T; Pumphrey G; NeSmith EG; Weinrich MC (Cancer Nursing, 2007)
There is a paucity of research on the effects of pretest measurement with prostate cancer screening. What effect does a pretest measurement have on posttest outcomes? This research reports knowledge of prostate cancer screening among men randomized to an Enhanced decision aid versus an Usual Care decision aid. Using a Solomon Four research design, there were a total of 198 men in 4 groups. Most of the sample was African American (78%), with a mean age of 52 years. The greatest posttest knowledge occurred with the Enhanced decision aid in contrast to the Usual Care. The Enhanced/Usual Care groups that had both a pretest and posttest and had received a previous digital rectal examination had the highest means (P = .015), with means of 9.1 and 7.0, respectively. Among men who had a previous digital rectal examination, the greatest increase in score occurred among men randomized to the Enhanced decision aid in contrast to the Usual Care decision aid, 2.9 versus 0.4 (P = .008). The outcome varied based on the status of (1) random group assignment of the Solomon Four design and (2) status of previous digital rectal examination. Implications for nurses include consideration 1 of a pretest to increase posttest knowledge scores.
Keywords: Cancer Screening -- Education; Decision Making -- Education; Health Knowledge -- Evaluation; Prostatic Neoplasms -- Prevention and Control; Study Design; Adult; Aged; Analysis of Covariance; Bivariate Statistics; Black Persons; Chi Square Test; Descriptive Statistics; Digital Rectal Examination; Family History; Funding Source; Kentucky; Logistic Regression; Male; Mantel-Haenszel Test; Middle Age; Multivariate Analysis; Pamphlets; Pretest-Posttest Design; Questionnaires; Random Assignment; Research Subject Recruitment; Socioeconomic Factors; T-Tests; Teaching Methods; White Persons; Human

Impact of Race on Selecting Appropriate Patients for Active Surveillance With Seemingly Low-risk Prostate Cancer. - Pietzak, Eugene J; Van Arsdalen, Keith; Patel, Kinnari; Malkowicz, S Bruce; Wein, Alan J; Guzzo, Thomas J (Urology, 2015)
Keywords: Black Persons; Outcomes (Health Care); Patient Selection; Prostatectomy; Prostatic Neoplasms -- Surgery; White Persons; Clinical Assessment Tools; Human; Male; Middle Age; Retrospective Design; Risk Assessment

Improvement of Knowledge, Attitudes, and Beliefs of African American Men Toward Prostate Cancer Screening. - Adams, Carlos D.; Forehand, Jeffery Wade; Pines, Eula W. (Journal of Doctoral Nursing Practice, 2020)
Background: Prostate cancer (PCa) is a major public health concern among African American (A.A.) men. A.A. men have the highest PCa incidences nationally and internationally. Objective: The goal of this pilot study was to evaluate the effectiveness of an evidence-based PCa awareness intervention designed to positively affect the knowledge, attitudes, and beliefs of A.A. men regarding PCa screening. Method: A quantitative pre/post survey research design was utilized. A convenience sample of 11 subjects were recruited. The intervention consisted of a pre-survey, video presentation, oral presentation, question and answer session, and post-survey. The Thomas Jefferson University Prostate Cancer Screening Survey was used as the survey instrument. Results: The findings revealed a strong positive correlation between age of participants and pre-test scores. As education level increased among the participants so did knowledge, attitudes, and beliefs. Conclusions: The study's goal was met by increasing awareness and changing knowledge, attitudes, and beliefs in A.A. men regarding PCa screening. Implications for Nursing: Nurses and healthcare providers should encourage discussions with A.A. men regarding advantages and disadvantages of PCa screening that embraces cultural awareness. PCa knowledge is important for shared decision-making with healthcare providers.
Keywords: Prostatic Neoplasms -- Education; Cancer Screening; Health Education; Black Persons -- Education; Attitude to Illness -- Evaluation; Health Knowledge -- Evaluation; Health Beliefs -- Evaluation; Outcomes of Education; Human; Southeastern United States; Male; Clinical Trials; Quantitative Studies; Pretest-Posttest Design; Convenience Sample; Videorecording; Questionnaires; Age Factors; Pilot Studies; Adult; Middle Age; Data Analysis Software; Descriptive Statistics; Decision Making, Shared

Improving Lifestyle Behaviors After Breast Cancer Treatment Among African American Women With and Without Diabetes: Role of Health Care Professionals. - Jarvandi, Soghra; Pérez, Maria; Margenthaler, Julie; Colditz, Graham A; Kreuter, Matthew W; Jeffe, Donna B (Annals of Behavioral Medicine, 2021)
Background: Little is known about the effect of health professionals' advice on promoting healthy lifestyle behaviors (diet and exercise) among breast cancer patients.Purpose: To identify predictors of receiving lifestyle advice from health professionals and its impact on healthy lifestyle behaviors.Methods: We used data from a randomized controlled trial of an interactive, cancer-communication video program using African American breast cancer survivor stories for newly diagnosed African American breast cancer patients (Stages 0-III). Participants completed five interviews over 2 years. This intervention did not significantly affect changes in quality-of-life outcomes. In secondary analysis, we examined differences in baseline variables between women with and without diabetes. Logistic regression models identified independent predictors of receiving advice from "a doctor or other health professional" to improve diet and exercise and of self-reported change in diet and exercise habits at 2 year follow-up.Results: Of 193 patients included (85% of 228 enrolled), 53 (28%) had diabetes. At 2 year follow-up, a greater proportion of women with (vs. without) diabetes reported receiving advice by a doctor/health professional to improve their diet (73% vs. 57%, p = .04,). Predictors of receiving dietary advice were obesity, diabetes, and breast-conserving surgery (each p < .05). Women receiving dietary advice were 2.75 times more likely to report improving their diet (95% confidence interval: 1.17, 6.46) at follow-up, but receiving physical activity advice was not significantly associated with patients reporting an increase in exercise.Conclusions: Although receiving dietary advice predicted dietary improvements, receiving exercise advice did not lead to an increase in physical activity.Clinical Trial Registration: Trial Number NCT00929084.

Increasing mammography screening among women over age 50 with a videotape intervention. - Avis NE; Smith KW; Link CL; Goldman MB (Preventive Medicine, 2004)
Background. A randomized trial was conducted to test the effectiveness of a videotape for increasing mammography screening among a multiethnic sample of older women. Methods. A multiethnic sample of Caucasian, African-American, and Hispanic women between the ages of 50 and 70 was recruited from Resident Lists compiled by the State of Massachusetts. After completing a baseline questionnaire, women were randomized to receive either a videotape or pamphlet about mammography and recontacted at 2 and 12 months after baseline to assess attitudes, beliefs, and mammography screening. A total of 581 women completed questionnaires at all three time points. Results. At baseline, approximately 75% of women reported having a mammogram in the past year and 90% reported having one in the past 2 years. Rates did not differ between groups. At the 12-month follow-up, mammography rates, adjusted for baseline screening, were 80.4% in the video and 74.8% in the pamphlet group. Logistic regression analysis of mammography at 12 months (within past year vs. >1 year ago) controlling for baseline mammogram produced an odds ratio of 1.48 for the video group that was not significantly different from unity (95% CI = 0.95-2.28). Conclusions. The videotape had a small effect on increasing mammography screening. Although the effect was smaller than more intensive interventions, the video is a convenient, low cost, and easily implemented method to increase mammography screening. © 2004 The Institute For Cancer Prevention and Elsevier Inc. All rights reserved.
Keywords: Breast Neoplasms -- Prevention and Control; Mammography -- Trends; Aged; Clinical Trials; Descriptive Statistics; Female; Focus Groups; Health Beliefs; Health Services Accessibility; Interviews; Logistic Regression; Massachusetts; Middle Age; Odds Ratio; P-Value; Prospective Studies; Questionnaires; T-Tests; Videorecording; Funding Source; Human

Increasing prostate cancer awareness in African American men. - Collins M (Oncology Nursing Forum, 1997)
Purpose/Objectives: To describe the knowledge base of African American men regarding prostate cancer and evaluate the immediate effects of an educational intervention on short-term knowledge acquisition. Design: Prospective one group pretest/post-test. Setting: Church meetings, Salvation Army senior meetings, health fairs, and senior citizens' meetings in the African American community of a large midwestern city. Sample: Convenience sample of 75 African American men (ages 23-88) who completed a pre- and postintervention questionnaire regarding knowledge and awareness of prostate cancer. Method: The questionnaire was based on patient education material from the American Cancer Society. The instrument consisted of seven statements related to prostate cancer incidence, risk factors, and detection. Following completion of the preintervention questionaire, the investigator provided subjects with information on prostate cancer. Subjects were retested. Main Research Variables: Knowledge and awareness of prostate cancer including incidence, risk factors, and detection in African American men. Findings: Correct responses increased from 23% (preeducation) to 64% (posteducation). The three most frequently missed questions on the pretest related to urinary frequency as an early sign of prostate cancer, incidence of prostate cancer in African American men, and increased risk among African American men for prostate cancer when compared to Caucasian men. These items remained the three most frequently missed questions on the post-test. Conclusions: An educational intervention had a positive effect on short-term knowledge and awareness of prostate cancer in African American men. Additional research is necessary to assess long-term retention of information and what effect, if any, increased knowledge has on health behavior. Implications for Nursing Practice: Continued efforts are warranted to encourage this high-risk group to participate in prostate screenings. To influence health behavior, patient education and information regarding the incidence and mortality of prostate cancer is critical in this high-risk population.
Keywords: Black Persons; Prostatic Neoplasms; Health Knowledge; Men's Health -- Education; Prospective Studies; Pretest-Posttest Design; Convenience Sample; Prostatic Neoplasms -- Education; Health Knowledge -- Evaluation; Questionnaires; Descriptive Statistics; Face Validity; Adult; Middle Age; Aged; Aged, 80 and Over; Male; Human

Increasing the Representation of Minority Students in the Biomedical Workforce: the ReTOOL Program. - Odedina, Folakemi T.; Reams, R. R.; Kaninjing, E.; Nguyen, J.; Mochona, B.; Lyon, D. E.; Askins, N.; Behar-Horenstein, L. S. (Journal of Cancer Education, 2019)
With the growing burden of cancer in minority populations and limited progress in eliminating cancer disparities, it has become important to develop a diverse oncology workforce in basic, clinical, and behavioral research who will address cancer disparities and increase the participation of minority populations in clinical trials. To address the lack of well-trained underrepresented minority cancer scientists in Florida, the University of Florida collaborated with Florida A&M University in 2012 to establish the Florida Prostate Cancer Research Training Opportunities for Outstanding Leaders (ReTOOL) Program. Since 2012, the ReTOOL program has expanded to (1) cover all areas of cancer disparities; (2) offer training opportunities to minority students from all historically Black colleges and universities (HBCUs) in Florida; and (3) successfully secure both intramural and extramural federal funding to continuously provide research training opportunities for minority students in Florida. Focusing primarily on training Black students, the ReTOOL model includes culturally sensitive recruitment, mentorship, didactic curriculum, networking, and hands on experience in cancer research. This paper discusses the lessons learned from administering the ReTOOL program for 5 years, which includes having the right inputs (such as majority-minority institutions partnership, funding, faculty advisors, committed mentors, culturally competent staff, and standardized program requirements) and processes (such as pipeline approach, structured applications system, didactic curriculum, research experience, and continuous mentoring) for an effective research training program. The program impact is an increase in the pool of underrepresented minority candidates with scientific and academic career progression paths focused on reducing cancer health disparities.
Keywords: Research, Medical -- Education; Research Personnel -- Education; Minority Groups; Female; Male; Florida; Students; Career Planning and Development; Human; Curriculum; Program Evaluation; Oncology -- Education; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Clinical Assessment Tools; Impact of Events Scale; Scales

Increasing uptake of evidence-based screening services though a community health worker-delivered multimodality program: study protocol for a randomized pragmatic trial. - Carrasquillo, Olveen; Seay, Julia; Jhaveri, Vasanti; Long, Timothy; Kenya, Sonjia; Thomas, Emmanuel; Sussman, Daniel; Trevil, Dinah; Koru-Sengul, Tulay; Kobetz, Erin (Trials, 2020)
Background: Underserved ethnic minority populations experience significant disparities in HIV, hepatitis C virus (HCV), colorectal cancer (CRC), and cervical cancer incidence and mortality. Much of the excess burden of these diseases among underserved communities is due to lack of preventive care, including screening. Barriers to disease screening include low awareness, lack of access to care and health insurance, and cultural beliefs regarding disease prevention. Our current trial aims to examine community health worker (CHW)-delivered, home-based multi-modality screening for HIV, HCV, CRC, and cervical cancer simultaneously.Design: We are conducting a randomized pragmatic trial among 900 Haitian, Hispanic, and African-American participants from diverse underserved communities in South Florida. People between the ages of 50 and 65 who have not had appropriate HIV, HCV, CRC, and cervical cancer screening per United States Preventive Services Task Force (USPSTF) recommendations are eligible for the study. Participants are recruited by CHWs and complete a structured interview to assess multilevel determinants of disease risk. Participants are then randomized to receive HIV, HCV, CRC, and cervical cancer screening via navigation to care by a CHW (Group 1) or via CHW-delivered home-based screening (Group 2). The primary outcome is completion of screening for each of these diseases within 6 months post-enrollment.Discussion: Our trial is among the first to examine the effectiveness of a CHW-delivered, multimodality, home-based disease-screening approach. If found to be effective, this approach may represent a cost-effective strategy for disease screening within underserved and underscreened minority groups.Trial Registration: Clinical Trials.gov # NCT02970136, registered November 21, 2016.

Individual, Provider, and System Risk Factors for Breast and Cervical Cancer Screening Among Underserved Black, Latina, and Arab Women. - Roman, LeeAnne; Meghea, Cristian; Ford, Sabrina; Penner, Louis; Hamade, Hiam; Estes, Tamika; Williams, Karen Patricia (Journal of Women's Health (15409996), 2014)
Background: Socioeconomic and racial/ethnic disparities in breast and cervical cancer screening persist. An exploratory study was conducted to better understand co-occurring risk factors in underserved groups that could inform interventions to improve screening adherence. The objective of this study was to examine associations between breast and cervical cancer screening adherence and co-occurring risk factors in three racial/ethnic groups of underserved women. Methods: Black, Latina, and Arab women ( N=514), ages 21 to 70 years, were enrolled into the Kin KeeperSM randomized controlled trial in communities around Detroit, Michigan. We used participant baseline assessments (e.g., demographic characteristics, health literacy) to explore screening risks using an additive approach and multivariate logistic analyses. Results: For black women, having more health literacy risks were associated with reduced odds of a clinical breast exam (CBE), mammogram, and Papanicolaou (Pap) test; more competing priorities were associated with reduced odds of a Pap test; lack of doctor mammogram recommendation was significantly associated with decreased odds of CBE. For Latina women, lack of doctor recommendations were significantly associated with decreased odds of CBE, mammogram, and Pap test. For Arab women, lack of doctor recommendations were significantly associated with decreased odds of CBE, mammogram, and Pap test; more competing priorities were significantly associated with reduced odds of CBE and Pap test. All results were significant at p<0.05. Conclusions: Characteristics associated with breast and cervical screening adherence differs among Black, Latina, and Arab underserved women. Interventions to improve screening should be tailored for racial/ethnic groups with particular attention to competing survival priorities, health literacy risks factors, and provider recommendations.
Keywords: Breast Neoplasms -- Diagnosis; Cervix Neoplasms -- Diagnosis; Medically Underserved; Professional-Client Relations; Ethnic Groups -- Classification; Cancer Screening; Human; Michigan; Black Persons; Hispanic Americans; Arabs; Exploratory Research; Risk Assessment; Female; Young Adult; Adult; Middle Age; Aged; Multivariate Analysis; Logistic Regression; Mammography; Cervical Smears; Health Knowledge; Questionnaires; Patient Attitudes; Confidence Intervals; Odds Ratio; Data Analysis Software

Individualizing colonoscopy screening by sex and race. - Lansdorp-Vogelaar I; van Ballegooijen M; Zauber AG; Boer R; Wilschut J; Winawer SJ; Habbema JDF (Gastrointestinal Endoscopy, 2009)
BACKGROUND: There is increasing discussion whether colorectal cancer (CRC) screening guidelines should be individualized by sex and race. OBJECTIVES: To determine individualized colonoscopic screening guidelines by sex and race for the average-risk population and to compare the cost-effectiveness of this approach with that of uniform guidelines for all. DESIGN: We used the MISCAN-Colon microsimulation model to estimate life expectancy and lifetime CRC screening and treatment costs in a U.S. cohort of black and white men and women at average risk for CRC. We compared the base-case strategy of no screening and 3 competing colonoscopy strategies: (1) the currently recommended 'uniform 10-yearly colonoscopy from age 50 years,' (2) a shorter interval 'uniform 8-yearly colonoscopy from age 51 years,' and (3) 'individualized screening according to sex and race.' RESULTS: The base-case strategy of no screening was the least expensive, yet least effective. The uniform 10-yearly colonoscopy strategy was dominated. The uniform 8-yearly colonoscopy and individualized strategies both increased life expectancy by 0.0433 to 0.0435 years per individual, at a cost of $15,565 to $15,837 per life-year gained. In the individualized strategy, blacks began screening 6 years earlier, with a 1-year shorter interval compared with whites. The individualized policies were essentially the same for men and women, because the higher CRC risk in men was offset by their shorter life expectancy. The results were robust for changes in model assumptions. CONCLUSIONS: The improvements in costs and effects of individualizing CRC screening on a population level were only marginal. Individualized guidelines, however, could contribute to decreasing disparities between blacks and whites. The acceptability and feasibility of individualized guidelines, therefore, should be explored.
Keywords: Colonoscopy; Ethnology; Health Screening; Patient Selection; Sex Factors; Cost Benefit Analysis; Data Analysis Software; Funding Source; Multivariate Analysis; Neoplasms -- Prevention and Control; Netherlands; Sensitivity and Specificity; Human

Influence of comorbidity on racial differences in receipt of surgery among US veterans with early-stage non-small-cell lung cancer. - Williams CD; Stechuchak KM; Zullig LL; Provenzale D; Kelley MJ; Williams, Christina D; Stechuchak, Karen M; Zullig, Leah L; Provenzale, Dawn; Kelley, Michael J (Journal of Clinical Oncology, 2013)
Purpose: It is unclear why racial differences exist in the frequency of surgery for lung cancer treatment. Comorbidity is an important consideration in selection of patients for lung cancer treatment, including surgery. To assess whether comorbidity contributes to the observed racial differences, we evaluated racial differences in the prevalence of comorbidity and their impact on receipt of surgery.Patients and Methods: A total of 1,314 patients (1,135 white, 179 black) in the Veterans Health Administration diagnosed with early-stage non-small-cell lung cancer in 2007 were included. The effect of comorbidity on surgery was determined by using generalized linear models with a logit link accounting for patient clustering within Veterans Administration Medical Centers.Results: Compared with whites, blacks had greater prevalence of hypertension, liver disease, renal disease, illicit drug abuse, and poor performance status, but lower prevalence of respiratory disease. The impact of most individual comorbidities on receipt of surgery was similar between blacks and whites, and comorbidity did not influence the race-surgery association in a multivariable analysis. The proportion of blacks not receiving surgery as well as refusing surgery was greater than that among whites.Conclusion: Blacks had a greater prevalence of several comorbid conditions and poor performance status; however, the overall comorbidity score did not differ by race. In general, the effect of comorbidity on receipt of surgery was similar in blacks and whites. Racial differences in comorbidity do not fully explain why blacks undergo lung cancer surgery less often than whites.
Keywords: Black Persons -- Statistics and Numerical Data; Carcinoma, Non-Small-Cell Lung -- Ethnology; Carcinoma, Non-Small-Cell Lung -- Surgery; Comorbidity; White Persons -- Statistics and Numerical Data; Health Services Accessibility; Lung Neoplasms -- Ethnology; Lung Neoplasms -- Surgery; Patient Selection; Veterans -- Statistics and Numerical Data; Aged; Aged, 80 and Over; Carcinoma, Non-Small-Cell Lung -- Pathology; Female; Health Services Accessibility -- Statistics and Numerical Data; Human; Hypertension -- Epidemiology; Karnofsky Performance Status; Kidney Diseases -- Epidemiology; Linear Regression; Liver Diseases -- Epidemiology; Lung Neoplasms -- Pathology; Male; Middle Age; Multivariate Analysis; Neoplasm Staging; Pneumonectomy -- Statistics and Numerical Data; Prevalence; Retrospective Design; Substance Use Disorders -- Epidemiology; United States

Initial results of a new clinical trial matching service to increase patient participation. - Gansler, T; Comis, R; Sharpe, K; Tis, L; Jin, M; Dahlquist, K; Kepner, J; Hao, Y; Cressman, G; Naples, K (Journal of Clinical Oncology, 2009)
e17504 Methods: Data from CTMS constituents and follow-up information describing enrollment status and barriers to trial participation are reviewed.Results: During 15 months of operation the CTMS provided information to 10,997 individuals; 7,521 (68.39%) used the website only, and 3,476 (31.61%) also contacted the ACS call center. Among 981 of the 3,476 (28.22% the basis of analyses below) who consented to and could be reached for follow-up and who answered the question on enrollment status, 119 (12.13%) enrolled in a CT. Trial phase was known for 74 enrollees (phase I: 17 [22.97%]; II: 36 [48.65%]; III: 21 [28.38%]; IV: 0 [0%]). Enrollment was negatively (p < 0.05) associated with poor ECOG functional status and black race, and was positively related to disease stage. Among the 757 individuals with available disease site and enrollment information, those with stomach cancer accounted for the most enrollments (25, 24.75% of all enrollments); followed by melanoma (12, 11.88%) and kidney, renal pelvis, bladder, ureter and urethra (also 12, 11.88%), and breast cancer (11, 10.89%). The highest enrollment rates (% enrollees among individuals with available follow-up) were for multiple myeloma/plasma cell disorders (4/14, 28.57%), melanoma (12/49, 24.49%), primary CNS malignancy (5/31, 16.13%), and soft tissue sarcoma (6/45, 13.33%). The following barriers were significantly associated with non-enrollment: 'I cannot travel to clinical trial site,' 'I cannot find a clinical trial using the modality or treatment I want,' 'My physical activity level is too low,' and 'I do not have measurable disease or am cancer-free.'Conclusions: 12% of CTMS participants with available follow-up data for enrollment status participated in a CT. Several determinants of CT participation were identified. Strategies for eliminating racial disparities, facilitating transportation, and increasing participation among patients with earlier stage disease and more common tumor types must be developed and implemented. No significant financial relationships to disclose.

Intake of plant foods and associated nutrients in prostate cancer risk. - Lewis JE; Soler-Vilá H; Clark PE; Kresty LA; Allen GO; Hu JJ (Nutrition & Cancer, 2009)
Plant foods and associated nutrients may impact prostate cancer (PC) risk and survival. Therefore, we compared dietary intake, mainly plant food groups among 382 controls and 478 PC cases (373 incident and 105 prevalent cases). Caucasian controls had significantly higher daily servings of vegetables (3.4 vs. 2.5, P= 0.002) and fruits and/or fruit juices (1.6 vs. 1.3, P = 0.02) compared to African American controls. In Caucasians, incident cases reported lower intake of fiber, vitamin C, vitamin A, alpha -carotene, beta -carotene, cryptoxanthin, folate, genistein, daidzein, and fruits and/or fruit juice than controls and/or prevalent cases. In African Americans, incident cases had lower intake of alpha -carotene compared to controls and prevalent cases. Reduced PC risk was associated with the highest tertile of cryptoxanthin (OR = 0.51; 95% CI = 0.35-0.75), fiber (OR = 0.56; 95% CI = 0.35-0.89), vitamin C (OR = 0.60; 95% CI = 0.41-0.88), and fruits and/or fruit juices (OR = 0.46; 95% CI = 0.31-0.68), with significant linear trends. Increased risk of PC was associated with the highest tertile of protein (OR = 1.99; 95% CI = 1.05-3.79) and daily servings of grains (OR = 1.99; 95% CI = 1.23-3.22) with significant linear trends. In summary, we demonstrate racial/ethnic differences in dietary intake of plant foods. The significantly higher consumption of protective dietary constituents among prevalent cases compared to incident cases suggests that PC survivors may be amenable to dietary change.
Keywords: Nutrients; Plants, Edible; Prostatic Neoplasms -- Risk Factors; Analysis of Variance; Black Persons; Body Mass Index; Descriptive Statistics; Funding Source; Prostatic Neoplasms -- Mortality; Race Factors; Research Subject Recruitment -- Methods; White Persons; Human

Interest in genetic prostate cancer susceptibility testing among African American men. - Weinrich S; Royal C; Pettaway CA; Dunston G; Faison-Smith L; Priest JH; Roberson-Smith P; Frost J; Jenkins J; Brooks KA; Powell I (Cancer Nursing, 2002)
Six regions for prostate cancer genes have been identified, and it is anticipated that prostate cancer susceptibility testing will be available in the future. This correlational study identified predictors for interest in prostate cancer susceptibility testing among African American men. Participants were 320 African American men from the African American Hereditary Prostate Cancer Study and the South Carolina Prostate Cancer Education and Screening Study participated. Two questions measured interest in genetic prostate cancer susceptibility testing and family history of prostate cancer. Chi-square analyses by family history as well as demographics (age, education, marital status) were performed. Most of the men (277 [87%]) indicated an interest in genetic prostate cancer susceptibility testing. Interest in undergoing testing did not vary by family history, age, or education. Marital status was the only significant demographic predictor. Men who were married were significantly more likely to respond with a 'yes' to interest in prostate cancer susceptibility testing than were men who were not married. The high 'yes' response rate and the men's confusion between the genetic prostate cancer susceptibility testing and prostate cancer screening highlight the need for public education once prostate cancer genes are identified and available for public testing.
Keywords: Genetic Screening; Disease Susceptibility; Prostatic Neoplasms; Black Persons -- Texas; Black Persons -- South Carolina; Correlational Studies; Chi Square Test; Texas; Race Factors; South Carolina; Descriptive Statistics; Consumer Attitudes -- Evaluation; Research Subject Recruitment; Questionnaires; Test-Retest Reliability; Family History; Adult; Middle Age; Aged; Aged, 80 and Over; Male; Human

Intervention to increase screening mammography among women 65 and older. - Michielutte R; Sharp PC; Foley KL; Cunningham LE; Spangler JG; Paskett ED; Case LD (Health Education Research, 2005)
This paper reports the results of a practice-based intervention program to increase mammography screening among women 65 and older who receive their health care in the private sector. Forty-three primary-care practices and 2147 women in central and western North Carolina were enrolled in the study, and 1911 women completed all phases of the study. The intervention was a three-stage educational and counseling program designed to become progressively more intensive at each stage. The interventions included provider education in the form of current information on issues in mammography for older women, simply written educational materials on breast cancer and screening mailed to women, and a brief telephone counseling session for the women. While the analysis revealed no overall effect across all three stages of the intervention program, tests for interaction indicated a significant program effect for women who were 80 or older, had less than 9 years of education, were black, or had no private insurance to supplement Medicare. The results suggested that providing primary-care physicians with information on screening older women and providing the women with useful educational materials can increase participation in screening mammography among subgroups of women currently least likely to receive mammography screening.
Keywords: Behavioral Changes -- In Old Age; Breast Neoplasms -- Prevention and Control -- In Old Age; Gerontologic Care; Mammography -- Trends -- In Old Age; Aged; Aged, 80 and Over; Conceptual Framework; Counseling; Descriptive Statistics; Female; Funding Source; Interviews; North Carolina; P-Value; Pretest-Posttest Design; Record Review; Regression; Two-Tailed Test; Human

It's not just what you say, it's also how you say it: opening the 'black box' of informed consent appointments in randomised controlled trials. - Wade J; Donovan JL; Lane JA; Neal DE; Hamdy FC (Social Science & Medicine, 2009)
Randomised controlled trials (RCTs) represent the gold standard methodology for determining effectiveness of healthcare interventions. Poor recruitment to RCTs can threaten external validity and waste resources. An inherent tension exists between safeguarding informed decision-making by participants and maximising numbers enrolled. This study investigated what occurs during informed consent appointments in an ongoing multi-centre RCT in the UK. Objectives were to investigate: 1] how study staff presented study information to participants; 2] what evidence emerged as to how well-informed participants were when proceeding to randomisation or treatment selection; and 3] what aspects of the communication process may facilitate improvements in providing evidence of informed consent. Qualitative analysis of a purposive sample of 23 recruitment appointments from three study centres and involving several recruitment staff applied techniques of thematic, content and conversation analysis (CA). Thematic analysis and CA revealed variation in appointment content and structure. Appointments were mostly recruiter-led or participant-led, and this structure was associated with what evidence emerged as to how participants understood information provided and whether they were in equipoise. Participant-led appointments provided this evidence more consistently. Detailed CA identified communication techniques which, when employed by recruiters, provided evidence as to how participants understood the choices before them. Strategic use of open questions, pauses and ceding the floor in the interaction facilitated detailed and systematic exploration of each participant's concerns and position regarding equipoise. We conclude that the current focus on content to be provided to achieve informed consent should be broadened to encompass consideration of how information is best conveyed to potential participants. A model of tailored information provision using the communication techniques identified and centred on eliciting and addressing participants' concerns is proposed. Use of these techniques is necessary to make potential participants' understanding of key issues and their position regarding equipoise explicit in order to facilitate truly informed consent.
Keywords: Communication; Consent; Consumer Participation; Patient Selection; Clinical Trials; Aged; Great Britain; Human; Male; Middle Age; Multicenter Studies; Prostatic Neoplasms; Audiorecording

'I've been through something': poetic explorations of African American women's cancer survivorship. - Kooken WC; Haase JE; Russell KM (Western Journal of Nursing Research, 2007)
This article describes common experiences of African American women breast cancer survivors through poetic analysis. Group-as-a-whole theory and empirical and interpretive phenomenology guided analysis of transcripts from three focus groups (n = 21) of African American breast cancer survivors. Familiarity with transcripts and themes led to awareness of poetic ways in which African American women described experiences. Black feminist literature and African American historical references contextualized survivors' experiences. Poetic interpretations of African American women's breast cancer experiences, from diagnosis to survivorship, were created from transcript dialogues. Verbatim words were used to construct the poems, as often as possible. Eleven poems describe the journey from diagnosis to survivorship as experienced by African American women. The poetry may raise levels of awareness of African American women's breast cancer survivorship experiences. Attention to subtleties that underpin culture within the context of health care environments may help health care providers to improve cultural competence.
Keywords: Black Persons -- United States; Breast Neoplasms; Cancer Survivors; Poetry; Adult; Aged; Audiorecording; Breast Neoplasms -- Diagnosis; Coping; Cultural Competence; Female; Focus Groups; Funding Source; Middle Age; Phenomenological Research; Professional-Patient Relations; Quality of Life -- Evaluation; Research Subject Recruitment; Secondary Analysis; Thematic Analysis; Theory; United States; Human

Knowledge of the limitations associated with prostate cancer screening among low-income men. - Weinrich SP; Seger R; Miller BL; Davis C; Kim S; Wheeler C; Weinrich M (Cancer Nursing, 2004)
This correlational pilot study measured limitations of prostate cancer screening, using a revised Knowledge of Prostate Cancer Questionnaire. Knowledge in 81 low-income men is reported. The Knowledge About Prostate Cancer Screening Questionnaire consists of 12 questions, with scores ranging from 0 to 12. Concepts measured include limitations, symptoms, risk factors, and screening age guidelines. The Total Knowledge Score had a mean of 6.60, with a standard deviation of 3.00, indicating that knowledge was low. Half of the men knew that 'some treatments for prostate cancer can make it harder for men to control their urine. 'More than half of the men knew that, 'some treatments for prostate cancer can cause problems with a man's ability to have sex.' Married men, low-income men, and Caucasian men had significantly lower Total Knowledge Scores than unmarried, higher income, and African American men. Implications for practice and research are discussed.
Keywords: Cancer Screening; Health Knowledge -- Evaluation; Prostatic Neoplasms -- Prevention and Control; Adult; Bivariate Statistics; Chi Square Test; Coefficient Alpha; Confidence Intervals; Construct Validity; Content Validity; Correlational Studies; Descriptive Statistics; Education, Continuing (Credit); Funding Source; Kentucky; Male; Marital Status; Middle Age; Multiple Regression; Multivariate Analysis; Pilot Studies; Poverty; Prostatic Neoplasms -- Education; Questionnaires; Race Factors; Research Subject Recruitment; T-Tests; Test-Retest Reliability; Human

Language adaptation and testing of the Prostate Health Questionnaire for Jamaican and Haitian men. - Kleier JA (Urologic Nursing, 2006)
A convenience sample of Jamaican and Haitian men completed the translated versions of the Prostate Health Questionnaire. The findings support that the translated survey is comprehensive, has internal consistency, and is reliable over time when used for these populations.
Keywords: Black Persons -- Florida; Health Promotion; Instrument Construction; Instrument Validation; Prostatic Neoplasms -- Prevention and Control; Questionnaires; Translations; Aged; Coefficient Alpha; Descriptive Statistics; Florida; Funding Source; Immigrants; Middle Age; Pearson's Correlation Coefficient; Post Hoc Analysis; Research Subject Recruitment; Summated Rating Scaling; Test-Retest Reliability; Validation Studies; West Indies; Human

Lessons Learned from Implementing a Prostate Cancer Risk Assessment Program for Underserved High-Risk Men in the Community: the Prostate REACH Project. - Fleisher, Linda; Davis, Stacy; Gross, Laura; Bagden, Loretta; Zakrzewski, Debra; González, Evelyn; Kandadai, Venk; Rusten, Cheryl; Baskett, Jerilyn; Obeid, Elias; Giri, Veda; Davis, Stacy N; et al. (Journal of Cancer Education, 2016)
Prostate cancer disproportionately affects Black men, who may also encounter barriers to participation in prostate cancer risk assessment. The Prostate Risk, Education and Assessment in the Community with Help (REACH) project was a community-based extension of a comprehensive prostate cancer risk assessment program at a comprehensive cancer center. The goals of the REACH project were the following: (1) establish a community prostate cancer risk assessment clinic, (2) conduct targeted recruitment, and (3) provide navigation services including follow-up for uninsured men. Key implementation steps included the following: (1) choosing a clinic site, (2) establishing patient access procedures, (3) establishing navigator services, (4) developing subsidy fund use guidelines, and (5) designing recruitment and promotion. Through community-based promotion, 64 men inquired about the program and 26 (41 %) participated. Of those screened, 46 % had abnormal results, and 2 men were diagnosed with prostate cancer. Here, we describe a unique demonstration project to implement a comprehensive prostate cancer risk assessment program in an underserved Black community and describe successes and challenges to inform future efforts to promote access to underserved men.
Keywords: Special Populations -- Psychosocial Factors; Early Detection of Cancer -- Psychosocial Factors; Patient Education; Ethnic Groups -- Education; Prostatic Neoplasms -- Prevention and Control; Male; Learning; Aged; Adult; Human; Patient Selection; Prostatic Neoplasms -- Psychosocial Factors; Risk Assessment; Prospective Studies; Program Evaluation; Patient Navigation; Prostatic Neoplasms -- Diagnosis; Middle Age; Prognosis; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Lessons learned in developing a support intervention for African American women with breast cancer. - Coward DD (Oncology Nursing Forum, 2005)
PURPOSE/OBJECTIVES: To describe the process of planning a theory-based support group project for African American women with breast cancer. DATA SOURCES: A needs assessment and recruitment strategies consistent with the Oncology Nursing Society's Multicultural Outcomes: Guidelines for Cultural Competence were used to adapt a support group intervention for newly diagnosed African American women in urban central Texas. DATA SYNTHESIS: The reviewed literature and local cancer survivor leaders indicated the need for education and support of newly diagnosed women. Although researchers worked for several years with lay leaders to gain legitimacy and trust, not enough participants were recruited to test an intervention specifically for African American women.CONCLUSIONS: Recruiting support group research participants from a relatively small minority population is problematic even when collaborating with population leaders. IMPLICATIONS FOR NURSING: Nurses may encounter barriers to conducting research in minority populations. Starting early to build credibility with that population, being flexible with eligibility criteria, beginning with pre-experimental studies, and paying participants may be required.
Keywords: Black Persons; Breast Neoplasms; Nursing Practice, Theory-Based; Oncologic Nursing; Support Groups; Information Needs -- Evaluation; Needs Assessment; Patient Education; Planning Techniques; Research Subject Recruitment; Texas; Urban Areas

Lived experiences of breast cancer survivors after diagnosis, treatment and beyond: qualitative study. - Williams, Faustine; Jeanetta, Stephen C. (Health Expectations, 2016)
Background: The number of breast cancer survivors has increased since 1990 due to advances in biomedical technology that lead to an increase in early diagnosis and treatment. Research on survivorship has focused on the psychological and treatment aspects of the disease. The goal of this study was focused on exploring the lived experiences of breast cancer survivors from diagnosis, treatment and beyond. Objective: To understand the lived experiences of women who are breast cancer survivors. Design, Setting and Participants: A purposive sampling strategy was used to recruit participants from two Missouri cancer centres. A total of 15 women breast cancer survivors were interviewed. Findings: Three major themes emerged that described the lived experiences of the women. These were factors from the diagnosis and treatment management impacting survivorship, relationship and support system and implication of survivorship. Participants noted that coping with the diagnosis and treatment was a stressful journey and required lots of adjustment and changes. Some developed various techniques such as journaling their activities which provided comfort. In addition, support from family was shared as the key which gave them strength and courage through the different stages of treatment. However, they found it difficult to articulate what survivorship meant. Conclusion: Using in ‐ depth interview techniques, this study shed light on the experiences of women who were diagnosed with breast cancer and have completed treatment. They acknowledged frustration with their diagnosis and body changes. Support received from family and friends helped them cope through their treatment. However, they felt abandoned once the treatment phase was over and were uncertain what survivorhood meant to them.
Keywords: Life Experiences; Breast Neoplasms -- Diagnosis; Cancer Survivors; Breast Neoplasms -- Therapy; Treatment Outcomes; Health; Human; Female; Qualitative Studies; Technology, Medical; Interviews; Breast Neoplasms -- Psychosocial Factors; Ethnic Groups; Race Factors; Research Subject Recruitment; Data Collection; Data Analysis; Reliability and Validity; White Persons; Black Persons; Neoplasm Staging; Disease Duration

Low-dose computed tomography lung cancer screening as a teachable moment for smoking cessation among African American smokers: A feasibility study. - Sly, Jamilia R.; Miller, Sarah J.; Li, Yaqi; Bolutayo, Kemi; Jandorf, Lina (Journal of Psychosocial Oncology, 2018)
Low-dose computed tomography (LDCT) screening may be a teachable moment for smoking cessation among African Americans. African Americans have been understudied within the context of LDCT and smoking cessation. The study objective was to evaluate the feasibility of recruiting African Americans to a future longitudinal trial and to obtain sample size estimates for that trial. Participants (N = 18) were African Americans eligible for LDCT screening who completed a questionnaire at three time points. Self-efficacy and intention to quit smoking were compared. The results of the current study show that it is feasible to recruit African Americans eligible for LDCT.
Keywords: Tomography, X-Ray Computed -- Methods; Lung Neoplasms; Cancer Screening; Smoking Cessation; Black Persons; Patient Education; Human; Prospective Studies; Pilot Studies; Questionnaires; Self-Efficacy

Magnifying gastroscopy using a soft black hood for difficult colonoscopy. - Nakamura H; Fu K; Yamamura A; Nakamura, Hisashi; Fu, Kuangi; Yamamura, Akihiko (Surgical Endoscopy, 2011)
Background: Various methods are reported as aids to cecal intubation for cases in which colonoscopy is difficult. This study aimed to investigate prospectively whether a gastroscope with magnification function, narrow-band imaging (NBI), and a soft black hood can aid insertion in cases of difficult colonoscopy and facilitate both accurate diagnosis and safe treatment.Methods: This prospective study recruited 177 patients. All were examined with a magnifying gastroscope. A commercially available soft black hood was attached to the gastroscope during insertion and magnification. Difficult colonoscopy was anticipated before colonoscopy in cases of patients with at least one of the following factors: low BMI (<20 kg/m(2)), adhesion due to previous surgery, or previous colonoscopy that could not reach to the cecum. The success rate and duration of cecal intubation then were assessed. All detected lesions were evaluated by magnifying NBI and then classified as non-neoplastic or neoplastic for endoscopic diagnosis. Subsequently, all the lesions were removed and examined histologically for comparison.Results: The overall success rate of cecal intubation was 100% (177/177), and the mean time taken to reach the cecum was 5.9 min. A total of 156 lesions were detected endoscopically, and the overall diagnostic accuracy of NBI with magnification was 98.7%. No associated complications occurred.Conclusion: Magnifying gastroscopy using a soft black hood and NBI is useful for cecal intubation in cases wherein colonoscopy is difficult, facilitating accurate diagnosis and safe treatment.
Keywords: Colonoscopy -- Equipment and Supplies; Adenocarcinoma -- Diagnosis; Adenoma -- Diagnosis; Adult; Aged; Aged, 80 and Over; Carcinoid Tumor -- Diagnosis; Cecum; Colonic Neoplasms -- Diagnosis; Colonic Polyps -- Diagnosis; Colonoscopy -- Methods; Equipment Design; Female; Human; Male; Middle Age; Prospective Studies; Videorecording; Young Adult; Clinical Trials

Making a difference. - Cavallo J (CURE: Cancer Updates, Research & Education, 2008)
Edith Joyner, 61, won't personally benefit from participating in the Sister Study, but it was important for her to join, she says, not only to honor her two sisters who battled the disease, but to help the next generation of females in her family avoid the same fate.
Keywords: Black Persons; Breast Neoplasms -- Prevention and Control; Clinical Trials; Female; Middle Age; Research Subject Recruitment

Minority recruitment in the prostate cancer prevention trial. - Moinpour CM; Atkinson JO; Thomas SM; Underwood SM; Harvey C; Parzuchowski J; Lovato LC; Ryan AM; Hill MS; DeAntoni E; Gritz ER; Thompson IM Jr.; et al. (Annals of Epidemiology, 2000)
Purpose: African American men have a higher prostate cancer risk profile than that of other men in the United States. The purpose of this manuscript is to summarize the challenges associated with enrolling and randomizing African American and other minority participants in the Prostate Cancer Prevention Trial (PCPT).Methods: The PCPT is a randomized trial of finasteride versus placebo for preventing prostate cancer in healthy men age 55 years and older; it is coordinated by the Southwest Oncology Group. The manuscript describes demographic and lifestyle characteristics of the PCPT randomized sample (18,882 men) by four racial and ethnic groups (Caucasian, African American, Hispanic, and other). African American men comprised 4% of the total randomized sample compared to our goal of 8%. Minority recruitment was emphasized through the Study Manual and training that occurred at trial activation. Supplemental minority recruitment activities were initiated a year after study activation and continued through the end of the accrual period. Minority recruitment was emphasized as follows: minority recruitment presentations at PCPT training seminars (held during twice yearly Southwest Oncology Group meetings); distribution of additional minority recruitment materials; engagement of four consultants for minority recruitment; production of a Minority Recruitment Manual; and a small pilot study involving minority outreach recruiters at five PCPT sites.Results: The consultants were helpful in implementing the pilot project and in suggesting and reviewing materials for minority recruitment. The five-site pilot project did not increase either enrollment or randomization of minorities (with a possible exception at one site).Conclusions: We suggest that a long-term perspective is required for successful recruitment of minority participants in clinical trials. Likewise, extensive minority recruitment efforts must be ready to implement at trial activation.
Keywords: Minority Groups; Prostatic Neoplasms -- Prevention and Control; Research Subject Recruitment; Clinical Trials; Funding Source; Life Style; Male; Prostatic Neoplasms -- Epidemiology; Human

Mixing beauty and health: lymphedema study looks for participants at beauty shops. - Long K (NurseWeek (15475131), 2007)
Keywords: Beauty; Cancer Survivors; Lymphedema; Black Persons; Breast Neoplasms; Female; Research Subject Recruitment

Mixing beauty and health: lymphedema study looks for participants at beauty shops. - Long K (NurseWeek, 2007)
Keywords: Cancer Survivors; Lymphedema; Black Persons; Breast Neoplasms; Female; Research Subject Recruitment

Mixing beauty and health: lymphedema study looks for participants at beauty shops. - Long K (Nursing Spectrum -- New England Edition, 2007)
Keywords: Beauty; Cancer Survivors; Lymphedema; Black Persons; Breast Neoplasms; Female; Research Subject Recruitment

Mixing beauty and health: lymphedema study looks for participants at beauty shops. - Long K (Nursing Spectrum -- Greater Chicago, 2007)
Keywords: Cancer Survivors; Lymphedema; Black Persons; Breast Neoplasms; Female; Research Subject Recruitment

Narratives of breast symptom discovery and cancer diagnosis: psychologic risk for advanced cancer at diagnosis. - Facione NC; Giancarlo CA (Cancer Nursing, 1998)
In spite of cancer screening programs, women continue to present with advanced breast cancer. How do women decide whether and when to seek an evaluation for self-discovered symptoms? This study examined 104 narratives told by 80 Anglo-, Latina-, and African-American women who participated in 1 of 16 community-based focus groups. The women's narratives contained powerful thematic messages about breast cancer and their expected behavior in the event of a self-discovered breast symptom. Narrative explanations that predicted an increased likelihood of advanced disease at diagnosis included these factors: incorrect symptom attributions and risk estimations; reluctance to consider the threat posed by the symptom; failure to tell another person about the symptom; and expectations of abandonment by male partners, deportation, prejudice, and refusal of treatment due to poverty. Stories of advanced breast cancer also told of reliance on alternative healing, concerns about overwhelming family resources, and extreme modesty that inhibited obtaining a physical examination. Interventions aimed at earlier detection of breast cancer must connect with the beliefs and assumptions embedded in these narratives, provide pragmatic solutions for perceived constraints on seeking evaluations of self-discovered symptoms, and explore the use of community narratives to confirm the value of early detection of breast cancer.
Keywords: Breast Neoplasms -- Psychosocial Factors; Breast Neoplasms -- Diagnosis; Patient Attitudes; Help Seeking Behavior; Symptoms; Funding Source; Research Subject Recruitment; Focus Groups; California; Patient Attitudes -- Evaluation; Narratives; Thematic Analysis; Qualitative Studies; Adult; Middle Age; Female; Human

National Surgical Adjuvant Breast and Bowel Project Study of Tamoxifen and Raloxifene trial: Advancing the science of recruitment and breast cancer risk assessment in minority communities. - McCaskill-Stevens, Worta; Wilson, John W; Cook, Elise D; Edwards, Cora L; Gibson, Regina V; McElwain, Diane L; Figueroa-Moseley, Colmar D; Paskett, Electra D; Roberson, Noma L; Wickerham, D Lawrence; Wolmark, Norman (Clinical Trials, 2013)
Keywords: Breast Neoplasms; Surgery, Operative; Colonic Neoplasms; Tamoxifen -- Therapeutic Use; Raloxifene -- Therapeutic Use; Minority Groups; Research Subject Recruitment; Human; Women; Black Persons; Hispanic Americans; White Persons; Adverse Drug Event; Risk Assessment; Corporations; Native Americans; Funding Source

National Trends in Nonoperative Management of Rectal Adenocarcinoma. - Ellis, Clayton Tyler; Samuel, Cleo A.; Stitzenberg, Karyn B. (Journal of Clinical Oncology, 2016)
Purpose: Neoadjuvant chemoradiation for stage II/III rectal cancer results in up to 49% of patients with a clinical complete response. As a result, many have questioned whether surgery can be omitted for this group of patients. Currently, there is insufficient evidence for chemoradiation only, or nonoperative management (NOM), to support its adoption. Despite this, anecdotal evidence suggests there is a trend toward increased use of NOM. Our objective was to examine the use of NOM for rectal cancer over time, as well as the patient- and facility-level factors associated with its use.Methods: We included all incident cases of invasive, nonmetastatic rectal adenocarcinoma reported to the National Cancer Database from 1998 to 2010. We performed univariate and multivariate analyses to assess for NOM use over time, as well as associated patient- and facility-level factors.Results: A total of 146,135 patients met the inclusion criteria: 5,741 had NOM and 140,394 had surgery with or without additional therapy. From 1998 to 2010, NOM doubled, from 2.4% to 5% of all cases annually. Patients who were black (adjusted odds ratio [AOR], 1.71; 95% CI, 1.57 to 1.86), uninsured (AOR, 2.35; 95% CI, 2.08 to 2.65) or enrolled in Medicaid (AOR, 2.10; 95% CI, 1.90 to 2.33), or treated at low-volume facilities (AOR, 1.53; 95% CI, 1.42 to 1.64) were more likely to receive NOM than were patients who were white, privately insured, and treated at a high-volume facility, respectively.Conclusion: NOM demonstrates promise for the treatment of rectal cancer; currently, however, the most appropriate strategy is to pursue this approach with well-informed patients in the context of a clinical trial. We observed evidence of increasing NOM use, with this increase occurring more frequently in black and uninsured/Medicaid patients, raising concern that increased NOM use may actually represent increasing disparities in rectal cancer care rather than innovation. Further studies are needed to assess survival differences by treatment strategy.
Keywords: Adenocarcinoma -- Therapy; Kidney Neoplasms -- Therapy; Neoadjuvant Therapy -- Trends; United States; Neoplasm Staging; Adenocarcinoma -- Epidemiology; Adenocarcinoma -- Pathology; Kidney Neoplasms -- Pathology; Aged; Male; Kidney Neoplasms -- Epidemiology; Resource Databases; Middle Age; Prospective Studies; Adult; Aged, 80 and Over; Female; Human

Navigating veterans with an abnormal prostate cancer screening test: a quasi-experimental study. - Simon, Melissa A; Nonzee, Narissa J; McKoy, June M; Liu, Dachao; Luu, Thanh Ha; Byer, Peter; Eklund, Elizabeth A; Richey, Elizabeth A; Wu, Zhigang; Dong, Xinqi; Rademaker, Alfred W (BMC Health Services Research, 2013)
Background: Prostate cancer disproportionately affects low-income and minority men. This study evaluates the impact of a patient navigation intervention on timeliness of diagnostic resolution and treatment initiation among veterans with an abnormal prostate cancer screen.Methods: Participants were enrolled between 2006 and 2010. The intervention involved a social worker and lay health worker navigation team that assisted patients in overcoming barriers to care. For navigated (n = 245) versus control (n = 245) participants, we evaluated rates of diagnostic resolution and treatment and adjusted for race, age, and Gleason score.Results: Of 490 participants, 68% were African American, 47% were ≥ 65 years old, and 35% had cancer. Among those with an abnormal screen, navigation did not have a significant effect on time to diagnostic resolution compared to controls (median days of 97 versus 111; adj. HR 1.17, 95% CI, 0.96-1.43, p = 0.12). On analysis of the period beyond 80 days, navigated men reached resolution faster than controls (median of 151 days versus 190 days; adj. HR 1.41, 95% CI, 1.07-1.86, p = 0.01). Among those with cancer, navigation did not have a significant effect on time to treatment initiation compared to controls (median of 93 days versus 87 days; adj. HR 1.15, 95% CI, 0.82-1.62, p = 0.41).Conclusion: Our navigation program did not significantly impact the overall time to resolution or treatment for men with prostate cancer compared to controls. The utility of navigation programs may extend beyond targeted navigation times, however, and future studies focusing on other outcomes measures are therefore needed.
Keywords: Early Detection of Cancer; Patient Navigation -- Methods; Prostatic Neoplasms -- Diagnosis; Veterans; Adult; Aged; Aged, 80 and Over; Clinical Assessment Tools; Hospitals, Veterans -- Administration; Human; Male; Middle Age; Prostate-Specific Antigen -- Blood; Prostatic Neoplasms -- Therapy; Social Work -- Methods; Time Factors; United States

New research suggests access, genetic differences play role in high minority cancer death rate. - Whitworth A (JNCI: Journal of the National Cancer Institute, 2006)
Keywords: Black Persons; Health Services Accessibility; Minority Groups; Neoplasms; Neoplasms -- Mortality; Poverty; Breast Neoplasms -- Mortality; Breast Neoplasms -- Pathology; Clinical Trials; Colorectal Neoplasms -- Drug Therapy; Female; Male; Neoplasms -- Therapy; Patient Selection; Trust; United States

News... news... news. (European Journal of Cancer, 2007)
Keywords: Adolescence; Aged -- Legislation and Jurisprudence; Antibodies, Monoclonal -- Therapeutic Use; Black Persons; Breast Neoplasms -- Risk Factors; Cancer Screening -- Trends; Capecitabine -- Therapeutic Use; Cervix Neoplasms -- Prevention and Control; Child; Child, Preschool; Childhood Neoplasms -- Complications; Colonography, Computed Tomographic -- Utilization; Colorectal Neoplasms -- Drug Therapy; Cryptorchidism -- Therapy; Drug Design; Erythropoietin -- Adverse Effects; Female; Great Britain; Infant; Infant, Newborn; Male; Medical Organizations; Neoplasms -- Drug Therapy; Neoplasms, Second Primary -- Risk Factors; Prostatic Neoplasms -- Prevention and Control; Research Subject Recruitment; Resuscitation Orders -- Legislation and Jurisprudence; Stomach Neoplasms -- Drug Therapy; Testicular Neoplasms -- Risk Factors; Tumor Markers, Biological; United Kingdom

Outcomes Among Minority Patients With Metastatic Colorectal Cancer in a Safety-net Health Care System. - Lau-Min, Kelsey; Prakash, Preeti; Jo, Eunji; Thrift, Aaron P; Hilsenbeck, Susan; Musher, Benjamin L (Clinical Colorectal Cancer, 2020)
Background: Metastatic colorectal cancer (CRC) outcomes continue to improve, but they vary significantly by race and ethnicity. We hypothesize that these disparities arise from unequal access to care.Materials and Methods: The Harris Health System (HHS) is an integrated health delivery network that provides medical care to the underserved, predominantly minority population of Harris County, Texas. As the largest HHS facility and an affiliate of Baylor College of Medicine's Dan L. Duncan Comprehensive Cancer Center, Ben Taub Hospital (BTH) delivers cancer care through multidisciplinary subspecialty that prioritize access to care, adherence to evidence-based clinical pathways, integration of supportive services, and mitigation of financial toxicity. We performed a retrospective analysis of minority patients diagnosed with and treated for metastatic CRC at BTH between January 2010 and December 2012. Kaplan-Meier survival curves were compared with survival curves from randomized control trials reported during that time period.Results: We identified 103 patients; 40% were black, 49% were Hispanic, and 12% were Asian or Middle Eastern. Thirty-five percent reported a language other than English as their preferred language. Seventy-four percent of patients with documented coverage status were uninsured. Eighty-four percent of patients received standard chemotherapy with a clinician-reported response rate of 63%. Overall survival for BTH patients undergoing chemotherapy was superior to that of subjects enrolled in the CRYSTAL (Cetuximab Combined with Irinotecan in First-Line Therapy for Metastatic Colorectal Cancer) trial (median, 24.0 vs. 19.9 months; P = .014).Conclusion: HHS provides a health delivery infrastructure through which minority patients with socioeconomic challenges experience clinical outcomes comparable with highly selected patients enrolled in randomized control trials. Efforts to resolve CRC disparities should focus on improving access of at-risk populations to high-quality comprehensive cancer care.

Outcomes and toxicity in african-american and caucasian patients in a randomized adjuvant chemotherapy trial for colon cancer. - McCollum, A. David; Catalano, Paul J.; Haller, Daniel G.; Mayer, Robert J.; Macdonald, John S.; Benson III, Al B.; Fuchs, Charles S.; Benson, Al B 3rd (JNCI: Journal of the National Cancer Institute, 2002)
Background: Previous studies have demonstrated that African-Americans with colon cancer have worse overall and stage-specific survival rates than Caucasians. Such differences could reflect variation in access to health care, in tumor biology, or in treatment efficacy. Little is known about potential differences in chemotherapy-related toxicities between African-Americans and Caucasians. In this study, we examined survival and toxic effects among African-American and Caucasian patients enrolled in a large, randomized phase III trial of adjuvant chemotherapy for resected colon cancer.Methods: We analyzed data on 3380 patients (344 African-Americans and 3036 Caucasians) enrolled in a randomized trial of adjuvant 5-fluorouracil-based chemotherapy in patients with stage II (high risk) and stage III colon cancer to evaluate differences in outcomes and toxicity. We compared disease-free survival (DFS) and overall survival (OS) between African-Americans and Caucasians by the Kaplan-Meier method, computed Cox proportional hazards by multivariable analysis, and compared treatment-related toxicity rates by Fisher's exact test. All statistical tests were two-sided.Results: We found no differences in DFS or OS between African-American and Caucasian patients. Five-year DFS was 57% (95% confidence interval [CI] = 52% to 62%) for African-Americans and 58% (95% CI = 56% to 60%) for Caucasians (P =.15), and 5-year OS was 65% (95% CI = 60% to 70%) for African-Americans and 66% (95% CI = 64% to 68%) for Caucasians (P =.38). On multivariable analysis, no statistically significant difference in disease recurrence or death was detected between the racial/ethnic groups (hazard ratios for African-Americans versus Caucasians: disease recurrence = 1.1, 95% CI = 0.9 to 1.3; death = 1.1, 95% CI = 0.9 to 1.3). Treatment-related toxicity differed between the African-American and Caucasian patients, with African-Americans experiencing statistically significantly lower rates of diarrhea (P<.001), nausea (P<.001), vomiting (P =.01), stomatitis (P<.001), and overall toxicity (P =.005).Conclusions: In this study of patients with similar access to health care resources and treatment with adjuvant chemotherapy, we found similar 5-year DFS and OS in African-Americans and Caucasians with stage II and III colon cancer. The two groups derived similar benefits from adjuvant chemotherapy. Moreover, African-Americans appeared to experience less treatment-related toxicity.
Keywords: Fluorouracil -- Therapeutic Use; Colonic Neoplasms -- Ethnology; Colonic Neoplasms -- Drug Therapy; Antimetabolites, Antineoplastic -- Therapeutic Use; Human; Fluorouracil -- Adverse Effects; Black Persons; Colonic Neoplasms -- Mortality; White Persons; Treatment Outcomes; Chemotherapy, Adjuvant; Clinical Trials; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials

Overall Survival of Black and White Men With Metastatic Castration-Resistant Prostate Cancer Treated With Docetaxel. - Halabi, Susan; Dutta, Sandipan; Tangen, Catherine M.; Rosenthal, Mark; Petrylak, Daniel P.; Thompson, Ian M.; Chi, Kim N.; Araujo, John C.; Logothetis, Christopher; Quinn, David I.; Fizazi, Karim; Morris, Michael J.; et al. (Journal of Clinical Oncology, 2019)
Purpose: Several studies have reported that among patients with localized prostate cancer, black men have a shorter overall survival (OS) time than white men, but few data exist for men with advanced prostate cancer. The primary goal of this analysis was to compare the OS in black and white men with metastatic castration-resistant prostate cancer (mCRPC) who were treated in phase III clinical trials with docetaxel plus prednisone (DP) or a DP-containing regimen.Methods: Individual participant data from 8,820 men with mCRPC randomly assigned in nine phase III trials to DP or a DP-containing regimen were combined. Race was based on self-report. The primary end point was OS. The Cox proportional hazards regression model was used to assess the prognostic importance of race (black v white) adjusted for established risk factors common across the trials (age, prostate-specific antigen, performance status, alkaline phosphatase, hemoglobin, and sites of metastases).Results: Of 8,820 men, 7,528 (85%) were white, 500 (6%) were black, 424 (5%) were Asian, and 368 (4%) were of unknown race. Black men were younger and had worse performance status, higher testosterone and prostate-specific antigen, and lower hemoglobin than white men. Despite these differences, the median OS was 21.0 months (95% CI, 19.4 to 22.5 months) versus 21.2 months (95% CI, 20.8 to 21.7 months) in black and white men, respectively. The pooled multivariable hazard ratio of 0.81 (95% CI, 0.72 to 0.91) demonstrates that overall, black men have a statistically significant decreased risk of death compared with white men ( P < .001).Conclusion: When adjusted for known prognostic factors, we observed a statistically significant increased OS in black versus white men with mCRPC who were enrolled in these clinical trials. The mechanism for these differences is not known.
Keywords: Prostatic Neoplasms, Castration-Resistant -- Drug Therapy; Black Persons -- Statistics and Numerical Data; Prostatic Neoplasms, Castration-Resistant -- Ethnology; White Persons -- Statistics and Numerical Data; Antineoplastic Agents, Combined -- Therapeutic Use; Human; Prostatic Neoplasms, Castration-Resistant -- Pathology; Prednisone -- Administration and Dosage; Prostatic Neoplasms, Castration-Resistant -- Mortality; Clinical Trials; Mitoxantrone -- Administration and Dosage; Male; Neoplasm Metastasis; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Scales

Overcoming the Challenges Of African-American Recruitment In Health Sciences Research: Strategies and Recommendations. - Owens, Otis L.; James, Calvin; Friedman, Daniela B. (Urologic Nursing, 2017)
Culturally appropriate recruiting strategies will increase the number of African-American men consenting to participate in prostate cancer research. This article describes the complexity of recruitment issues and highlights strategies that enhance research participation.
Keywords: Research Subject Recruitment -- Methods; Health Status Disparities; Prostatic Neoplasms -- Prevention and Control; Human; Conceptual Framework; Churches; Culture; Public Spaces; Organizations; Purposive Sample; Practitioner's Office; Male; Adult; Descriptive Research; Descriptive Statistics; Snowball Sample; South Carolina

Participation in cancer clinical trials: race-, sex-, and age-based disparities. - Murthy VH; Krumholz HM; Gross CP; Murthy, Vivek H; Krumholz, Harlan M; Gross, Cary P (JAMA: Journal of the American Medical Association, 2004)
Context: Despite the importance of diversity of cancer trial participants with regard to race, ethnicity, age, and sex, there is little recent information about the representation of these groups in clinical trials.Objective: To characterize the representation of racial and ethnic minorities, the elderly, and women in cancer trials sponsored by the National Cancer Institute.Design, Setting, and Patients: Cross-sectional population-based analysis of all participants in therapeutic nonsurgical National Cancer Institute Clinical Trial Cooperative Group breast, colorectal, lung, and prostate cancer clinical trials in 2000 through 2002. In a separate analysis, the ethnic distribution of patients enrolled in 2000 through 2002 was compared with those enrolled in 1996 through 1998, using logistic regression models to estimate the relative risk ratio of enrollment for racial and ethnic minorities to that of white patients during these time periods.Main Outcome Measure: Enrollment fraction, defined as the number of trial enrollees divided by the estimated US cancer cases in each race and age subgroup.Results: Cancer research participation varied significantly across racial/ethnic and age groups. Compared with a 1.8% enrollment fraction among white patients, lower enrollment fractions were noted in Hispanic (1.3%; odds ratio [OR] vs whites, 0.72; 95% confidence interval [CI], 0.68-0.77; P<.001) and black (1.3%; OR, 0.71; 95% CI, 0.68-0.74; P<.001) patients. There was a strong relationship between age and enrollment fraction, with trial participants 30 to 64 years of age representing 3.0% of incident cancer patients in that age group, in comparison to 1.3% of 65- to 74-year-old patients and 0.5% of patients 75 years of age and older. This inverse relationship between age and trial enrollment fraction was consistent across racial and ethnic groups. Although the total number of trial participants increased during our study period, the representation of racial and ethnic minorities decreased. In comparison to whites, after adjusting for age, cancer type, and sex, patients enrolled in 2000 through 2002 were 24% less likely to be black (adjusted relative risk ratio, 0.76; 95% CI, 0.65-0.89; P<.001). Men were more likely than women to enroll in colorectal cancer trials (enrollment fractions: 2.1% vs 1.6%, respectively; OR, 1.30; 95% CI, 1.24-1.35; P<.001) and lung cancer trials (enrollment fractions: 0.9% vs 0.7%, respectively; OR, 1.23; 95% CI, 1.16-1.31; P<.001).Conclusions: Enrollment in cancer trials is low for all patient groups. Racial and ethnic minorities, women, and the elderly were less likely to enroll in cooperative group cancer trials than were whites, men, and younger patients, respectively. The proportion of trial participants who are black has declined in recent years.
Keywords: Cancer Patients; Clinical Trials; Research Subject Recruitment; Research Subjects; Adult; Age Factors; Aged; Confidence Intervals; Cross Sectional Studies; Ethnic Groups; Health Services Accessibility; Logistic Regression; Middle Age; National Cancer Institute (U.S.); Neoplasms -- Therapy; Odds Ratio; Pearson's Correlation Coefficient; Race Factors; Relative Risk; Sex Factors; Funding Source; Human

Participation rates in a case-control study: the impact of age, race, and race of interviewer. - Moorman PG; Newman B; Millikan RC; Tse CJ; Sandler DP; Moorman, P G; Newman, B; Millikan, R C; Tse, C K; Sandler, D P (Annals of Epidemiology, 1999)
Purpose: Despite concerns about declining participation rates in epidemiologic studies in recent years, relatively few papers have discussed obstacles to recruiting study participants or strategies for optimizing response rates. This report describes factors associated with nonparticipation in a population-based, case-control study of breast cancer and discusses ways to overcome barriers to participation.Methods: Contact and cooperation rates were calculated for participants in the Carolina Breast Cancer Study (CBCS), stratified by case status, age, race, and race of interviewer. Demographic and breast cancer risk factor characteristics of partial and full responders also were compared.Results: Contact rates and cooperation rates varied by case/control status and demographic characteristics. Contact rates were lower among controls, younger women, and black women. Cooperation rates were lower among controls, older women, and black cases. Cooperation rates were higher among both black and nonblack women when participants and interviewers were concordant on race.Conclusions: Obstacles to recruitment seem to differ among race and age subgroups, suggesting that recruitment strategies may need to be tailored to potential participants based upon demographic characteristics. Strategies have been implemented to improve response rates in this and other epidemiologic studies; however, additional research and innovation in this area are needed.
Keywords: Population-Based Case Control; Research Subject Recruitment -- Methods; Consumer Participation; Breast Neoplasms -- Epidemiology; Epidemiological Research; Registries, Disease; Random Sample; Interviews; Descriptive Statistics; Confidence Intervals; Patient Compliance; Race Factors; Age Factors; Adult; Middle Age; Aged; Female; Funding Source; Human

Partnering around cancer clinical trials (PACCT): study protocol for a randomized trial of a patient and physician communication intervention to increase minority accrual to prostate cancer clinical trials. - Eggly, Susan; Hamel, Lauren M.; Heath, Elisabeth; Manning, Mark A.; Albrecht, Terrance L.; Barton, Ellen; Wojda, Mark; Foster, Tanina; Carducci, Michael; Lansey, Dina; Ting Wang; Abdallah, Rehab; et al. (BMC Cancer, 2017)
Background: Cancer clinical trials are essential for testing new treatments and represent state-of-the-art cancer treatment, but only a small percentage of patients ever enroll in a trial. Under-enrollment is an even greater problem among minorities, particularly African Americans, representing a racial/ethnic disparity in cancer care. One understudied cause is patient-physician communication, which is often of poor quality during clinical interactions between African-American patients and non-African-American physicians. Partnering Around Cancer Clinical Trials (PACCT) involves a transdisciplinary theoretical model proposing that patient and physician individual attitudes and beliefs and their interpersonal communication during racially discordant clinical interactions influence outcomes related to patients' decisions to participate in a trial. The overall goal of the study is to test a multilevel intervention designed to increase rates at which African-American and White men with prostate cancer make an informed decision to participate in a clinical trial.Methods/design: Data collection will occur at two NCI-designated comprehensive cancer centers. Participants include physicians who treat men with prostate cancer and their African-American and White patients who are potentially eligible for a clinical trial. The study uses two distinct research designs to evaluate the effects of two behavioral interventions, one focused on patients and the other on physicians. The primary goal is to increase the number of patients who decide to enroll in a trial; secondary goals include increasing rates of physician trial offers, improving the quality of patient-physician communication during video recorded clinical interactions in which trials may be discussed, improving patients' understanding of trials offered, and increasing the number of patients who actually enroll. Aims are to 1) determine the independent and combined effects of the two interventions on outcomes; 2) compare the effects of the interventions on African-American versus White men; and 3) examine the extent to which patient-physician communication mediates the effect of the interventions on the outcomes.Discussion: PACCT has the potential to identify ways to increase clinical trial rates in a diverse patient population. The research can also improve access to high quality clinical care for African American men bearing the disproportionate burden of disparities in prostate and other cancers.Trial Registration: Clinical Trials.gov registration number: NCT02906241 (September 8, 2016).
Keywords: Physician-Patient Relations; Prostatic Neoplasms -- Drug Therapy; Minority Groups -- Psychosocial Factors; Human; White Persons -- Psychosocial Factors; Patient Selection; Prostatic Neoplasms -- Ethnology; Models, Theoretical; Male; Black Persons -- Psychosocial Factors; Communication; Consumer Participation; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Funding Source

Patient Navigation for Colonoscopy Completion: Results of an RCT. - DeGroff, Amy; Schroy, Paul C 3rd; Morrissey, Kerry Grace; Slotman, Beth; Rohan, Elizabeth A; Bethel, James; Murillo, Jennifer; Ren, Weijia; Niwa, Shelley; Leadbetter, Steven; Joseph, Djenaba (American Journal of Preventive Medicine, 2017)
Introduction: Colorectal cancer is a leading cause of cancer-related death in the U.S. Although screening reduces colorectal cancer incidence and mortality, screening rates among U.S. adults remain less than optimal, especially among disadvantaged populations. This study examined the efficacy of patient navigation to increase colonoscopy screening.Study Design: RCT.Setting/participants: A total of 843 low-income adults, primarily Hispanic and non-Hispanic blacks, aged 50-75 years referred for colonoscopy at Boston Medical Center were randomized into the intervention (n=429) or control (n=427) groups. Participants were enrolled between September 2012 and December 2014, with analysis following through 2015.Intervention: Two bilingual lay navigators provided individualized education and support to reduce patient barriers and facilitate colonoscopy completion. The intervention was delivered largely by telephone.Main Outcome Measure: Colonoscopy completion within 6 months of study enrollment.Results: Colonoscopy completion was significantly higher for navigated patients (61.1%) than control group patients receiving usual care (53.2%, p=0.021). Based on regression analysis, the odds of completing a colonoscopy for navigated patients was one and a half times greater than for controls (95% CI=1.12, 2.03, p=0.007). There were no differences between navigated and control groups in regard to adequacy of bowel preparation (95.3% vs 97.3%, respectively).Conclusions: Navigation significantly improved colonoscopy screening completion among a racially diverse, low-income population. Results contribute to mounting evidence demonstrating the efficacy of patient navigation in increasing colorectal cancer screening. Screening can be further enhanced when navigation is combined with other evidence-based practices implemented in healthcare systems and the community.
Keywords: Patient Navigation -- Methods; Colorectal Neoplasms; Health Screening -- Methods; Early Detection of Cancer -- Methods; Healthcare Disparities -- Statistics and Numerical Data; Academic Medical Centers -- Statistics and Numerical Data; Poverty; Male; Socioeconomic Factors; Middle Age; Colorectal Neoplasms -- Epidemiology; Colonoscopy -- Statistics and Numerical Data; Early Detection of Cancer -- Statistics and Numerical Data; Massachusetts; Health Screening -- Statistics and Numerical Data; Referral and Consultation -- Statistics and Numerical Data; Aged; Program Evaluation; Colorectal Neoplasms -- Prevention and Control; Incidence; Self Report; Female; Occult Blood; Patient Navigation -- Statistics and Numerical Data; Human; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials

Patient Perspectives on the Ethical Implementation of a Rapid Learning System for Oncology Care. - Jones, Rochelle D.; Sabolch, Aaron N.; Aakhus, Erin; Spence, Rebecca A.; Bradbury, Angela R.; Jagsi, Reshma (Journal of Oncology Practice, 2017)
Introduction A rapid learning system (RLS) of health care harnesses data generated from routine patient care to create a virtuous cycle of data collection and analysis for quality improvement and research. The success of such systems depends on understanding patient perspectives regarding the ethical issues that arise from the ongoing implementation of this transformative concept. Methods An interview guide was designed to evaluate patient perspectives to inform the ethical implementation of an oncology RLS. A purposively selected, diverse sample of 32 patients with cancer was recruited from two institutions to participate in semistructured, in-depth interviews for formal qualitative analysis. Results The extent to which respondents expressed discomfort with more permissive system features (less formal notification/consent, broader uses/users, inclusion of sensitive data) reflected their trust, which in turn seemed to vary by sociodemographic features. It was also influenced by their familiarity with technology and their attitudes and beliefs regarding privacy and the use of electronic medical records more generally. Distrust of insurers and the pharmaceutical industry led subjects to desire greater oversight and restriction of these potential users of the system. Subjects were most comfortable when doctors were the primary users, engaged patients directly in the notification and consent discussion, and oversaw the system. Conclusion Those actively developing RLSs should recognize the critical importance of trust and the key role that doctors will need to play in order for such systems to be successful and to ensure that their implementation is ethically palatable to the patients whose data are being included.
Keywords: Patient Care -- Methods; Ethics; Oncologic Care -- Education; Attitude of Health Personnel; Electronic Health Records; Human; Physicians -- Evaluation; Privacy and Confidentiality; Quality Improvement; Trust; Data Collection; Interviews; Patient Satisfaction -- Evaluation; Cancer Patients; Michigan; Geographic Locations; Research Subject Recruitment; Qualitative Studies; Data Analysis; Data Analysis Software; Health Beliefs; Male; Female; Middle Age; Aged; Aged, 80 and Over; White Persons; Black Persons; Hispanic Americans; Asians; Neoplasms -- Classification; Breast Neoplasms; Prostatic Neoplasms; Lung Neoplasms; Genetics

Patient trust in physician influences colorectal cancer screening in low-income patients. - Gupta, Shivani; Brenner, Alison T; Ratanawongsa, Neda; Inadomi, John M (American Journal of Preventive Medicine, 2014)
Background: Colorectal cancer (CRC) screening is effective but underutilized. Although physician recommendation is an important predictor of screening, considerable variation in CRC screening completion remains.Purpose: To characterize the influence of patient trust in care providers on CRC screening behavior.Methods: Data were collected as part of a cluster-randomized CRC screening intervention trial performed in the San Francisco Community Health Network from March 2007 to January 2012 (analysis, Spring 2012). All study participants received a recommendation to complete CRC screening from their primary care provider (PCP). Included participants were aged 50-79 years, not current with screening, and completed the Wake Forest Trust Scale (WFTS) measuring trust in PCPs and doctors in general. Primary outcome was CRC screening completion (colonoscopy or fecal occult blood testing) within 12 months following enrollment. Multivariable association adjusted for race/ethnicity, language, and other sociodemographics was estimated using generalized estimating equations with logit link and binomial distribution.Results: WFTS response was 70.3% (701). Most participants (83%) were Latino, Asian, or black. Most had income <$30,000 (96%) and public health insurance (86%). Higher trust in PCP was associated with screening completion (OR=1.11, 95% CI=1.03, 1.17), but trust in doctors was not (OR=1.02, 95% CI=0.82, 1.28). Race, language, and other sociodemographic factors were not significant in multivariable analysis.Conclusions: After controlling for traditional factors, trust in PCP remained the only significant driver of CRC screening completion in low-income patients. Interventions to promote CRC screening may be improved by including efforts to enhance patient trust in PCP.
Keywords: Colorectal Neoplasms -- Diagnosis; Health Screening -- Methods; Physician-Patient Relations; Trust; Aged; Colonoscopy -- Statistics and Numerical Data; Colorectal Neoplasms -- Psychosocial Factors; Female; Human; Male; Health Screening -- Psychosocial Factors; Middle Age; Occult Blood; Patient Attitudes; Poverty; California

Patient-reported outcomes in women with breast cancer enrolled in a dual-center, double-blind, randomized controlled trial assessing the effect of acupuncture in reducing aromatase inhibitor-induced musculoskeletal symptoms. - Bao, Ting; Cai, Ling; Snyder, Claire; Betts, Kelly; Tarpinian, Karineh; Gould, Jeff; Jeter, Stacie; Medeiros, Michelle; Chumsri, Saranya; Bardia, Aditya; Tan, Ming; Singh, Harvinder; et al. (Cancer (0008543X), 2014)
Background: Aromatase inhibitors (AIs) have been associated with decrements in patient-reported outcomes (PROs). The objective of this study was to assess whether real acupuncture (RA), compared with sham acupuncture (SA), improves PROs in patients with breast cancer who are receiving an adjuvant AI.Methods: Postmenopausal women with a stage 0 through III breast cancer who received an AI and had treatment-associated musculoskeletal symptoms were randomized to receive 8 weekly RA versus SA in a dual-center, randomized controlled trial. The National Surgical Adjuvant Breast and Bowel Project (NSABP) menopausal symptoms questionnaire, the Center for Epidemiological Studies Depression (CESD) scale, the Hospital Anxiety and Depression Scale (HADS), the Pittsburgh Sleep Quality Index (PSQI), the hot flash daily diary, the Hot Flash-Related Daily Interference Scale (HFRDI), and the European quality-of-life survey (EuroQol) were used to assess PROs at baseline and at 4weeks, 8 weeks, and 12 weeks.Results: The intention-to-treat analysis included 23 patients in the RA arm and 24 patients in the SA arm. There were no significant differences in baseline characteristics between the 2 groups. Compared with baseline, scores in the RA arm improved significantly at week 8 on the CESD (P = .022), hot flash severity (P = .006), hot flash frequency (P = .011), the HFRDI (P = .014), and NSABP menopausal symptoms (P = .022); scores in the SA arm improved significantly on the EuroQol (P = .022),the HFRDI (P = .043), and NSABP menopausal symptoms (P = .005). Post-hoc analysis indicated that African American patients (n = 9) benefited more from RA than SA compared with non-African American patients (n = 38) in reducing hot flash severity (P < .001) and frequency (P < .001) scores.Conclusions: Both RA and SA were associated with improvement in PROs among patients with breast cancer who were receiving AIs, and no significant difference was detected between arms. Racial differences in response to acupuncture warrant further study.
Keywords: Acupuncture; Aromatase Inhibitors -- Adverse Effects; Bone Diseases -- Prevention and Control; Breast Neoplasms -- Therapy; Muscular Diseases -- Prevention and Control; Adult; Aged; Aged, 80 and Over; Bone Diseases -- Chemically Induced; Breast Neoplasms -- Psychosocial Factors; Double-Blind Studies; Female; Human; Middle Age; Muscular Diseases -- Chemically Induced; Psychological Tests; Quality of Life; Questionnaires; Scales

Pharmacist intervention in colorectal cancer screening initiative. - Holle, Lisa M.; Levine, Joel; Buckley, Thomas; White, C. Michael; White, Cedric; Hadfield, Matthew J. (Journal of the American Pharmacists Association: JAPhA, 2020)
Objectives: To assess the novel approach of using the community pharmacist as the primary health care team member to facilitate colorectal cancer (CRC) risk counseling and screening in socioeconomically disadvantaged populations.Setting: A collaborative effort between the UConn Health Colon Cancer Prevention Program and UConn School of Pharmacy in conjunction with large independent chain pharmacies (medium to medium-high volume) located in metropolitan areas of Connecticut, including Hartford, Bridgeport, New Haven, and Stamford. Pharmacies located in hospitals, across the street from a large physician practice, or within the community.Practice Description: The study involved 2 phases. The first phase involved education and training for community pharmacists regarding counseling approaches for patients on the topic of CRC. The second phase of the study involved patient recruitment and counseling with subsequent fecal immunohistochemical testing (FIT).Practice Innovation: A community pharmacist provided face-to-face counseling on CRC risk factor reduction and provided CRC screening to patients who were without insurance or underinsured. No CRC screening or education program existed beforehand.Evaluation: A target sample size of 60 participants was needed with a type 1 error rate of 5% and a power of 80%. Exploration of variables using multivariate logistic regression model included any variable with a univariate P < 0.2. Multivariate P values < 0.05 were considered independent predictors.Results: After approaching 312 consumers, 16 of them consented to the study. The majority of participants (88%) were African American or Latino, and 69% were currently unemployed. Eight participants agreed to complete FIT, and 88% of participants completed FIT correctly. Only 1 positive FIT result was observed, but a subsequent colonoscopy was negative. Of the 12 questions that assessed baseline CRC knowledge in the initial survey, 16 participants answered an average of 2.6 (range, 0-6, SD, 1.6) questions incorrectly. Only 4 participants completed the follow-up survey of CRC knowledge and program satisfaction; thus, exploration of variables was not conducted. Patients indicated high satisfaction with the program of education and FIT dispensing.Conclusion: This study faced difficulty in recruiting pharmacists to participate, with the main reason being lack of compensation and disruption to workflow. Patient participation in the trial was also low because of a lack of time or interest in participation. Of the patients who did participate, the level of satisfaction in having the pharmacist speak to them about CRC screening was high. This service is an excellent example of how the pharmacist can provide a more accessible, convenient, and responsive approach to patients' needs while improving health equity. Future studies that employ a revenue model to build the infrastructure and capacity necessary to offer this service efficiently and consistently are needed.

Phase II Trial of Abiraterone Acetate Plus Prednisone in Black Men With Metastatic Prostate Cancer. - Tsao, Che‐Kai; Sfakianos, John; Liaw, Bobby; Gimpel‐Tetra, Kiev; Kemeny, Margaret; Bulone, Linda; Shahin, Mohammad; Oh, William Kyu; Galsky, Matthew David (Oncologist, 2016)
Lessons Learned: The safety and activity findings of abiraterone acetate plus prednisone treatment in black men with mCRPC were similar to results from previously conducted studies with largely white populations.Poor trial accrual continues to be a challenge in black men with mCRPC and further efforts are needed to address such underrepresentation. Background.: Self‐identified black men have higher incidence and mortality from prostate cancer in the United States compared with white men but are dramatically underrepresented in clinical trials exploring novel therapies for metastatic castration‐resistant prostate cancer (mCRPC). Methods.: Black men with mCRPC were treated with abiraterone acetate (AA), 1,000 mg daily, and prednisone (P), 5 mg twice daily. The primary objective was to determine antitumor activity (defined by a ≥30% decline in prostate‐specific antigen [PSA] level) and to correlate germline polymorphisms in androgen metabolism genes with antitumor activity. Secondary objectives included determining safety, post‐treatment changes in measurable disease, and time to disease progression. Results.: From April 2013 to March 2016, a total of 11 black men were enrolled and received AA plus P (AA+P); 7 of 10 evaluable patients were docetaxel naive. Post‐treatment declines in PSA level of ≥30% were achieved in 90% of patients. The side effect profile was consistent with prior clinical trials exploring AA+P in mCRPC. Due to poor accrual, the study was closed prematurely with insufficient sample size for the planned pharmacogenetic analyses. Conclusion.: In this small prospective study terminated for poor accrual, the safety and activity of AA+P in black men with mCRPC was similar to that reported in prior studies exploring AA in largely white populations. Further efforts are needed to address underrepresentation of black men in mCRPC trials. 作者总结 经验 • 醋酸阿比特龙联合泼尼松治疗转移性去势抵抗性前列腺癌 (mCRPC) 黑人男性患者的安全性和有效性与既往主要在白人群体中开展的研究结果相似。 • mCRPC 临床试验中黑人男性患者入组不理想仍然是该人群研究的一大难题, 有必要进一步努力解决这一人群代表性不足的问题。 摘要 背景. 美国黑人男性前列腺癌的发病率和死亡率均高于白人男性, 但在转移性去势抵抗性前列腺癌 (mCRPC) 新治疗研发的临床试验中, 黑人男性的代表性却明显不足。 方法. 患有mCRPC的黑人男性接受醋酸阿比特龙 (AA) 1 000 mg每日1次和泼尼松 (P) 5 mg每日2次治疗。主要目的为确定该治疗方案的抗肿瘤活性[定义为前列腺特异性抗原 (PSA) 水平下降≥30%], 以及雄激素代谢基因生殖系多态性与抗肿瘤活性之间的相关性。次要目的包括确定安全性、可测量病灶在治疗后的改变, 以及至疾病进展时间。 结果. 从2013年4月至2016年3月, 研究共入组11例黑人男性接受AA+P治疗, 7/10例可评价患者未接受过多西他赛治疗。90%的患者治疗后PSA水平下降≥30%。副作用特征与既往研究AA+P治疗mCRPC的临床试验情况一致。研究因招募入组极不理想而提前关闭, 计划的药物遗传学分析样本量不足。 结论. 本项小型前瞻性研究因招募入组过慢而终止, AA+P在mCRPC黑人男性患者中的安全性和有效性与既往主要在白人男性中开展的AA研究相似。有必要进一步努力解决黑人男性在mCRPC临床试验中代表性不足的问题。The Oncologist 2016;21:1414–1415
Keywords: Abiraterone Acetate -- Therapeutic Use; Prednisone -- Therapeutic Use; Drug Therapy, Combination; Black Persons; Prostatic Neoplasms -- Drug Therapy; Neoplasm Metastasis -- Drug Therapy; Human; Clinical Trials; Abiraterone Acetate -- Administration and Dosage; Prednisone -- Administration and Dosage; Prostate-Specific Antigen; Androgens -- Metabolism; Sample Size; Female; Polymorphism, Genetic; Pilot Studies; Prospective Studies; Neoplasm Staging; Middle Age; Aged

Phase II trial of bevacizumab (B) and oral satraplatin (S) and prednisone in docetaxel pretreated metastatic castrate resistant prostate cancer (CRPC). - Vaishampayan, U N; Heilbrun, L K; Heath, E I; Smith, D W; Dickow, B; Baranowski, K; Powell, I; Fontana, J (Journal of Clinical Oncology, 2009)
e16028 Background: In metastatic CRPC, second line therapy after docetaxel, remains a currently unmet need. Based on the efficacy and tolerability of S and B in prostate cancer, and the clinical synergy noted between chemotherapy and B, a phase II trial of the combination was conducted.Methods: Metastatic CRPC patients, with prior docetaxel based chemotherapy were eligible to receive S 80 mg/m2 orally for days 1-5, and B 10 mg/kg on day 1, and 15mg/kg on day 15 of each 35 day cycle. Prednisone was administered at a dose of 5 mg twice daily. Response was assessed every 2 cycles. Toxicity was assessed weekly during cycle 1 and on days 1 and 15 of each subsequent cycle. Primary endpoint was time to progression defined as a skeletal event, new areas of metastases on bone scans or per RECIST criteria for measurable disease.Results: 19 of 28 patients have been enrolled to date; 7 African American and 12 Caucasian,, with median age of 68.5 years and median pretherapy PSA of 137.8 ng/mL (range 16.8-994 ng/mL). 7 (44%) had bone pain, Gleason score of 7 and ≥ 8 in 7 and 12 patients respectively. Measurable disease progression was noted in 5 patients, bone scan progression in 6 patients, progression of both in 3 patients, and PSA only progression in 5 patients. 76 cycles have been administered; 7 patients continued on therapy beyond 6 cycles. The only grade 4 toxicity noted was pulmonary embolism in 2 patients, after 2 and 6 cycles of therapy. Grade 3 neutropenia, gastrointestinal toxicity, and electrolyte abnormalities were noted in 1 patient each. There were no treatment related deaths. 16/19 patients are response evaluable. 7 patients had a PSA decline of which 4 patients had a ≥30% PSA decline. 3 of 6 patients had a measurable disease response. 11 of 16 patients have progressed to date after median of 6 cycles of therapy. Time to progression and survival data will be reported.Conclusions: The combination was well tolerated, and revealed preliminary evidence of clinical efficacy in docetaxel pretreated metastatic CRPC. [Table: see text].

Phase II Trial of Carboplatin, Everolimus, and Prednisone in Metastatic Castration-resistant Prostate Cancer Pretreated With Docetaxel Chemotherapy: A Prostate Cancer Clinical Trial Consortium Study. - Vaishampayan, Ulka; Shevrin, Daniel; Stein, Mark; Heilbrun, Lance; Land, Susan; Stark, Karri; Li, Jing; Dickow, Brenda; Heath, Elisabeth; Smith, Daryn; Fontana, Joseph (Urology, 2015)
Objective: To conduct a phase II trial of the combination of carboplatin, prednisone, and everolimus in metastatic castrate-resistant prostate cancer (mCRPC) as mTOR inhibition can overcome resistance to chemotherapy in prostate cancer.Methods: Patients with progressive mCRPC pretreated with docetaxel-based regimen were eligible. Performance status of 0-1 and adequate bone marrow, renal, and liver function were required. Primary end point was time to progression. Treatment consisted of carboplatin (starting dose equal to area under the curve (AUC of 5) intravenously every 21 days along with oral everolimus 5 mg once daily and prednisone 5 mg twice daily.Results: Twenty-six patients were enrolled with median age of 69 years with 8 patients of African American origin. Grade 3 or 4 thrombocytopenia or neutropenia in 4 of 6 initial patients required dose adjustment of carboplatin to AUC of 4 for subsequent patients. There were no pharmacokinetic interactions between carboplatin and everolimus. The median time to progression was 2.5 months (90% confidence interval [CI], 1.8-4.3 months), and median overall survival was 12.5 months (90% CI, 7.7-18.7 months). Of 10 patients, 8 that demonstrated positive nuclear phosphorylated AKT (pAKT) staining on immunohistochemistry progressed within 9 weeks, whereas 2 patients with negative staining continued without progression for prolonged durations of 30 and 48 weeks. TSC1 gene mutations did not correlate with clinical outcome.Conclusion: The addition of the mTOR inhibitor everolimus to carboplatin demonstrated minimal clinical efficacy in metastatic prostate cancer. pAKT testing warrants further evaluation as a predictive marker of response to everolimus therapy.
Keywords: Antineoplastic Agents, Combined -- Therapeutic Use; Prostatic Neoplasms, Castration-Resistant -- Pathology; Prostatic Neoplasms, Castration-Resistant -- Drug Therapy; Adenocarcinoma -- Drug Therapy; Adenocarcinoma; Disease Progression; Neoplasm Metastasis; Hydrocarbons -- Administration and Dosage; Male; Survival; Aged; Carboplatin -- Pharmacokinetics; Prednisone -- Administration and Dosage; Carboplatin -- Administration and Dosage; Human; Phosphorylation; Proteins; Prostate-Specific Antigen -- Blood; Antineoplastic Agents, Combined -- Adverse Effects; Transferases -- Analysis; Transferases -- Metabolism; Prostatic Neoplasms, Castration-Resistant; Clinical Trials; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Funding Source

Physical Activity Maintenance Following Home-Based, Individually Tailored Print Interventions for African American Women. - Pekmezi, Dori; Ainsworth, Cole; Desmond, Renee; Pisu, Maria; Williams, Victoria; Wang, Kaiying; Holly, Taylor; Meneses, Karen; Marcus, Bess; Demark-Wahnefried, Wendy (Health Promotion Practice, 2020)
African American women report low participation in physical activity and are disproportionately burdened by related conditions (obesity, breast, and colon cancer). Physical activity interventions have shown promising results among African American women, but most studies in this area have focused on short-term increases. More enduring changes in health behavior will be needed to eliminate existing health disparities. Thus, the current study examined 12-month physical activity and psychosocial outcomes from a pilot randomized controlled trial (N = 84) of a Home-based Individually tailored Physical activity Print (HIPP) intervention for African American women in the Deep South. Retention was 77.4% at 12 months. HIPP participants increased self-reported moderate-to-vigorous physical activity from 35.1 minutes/week (standard deviation [SD] = 47.8) at baseline to 124 minutes/week (SD = 95.5) at 12 months, compared with the wellness contact control participants who reported increases from 48.2 minutes/week (SD = 51.3) to 102.5 minutes/week (SD = 94.5) over 12 months (between-group p >.05). Results indicate that modest improvements in moderate-to-vigorous physical activity and related psychosocial variables occurred during the active intervention phase (months 0-6) and were sustained during the tapered maintenance period (months 6-12). Low-cost, high-reach, home-based strategies have great potential for supporting sustained participation in physical activity and achieving long-term health benefits among African American women in the Deep South.
Keywords: Black Persons; Women; Health Behavior; Behavioral Changes; Physical Activity; Home Rehabilitation; Psychological Well-Being; Health Promotion -- Methods; Human; Health Status Disparities; Pilot Studies; Randomized Controlled Trials; Descriptive Statistics; Random Assignment; Patient Centered Care; Individualized Medicine; Obesity -- Prevention and Control; Neoplasms -- Prevention and Control; Minority Groups

Physiologic vasomotor symptoms are associated with verbal memory dysfunction in breast cancer survivors. - Fogel, Jessica; Rubin, Leah H.; Kilic, Ece; Walega, David R.; Maki, Pauline M. (Menopause (10723714), 2020)
Objective: Vasomotor symptoms (VMS), sleep disturbance, and cognitive complaints are common among women with a history of breast cancer and contribute to decreased quality of life. Studies in healthy women showed an association between verbal memory performance and physiologic VMS measured with ambulatory skin conductance monitors but not with VMS by self-report. We hypothesized that we would find a similar association in women with breast cancer.Methods: Participants included 30 female breast cancer survivors (mean age 52.7 y; 26.7% African-American) with moderate-to-severe VMS enrolled in a larger clinical trial of a nonhormonal intervention for VMS. At baseline, participants completed assessments of physiologic VMS, actigraphy-based assessments of sleep, questionnaires about mood, and two tests of verbal memory - Logical Memory (LM) and the California Verbal Learning Test (CVLT). Using baseline data, we conducted multivariate regression analyses to examine the association between VMS and memory, controlling for sleep and other factors.Results: On average, women reported 46% of total physiologic VMS. A higher frequency of physiologic VMS - but not reported VMS - was significantly associated with lower scores on the California Verbal Learning Test short-delay free recall (r[28] = -0.41, P = 0.03), long-delay free recall (r[28] = -0.42, P = 0.03), and total clustering, (r[28] = -0.39, P = 0.04). These associations were independent of sleep, mood, and other factors.Conclusions: Independent of their effect on sleep, VMS may be a modifiable contributor to memory difficulties in women with breast cancer. These findings underscore the importance of objective measurement of VMS in cognitive studies. : Video Summary:http://links.lww.com/MENO/A623.

Population- and community-based recruitment of African Americans and Latinos: the San Francisco Bay Area Lung Cancer Study. - Cabral DN; Nápoles-Springer AM; Miike R; McMillan A; Sison JD; Wrensch MR; Pérez-Stable EJ; Wiencke JK (American Journal of Epidemiology, 2003)
Empiric data on recruitment of minorities into clinical or population studies are limited. The authors evaluated population- and community-based recruitment methods in a 1998-2001 case-control study of lung cancer among African Americans and Latinos. For lung cancer cases in the San Francisco Bay Area of California, rapid case ascertainment by the tumor registry combined with telephone screening identified 470 (9%) African Americans and 262 (5%) Latinos. When random digit dialing (RDD) and Health Care Financing Administration (HCFA) records failed to yield adequate numbers of controls in appropriate age-gender-ethnicity groups, community-based recruitment methods were used. Demographic characteristics and behavioral and occupational risk factors for controls, by recruitment method, were compared with those for lung cancer cases to evaluate potential bias. The average numbers of hours spent per control recruited were 18.6 for RDD, 11.4 for HCFA, and less than 1 for the community-based methods. The prevalence of smoking-related lung cancer risk factors was significantly higher among African-American community-based controls than for those identified through RDD (p < 0.005). Compared with HCFA controls, Latino RDD controls reported significantly higher cumulative smoking exposure (p < 0.05). Further assessment of strategies for successful recruitment of minority participants into epidemiologic studies is warranted.
Keywords: Black Persons; Hispanic Americans; Lung Neoplasms -- Epidemiology; Research Subject Recruitment; Aged; Analysis of Variance; Bias (Research); California; Case Control Studies; Descriptive Statistics; Epidemiological Research; Female; Interviews; Logistic Regression; Male; Middle Age; P-Value; Funding Source; Human

Post-treatment symptoms among ethnic minority breast cancer survivors. - Eversley R; Estrin D; Dibble S; Wardlaw L; Pedrosa M; Favila-Penney W (Oncology Nursing Forum, 2005)
PURPOSE/OBJECTIVES: To determine racial and ethnic differences in the range and number of post-treatment symptoms among women who have undergone surgical and postsurgical treatment for breast cancer. DESIGN: Retrospective study. SETTING: Community-based social services agency and public health clinic. Methods: Face-to-face interview of 116 women who had undergone breast cancer surgery. SAMPLE: Primarily low-income women in an urban area in northern California. Participants were recruited via posted flyers regarding the study. MAIN RESEARCH VARIABLES: Outcomes (depression, fatigue, pain, and swelling from lymphedema) and demographics (ethnicity, age, income, insurance, education, and marital status). FINDINGS: The typical participant was 47 years old, had 12 years of education, and was a parent (74%), unmarried (67%), heterosexual (88%), uninsured (68%), and employed (66%). Thirty percent were Caucasian, 30% African American, 25% Latina, and 15% women of other ethnic backgrounds. African American women and Latinas reported increased rates of pain and an increased number of symptoms. Latinas also reported higher rates of fatigue and depression. In multivariate analyses, an increased number of symptoms were associated with decreased income, with receiving chemotherapy, with having a mastectomy, and with Latina ethnicity. CONCLUSIONS: These data suggest an increased rate of post-treatment symptoms experienced by low-income and ethnic minority women. IMPLICATIONS FOR NURSING: A need exists for affordable, culturally appropriate symptom management interventions. Nursing will have a vital role in designing, testing, and offering such interventions.
Keywords: Breast Neoplasms; Cancer Survivors; Minority Groups; Treatment Outcomes -- Evaluation; Analysis of Variance; Black Persons; Breast Neoplasms -- Drug Therapy; Breast Neoplasms -- Radiotherapy; Breast Neoplasms -- Surgery; Brief Pain Inventory; California; Cancer Fatigue; Center for Epidemiological Studies Depression Scale; Chi Square Test; Clinical Assessment Tools; Coefficient Alpha; Convenience Sample; Data Analysis Software; Depression; Descriptive Research; Education, Continuing (Credit); Female; Funding Source; Hispanic Americans; Interviews; Middle Age; Postoperative Pain; Psychological Tests; Regression; Research Subject Recruitment; Retrospective Design; White Persons; Human

Predictors of biospecimen donation in the Black Women's Health Study. - Adams-Campbell, Lucile; Dash, Chiranjeev; Palmer, Julie; Wiedemeier, Manuela; Russell, Cordelia; Rosenberg, Lynn; Cozier, Yvette; Adams-Campbell, Lucile L; Palmer, Julie R; Wiedemeier, Manuela V; Russell, Cordelia W; Cozier, Yvette C (Cancer Causes & Control, 2016)
Purpose: Although African-Americans experience higher cancer morbidity and mortality rates compared to their White counterparts, their participation in biospecimen research is lower than that of their white peers. This study investigated the prevalence and predictors of biospecimen donation in a large, cohort study of Black women.Methods: The BWHS is a follow-up study of U.S. Black women aged 21-69 years enrolled through postal health questionnaires. Between January 2004 and December 2007, participants were sent a consent form with a postage-paid return envelope, and a mouthwash collection kit. Univariate and age- and educational status-adjusted logistic regression models were used to estimate the association of socio-demographic, lifestyle and medical factors with donation of biospecimens.Results: Buccal cells with consent forms were obtained from 26,790 women, for a response rate of 51 %. The strongest predictors of biospecimen donation were age: response increased from 48.6 % among those aged <40 to 63.1 % among those aged 60 and older [RR 1.30 (95 % CI 1.27, 1.34)]; multivitamin use [RR (95 % CI) 1.32 (1.30, 1.34)]; physician visit in the previous 2 years [RR (95 % CI) 1.61 (1.58, 1.65)], and a history of breast [RR (95 % CI) 1.59 (1.56, 1.63)], colon [RR (95 % CI) 1.18 (1.16, 1.20)], and cervical [RR (95 % CI) 1.63 (1.60, 1.67)] cancer screening.Conclusions: We found that 51 % of women in the geographically-dispersed Black Women's Health Study cohort were willing to provide mouthwash samples to be used for genetic analyses. The response in this study is encouraging given published findings of low overall participation rates of African-Americans in genetic studies.
Keywords: Early Detection of Cancer -- Utilization; Black Persons -- Statistics and Numerical Data; Health Behavior; Patient Selection; Young Adult; Middle Age; Breast Neoplasms -- Diagnosis; Prospective Studies; Aged; Cervix Neoplasms -- Diagnosis; Women's Health; Female; Logistic Regression; Sequence Analysis; Colonic Neoplasms -- Diagnosis; Adult; Tissue Banks; Specimen Handling; Age Factors; Vitamins -- Therapeutic Use; Human; Funding Source

Prevalence and Predictors of Low Serum 25-Hydroxyvitamin D among Female African-American Breast Cancer Survivors. - Sheean, Patricia; Arroyo, Claudia; Woo, Jennifer; Schiffer, Linda; Stolley, Melinda (Journal of the Academy of Nutrition & Dietetics, 2018)
Background African-American breast cancer survivors commonly demonstrate low serum 25-hydroxyvitamin D (25(OH)D). Decreased cutaneous conversion, high levels of adiposity, and even breast cancer treatment may influence vitamin D status. Previous investigations have analyzed African-American women in aggregate with other breast cancer survivors and have not comprehensively addressed these influential factors. Objectives To determine the prevalence of low serum 25(OH)D in an exclusively African-American cohort of female breast cancer survivors with overweight/obesity and to evaluate the role of ultraviolet (UV) light exposure, body composition, and dietary sources of vitamin D on serum 25(OH)D levels. Design Cross-sectional. Participants Pre- and postmenopausal African-American breast cancer survivors (n=244) were recruited from various neighborhoods in the city of Chicago, IL, between September 2011 and September 2014 for a larger weight loss trial. Main outcome measures Demographic, clinical, anthropometric (body mass index [calculated as kg/m 2 ], waist circumference, and hip circumference), blood specimen, dietary intake (food frequency questionnaire), and sun behavior data were collected by trained study personnel before trial participation. Dual-energy x-ray absorptiometry was used to quantify adiposity (total, percentage, regional, visceral) and lean mass. Serum 25(OH)D was used as the biomarker reflective of vitamin D status. Statistical analyses Mean (±standard deviation), frequencies, and multivariate linear regression modeling. Results The average participant was 57.4 years old (±10.0), 6.9 years (±5.2) from initial breast cancer diagnosis with a body mass index of 36.2 (±6.2). The majority of participants (60%) reported habitual oral vitamin D supplementation with mean intake of 327 IU (±169). Vitamin D deficiency was prevalent in 81% and 43%, when the cut points of the Endocrine Society (<30 ng/mL or <75 nmol/L) and the Institute of Medicine (<20 ng/mL or <50 nmol/L) were applied, respectively. A multivariate model adjusting for age, seasonality of blood draw, total energy intake, use of supplemental vitamin D, darker skin pigmentation, breast cancer stage, and waist-to-hip ratio was able to explain 28.8% of the observed variance in serum 25(OH)D concentrations. No significant associations were detected for body mass index or any dual-energy x-ray absorptiometry measures of body composition. Conclusions Considering the number of women who endorsed use of vitamin D supplementation, the prevalence of vitamin D deficiency among these African-American breast cancer survivors was high. Vitamin D supplementation, sun behavior, and waist-to-hip ratio may serve as future points of intervention to improve the vitamin D status of this minority survivor population.
Keywords: Black Persons; Vitamin D Deficiency -- Epidemiology; Breast Neoplasms; Cancer Survivors; Obesity; Human; Female; Ultraviolet Rays; Body Composition; Diet; Vitamin D -- Blood; Cross Sectional Studies; Illinois; Prospective Studies; Nutritional Assessment; Questionnaires; Sunlight; Environmental Exposure; Absorptiometry, Photon; Linear Regression; Multivariate Analysis; Middle Age; Aged; Descriptive Statistics; Dietary Supplementation; Epidemiological Research

Prevalence of and Risk Factors for Anal High-grade Squamous Intraepithelial Lesions in Women Living with Human Immunodeficiency Virus. - Stier, Elizabeth A; Lensing, Shelly Y; Darragh, Teresa M; Deshmukh, Ashish A; Einstein, Mark H; Palefsky, Joel M; Jay, Naomi; Berry-Lawhorn, J Michael; Wilkin, Timothy; Wiley, Dorothy J; Barroso, Luis F; Cranston, Ross D; et al. (Clinical Infectious Diseases, 2020)
Background Women living with human immunodeficiency virus (WLHIV) have disproportionately high rates of squamous cell carcinoma of the anus compared with the general population of women. Anal high-grade squamous intraepithelial lesions (HSILs) precede anal cancer, and accurate studies of HSIL prevalence among WLHIV in the United States are lacking. Methods The AIDS Malignancy Consortium 084 study was a multicenter national trial to evaluate the prevalence of and risk factors for anal HSIL in a US cohort. Eligible participants were WLHIV aged ≥18 years with no history of anal HSIL. Study participants had an examination including collection of cervical/vaginal and anal specimens, followed by high-resolution anoscopy with biopsy. Results We enrolled 256 women with evaluable anal pathology. The mean age was 49.4 years, 64% women were non-Hispanic black, 67% were former or current smokers, and 56% reported ever having anal sex with a man. The median CD4 T-cell count was 664 cells/μL. The prevalence of anal histologic HSIL (hHSIL) was 27% (95% confidence interval [CI], 22%–33%). There was a strong concordance (240/254) between local and consensus pathologists for hHSIL vs less than hHSIL (κ = 0.86 [95% CI,.79–.93]). Current CD4 count of ≤200 cells/μL was the strongest predictor of consensus anal hHSIL diagnosis (adjusted odds ratio [aOR], 10.34 [95% CI, 3.47–30.87]). History of anoreceptive intercourse was also associated with hHSIL (aOR, 2.44 [95% CI, 1.22–4.76]). Conclusions The prevalence of anal hHSIL in WLHIV in the United States was 27% in this study where all participants received high-resolution anoscopy and biopsy.
Keywords: Carcinoma, Squamous Cell -- Risk Factors; Neoplasia, Anal Intraepithelial -- Risk Factors; HIV-Positive Persons; Women's Health -- United States; Neoplasia, Anal Intraepithelial -- Epidemiology -- United States; Human; United States; Anus Neoplasms -- Diagnosis; Minimally Invasive Procedures; Middle Age; Confidence Intervals; Anus -- Anatomy and Histology; Biopsy

Proactive versus reactive recruitment to a physical activity intervention for breast cancer survivors: Does it matter? - Zhou, Eric S; Dunsiger, Shira I; Pinto, Bernardine M (Clinical Trials, 2013)
Keywords: Research Subject Recruitment -- Methods; Cancer Survivors; Breast Neoplasms; Physical Activity; Clinical Trials; Human; Female; Socioeconomic Factors; Center for Epidemiological Studies Depression Scale; Clinical Assessment Tools; Psychological Tests; Data Analysis Software; T-Tests; Middle Age; White Persons; Black Persons; Education; Funding Source

Promoting informed decision making: evaluating a community-based Prostate Health Awareness program. - Bridge PD; Berry-Bobovski LC; Gallagher RE (Journal of Cancer Education, 2004)
BACKGROUND: For health educators, the controversy surrounding routine prostate cancer screening provides curriculum development and delivery challenges. The purpose of this study was to evaluate a community-based prostate health awareness program. METHODS: Using a pretest-posttest design, participants were recruited from community-based organizations to assess the effectiveness of the program in the areas of knowledge gain, short-term intentions, and changing prostate health behaviors. RESULTS: Many of the participants reported having been tested for prostate cancer, yet there was a lower than expected pretest knowledge base. There were significant increases in knowledge on the posttest and some impact on short-term intentions and behavior. DISCUSSION: A community-based prostate health awareness program prior to the patient-physician encounter can assist health-care professionals in the education process and give men the tools to make an informed decision.
Keywords: Cancer Screening; Health Behavior; Health Education; Health Knowledge; Prostatic Neoplasms -- Prevention and Control; Asians; Behavioral Changes; Black Persons; Coefficient Alpha; Convenience Sample; Curriculum; Descriptive Statistics; Educational Status; Evaluation Research; Funding Source; Health Promotion; Hispanic Americans; Internal Consistency; Male; Middle Age; P-Value; Pretest-Posttest Design; Program Evaluation; Research Instruments; Suburban Areas; Surveys; Urban Areas; White Persons; Wilcoxon Signed Rank Test; Human

Prospective approach to breast cancer risk prediction in African American women: the black women's health study model. - Boggs, Deborah A; Rosenberg, Lynn; Adams-Campbell, Lucile L; Palmer, Julie R (Journal of Clinical Oncology, 2015)
Purpose: Breast cancer risk prediction models have underestimated risk for African American women, contributing to lower recruitment rates in prevention trials. A model previously developed for African American women was found to underestimate risk in the Black Women's Health Study (BWHS).Methods: We developed a breast cancer risk model for African American women using relative risks derived from 10 years of follow-up of BWHS participants age 30 to 69 years at baseline. Using the subsequent 5 years of follow-up data, we evaluated calibration as the ratio of expected to observed number of breast cancers and assessed discriminatory accuracy using the concordance statistic.Results: The BWHS model included family history, previous biopsy, body mass index at age 18 years, age at menarche, age at first birth, oral contraceptive use, bilateral oophorectomy, estrogen plus progestin use, and height. There was good agreement between predicted and observed number of breast cancers overall (expected-to-observed ratio, 0.96; 95% CI, 0.88 to 1.05) and in most risk factor categories. Discriminatory accuracy was higher for women younger than age 50 years (area under the curve [AUC], 0.62; 95% CI, 0.58 to 0.65) than for women age ≥ 50 years (AUC, 0.56; 95% CI, 0.53 to 0.59). Using a 5-year predicted risk of 1.66% or greater as a cut point, 2.8% of women younger than 50 years old and 32.2% of women ≥ 50 years old were classified as being at elevated risk of invasive breast cancer.Conclusion: The BWHS model was well calibrated overall, and the predictive ability was best for younger women. The proportion of women predicted to meet the 1.66% cut point commonly used to determine eligibility for breast cancer prevention trials was greatly increased relative to previous models.
Keywords: Breast Neoplasms -- Epidemiology; Breast Neoplasms -- Ethnology; Adult; Black Persons; Aged; Pharmacokinetics; Breast Neoplasms -- Diagnosis; Calibration; Data Analysis, Statistical; Female; Human; Incidence; Middle Age; Models, Theoretical; Prospective Studies; Reproducibility of Results; Risk Assessment; Women's Health

Prostate cancer community collaboration and partnership: education, awareness, recruitment, and outreach to southern African-American males. - Hughes GD; Sellers DB; Fraser L Jr.; Teague R; Knight BN (Journal of Cultural Diversity, 2007)
Prostate cancer is a significant health problem for African-American men intensified by low participation in screenings, clinical trials, and prospective cohort studies. Ten focus groups were conducted with African-American males and their female partners/spouses. Perceptions and knowledge about prostate cancer, as well as willingness to participate in screening and research studies were measured. Participants had a basic level of knowledge about prostate cancer, and the importance of education was a unified theme. Dialogue with targeted African-American men and their partners/spouses may increase awareness and retention in medical research, while influencing health promotion, education and behavior.
Keywords: Black Persons; Health Knowledge; Patient Attitudes; Prostatic Neoplasms -- Ethnology; Audiorecording; Cancer Screening; Female; Focus Groups; Interviews; Male; Mississippi; Professional-Patient Relations; Prostatic Neoplasms -- Prevention and Control; Research Subjects; Spouses; Trust; Human

Prostate cancer education in African American churches. - Weinrich S; Holdford D; Boyd M; Creanga D; Cover K; Johnson A; Frank-Stromborg M; Weinrich M (Public Health Nursing, 1998)
The use of churches as recruitment sites of African Americans into health promotion activities is a popular theme in the 1990s literature. This research measured the impact of previous exposure to cancer on participation in an educational program and a free prostate cancer screening. Cues to action from the Health Belief Model provided the conceptual framework. Over 500 men attended a prostate cancer educational program at their church. Men who participated in the educational program and completed the questionnaire were given a voucher that they could take to their doctor of choice for a free prostate cancer examination. Having a member of the congregation who was previously diagnosed with cancer was a significant cue to attendance at the educational program (P = 0.03). Recommendations for future cancer screening in churches are given.
Keywords: Prostatic Neoplasms -- Prevention and Control; Prostatic Neoplasms -- Education; Black Persons; Cancer Screening -- Methods; Churches -- Utilization; Funding Source; Descriptive Research; Correlational Studies; Hypothesis; Stratified Random Sample; Research Subject Recruitment; Questionnaires; Interviews; Descriptive Statistics; Data Analysis Software; Health Belief Model; Race Factors; Adult; Middle Age; Aged; Male; Human

Prostate-specific antigen response in black and white patients treated with abiraterone acetate for metastatic castrate-resistant prostate cancer. - Ramalingam, Sundhar; Humeniuk, Michael S.; Hu, Rachel; Rasmussen, Julia; Healy, Patrick; Wu, Yuan; Harrison, Michael R.; Armstrong, Andrew J.; George, Daniel J.; Zhang, Tian (Urologic Oncology, 2017)
Purpose: Evidence suggests differences in androgen receptor AR signaling between black (B) and white (W) patients with prostate cancer, but pivotal trials of abiraterone acetate (AA) for patients with metastatic castration-resistant prostate cancer (mCRPC) enrolled few black patients, a population with a higher mortality from prostate cancer. Our primary objective was to determine differences in response to AA between B and W patients.Methods: We performed a retrospective case-control study of B vs. W patients treated with AA between May 1, 2008 and June 16, 2015 at Duke University Medical Center. Patients were identified (W control patients were matched 2:1 to B patients stratified based on previous docetaxel exposure) through pharmacy records and were eligible if treated with AA for metastatic castration-resistant prostate cancer. Patients with previous enzalutamide use were excluded. The primary objective was to compare the rate of≥90% prostate-specific antigen (PSA) decline from baseline between B vs. W patients. Secondary outcomes included comparing time on therapy, time to PSA progression, and overall survival among groups.Results: Baseline characteristics among patients (n = 45 B, n = 90 W) were identified; these included Karnofsky performance status, PSA, Gleason score, alkaline phosphatase, albumin, hemoglobin, lactate dehydrogenase, opiate use for pain, and metastatic sites. Baseline characteristics among groups were similar except for median hemoglobin (B = 11.4g/dl, W = 12.3g/dl). The proportion of B patients achieving a≥90% PSA level decline was 37.8% vs. 28.9% for W patients (P = 0.296). Statistically significant differences were found in the proportion of patients achieving a≥50% PSA level decline (B = 68.9%, W = 48.9% [P = 0.028]) and≥30% PSA level decline (B = 77.8%, W = 54.4% [P = 0.008]). Rates of primary abiraterone-refractory disease (PSA increase as best response) trended higher in W (31.1%) than in B (15.6%) patients (P = 0.052). Median treatment duration (B = 9.4 mo, W = 8.3 mo) did not differ (Wilcoxon P = 0.444). Median overall survival (B = 27.3 mo [95% CI: 13.9, not estimable], W = 24.8 mo [95% CI: 19, 31.6] [P = 0.669]) and median time to PSA progression (B = 11.0 mo [95% CI: 4.3, 18.0], W = 9.4 mo [95% CI: 6.2, 13.0] [P = 0.917]) did not differ.Conclusions: Black patients may have a higher PSA response to AA than white patients. An ongoing prospective clinical study (NCT01940276) is evaluating outcomes between black and white patients treated with AA.
Keywords: Blood Coagulation Factors -- Blood; Prostate-Specific Antigen -- Blood; Prostatic Neoplasms, Castration-Resistant -- Drug Therapy; Male; Prostatic Neoplasms, Castration-Resistant -- Blood; Neoplasm Metastasis; Disease Progression; Prostatic Neoplasms, Castration-Resistant -- Ethnology; Case Control Studies; Prospective Studies; Black Persons; Prostatic Neoplasms, Castration-Resistant -- Pathology; White Persons; Retrospective Design; Human; Clinical Assessment Tools; Karnofsky Performance Status; Scales

Provider-Based Research Networks Demonstrate Greater Hospice Use for Minority Patients With Lung Cancer. - Penn, Dolly; Stitzenberg, Karyn B.; Cobran, Ewan K.; Godley, Paul A. (Journal of Oncology Practice, 2014)
Purpose: The Community Clinical Oncology Program (CCOP) and Minority-Based Community Clinical Oncology Program (MBCCOP) are provider-based research networks (PBRN) that improve minority enrollment in cancer-focused clinical trials. We hypothesized that affiliation with a PBRN may also mitigate racial differences in hospice enrollment for patients with lung cancer. Methods: We used the SEER-Medicare data, linked to the National Cancer Institute’s CCOP program data, to identify all patients (≥ age 65 years) with lung cancer, diagnosed from 2001 to 2007. We defined clinical treatment settings as CCOP, MBCCOP, academic, or community-affiliated and used multivariable logistic regression analysis to determine factors associated with hospice enrollment. Results: Forty-one thousand eight hundred eighty-five (55.1%) patients with lung cancer enrolled in hospice before death. Approximately 55% of CCOP, 57% of MBCCOP, 57% of academic, and 52% of community patients enrolled. Patients who were more likely to enroll were female (odds ratio [OR], 1.36; 95% CI, 1.31 to 1.40); ≥ age 79 years (OR, 1.11; 95%CI, 1.06 to 1.16); white; lived in more educated areas; had minimal comorbidities; and had distant disease. Asian and black patients in academic (41.1% and 50.4%, respectively) and community practices (35.2% and 43.4%, respectively) were less likely to enroll in hospice compared with white patients (academic, 58.8%; community, 53.1%). However, hospice enrollment was equivalent for black and white patients in MBCCOP (59.5% v 57.2%) and CCOP (52.2% v 56.3%) practices. Conclusion: Minority patients with lung cancer receiving treatment in cancer-focused PBRN- affiliated practices have greater hospice enrollment than those treated in academic and community practices.
Keywords: Cancer Patients; Lung Neoplasms; Hospice Care -- Utilization; Race Factors; Human; Aged; Aged, 80 and Over; Female; Male; Descriptive Statistics; Logistic Regression; Odds Ratio; Confidence Intervals; White Persons; Sex Factors; Black Persons; Asians; Pearson's Correlation Coefficient; Hispanic Americans; Data Analysis Software; Databases, Health; Funding Source

Psychosocial benefits of a novel mindfulness intervention versus standard support in distressed women with breast cancer. - Monti, Daniel A; Kash, Kathryn M; Kunkel, Elisabeth J; Moss, Aleeze; Mathews, Michael; Brainard, George; Anne, Ranni; Leiby, Benjamin E; Pequinot, Edward; Newberg, Andrew B (Psycho-Oncology, 2013)
OBJECTIVE: It is well documented that stress is associated with negative health outcomes in cancer patients. The purpose of this study was to assess the effects of a novel mindfulness intervention called mindfulness-based art therapy (MBAT) versus standard educational support, on indices of stress and quality of life in breast cancer patients with high stress levels. METHODS: A total of 191 women were enrolled, stratified by age and stress level, and randomized to receive either an 8-week MBAT intervention or a breast cancer educational support program of equal time and duration. Psychosocial stress was measured using the Symptoms Checklist-90-Revised, and quality of life was measured using the Medical Outcomes Study Short-Form Health Survey at baseline, immediately post-intervention, and at 6 months. RESULTS: Results showed overall significant improvements in psychosocial stress and quality of life in both the MBAT and educational support groups immediately post-intervention; however, participants with high stress levels at baseline had significantly improved overall outcomes only in the MBAT group, both immediately post-intervention and at 6 months. In addition, at 6 months follow-up, participants attending five or more sessions trended toward retaining treatment effects better in the MBAT than in the control group. Finally, black women and white women were similar in terms of how they benefited from the MBAT intervention, even though white participants tended to have higher educational level and marital status. CONCLUSIONS: In conclusion, MBAT is associated with significant, sustained benefits across a diverse range of breast cancer patients, particularly those with high stress levels. Copyright © 2013 John Wiley & Sons, Ltd.
Keywords: Art Therapy -- Methods; Breast Neoplasms -- Therapy; Mindfulness -- Methods; Patient Education -- Methods; Quality of Life -- Psychosocial Factors; Stress, Psychological -- Therapy; Adaptation, Psychological; Adult; Aged; Aged, 80 and Over; Breast Neoplasms -- Psychosocial Factors; Female; Prospective Studies; Health Status; Human; Experimental Studies; Middle Age; Socioeconomic Factors; Stress, Psychological -- Diagnosis; Stress, Psychological -- Psychosocial Factors; Treatment Outcomes

Psychosocial factors related to repeat mammography screening over 5 years in African American women. - Russell KM; Champion VL; Skinner CS (Cancer Nursing, 2006)
The purpose of this study was to investigate health beliefs associated with repeat mammography screening in African American women 51 years or older over a 5-year period. Long-term repeat mammography screening is inconsistent in African American women; therefore, this study measured demographic, knowledge, and health belief predictors of repeat screening. The theoretical framework for this study was the health belief model. Baseline data from a larger randomized controlled trial were analyzed using descriptive statistics and logistic regression. The sample consisted of 602 African American women with no breast cancer history and at least 1 reported screening mammogram in the past 5 years. They were recruited from 3 primary care health settings. Having been screened 4 to 5 times in the past 5 years was associated with more knowledge about screening guidelines and fewer perceived barriers to screening. Results point to the importance of collaborating with African American communities to promote life-long mammography screening by increasing access to culturally appropriate information on screening guidelines and ameliorating barriers to screening within the context of the African American experience.
Keywords: Black Persons -- Psychosocial Factors -- Midwestern United States; Health Beliefs -- Evaluation; Mammography -- Utilization; Aged; Aged, 80 and Over; Bivariate Statistics; Chi Square Test; Clinical Trials; Coefficient Alpha; Conceptual Framework; Correlational Studies; Data Analysis Software; Descriptive Research; Descriptive Statistics; Female; Funding Source; Health Belief Model; Health Knowledge -- Evaluation; Health Services Accessibility -- Evaluation; Logistic Regression; Middle Age; Midwestern United States; Scales; Secondary Analysis; Self Report; Self-Efficacy -- Evaluation; Summated Rating Scaling; Human

Puerto Rican women's perceptions of heart disease risk. - Lange J; Evans-Benard S; Cooper J; Fahey E; Kalapos M; Tice D; Wang-D'Amato N; Watsky N (Clinical Nursing Research, 2009)
Women frequently fail to recognize that coronary heart disease (CHD), not breast cancer, is the primary cause of female mortality. CHD mortality among U.S. mainland Puerto Rican (PR) women is second only to African American women. It is unknown what PR women understand about their risk, what factors they believe contribute to CHD, or whether they know the atypical symptoms often experienced by women. Most CHD studies exclude Hispanic women. Those that do often aggregate their results, making subgroup variations invisible. This study explored awareness of CHD symptoms, risks, and help-seeking behaviors among 12 PR women. Focus group methodology revealed that participants were unaware of their risk and had misconceptions about CHD symptoms and contributing factors. Barriers to early recognition and treatment included lack of knowledge, gender role conflict (caregiver vs. care recipient), and fears of falsely alarming family members or the embarrassment of feeling 'dismissed' by health care providers.
Keywords: Attitude to Illness; Cardiovascular Risk Factors; Health Knowledge; Hispanic Americans; Adult; Attitude to Illness -- Evaluation; Audiorecording; Conceptual Framework; Descriptive Research; Female; Field Notes; Focus Groups; Funding Source; Health Beliefs -- Evaluation; Health Knowledge -- Evaluation; Leininger's Theory of Culture Care Diversity and Universality; Middle Age; New England; Puerto Rico; Qualitative Studies; Questionnaires; Research Subject Recruitment; Human

Quality of breast cancer care: perception versus practice. - Bickell NA; Neuman J; Fei K; Franco R; Joseph KA; Bickell, Nina A; Neuman, Jennifer; Fei, Kezhen; Franco, Rebeca; Joseph, Kathie-Ann (Journal of Clinical Oncology, 2012)
Purpose: Because insurers use performance and quality metrics to inform reimbursement, identifying remediable causes of poor-quality cancer care is imperative. We undertook this descriptive cohort study to assess key predictors of women's perceived quality of their breast cancer care and actual guideline-concordant quality of care received.Patients and Methods: We surveyed inner-city women with newly diagnosed and surgically treated early-stage breast cancer requiring adjuvant treatment who were enrolled onto a randomized controlled trial (RCT) of patient assistance to reduce disparities in care. We assessed women's perceived quality of care and perceived quality of the process of getting care, such as getting referrals, test results, and treatments; we abstracted records to determine the actual quality of care.Results: Of the 374 new patients with early-stage breast cancer enrolled onto the RCT, only a slight majority of women (55%) perceived their quality of care as excellent; 88% actually received good-quality, guideline-concordant care. Excellent perceived quality (P < .001) was significantly associated with patients' perception of the quality of the process of getting care (adjusted relative risk [RR], 1.78; 95% CI, 1.65 to 1.87). Also associated with perceived quality-and mediated by race-were trust in one's physician (adjusted RR, 1.43; 95% CI, 1.16 to 1.64) and perceived racism, which affected black women more than women of other races/ethnicities (black race-adjusted RR for perceived racism, 0.33 [95% CI, 0.10 to 0.87]; black race-adjusted RR for trust, 1.61 [95% CI, 0.97 to 1.90]; c = 0.82 for the model; P < .001). Actual quality of care provided did not affect perceived quality of care received.Conclusion: Patients' perceived quality of care differs from their receipt of high-quality care. Mutable targets to improve perceived quality of care include the processes of getting care and trusting their physician.
Keywords: Attitude to Health -- Ethnology; Breast Neoplasms -- Therapy; Mastectomy -- Standards; Patients -- Psychosocial Factors; Perception; Quality of Health Care -- Standards; Urban Health Services -- Standards; Adult; Aged; Aged, 80 and Over; Breast Neoplasms -- Diagnosis; Breast Neoplasms -- Ethnology; Breast Neoplasms -- Psychosocial Factors; Clinical Trials; Ethnic Groups -- Psychosocial Factors; Female; Guideline Adherence; Human; Logistic Regression; Middle Age; Neoplasm Staging; New York; Odds Ratio; Patient Satisfaction; Physician-Patient Relations; Practice Guidelines; Surveys

Race and sex differences in the receipt of timely and appropriate lung cancer treatment. - Shugarman LR; Mack K; Sorbero ME; Tian H; Jain AK; Ashwood JS; Asch SM (Medical Care, 2009)
BACKGROUND: Previous research suggests that disparities in non-small-cell lung cancer (NSCLC) survival can be explained in part by disparities in the receipt of cancer treatment. Few studies, however, have considered race and sex disparities in the timing and appropriateness of treatment across stages of diagnosis. OBJECTIVE: To evaluate the relationship of sex and race with the receipt of timely and clinically appropriate NSCLC treatment for each stage of diagnosis. METHOD: Surveillance Epidemiology and End Result data linked to Medicare claims for beneficiaries diagnosed with NSCLC between 1995 and 1999 were used to evaluate the relationship between race and sex with timely and appropriate NSCLC treatment while controlling for other demographic characteristics, comorbidities, socioeconomic status, and provider supply (N = 22,145). RESULTS: Overall adjusted rates of timely and appropriate treatment are 37.2%, 58.1%, and 29.2% for Medicare beneficiaries diagnosed with stage I or II, III, and IV NSCLC, respectively. Among stage I or II patients, women were 25% less likely to receive timely surgical resection relative to men, and blacks were 66% less likely to receive timely and appropriate treatment than whites. Black men were least likely to receive resection (22.2% compared with 43.7% for white men). Blacks were 34% less likely to receive timely surgery, chemotherapy, or radiation for stage III disease and were 51% less likely to receive chemotherapy in a timely fashion for stage IV disease relative to whites. CONCLUSION: Significant variations in appropriate timely treatment were found within and across stages of diagnosis, confirming that sex and race differences in NSCLC treatment exist.
Keywords: Black Persons -- Statistics and Numerical Data; Carcinoma, Non-Small-Cell Lung -- Therapy; Health Services Accessibility -- Statistics and Numerical Data; Lung Neoplasms -- Therapy; White Persons -- Statistics and Numerical Data; Aged; Aged, 80 and Over; Black Persons; Carcinoma, Non-Small-Cell Lung -- Diagnosis; Carcinoma, Non-Small-Cell Lung -- Ethnology; Female; Guideline Adherence -- Statistics and Numerical Data; Health Services Research; Insurance -- Statistics and Numerical Data; Logistic Regression; Lung Neoplasms -- Diagnosis; Lung Neoplasms -- Ethnology; Male; Medicare -- Statistics and Numerical Data; Men; Multivariate Analysis; Patient Selection; Practice Guidelines; Practice Patterns -- Statistics and Numerical Data; Registries, Disease; Sensitivity and Specificity; Sex Factors; United States; White Persons; Women; Human

Racial differences in clinical outcomes from metastatic breast cancer: a pooled analysis of CALGB 9342 and 9840--Cancer and Leukemia Group B. - Polite BN; Cirrincione C; Fleming GF; Berry DA; Seidman A; Muss H; Norton L; Shapiro C; Bakri K; Marcom K; Lake D; Schwartz JH; et al. (Journal of Clinical Oncology, 2008)
Purpose: African American women are more likely to be diagnosed with metastatic breast cancer at the time of presentation than whites, and have shorter survival once diagnosed. This study examines racial differences in clinical outcomes in the setting of two large cooperative group randomized clinical trials.Patients and Methods: The study cohort consisted of 787 white (80%) and 195 African American (20%) patients with metastatic breast cancer enrolled in two successive Cancer and Leukemia Group B (CALGB) trials using taxanes in the metastatic setting. Differences in overall survival (OS), response incidence, and time to treatment failure (TTF) were examined by race. In addition, differences in the incidence of baseline and treatment-related toxicities were examined.Results: With 779 deaths (166 African Americans and 613 whites), median OS was 14.3 months for African Americans and 18.75 months for whites (hazard ratio [HR] = 1.37; 95% CI, 1.15 to 1.63). When adjusted for prognostic factors, African Americans had a 24% increase in the hazard of death compared with whites (HR = 1.24; 95% CI, 1.02 to 1.51). No significant differences in TTF or overall response to therapy were seen. No clinically significant toxicity differences were seen.Conclusion: African Americans with metastatic breast cancer have an increased hazard of death compared with whites despite the receipt of similar per-protocol treatment, but experience no differences in TTF or overall response to therapy. We hypothesize that more direct and robust measures of comorbidities, and perhaps other factors such as receipt of subsequent therapy could help further explain the observed survival difference.
Keywords: Black Persons; Breast Neoplasms -- Mortality; Survival Analysis; White Persons; Adult; Aged; Antineoplastic Agents -- Therapeutic Use; Breast Neoplasms -- Drug Therapy; Breast Neoplasms -- Ethnology; Female; Logistic Regression; Middle Age; Multicenter Studies; Neoplasm Metastasis; Paclitaxel -- Therapeutic Use; Time Factors; Treatment Failure; Human

Racial disparities in cancer survival among randomized clinical trials patients of the Southwest Oncology Group. - Albain KS; Unger JM; Crowley JJ; Coltman CA Jr; Hershman DL; Albain, Kathy S; Unger, Joseph M; Crowley, John J; Coltman, Charles A Jr; Hershman, Dawn L (JNCI: Journal of the National Cancer Institute, 2009)
Background: Racial disparities in cancer outcomes have been observed in several malignancies. However, it is unclear if survival differences persist after adjusting for clinical, demographic, and treatment variables. Our objective was to determine whether racial disparities in survival exist among patients enrolled in consecutive trials conducted by the Southwest Oncology Group (SWOG).Methods: We identified 19 457 adult cancer patients (6676 with breast, 2699 with lung, 1244 with colon, 1429 with ovarian, and 1843 with prostate cancers; 1291 with lymphoma; 2067 with leukemia; and 2208 with multiple myeloma) who were treated on 35 SWOG randomized phase III clinical trials from October 1, 1974, through November 29, 2001. Patients were grouped according to studies of diseases with similar histology and stage. Cox regression was used to evaluate the association between race and overall survival within each disease site grouping, controlling for available prognostic factors plus education and income, which are surrogates for socioeconomic status. Median and ten-year overall survival estimates were derived by the Kaplan-Meier method. All statistical tests were two-sided.Results: Of 19 457 patients registered, 2308 (11.9%, range = 3.9%-21.6%) were African American. After adjustment for prognostic factors, African American race was associated with increased mortality in patients with early-stage premenopausal breast cancer (hazard ratio [HR] for death = 1.41, 95% confidence interval [CI] = 1.10 to 1.82; P = .007), early-stage postmenopausal breast cancer (HR for death = 1.49, 95% CI = 1.28 to 1.73; P < .001), advanced-stage ovarian cancer (HR for death = 1.61, 95% CI = 1.18 to 2.18; P = .002), and advanced-stage prostate cancer (HR for death = 1.21, 95% CI = 1.08 to 1.37; P = .001). No statistically significant association between race and survival for lung cancer, colon cancer, lymphoma, leukemia, or myeloma was observed. Additional adjustments for socioeconomic status did not substantially change these observations. Ten-year (and median) overall survival rates for African American vs all other patients were 68% (not reached) vs 77% (not reached), respectively, for early-stage, premenopausal breast cancer; 52% (10.2 years) vs 62% (13.5 years) for early-stage, postmenopausal breast cancer; 13% (1.3 years) vs 17% (2.3 years) for advanced ovarian cancer; and 6% (2.2 years) vs 9% (2.7 years) for advanced prostate cancer.Conclusions: African American patients with sex-specific cancers had worse survival than white patients, despite enrollment on phase III SWOG trials with uniform stage, treatment, and follow-up.
Keywords: Black Persons -- Statistics and Numerical Data; Health Status; Neoplasms -- Mortality; Adult; Aged; Breast Neoplasms -- Mortality; Clinical Trials; Colorectal Neoplasms -- Mortality; Confidence Intervals; Confounding Variable; Cox Proportional Hazards Model; Educational Status; Female; Income; Kaplan-Meier Estimator; Leukemia -- Mortality; Lung Neoplasms -- Mortality; Lymphoma -- Mortality; Male; Middle Age; Multiple Myeloma -- Mortality; Neoplasm Staging; Neoplasms -- Pathology; Neoplasms -- Therapy; Odds Ratio; Ovarian Neoplasms -- Mortality; Prognosis; Prostatic Neoplasms -- Mortality; Risk Assessment; Risk Factors; Socioeconomic Factors; Survival; United States; White Persons -- Statistics and Numerical Data; Human

Racial disparities in traumatic stress in prostate cancer patients: secondary analysis of a National URCC CCOP Study of 317 men. - Purnell JQ; Palesh OG; Heckler CE; Adams MJ; Chin N; Mohile S; Peppone LJ; Atkins JN; Moore DF; Spiegel D; Messing E; Morrow GR; et al. (Supportive Care in Cancer, 2011)
Introduction: African American men have the highest rates of prostate cancer of any racial group, but very little is known about the psychological functioning of African American men in response to prostate cancer diagnosis and treatment.Purpose: In this secondary analysis of a national trial testing a psychological intervention for prostate cancer patients, we report on the traumatic stress symptoms of African American and non-African American men.Methods: This analysis includes 317 men (African American: n = 30, 9%; non-African American: n = 287, 91%) who were enrolled in the intervention trial, which included 12 weeks of group psychotherapy and 24 months of follow-up. Using mixed model analysis, total score on the Impact of Events Scale (IES) and its Intrusion and Avoidance subscales were examined to determine mean differences in traumatic stress across all time points (0, 3, 6, 12, 18, and 24 months). In an additional analysis, relevant psychosocial, demographic, and clinical variables were added to the model.Results: Results showed significantly higher levels of traumatic stress for African American men compared to non-African American men in all models independently of the intervention arm, demographics, and relevant clinical variables. African Americans also had a consistently higher prevalence of clinically significant traumatic stress symptoms (defined as IES total score ≥ 27). These elevations remained across all time points over 24 months.Conclusions: This is the first study to show a racial disparity in traumatic stress specifically as an aspect of overall psychological adjustment to prostate cancer. Recommendations are made for appropriate assessment, referral, and treatment of psychological distress in this vulnerable population.
Keywords: Black Persons -- Statistics and Numerical Data; Health Status; Prostatic Neoplasms -- Psychosocial Factors; Stress Disorders, Post-Traumatic -- Psychosocial Factors; Stress, Psychological; White Persons -- Statistics and Numerical Data; Adaptation, Psychological; Adult; Aged; Aged, 80 and Over; Health Status Indicators; Impact of Events Scale; Male; Middle Age; Prostatic Neoplasms -- Epidemiology; Psychological Tests; Psychometrics; Quality of Life -- Psychosocial Factors; Scales; Stress Disorders, Post-Traumatic -- Epidemiology; United States

Racial disparities in treatment and survival of male breast cancer. - Crew KD; Neugut AI; Wang X; Jacobson JS; Grann VR; Raptis G; Hershman DL (Journal of Clinical Oncology, 2007)
PURPOSE: Black women with breast cancer have poorer survival than do white women, but little is known about racial disparities in male breast cancer. We analyzed race and other predictors of treatment and survival among men with stage I-III breast cancer. PATIENTS AND METHODS: We used the Surveillance, Epidemiology, and End Results (SEER) Medicare database to identify men 65 years of age or older diagnosed with stage I-III breast cancer from 1991 to 2002. Multivariate regression was used to compare those treated with those not treated with either chemotherapy or radiation therapy, adjusting for known clinical and demographic factors. Cox proportional hazards regression models were used to analyze survival. RESULTS: Of 510 male breast cancer cases (456 white, 34 black), 94% underwent mastectomy, 28% received adjuvant chemotherapy, and 29% received radiation therapy. Among those with known hormone receptors, 95% had hormone-sensitive tumors. In a multivariate analysis, chemotherapy was associated with younger age, advanced stage, and hormone receptor-negative tumors. Radiation therapy was associated with younger age and advanced stage. Black men were approximately 50% less likely to undergo consultation with an oncologist and subsequently receive chemotherapy; however, the results did not reach statistical significance. The breast cancer-specific mortality hazard ratio was more than tripled for black versus white men (hazard ratio = 3.29; 95% CI, 1.10 to 9.86). CONCLUSION: After adjustment for known clinical, demographic, and treatment factors, there was an association of black race with increased male breast cancer-specific mortality. Although male breast cancer is rare, the reasons for these disparities need to be better understood.
Keywords: Black Persons; Breast Neoplasms, Male -- Mortality; Breast Neoplasms, Male -- Therapy; White Persons; Age Factors; Aged; Aged, 80 and Over; Breast Neoplasms, Male -- Ethnology; Breast Neoplasms, Male -- Pathology; Chemotherapy, Adjuvant; Cox Proportional Hazards Model; Kaplan-Meier Estimator; Male; Mastectomy; Medicare; Neoplasm Staging; Odds Ratio; Patient Selection; Predictive Value of Tests; Prognosis; Prospective Studies; Radiotherapy, Adjuvant; Referral and Consultation; Time Factors; Treatment Outcomes; United States; Human

Racial/ethnic and age disparities in chemotherapy selection for colorectal cancer. - Obeidat NA; Pradel FG; Zuckerman IH; Trovato JA; Palumbo FB; DeLisle S; Mullins CD (American Journal of Managed Care, 2010)
Objectives: To test the hypotheses that African American patients and older patients with stage IV colorectal cancer were less likely to receive newer chemotherapy agents. Study Design: Retrospective cohort design. Methods: Among 5068 Surveillance, Epidemiology, and End Results -- Medicare patients diagnosed as having stage IV colorectal cancer between 2000 and 2002, a total of 2466 received chemotherapy and were included in the analysis. Irinotecan hydrochloride was the first of the 'newer' chemotherapy agents and was marketed in 2000 as a first-line add-on agent. Descriptive statistics were generated, and a multivariable logistic regression was run to estimate the odds of receiving irinotecan among African American patients and older patients and within 2 months of chemotherapy initiation. Results: African American patients had lower odds of initiating treatment with a newer chemotherapy than white patients (adjusted odds ratio, 0.641; 95% confidence interval, 0.453-0.907). An age disparity was also found, with all older age groups being significantly less likely to initiate treatment with a newer chemotherapy than the youngest age group: the adjusted odds of receiving newer chemotherapy agents (relative to patients aged 66-70 years) were lower and significant among patients aged 71 to 75, 76 to 80, and older than 80 years (odds ratios, 0.708, 0.527, and 0.213, respectively). Conclusions: Disparities in chemotherapy selection exist among patients receiving chemotherapy for stage IV colorectal cancer. On initiating chemotherapy, African American patients and older patients were less likely to receive a newer agent.
Keywords: Age Factors; Chemotherapy, Cancer -- Evaluation -- In Old Age; Colorectal Neoplasms -- Drug Therapy -- In Old Age; Patient Selection; Race Factors; Aged; Aged, 80 and Over; Bivariate Statistics; Black Persons; Chi Square Test; Clinical Assessment Tools; Confidence Intervals; Data Analysis Software; Data Analysis, Statistical; Descriptive Statistics; Female; Funding Source; Human; Male; Odds Ratio; P-Value; Retrospective Design; Sex Factors; White Persons

Racial/Ethnic Differences in Patients' Selection of Surgeons and Hospitals for Breast Cancer Surgery. - Freedman, Rachel A.; Kouri, Elena M.; West, Dee W.; Keating, Nancy L. (JAMA Oncology, 2015)
Keywords: Race Factors; Ethnic Groups; Patient Selection -- Evaluation; Surgeons; Hospitals -- Evaluation; Breast Neoplasms -- Surgery; Oncology; Human; Female; Breast Neoplasms -- Physiopathology; Patient Care -- Methods; Surveys; Breast Neoplasms -- Diagnosis; Hispanic Americans; Black Persons; California; Marriage; Education; Literacy; Health Knowledge -- Evaluation; Independent Variable; Dependent Variable; Insurance Carriers; Data Analysis; Chi Square Test; Fisher's Exact Test; Kruskal-Wallis Test; Logistic Regression; Decision Making

Randomized controlled trial of yoga among a multiethnic sample of breast cancer patients: effects on quality of life. - Moadel AB; Shah C; Wylie-Rosett J; Harris MS; Patel SR; Hall CB; Sparano JA (Journal of Clinical Oncology, 2007)
PURPOSE: This study examines the impact of yoga, including physical poses, breathing, and meditation exercises, on quality of life (QOL), fatigue, distressed mood, and spiritual well-being among a multiethnic sample of breast cancer patients. PATIENTS AND METHODS: One hundred twenty-eight patients (42% African American, 31% Hispanic) recruited from an urban cancer center were randomly assigned (2:1 ratio) to a 12-week yoga intervention (n = 84) or a 12-week waitlist control group (n = 44). Changes in QOL (eg, Functional Assessment of Cancer Therapy) from before random assignment (T1) to the 3-month follow-up (T3) were examined; predictors of adherence were also assessed. Nearly half of all patients were receiving medical treatment. RESULTS: Regression analyses indicated that the control group had a greater decrease in social well-being compared with the intervention group after controlling for baseline social well-being and covariates (P < .0001). Secondary analyses of 71 patients not receiving chemotherapy during the intervention period indicated favorable outcomes for the intervention group compared with the control group in overall QOL (P < .008), emotional well-being (P < .015), social well-being (P < .004), spiritual well-being (P < .009), and distressed mood (P < .031). Sixty-nine percent of intervention participants attended classes (mean number of classes attended by active class participants = 7.00 +/- 3.80), with lower adherence associated with increased fatigue (P < .001), radiotherapy (P < .0001), younger age (P < .008), and no antiestrogen therapy (P < .02). CONCLUSION: Despite limited adherence, this intent-to-treat analysis suggests that yoga is associated with beneficial effects on social functioning among a medically diverse sample of breast cancer survivors. Among patients not receiving chemotherapy, yoga appears to enhance emotional well-being and mood and may serve to buffer deterioration in both overall and specific domains of QOL.
Keywords: Breast Neoplasms -- Therapy; Quality of Life; Yoga; Adaptation, Psychological; Adult; Aged; Breast Neoplasms -- Ethnology; Breast Neoplasms -- Psychosocial Factors; Randomized Controlled Trials; Female; Middle Age; Regression; Social Adjustment; Human

Randomized trial of black cohosh for the treatment of hot flashes among women with a history of breast cancer. - Jacobson JS; Troxel AB; Evans J; Klaus L; Vahdat L; Kinne D; Lo KMS; Moore A; Rosenman PJ; Kaufman EL; Neugut AI; Grann VR; et al. (Journal of Clinical Oncology, 2001)
Purpose: Most breast cancer survivors experience hot flashes; many use complementary or alternative remedies for these symptoms. We undertook a randomized clinical trial of black cohosh, a widely used herbal remedy for menopausal symptoms, among breast cancer patients. Patients and Methods: Patients diagnosed with breast cancer who had completed their primary treatment were randomly assigned to black cohosh or placebo, stratified on tamoxifen use. At enrollment, patients completed a questionnaire about demographic factors and menopausal symptoms. Before starting to take the pills and at 30 and 60 days, they completed a 4-day hot flash diary. At the final visit, they completed another menopausal symptom questionnaire. Follicle-stimulating hormone (FSH) and luteinizing hormone (LH) levels were measured in a subset of patients at the first and final visits. Results: Of 85 patients (59 on tamoxifen, 26 not on tamoxifen) enrolled in the study, 42 were assigned to treatment and 43 were assigned to placebo; 69 completed all three hot flash diaries. Both treatment and placebo groups reported declines in number and intensity of hot flashes; the differences between the groups were not statistically significant. Both groups also reported improvements in menopausal symptoms that were, for the most part, not significantly different. Changes in blood levels of FSH and LH also did not differ in the two groups. Conclusion: Black cohosh was not significantly more efficacious than placebo against most menopausal symptoms, including number and intensity of hot flashes. Our study illustrates the feasibility and value of standard clinical trial methodology in assessing the efficacy and safety of herbal agents.
Keywords: Breast Neoplasms -- Complications; Perimenopausal Symptoms -- Drug Therapy; Plant Extracts -- Therapeutic Use; Diaries; Tamoxifen -- Therapeutic Use; Combined Modality Therapy; Follicle-Stimulating Hormone -- Blood; Luteinizing Hormone -- Blood; Clinical Trials; Placebos; Double-Blind Studies; Analysis of Covariance; Wilcoxon Rank Sum Test; Middle Age; Male; Funding Source; Human

Randomized trial of community health worker-led decision coaching to promote shared decision-making for prostate cancer screening among Black male patients and their providers. - Makarov, Danil V.; Feuer, Zachary; Ciprut, Shannon; Lopez, Natalia Martinez; Fagerlin, Angela; Shedlin, Michele; Gold, Heather T.; Li, Huilin; Lynch, Gina; Warren, Rueben; Ubel, Peter; Ravenell, Joseph E. (Trials, 2021)
Background: Black men are disproportionately affected by prostate cancer, the most common non-cutaneous malignancy among men in the USA. The United States Preventive Services Task Force (USPSTF) encourages prostate-specific antigen (PSA) testing decisions to be based on shared decision-making (SDM) clinician professional judgment, and patient preferences. However, evidence suggests that SDM is underutilized in clinical practice, especially among the most vulnerable patients. The purpose of this study is to evaluate the efficacy of a community health worker (CHW)-led decision-coaching program to facilitate SDM for prostate cancer screening among Black men in the primary care setting, with the ultimate aim of improving/optimizing decision quality.Methods: We proposed a CHW-led decision-coaching program to facilitate SDM for prostate cancer screening discussions in Black men at a primary care FQHC. This study enrolled Black men who were patients at the participating clinical site and up to 15 providers who cared for them. We estimated to recruit 228 participants, ages 40-69 to be randomized to either (1) a decision aid along with decision coaching on PSA screening from a CHW or (2) receiving a decision aid along with CHW-led interaction on modifying dietary and lifestyle to serve as an attention control. The independent randomization process was implemented within each provider and we controlled for age by dividing patients into two strata: 40-54 years and 55-69 years. This sample size sufficiently powered the detection differences in the primary study outcomes: knowledge, indicative of decision quality, and differences in PSA screening rates. Primary outcome measures for patients will be decision quality and decision regarding whether to undergo PSA screening. Primary outcome measures for providers will be acceptability and feasibility of the intervention. We will examine how decision coaching about prostate cancer screening impact patient-provider communication. These outcomes will be analyzed quantitatively through objective, validated scales and qualitatively through semi-structured, in-depth interviews, and thematic analysis of clinical encounters. Through a conceptual model combining elements of the Preventative Health Care Model (PHM) and Informed Decision-Making Model, we hypothesize that the prostate cancer screening decision coaching intervention will result in a preference-congruent decision and decisional satisfaction. We also hypothesize that this intervention will improve physician satisfaction with counseling patients about prostate cancer screening.Discussion: Decision coaching is an evidence-based approach to improve decision quality in many clinical contexts, but its efficacy is incompletely explored for PSA screening among Black men in primary care. Our proposal to evaluate a CHW-led decision-coaching program for PSA screening has high potential for scalability and public health impact. Our results will determine the efficacy, cost-effectiveness, and sustainability of a CHW intervention in a community clinic setting in order to inform subsequent widespread dissemination, a critical research area highlighted by USPSTF.Trial Registration: The trial was registered prospectively with the National Institute of Health registry ( www.clinicaltrials.gov ), registration number NCT03726320 , on October 31, 2018.

Randomized trial of peer counseling on reproductive health in African American breast cancer survivors. - Schover LR; Jenkins R; Sui D; Adams JH; Marion MS; Jackson KE (Journal of Clinical Oncology, 2006)
PURPOSE: We designed a peer counseling program to improve sexual function, increase knowledge about reproductive health, and decrease menopausal symptoms and infertility-related distress for African American breast cancer survivors. PATIENTS AND METHODS: Women were randomly assigned to immediate counseling or a 3-month waitlist. Three peer counselors conducted a 3-session intervention using a detailed workbook. Questionnaires at baseline, after the waitlist period, at posttreatment, and at 3-month follow-up assessed spirituality, sexual function, menopause symptoms, emotional distress, relationship satisfaction, fertility concerns, and knowledge about reproductive health and breast cancer. At the postcounseling assessment, women rated the workbook, their counselor, and the program. RESULTS: Of 93 women screened, 60 women (65%) enrolled in the study. Women who completed counseling (80%; N = 48) had a mean age of 49 years (standard deviation [SD], 8 years) and a mean follow-up of 4.5 years (SD, 3.8 years) since cancer diagnosis. Almost all rated the workbook as very easy to understand (94%) and their counselor as very knowledgeable (96%) and very skillful (98%). Eighty-one percent rated the program as 'very useful to me.' Immediate counseling and waitlist groups did not differ at baseline in psychologic adjustment, nor did scores change during the waitlist period. Therefore, the groups were combined in analyzing outcomes. Knowledge of reproductive issues improved significantly from baseline to 3-month follow-up (P < .0001), as did emotional distress (P = .0047) and menopause symptoms (P = .0128). Sexually dysfunctional women became less distressed (P = .0167). CONCLUSION: Women valued the Sisters Peer Intervention in Reproductive Issues After Treatment program highly and found it relevant. The program had positive effects on knowledge and target symptoms.
Keywords: Breast Neoplasms -- Psychosocial Factors; Counseling; Reproductive Health; Adaptation, Psychological; Adult; Black Persons; Aged; Breast Neoplasms -- Ethnology; Female; Hot Flashes -- Prevention and Control; Knowledge; Middle Age; Human

Randomized trial to increase colorectal cancer screening in an ethnically diverse sample of first-degree relatives. - Bastani, Roshan; Glenn, Beth A; Maxwell, Annette E; Ganz, Patricia A; Mojica, Cynthia M; Alber, Susan; Crespi, Catherine M; Chang, L Cindy (Cancer (0008543X), 2015)
Background: Ethnic minorities, especially African Americans and Latinos, bear a disproportionate burden of colorectal cancer (CRC), as reflected in incidence, cancer stage, and mortality statistics. In all ethnic groups, first-degree relatives (FDRs) of CRC cases are at an elevated disease risk. However, underuse of CRC screening persists and is particularly evident among minority groups. The current study tested a stepped intervention to increase CRC screening among an ethnically diverse sample of FDRs of CRC cases.Methods: A statewide cancer registry was used to recruit CRC cases and through them their FDRs. Relatives who were not current on CRC screening were randomized to intervention or usual-care control arms. The stepped intervention consisted of ethnically targeted and individually tailored print materials followed by telephone counseling for those unscreened at 6 months.Results: The study sample of 1280 individuals consisted of 403 Latino, 284 African American, 242 Asian, and 351 white FDRs. Statistically significant effects were observed for the cumulative print plus telephone intervention at 12 months (26% in the intervention vs 18% in the control group) and the print intervention alone at 6 months (15% in the intervention vs 10% in the control group). The effect of the print intervention alone versus the cumulative interventions was not statistically significantly different. Stratified analyses indicated that the intervention was effective among white, Latino, and Asian individuals, but not among African-Americans.Conclusions: Overall, the intervention was effective in increasing screening rates. Oversampling racial/ethnic minorities allowed for the examination of effects within subgroups, revealing no effect among African American individuals. This finding illustrates the importance of including sufficient numbers of participants from diverse ethnic subgroups in intervention research to enable such stratified analyses.

Re: Prognosis and treatment of patients with breast tumors of one centimeter or less and negative axillary lymph nodes. - Mirchandani, Deepu; Muggia, Franco; Mirchandani, D; Muggia, F (JNCI: Journal of the National Cancer Institute, 2001)
Presents correspondence on prognosis and treatment of patient with breast tumors. Emphasis on the need for definitive clinical trials for acceptance of adjuvant chemotherapy; Risks and benefits to adjuvant hormonal treatment; Impact of breast cancer recurrence in older patients.
Keywords: Breast Neoplasms -- Drug Therapy; Selective Estrogen Receptor Modulators -- Therapeutic Use; Chemotherapy, Adjuvant; Antineoplastic Agents, Hormonal -- Therapeutic Use; Proteins -- Drug Effects; Female; Middle Age; Breast Neoplasms -- Mortality; Tamoxifen -- Therapeutic Use; Breast Neoplasms; Adult; Prognosis; Neoplasm Recurrence, Local; Aged; Relative Risk; Selective Estrogen Receptor Modulators -- Adverse Effects; Proteins -- Analysis; Tamoxifen -- Adverse Effects; Patient Selection; Hematologic Diseases -- Mortality; Risk Assessment; Human; Hematologic Diseases -- Chemically Induced; Lymph Nodes -- Pathology; Black Persons; Age Factors; Antineoplastic Agents, Hormonal -- Adverse Effects; Clinical Trials -- Methods; Ethnic Groups; Neoplasm Staging; Treatment Outcomes; Breast Neoplasms -- Pathology; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Impact of Events Scale; Scales

Real-world outcomes of sipuleucel-T treatment in PROCEED, a prospective registry of men with metastatic castration-resistant prostate cancer. - Higano, Celestia S.; Armstrong, Andrew J.; Sartor, A. Oliver; Vogelzang, Nicholas J.; Kantoff, Philip W.; McLeod, David G.; Pieczonka, Christopher M.; Penson, David F.; Shore, Neal D.; Vacirca, Jeffrey; Concepcion, Raoul S.; Tutrone, Ronald F.; et al. (Cancer (0008543X), 2019)
Background: The large registry, PROVENGE Registry for the Observation, Collection, and Evaluation of Experience Data (PROCEED)(NCT01306890), evaluated sipuleucel-T immunotherapy for asymptomatic/minimally symptomatic metastatic castration-resistant prostate cancer (mCRPC).Methods: PROCEED enrolled patients with mCRPC receiving 3 biweekly sipuleucel-T infusions. Assessments included overall survival (OS), serious adverse events (SAEs), cerebrovascular events (CVEs), and anticancer interventions (ACIs). Follow-up was for ≥3 years or until death or study withdrawal.Results: In 2011-2017, 1976 patients were followed for 46.6 months (median). The median age was 72 years, and the baseline median prostate-specific antigen level was 15.0 ng/mL; 86.7% were white, and 11.6% were African American. Among the patients, 1902 had 1 or more sipuleucel-T infusions. The median OS was 30.7 months (95% confidence interval [CI], 28.6-32.2 months). Known prognostic factors were independently associated with OS in a multivariable analysis. Among the 1255 patients who died, 964 (76.8%) died of prostate cancer (PC) progression. The median time from the first infusion to PC death was 42.7 months (95% CI, 39.4-46.2 months). The incidence of sipuleucel-T-related SAEs was 3.9%. The incidence of CVEs was 2.8%, and the rate per 100 person-years was 1.2 (95% CI, 0.9-1.6). The CVE incidence among 11,972 patients with mCRPC from the Surveillance, Epidemiology, and End Results-Medicare database was 2.8%; the rate per 100 person-years was 1.5 (95% CI, 1.4-1.7). One or more ACIs (abiraterone, enzalutamide, docetaxel, cabazitaxel, or radium 223) were received by 77.1% of the patients after sipuleucel-T; 32.5% and 17.4% of the patients experienced 1- and 2-year treatment-free intervals, respectively.Conclusions: PROCEED provides contemporary survival data for sipuleucel-T-treated men in a real-world setting of new life-prolonging agents, which will be useful in discussing treatment options with patients and in powering future trials with sipuleucel-T. The safety and tolerability of sipuleucel-T in PROCEED were consistent with previous findings.
Keywords: Tissue Extracts -- Therapeutic Use; Prostatic Neoplasms, Castration-Resistant -- Drug Therapy; Data Collection; Neoplasm Metastasis; Human; Prostatic Neoplasms, Castration-Resistant -- Pathology; Aged; Prospective Studies; Tissue Extracts -- Pharmacodynamics; Male; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies

Recruiting African American men for cancer screening studies: applying a culturally based model. - Abernethy AD; Magat MM; Houston TR; Arnold HL Jr.; Bjorck JP; Gorsuch RL (Health Education & Behavior, 2005)
In a study of psychosocial factors related to prostate cancer screening (PCS) of African American men, researchers achieved significant success in recruitment. Key strategies included addressing specific barriers to PCS for African American men and placing recruitment efforts in a conceptual framework that addressed cultural issues (PEN-3 model). To conduct cancer prevention research in the African American community, to engage in health promotion in collaboration with churches, and to recruit African American men, a culturally competent approach that incorporates the values of the community is essential. Implications for addressing specific barriers to recruitment and building partnerships in health promotion research are discussed.
Keywords: Black Persons; Cancer Screening; Research Subject Recruitment; Churches; Conceptual Framework; Cross Sectional Studies; Culture; Funding Source; Health Behavior; Health Education; Health Promotion; Male; Models, Theoretical; Prostatic Neoplasms -- Prevention and Control; Human

Recruiting African American women to participate in hereditary breast cancer research. - Halbert CH; Brewster K; Collier A; Smith C; Kessler L; Weathers B; Stopfer JE; Domchek S; Wileyto EP (Journal of Clinical Oncology, 2005)
PURPOSE: This study evaluated the process of recruiting African American women to participate in genetic counseling research for BRCA1 and BRCA2 (BRCA1/2) mutations with respect to referral, study enrollment, and participation in genetic counseling. PATIENTS AND METHODS: African American women (n = 783) were referred for study enrollment. RESULTS: Of 783 referrals, 164 (21%) women were eligible for enrollment. Eligible women were most likely to be referred from oncology clinics (44%) and were least likely to be referred from general medical practices (11%; chi(2) = 96.80; P = .0001). Overall, 62% of eligible women enrolled onto the study and 50% of enrollees completed genetic counseling. Women with a stronger family history of cancer (odds ratio [OR] = 3.18; 95% CI, 1.36 to 7.44; P = .01) and those referred from oncology clinics and community oncology resources (OR = 2.97; 95% CI, 1.34 to 6.58; P = .01) were most likely to enroll onto the study. Referral from oncology clinics was associated significantly with participation in genetic counseling (OR = 5.46; 95% CI, 1.44 to 20.60; P = .01). CONCLUSION: Despite receiving a large number of referrals, only a small subset of women were eligible for enrollment. Oncology settings were the most effective at identifying eligible African American women and general medical practices were the least effective. Factors associated with enrollment included having a stronger family history of cancer and being referred from oncology clinics and community oncology resources. Referral from oncology clinics was the only factor associated significantly with participation in genetic counseling. Education about hereditary breast cancer may be needed among primary care providers to enhance appropriate referral of African American women to genetic counseling for BRCA1/2 mutations.
Keywords: Black Persons; Breast Neoplasms -- Ethnology; Breast Neoplasms; Genes, BRCA; Genetic Counseling -- Utilization; Referral and Consultation; Attitude to Health -- Ethnology; Breast Neoplasms -- Psychosocial Factors; Female; Genetic Counseling -- Psychosocial Factors; Middle Age; Mutation; Patient Selection; Risk Factors; Socioeconomic Factors

Recruiting African-American barbershops for prostate cancer education. - Hart A Jr; Underwood SM; Smith WR; Bowen DJ; Rivers BM; Jones RA; Parker D; Allen JC; Hart, Alton Jr; Underwood, Sandra M; Smith, Wally R; Bowen, Deborah J; et al. (Journal of the National Medical Association, 2008)
Prostate cancer is the most common cause of cancer in men and the second leading cause of cancer deaths. African-American men bear a disproportionate burden of prostate cancer diagnosis and mortality. Current guidelines for prostate cancer screening differ among various medical organizations. Therefore, it is important that African-American men have the appropriate information needed to make informed decisions about prostate cancer screening. Unfortunately, a large percentage of African-American men could potentially be excluded from receiving culturally appropriate prostate cancer education. Therefore, a study was designed to recruit and intervene with African-American men and barbershops for increasing prostate cancer screening decision-making. The purpose of this study was to learn effective strategies for recruiting African-American barbershops for prostate cancer education and to determine barbershop proprietors' willingness to allow their barbershops to be used for research. In this paper, we present the outcomes of our recruitment methods for African-American barbershops, including a comparative description of participating and nonparticipating barbershops using the iMark Data System. One-hundred percent of the surveyed proprietors reported that they would allow their clients to learn about prostate cancer. Ninety-six percent reported they would consider allowing their clients to have access to handheld computers to learn about prostate cancer. We conclude from this study that African-American barbershops in general are welcoming environments in which to implement community-based prostate cancer education and public health research.
Keywords: Black Persons; Health Education -- Methods; Occupations and Professions; Prostatic Neoplasms -- Prevention and Control; Adult; Male; United States

Recruiting and engaging African-American men in health research. - Randolph, Schenita; Coakley, Tanya; Shears, Jeffrey (Nurse Researcher, 2018)
Background Improving the health of black and minority ethnic (BME) men in the US continues to be a public health priority. Compared with men of other races and ethnicities, African-American men have higher rates of mortality and morbidity from chronic illness and diseases including cancer, heart disease, prostate cancer, diabetes and HIV/AIDS. One way to address these disparities is to include African-American men in health research, to elicit their perspectives on health risks and protective factors. These can then inform interventions aimed at reducing health disparities. However, challenges remain in recruiting and engaging African-American men in health research. Aim To provide strategies for recruiting African-American men in health research, using as an exemplar a qualitative study of fathers' perspectives of sexual health promotion with young African-American males. Discussion Efforts are needed to increase the representation of African-American men in health research. Ensuring that researchers are aware of the cultural, social and environmental factors related to decisions to participate in research can lead to effective methods to recruit and engage them. Conclusion There are several essential strategies for increasing African-American men's participation in health research: ensuring the research team is culturally and gender-sensitive; recruiting in trusted environments; using respected gatekeepers; developing trust with participants; and being transparent. Implications for practice Implementing strategies to include African-American men in health research has the potential to improve health disparities in the US.
Keywords: Sexual Health; Black Persons; Research Subject Recruitment; Health Promotion; Healthcare Disparities -- United States; United States

Recruiting and engaging African-American men in health research. - Randolph, Schenita; Coakley, Tanya; Shears, Jeffrey (Nurse Researcher, 2018)
Background Improving the health of black and minority ethnic (BME) men in the US continues to be a public health priority. Compared with men of other races and ethnicities, African-American men have higher rates of mortality and morbidity from chronic illness and diseases including cancer, heart disease, prostate cancer, diabetes and HIV/AIDS. One way to address these disparities is to include African-American men in health research, to elicit their perspectives on health risks and protective factors. These can then inform interventions aimed at reducing health disparities. However, challenges remain in recruiting and engaging African-American men in health research. Aim To provide strategies for recruiting African-American men in health research, using as an exemplar a qualitative study of fathers' perspectives of sexual health promotion with young African-American males. Discussion Efforts are needed to increase the representation of African-American men in health research. Ensuring that researchers are aware of the cultural, social and environmental factors related to decisions to participate in research can lead to effective methods to recruit and engage them. Conclusion There are several essential strategies for increasing African-American men's participation in health research: ensuring the research team is culturally and gender-sensitive; recruiting in trusted environments; using respected gatekeepers; developing trust with participants; and being transparent. Implications for practice Implementing strategies to include African-American men in health research has the potential to improve health disparities in the US.
Keywords: Black Persons; Minority Groups; Men; Research Subject Recruitment; Male; Health Services Research; Qualitative Studies; Sexual Health; Health Promotion; Men's Health

Recruiting and motivating black subjects to complete a lengthy survey in a large cohort study: an exploration of different strategies. - Herring, Patti; Butler, Terry; Hall, Sonja; Bennett, Hannelore; Montgomery, Susanne B; Fraser, Gary (BMC Medical Research Methodology, 2014)
Background: The effectiveness of multiple innovative recruitment strategies for enrolling Black/African American participants to the Adventist Health Study-2 (AHS-2) is described. The study's focus is diet and breast, prostate and colon cancer.Methods: Promotions centered on trust, relationship building and incentives for increasing enrollment and questionnaire return rate. Of the sub-studies described, one had a randomized control group, and the others, informal controls. The subjects are from all states of the U.S. and some provinces of Canada. The offer of a Black art piece, follow-up calls, a competitive tournament as well as other strategies accounted for nearly 3,000 additional returns even though they were often used in small subsets.Results: Flexibility and multiple strategies proved advantageous in gaining the cooperation of Blacks, who are usually reluctant to participate in research studies.Conclusions: Lessons learned during initial enrollment should help us retain our final Black cohort of 26,000, and obtain new information when required.
Keywords: Black Persons -- Psychosocial Factors; Motivation; Patient Selection; Questionnaires; Breast Neoplasms -- Epidemiology; Canada; Prospective Studies; Colonic Neoplasms -- Epidemiology; Cost Benefit Analysis; Diet; Female; Human; Male; Physician-Patient Relations; Prostatic Neoplasms -- Epidemiology; Reward; United States

Recruiting black Americans in a large cohort study: the Adventist Health Study-2 (AHS-2) design, methods and participant characteristics. - Herring, R Patti; Butler, Terry; Hall, Sonja; Montgomery, Susanne B; Fraser, Gary E (Ethnicity & Disease, 2010)
Objective: The goal of the prospective Adventist Health Study-2 (AHS-2) was to examine the relationship between diet and risk of breast, prostate and colon cancers in Black and White participants. This paper describes the study design, recruitment methods, response rates, and characteristics of Blacks in the AHS-2, thus providing insights about effective strategies to recruit Blacks to participate in research studies.Design: We designed a church-based recruitment model and trained local recruiters who used various strategies to recruit participants in their churches. Participants completed a 50-page self-administered dietary and lifestyle questionnaire.Participants: Participants are Black Seventh-day Adventists, aged 30-109 years, and members of 1,209 Black churches throughout the United States and Canada.Results: Approximately 48,328 Blacks from an estimated target group of over 90,000 signed up for the study and 25,087 completed the questionnaire, comprising about 26% of the larger 97,000 AHS-2-member cohort. Participants were diverse in age, geographic location, education, and income. Seventy percent were female with a median age of 59 years.Conclusion: In spite of many recruitment challenges and barriers, we successfully recruited a large cohort whose data should provide some answers as to why Blacks have poorer health outcomes than several other ethnic groups, and help explain existing health disparities.
Keywords: Black Persons; Breast Neoplasms -- Ethnology; Colonic Neoplasms -- Ethnology; Diet; Patient Selection; Prostatic Neoplasms -- Ethnology; Adult; Aged; Aged, 80 and Over; Canada; Prospective Studies; Female; Human; Male; Middle Age; Program Development; Christianity; Study Design; United States

Recruiting black men to a clinical trial to evaluate prostate cancer screening -- Detroit, Michigan, 1998. (MMWR: Morbidity & Mortality Weekly Report, 1998)
Keywords: Research Subject Recruitment; Clinical Trials; Black Persons; Prostatic Neoplasms -- Ethnology; Prostatic Neoplasms -- Prevention and Control; Patient Selection; Male; Middle Age; Aged; Michigan

Recruiting diverse patients to a breast cancer risk communication trial--waiting rooms can improve access. - Bodurtha JN; Quillin JM; Tracy KA; Borzelleca J; McClish D; Wilson DB; Jones RM; Quillin J; Bowen D; Bodurtha, Joann N; Quillin, John M; Tracy, Kelly A; et al. (Journal of the National Medical Association, 2007)
Low participation among underserved populations in health research constrains progress in public health practices. From 2003 to 2005, Women's Health Clinic patients at the VCU Health System were recruited to a trial investigating breast cancer risk communication. In secondary analyses, we examined dimensions of the recruitment of these diverse women. The sample characteristics (age, insurance, race and previous mammograms) were compared to the overall clinic. Of recruitment attempts for eligible women, 45% consented; of those who declined, the top cited reasons were lack of time (40%) and lack of interest (18%). Of 899 participants, 35% qualified for the indigent care program, compared to 31% of the overall clinic (P<0.001). Forty-five percent of participants were African American, compared to 54% of overall clinic patients (P<0.001). Participants were younger (50 vs. 53 years, P<0.001) than the overall clinic population. Nonrepresentative enrollment of patients in clinical trials is common and could lead to suboptimal applicability of findings. Although there were statistically significant race and age differences between the study sample and the overall population, we demonstrate that waiting room recruitment can engage diverse women in a clinical trial and cancer risk communication.
Keywords: Breast Neoplasms -- Therapy; Clinical Trials; Communication; Patient Attitudes; Patient Selection; Adult; Aged; Female; Middle Age; Relative Risk; Human

Recruiting families at risk for hereditary breast and ovarian cancer from a statewide cancer registry: a methodological study. - Katapodi, Maria; Duquette, Deb; Yang, James; Mendelsohn-Victor, Kari; Anderson, Beth; Nikolaidis, Christos; Mancewicz, Emily; Northouse, Laurel; Duffy, Sonia; Ronis, David; Milliron, Kara; Probst-Herbst, Nicole; et al. (Cancer Causes & Control, 2017)
Purpose: Cancer genetic services (counseling/testing) are recommended for women diagnosed with breast cancer younger than 45 years old (young breast cancer survivors-YBCS) and at-risk relatives. We present recruitment of YBCS, identification and recruitment of at-risk relatives, and YBCS willingness to contact their cancer-free, female relatives.Methods: A random sample of 3,000 YBCS, stratified by race (Black vs. White/Other), was identified through a population-based cancer registry and recruited in a randomized trial designed to increase use of cancer genetic services. Baseline demographic, clinical, and family characteristics, and variables associated with the Theory of Planned Behavior (TPB) were assessed as predictors of YBCS' willingness to contact at-risk relatives.Results: The 883 YBCS (33.2% response rate; 40% Black) who returned a survey had 1,875 at-risk relatives and were willing to contact 1,360 (72.5%). From 853 invited at-risk relatives (up to two relatives per YBCS), 442 responded (51.6% response rate). YBCS with larger families, with a previous diagnosis of depression, and motivated to comply with recommendations from family members were likely to contact a greater number of relatives. Black YBCS were more likely to contact younger relatives and those living further than 50 miles compared to White/Other YBCS.Conclusion: It is feasible to recruit diverse families at risk for hereditary cancer from a population-based cancer registry. This recruitment approach can be used as a paradigm for harmonizing processes and increasing internal and external validity of large-scale public health genomic initiatives in the era of precision medicine.
Keywords: Ovarian Neoplasms; Data Collection; Patient Selection; Breast Neoplasms; Family -- Psychosocial Factors; Adult; Risk Factors; Middle Age; Depression; Survivors; Female; Ovarian Neoplasms -- Psychosocial Factors; Counseling; Breast Neoplasms -- Psychosocial Factors; Human; Randomized Controlled Trials; Random Assignment

Recruitment and Retention Strategies of African American and Latina American Breast Cancer Survivors in a Longitudinal Psycho-Oncology Study. - Ashing-Giwa, Kimlin; Rosales, Monica (Oncology Nursing Forum, 2012)
Purpose/Objectives: To describe recruitment and retention strategies of a psychosocial intervention with African American and Latina American breast cancer survivors (BCSs).Design: Prospective design with pre- and post-testing.Setting: A mailed survey and assignment to telephone counseling or education booklet only.Sample: 587 African American and Latina American BCSs were recruited.Methods: The sample was drawn from the population-based California cancer and hospital registries, as well as community agencies. Mailed self-report health-related quality-of-life assessments were at baseline and 4-6 months follow-up.Main Research Variables: Accrual outcomes; recruitment and retention strategies.Findings: A total of 375 (64%) completed the baseline survey and 320 (55%) completed both baseline and follow-up assessments. The recruitment outcomes suggest that very special attention must be paid to the initial recruitment of Latina Americans to engage their interest and participation. For African Americans, particular attention must be devoted to their retention to address potential attrition.Conclusions: Findings suggest that the inclusion of lower-income and ethnic minority cancer survivors in a longitudinal intervention study is doable. The results indicate that recruitment outcomes are influenced by participant and study characteristics. Successful enrollment requires investigations that attend to culturally and socioecologically informed recruitment and retention strategies, from staff selection, training, and supervision to overall study approach protocol, to address barriers to participation.Implications for Nursing: Nursing research and practice have championed survivorship care, including psychosocial care. This article outlines practical strategies to recruit and retain population-based samples, ethnic minorities, and underserved survivors.
Keywords: Cancer Survivors; Research Subject Recruitment; Research Subject Retention; Black Persons; Hispanic Americans; Human; Prospective Studies; Pretest-Posttest Design; Surveys; Self Report; Quality of Life; Female; Questionnaires; Short Form-36 Health Survey (SF-36); Scales; Telephone; Funding Source

Recruitment and Retention Strategies of African American and Latina American Breast Cancer Survivors in a Longitudinal Psycho-Oncology Study. - Ashing-Giwa, Kimlin; Rosales, Monica (Oncology Nursing Forum, 2012)
Purpose/Objectives: To describe recruitment and retention strategies of a psychosocial intervention with African American and Latina American breast cancer survivors (BCSs).Design: Prospective design with pre- and post-testing.Setting: A mailed survey and assignment to telephone counseling or education booklet only.Sample: 587 African American and Latina American BCSs were recruited.Methods: The sample was drawn from the population-based California cancer and hospital registries, as well as community agencies. Mailed self-report health-related quality-of-life assessments were at baseline and 4-6 months follow-up.Main Research Variables: Accrual outcomes; recruitment and retention strategies.Findings: A total of 375 (64%) completed the baseline survey and 320 (55%) completed both baseline and follow-up assessments. The recruitment outcomes suggest that very special attention must be paid to the initial recruitment of Latina Americans to engage their interest and participation. For African Americans, particular attention must be devoted to their retention to address potential attrition.Conclusions: Findings suggest that the inclusion of lower-income and ethnic minority cancer survivors in a longitudinal intervention study is doable. The results indicate that recruitment outcomes are influenced by participant and study characteristics. Successful enrollment requires investigations that attend to culturally and socioecologically informed recruitment and retention strategies, from staff selection, training, and supervision to overall study approach protocol, to address barriers to participation.Implications for Nursing: Nursing research and practice have championed survivorship care, including psychosocial care. This article outlines practical strategies to recruit and retain population-based samples, ethnic minorities, and underserved survivors.
Keywords: Cancer Survivors; Research Subject Recruitment; Research Subject Retention; Black Persons; Hispanic Americans; Human; Prospective Studies; Pretest-Posttest Design; Surveys; Self Report; Quality of Life; Female; Questionnaires; Short Form-36 Health Survey (SF-36); Scales; Telephone; Funding Source

Recruitment experience in the first phase of the African American Hereditary Prostate Cancer (AAHPC) study. - Royal C; Baffoe-Bonnie A; Kittles R; Powell I; Bennett J; Hoke G; Pettaway C; Weinrich S; Vijayakumar S; Ahaghotu C; Mason T; Johnson E; et al. (Annals of Epidemiology, 2000)
The African American Hereditary Prostate Cancer (AAHPC) Study is an ongoing multicenter genetic linkage study organized by Howard University and the National Human Genome Research Institute (NHGRI), with support from the Office for Research on Minority Health and the National Cancer Institute. The goals of the study are to: (i) look for evidence of involvement of chromosome 1q24-25 (HPC1) in African American men with hereditary prostate cancer (HPC) and (ii) conduct a genome-wide search for other loci associated with HPC in African American men. To accomplish these goals, a network has been established including Howard University, the NHGRI, and six Collaborative Recruitment Centers (CRCs). The CRCs are responsible for the identification and enrollment of 100 African American families. To date, 43 families have been enrolled. Recruitment strategies have included mass media campaigns, physician referrals, community health-fairs/prostate cancer screenings, support groups, tumor registries, as well as visits to churches, barber shops, and universities. By far, the most productive recruitment mechanisms have been physician referrals and tumor registries, yielding a total of 35 (81%) families. Approximately 41% (n = 3400) of probands initially contacted by phone or mail expressed interest in participating; the families of 2% of these met the eligibility criteria, and 75% of those families have been enrolled in the study, indicating a 0.5% recruitment yield (ratio of participants to contacts). As the first large-scale genetic linkage study of African Americans, on a common disease, the challenges and successes of the recruitment process for the AAHPC Study should serve to inform future efforts to involve this population in similar studies.
Keywords: Research Subject Recruitment; Black Persons; Prostatic Neoplasms -- Familial and Genetic; Prostatic Neoplasms -- Epidemiology; Communication Barriers

Recruitment for breast cancer predisposition studies in an underserved African American population. - Patterson A; Davis H; Euhus D; Neuhausen S; Strong L; Tomlinson G (Breast Journal, 2005)
Keywords: Black Persons; Breast Neoplasms -- Ethnology; Breast Neoplasms; Disease Susceptibility; Medically Underserved Area; Patient Selection; Breast Neoplasms -- Prevention and Control; Female; United States; Women's Health

Recruitment of a Population-Based Sample of Young Black Women with Breast Cancer through a State Cancer Registry. - Bonner, Devon; Cragun, Deborah; Reynolds, Monique; Vadaparampil, Susan T.; Pal, Tuya (Breast Journal, 2016)
Given that Black women remain underrepresented in clinical research studies, we sought to recruit a population-based sample of young Black women with breast cancer through a state cancer registry. Demographic and clinical information on all Black women diagnosed with invasive breast cancer at or below age 50 between 2009 and 2012 in Florida was obtained through the state cancer registry. Survivors were invited to participate in the study through state-mandated recruitment methods. Participant demographic and clinical characteristics were compared using Chi-squared tests for categorical variables and the two sample t-test for continuous variables to identify differences between: (i) consented participants versus all other eligible; and (ii) living versus deceased. Of the 1,647 young Black women with breast cancer, mean age at diagnosis was 42.5, with the majority having localized or regional disease, unmarried, privately insured, and employed. There were no significant differences in demographic and clinical variables between the 456 consented study participants versus the remaining 1,191 presumed eligible individuals. Compared to potential participants, women determined to be deceased prior to recruitment ( n = 182) were significantly more likely to have distant disease and a triple-negative phenotype. They were also significantly more likely to be unemployed, and uninsured or have public insurance (i.e., Medicaid or Medicare). Our results demonstrate that recruitment of a population-based sample of breast cancer survivors through a state cancer registry is a feasible strategy in this underserved and underrepresented population. However, survival bias, which was observed due to the lag time between diagnosis and recruitment, is important to adjust for when generalizing findings to all young Black breast cancer patients.
Keywords: Research Subject Recruitment -- Methods; Black Persons; Women; Breast Neoplasms -- Ethnology; Cancer Survivors; Registries, Disease -- Utilization -- Florida; Florida; Chi Square Test; T-Tests; Descriptive Statistics; Data Analysis Software; P-Value; Human; Female; Adult; Middle Age; Socioeconomic Factors; Funding Source; Pilot Studies

Recruitment of African American women for research on breast cancer early detection: using culturally appropriate interventions. - Kelley, Mary Ann (Southern Online Journal of Nursing Research, 2011)
Rural, Southern, African American, women comprise a population that can be difficult to reach for health education. With the health disparity regarding early detection of breast cancer greater among African American women than Caucasian women, a successful program for recruitment of participants is needed. Recruitment strategies used in a study using a 2-group, pre-post intervention design with a booster treatment and a follow-up at 1 and 2 months post-intervention design is described Innovative recruitment methods were implemented to include snowballing, community participation, rural churches, and culturally appropriate interventions. Study findings included a successful recruitment of 159 rural African American participants with 86% retention in the intervention group and 68% retention in the control group. Implications for future studies include using collaborative work between different agencies within rural communities to reach underserved minority populations. Nurses are important partners to reach women in their own communities.
Keywords: Black Persons; Breast Neoplasms -- Diagnosis; Early Diagnosis; Health Education; Research Subject Recruitment; Research Subject Retention; Rural Areas; Breast Self-Examination; Churches; Communication; Conceptual Framework; Cultural Sensitivity; Descriptive Statistics; Environment; Female; Group Processes; Healthy People 2010; Human; Nursing Theory; Patient Compliance; Personal Boundaries; Risk Assessment; Snowball Sample; Southeastern United States; Time Factors; Transcultural Care

Recruitment of Low Income, Predominantly Minority Cancer Survivors to a Randomized Trial of the 'I Can Cope' Cancer Education Program. - Dignan, Mark; Evans, Mary; Kratt, Polly; Pollack, Lori A; Pisu, Maria; Smith, Judith Lee; Prayor-Patterson, Heather; Houston, Peter; Watson, Christopher; Hullett, Sandral; Martin, Michelle Y (Journal of Health Care for the Poor & Underserved, 2011)
Abstract:This report describes recruitment of minority cancer survivors for a randomized trial of I Can Cope, a support program of the American Cancer Society. Survivor Education and Evaluation (SURE), was designed to recruit patients, age 19 and older, with a primary cancer diagnosis. Recruitment was primarily carried out in a public hospital in Birmingham, Alabama. Of 373 patients approached, 226 were eligible for the study, 175 consented, and 140 were randomized during the 20-month recruitment period. Only 43 declined participation. This resulted in a 61.9% recruitment yield. The mean age of participants was 54.2 years (SD=10.9), 92 (65.7%) were female, and 111 (79.3%) were African American. Twenty-three different cancers were represented including breast (37.1%), colorectal (12.1%), hematologic (12.9%), and lung (7.1%). Over half (63%) had been diagnosed within 12 months. The experience of the SURE project provides evidence for optimism in recruiting racial minorities to cancer research studies.
Keywords: Black Persons; Cancer Survivors; Minority Groups; Randomized Controlled Trials; Research Subject Recruitment; Adult; Aged; Alabama; Consent (Research); Demography; Descriptive Statistics; Female; Funding Source; Health Education; Hospitals, Public; Human; Male; Medically Underserved; Middle Age; Research Subject Retention; Socioeconomic Factors; Surveys; Telephone

Recruitment strategy cost and impact on minority accrual to a breast cancer prevention trial. - Dew, Alexander; Khan, Seema; Babinski, Christie; Michel, Nancy; Heffernan, Marie; Stephan, Stefanie; Jordan, Neil; Jovanovic, Borko; Carney, Paula; Bergan, Raymond (Clinical Trials, 2013)
Keywords: Breast Neoplasms -- Prevention and Control; Minority Groups; Research Subject Recruitment -- Illinois; Costs and Cost Analysis; Clinical Trials; Human; Advertising; Illinois; Genistein -- Therapeutic Use; Isoflavones -- Therapeutic Use; Adult; Middle Age; White Persons; Black Persons; Asians; Native Americans; Hispanic Americans; Fisher's Exact Test; Funding Source

Recruitment Techniques and Strategies in a Community-Based Colorectal Cancer Screening Study of Men and Women of African Ancestry. - Davis, Stacy N.; Govindaraju, Swapamthi; Jackson, Brittany; Williams, Kimberly R.; Christy, Shannon M.; Vadaparampil, Susan T.; Quinn, Gwendolyn P.; Shibata, David; Roetzheim, Richard; Meade, Cathy D.; Gwede, Clement K. (Nursing Research, 2018)
Background: Recruiting ethnically diverse Black participants to an innovative, community-based research study to reduce colorectal cancer screening disparities requires multipronged recruitment techniques. Objectives: This article describes active, passive, and snowball recruitment techniques, and challenges and lessons learned in recruiting a diverse sample of Black participants. Methods: For each of the three recruitment techniques, data were collected on strategies, enrollment efficiency (participants enrolled/participants evaluated), and reasons for ineligibility. Results: Five hundred sixty individuals were evaluated, and 330 individuals were enrolled. Active recruitment yielded the highest number of enrolled participants, followed by passive and snowball. Snowball recruitment was the most efficient technique, with enrollment efficiency of 72.4%, followed by passive (58.1%) and active (55.7%) techniques. There were significant differences in gender, education, country of origin, health insurance, and having a regular physician by recruitment technique (p < .05). Discussion:Multipronged recruitment techniques should be employed to increase reach, diversity, and study participation rates among Blacks. Although each recruitment technique had a variable enrollment efficiency, the use of multipronged recruitment techniques can lead to successful enrollment of diverse Blacks into cancer prevention and control interventions.
Keywords: Research Subject Recruitment; Colorectal Neoplasms; Cancer Screening; Black Persons; Healthcare Disparities; Human; Male; Female; Snowball Sample; Florida; Health Information; Middle Age; Funding Source

Rehabilitation for cancer patients at Black Lion hospital, Addis Ababa, Ethiopia: a cross-sectional study. - Worku, Teshager; Semahegn, Agumasie; Tesfaye, Gezahegn; Mengistu, Zuriash (BMC Palliative Care, 2017)
Background: In Ethiopia, there were greater than 2000 adult and 200 pediatric cancer patients annually in 2010, but the estimated number of cancer patients were increasing. Oncologic rehabilitation treatment may result in improved physical and mental impairment. There is a paucity of information about rehabilitation service utilization among cancer patients in Ethiopia. Hence, the purpose of this study was to assess the rehabilitation service for cancer patient and associated factors at Black Lion hospital, Addis Ababa, Ethiopia. Methods: A hospital-based cross-sectional quantitative study was conducted from March to April 2014. Convenient sampling method was employed to recruit the study participants. Interviewer administered questionnaire was used to collect data. Data were entered into EPI data version 3.1 and exported to SPSS (16.0) software for analysis. Descriptive analysis, binary and multiple logistic regression were carried out. Significance association was interpreted using adjusted odds ratio at 95% confidence interval and p-value less than 0.05. Result: A sample of 423 patients aged 18 years and older were involved in the study. Breast cancer (25%), colorectal cancer (20.6%), cervical cancer (14.7%), lymphoma (7.7%), lung (7.2%), leukemia (5.4%), kidney (3.6%) and prostate cancer (2.6%) were the common forms of cancer diagnosed at cancer unit of the Black Lion Hospital. Twenty six percent of cancer patients received rehabilitation service at least once. The main rehabilitation services given were nutritional and psychological support. Unavailability of supplies, lack of professionals and cost of service were among the barriers to receiving rehabilitation services. Conclusion: Only a few cancer patients received cancer rehabilitation services. Increasing the knowledge of the professionals, stocking cancer units with necessary supplies, and other comprehensive programs are needed.
Keywords: Cancer Patients -- Evaluation; Rehabilitation, Cancer; Hospitals; Human; Cross Sectional Studies; Ethiopia; Geographic Locations; Oncology; Physical Activity; Mental Health; Quantitative Studies; Questionnaires; Research Subject Recruitment; Data Analysis Software; Interviews; Odds Ratio; Confidence Intervals; Breast Neoplasms -- Diagnosis; Colorectal Neoplasms; Cervix Neoplasms; Female; Lymphoma; Health Resource Utilization; Male; Adolescence; Adult; Middle Age

Reliability and between-group stability of a health-related quality of life symptom index for persons with anal high-grade squamous intraepithelial lesions: an AIDS Malignancy Consortium Study (AMC-A03). - Atkinson, Thomas M.; Palefsky, Joel; Li, Yuelin; Webb, Andrew; Berry, J. Michael; Goldstone, Stephen; Levine, Rebecca; Wilkin, Timothy J.; Bucher, Gary; Cella, David; Burkhalter, Jack E. (Quality of Life Research, 2019)
Purpose: The Anal Cancer HSIL Outcomes Research (ANCHOR) trial aims to determine whether treating precancerous anal high-grade squamous intraepithelial lesions (HSIL), versus active surveillance, is effective in reducing anal cancer incidence in HIV-infected individuals. We evaluated the reliability (i.e., internal consistency, test-retest) and between-group stability of a 25-item ANCHOR Health-Related Symptom Index (A-HRSI).Methods: ANCHOR participants at least 1-month post-randomization to treatment or active surveillance completed the A-HRSI via telephone. Participants were contacted 7-10 days later to complete the A-HRSI and a participant global impression of change (PGIC) item.Results: Participants (n = 100) were enrolled (mean age = 51.4, 79% cisgender-male, 73% African American, 9% Hispanic) from five ANCHOR sites. Cronbach's α was good for the physical symptoms (0.82) domain and fair for the physical impacts (0.79) and psychological symptoms (0.73) domains. Intraclass correlation coefficients were good for each of respective domains (i.e., 0.80, 0.85, and 0.82). There were no significant differences in PGIC between the treatment (n = 56) and active surveillance (n = 44) groups (F(1,98) = 2.03, p = 0.16).Conclusions: The A-HRSI is able to reliably assess participant-reported symptoms and impacts of anal HSIL across a 7-10 days of timeframe. Future work will involve the establishment of construct and discriminant validity prior to inclusion in the full ANCHOR trial.
Keywords: Cervix Dysplasia -- Therapy; Quality of Life -- Psychosocial Factors; Outcomes (Health Care) -- Methods; Anus Neoplasms -- Prevention and Control; Cervix Dysplasia -- Psychosocial Factors; Self Report; Acquired Immunodeficiency Syndrome -- Complications; Female; Middle Age; Male; Treatment Outcomes; Cervix Dysplasia -- Pathology; Reproducibility of Results; Adult; Scales

Reported Benefits of Participation in a Research Study. - Castillo, Anabella; Jandorf, Lina; Thélémaque, Linda; King, Sheba; Duhamel, Katherine (Journal of Community Health, 2012)
Racial and ethnic minorities are significantly underrepresented in clinical research trials. Several socio-cultural and systemic barriers, ranging from discrimination by the health care system, medical mistrust, to low physician referral rates and lack of knowledge of research studies have been identified as impacting participation. One hundred and fifteen participants were culturally matched and were interviewed followed by up to an additional four interviews over a 12 month period. Responses were analyzed to understand the perceived benefits to participating in a prospective, randomized, longitudinal clinical research trial about screening colonoscopy. Over two-thirds (64.4%) of participants reported 'knowledge, awareness, and/or information about colonoscopy and general health' as being the greatest benefit they received. Desire to undergo the screening and the pride of completing the study was ranked second and third, respectively. Understanding the reasons that participants choose to participate in research studies will ultimately assist researchers close the gap in minority representation, allowing for greater generalizability of research findings.
Keywords: Research Subjects -- Psychosocial Factors; Colonoscopy -- Evaluation; Colorectal Neoplasms -- Diagnosis; Funding Source; Human; Interviews; Randomized Controlled Trials; Prospective Studies; Descriptive Statistics; Black Persons; Health Knowledge -- Evaluation; Male; Female; Middle Age

Reported family history of cancer in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial. - Pinsky PF; Kramer BS; Reding D; Buys S (American Journal of Epidemiology, 2003)
The authors analyzed data from almost 150,000 subjects aged 55-74 years enrolled in the Prostate, Lung, Colorectal, and Ovarian Cancer Screening Trial who completed a self-administered baseline questionnaire (1993-2001) that included items about family history of cancer. Male respondents reported significantly less family history of cancer than females. The relative underreporting by male respondents relative to females was greater for female family members (28% lower for sisters and 21% lower for mothers) than for male family members (13% lower for brothers and 9% lower for fathers). Black, Hispanic, and Asian respondents reported significantly less family history of cancer than Whites. Reported family history prevalences for parents decreased with respondents' age, while those for siblings increased with respondents' age. The four most commonly reported cancers in families were breast (11.8%), lung (10.1%), colorectal (9.4%), and prostate (7.3%) cancer. Expected prevalences in family members of history of cancer overall and history of specific types of cancer were calculated using incidence rates and life table data obtained from the Surveillance, Epidemiology, and End Results Program. Overall, the ratio of reported cancer rates to expected cancer rates in family members was approximately 0.7. Liver, bone, stomach, and brain cancer had greater-than-average reported:expected ratios, while lymphoma, bladder cancer, melanoma, and testicular cancer had lower-than-average ratios.
Keywords: Cancer Screening; Family History; Neoplasms -- Familial and Genetic; Aged; Clinical Trials; Colorectal Neoplasms -- Epidemiology; Colorectal Neoplasms -- Familial and Genetic; Confidence Intervals; Female; Logistic Regression; Lung Neoplasms -- Epidemiology; Lung Neoplasms -- Familial and Genetic; Male; Middle Age; Ovarian Neoplasms -- Epidemiology; Ovarian Neoplasms -- Familial and Genetic; P-Value; Poisson Distribution; Prostatic Neoplasms -- Epidemiology; Prostatic Neoplasms -- Familial and Genetic; Questionnaires; Sex Factors; Human

Representation of Minorities and Elderly Patients in Multiple Myeloma Clinical Trials. - Duma, Narjust; Azam, Tariq; Riaz, Irbaz Bin; Gonzalez‐Velez, Miguel; Ailawadhi, Sikander; Go, Ronald (Oncologist, 2018)
Abstract: Multiple myeloma (MM) occurs in all races, but the incidence in non‐Hispanic black patients (NHBs) is two to three times higher than in non‐Hispanic white patients (NHWs). We determined the representation of minorities and elderly patients in MM clinical trials. Enrollment data from all therapeutic trials reported in ClinicalTrials.gov from 2000 to 2016 were analyzed. Enrollment fraction (EF) was defined as the number of trial enrollees divided by the 2014 MM prevalence. Participation in MM clinical trials varied significantly across racial and ethnic groups; NHWs were more likely to be enrolled in clinical trials (EF 0.18%) than NHBs (EF 0.06%, p < .0001) and Hispanic patients (EF 0.04%, p < .0001). The median age of trial participants was 62 years, with 7,956 participants (66%) being less than 65 years of age. Collaborations between investigators, sponsors, and the community are necessary to increase access to clinical trials to our minority and elderly patients.
Keywords: Multiple Myeloma -- Epidemiology -- In Old Age; Clinical Trials; Minority Groups; Black Persons; White Persons; Human; Aged; Race Factors; Ethnic Groups; Hispanic Americans; Middle Age

Representation of Minorities and Women in Oncology Clinical Trials: Review of the Past 14 Years. - Duma, Narjust; Aguilera, Jesus Vera; Paludo, Jonas; Haddox, Candace L.; Velez, Miguel Gonzalez; Yucai Wang; Leventakos, Konstantinos; Hubbard, Joleen M.; Mansfield, Aaron S.; Go, Ronald S.; Adjei, Alex A. (Journal of Oncology Practice, 2018)
Purpose Many cancer clinical trials lack appropriate representation of specific patient populations, limiting their generalizability. Therefore, we determined the representation of ethnic minorities and women in cancer clinical trials. Methods Enrollment data from all therapeutic trials reported as completed in ClinicalTrials.gov from 2003 to 2016 were analyzed. We calculated enrollment fractions (EFs) for each group, defined as the number of enrollees divided by the 2013 Surveillance, Epidemiology, and End Results (SEER) database cancer prevalence. Results Of 1,012 clinical trials, 310 (31%) reported ethnicity with a total of 55,689 enrollees. Participation varied significantly across ethnic groups. Non-Hispanic whites were more likely to be enrolled in clinical trials (EF, 1.2%) than African Americans (EF, 0.7%; P,.001) and Hispanics (EF, 0.4%; P , .001). A decrease in African American (6% v 9.2%) and Hispanic (2.6% v 3.1%) enrollment was observed when compared with historical data from 1996 to 2002. Younger patients (age younger than 65 years) were more likely to be enrolled in clinical trials than the elderly (64% v 36%; P,.001). Low recruitment of female patients was observed in clinical trials for melanoma (35%), lung cancer (39%), and pancreatic cancer (40%). Conclusion Weobserved a decrease in recruitment of minorities over the past14 years compared with historical data. African Americans, Hispanics, and women were less likely to be enrolled in cancer clinical trials. Future trials should take extra measures to recruit participants that adequately represent the US cancer population.
Keywords: Oncology; Clinical Trials; Human; Female; Minority Groups; Databases; Time Factors; Systematic Review; Bias (Research)

Research and under represented groups. - Broome B (Journal of Cultural Diversity, 2007)
Keywords: Medically Underserved; Research Subjects; Aged; Australia; Black Persons; Immunization -- In Old Age; Patient Attitudes; Prostatic Neoplasms; Race Factors; Transcultural Care

Rethinking sources of representative controls for the conduct of case-control studies in minority populations. - Bandera, Elisa V; Chandran, Urmila; Zirpoli, Gary; McCann, Susan E; Ciupak, Gregory; Ambrosone, Christine B (BMC Medical Research Methodology, 2013)
Background: Recruitment of controls remains a challenge in case-control studies and particularly in studies involving minority populations.Methods: We compared characteristics of controls recruited through random digit dialing (RDD) to those of community controls enrolled through churches, health events and other outreach sources among women of African ancestry (AA) participating in the Women's Circle of Health Study, a case-control study of breast cancer. Odds ratios and 95% confidence intervals were also computed using unconditional logistic regression to evaluate the impact of including the community controls for selected variables relevant to breast cancer and for which there were significant differences in distribution between the two control groups.Results: Compared to community controls (n=347), RDD controls (n=207) had more years of education and higher income, lower body mass index, were more likely to have private insurance, and less likely to be single. While the percentage of nulliparous women in the two groups was similar, community controls tended to have more children, have their first child at a younger age, and were less likely to breastfeed their children. Dietary intake was similar in the two groups. Compared to census data, the combination of RDD and community controls seems to be more representative of the general population than RDD controls alone. Furthermore, the inclusion of the community group had little impact on the magnitude of risk estimates for most variables, while enhancing statistical power.Conclusions: Community-based recruitment was found to be an efficient and feasible method to recruit AA controls.
Keywords: Breast Neoplasms -- Epidemiology; Adenocarcinoma -- Epidemiology; Case Control Studies; Control Group; Minority Groups; Adult; Black Persons; Aged; White Persons; Female; Human; Male; Middle Age; Patient Selection; Study Design; Risk Factors; Young Adult

Review: aromatherapy massage is associated with small, transient reductions in anxiety...commentary on Cooke B, Ernst E. Aromatherapy: a systematic review. BR J GEN PRACT 2000 Jan;50:493-6 - Flemming K (Evidence Based Nursing, 2000)
QUESTION: Does aromatherapy (treatment with aromatic plant extracts known as essential oils) have an effect on clinical outcomes in patients with various conditions? Data sources: Clinical trials that were published in any language up to June 1999 were identified by searching Medline, EMBASE/Excerpta Medica, British Nursing Index, CISCOM, and AMED using the terms alternative medicine, massage, essential oils, and aromatherapy; and by contacting experts. Study selection: Randomised controlled trials of the use of aromatherapy in human patients were included. Studies of the local effects of aromatherapy (eg, antiseptic effects of tea tree oil) and pre-clinical studies of healthy volunteers were excluded. Data extraction: Data were extracted on the condition under investigation, sample characteristics, type of intervention and placebo, outcomes, and results. Methodological quality of studies was assessed using the Jadad scale (randomisation, blinding, and accounting for dropouts). Main results: 12 studies were identified. 6 trials evaluated the effects of aromatherapy massage on anxiety or wellbeing in patients with cancer, patients who had cardiac surgery, and patients in an intensive care unit. All interventions were given by nurses in hospital settings. Jadad scores for methodological quality ranged from 0-2 out of 5, with a rating of 5 indicating the highest quality. Study results could not be pooled because of study heterogeneity. 5 of the studies reported that patients who received aromatherapy massage had small reductions in anxiety or improvements in wellbeing immediately after the intervention: foot massage with plain oil plus orange blossom oil; massage with oil plus aroma; massage plus lavender oil; and full body massage with bland oil plus chamomile oil (2 studies). 1 study of massage with almond oil plus English lavender oil compared with spike lavender oil found no group differences for anxiety. The remaining 6 trials each dealt with the effects of a unique intervention on a specific condition. 5 of the trials found a benefit of aromatherapy over placebo or control: inhalation of a vaporised aromatic mixture to improve pulmonary function in the common cold; oral aromatic liquid to prevent relapse of bronchitis; dummy cigarettes with black pepper smell or menthol smell for smoking withdrawal symptoms; inhalation of steam plus aroma for anxiety; and scalp massage of carrier oils plus essential oils for alopecia areata. 1 study found no difference for bath water with natural or synthetic lavender oil and placebo for perineal discomfort after childbirth. Conclusions: Aromatherapy massage has a small, transient effect on reduction of anxiety immediately after administration. Individual studies suggest possible benefits of inhaled or oral aromatherapy for various conditions.
Keywords: Aromatherapy; Massage; Anxiety -- Prevention and Control; Clinical Trials; Systematic Review; Treatment Outcomes; Psychological Well-Being; Cancer Patients; Cardiac Patients; Critically Ill Patients

Screening and prevention trials step up minority recruitment. - Reynolds T; Reynolds, T (JNCI: Journal of the National Cancer Institute, 1996)
Keywords: Clinical Trials; Health Screening -- Statistics and Numerical Data; Minority Groups -- Statistics and Numerical Data; Neoplasms -- Prevention and Control; Black Persons -- Statistics and Numerical Data; Breast Neoplasms -- Prevention and Control; Female; Hispanic Americans -- Statistics and Numerical Data; Male; Prostatic Neoplasms -- Prevention and Control; United States

Screening strategies for the detection of anal high-grade squamous intraepithelial lesions in women living with HIV. - Chiao, Elizabeth Y.; Lensing, Shelly Y.; Wiley, Dorothy J.; Deshmukh, Ashish A.; Lee, Jeannette; Darragh, Teresa M.; Einstein, Mark H.; Jay, Naomi; Berry-Lawhorn, John Michael; Palefsky, Joel M.; Wilkin, Timothy; Barroso, Luis F.; et al. (AIDS (02699370), 2020)
Objective: HIV-infected women (WLHIV) have more than 10-fold higher risk for squamous cell cancer of the anus. Experts suggest cytology-based strategies developed for cervical cancer screening may prevent anal cancer by detecting anal cytologic or histological high-grade squamous intraepithelial lesion (hHSIL) for treatment. Currently, there is no consensus on anal-hHSIL screening strategies for WLHIV.Design: Between 2014 and 2016, 276 WLHIV were recruited at 12 US AIDS Malignancy Consortium clinical trials sites to evaluate hHSIL prevalence and (test) screening strategies.Methods: Participants completed detailed questionnaire, underwent anal assessments including high-risk human papillomavirus (hrHPV) testing using hrHPV-Hybrid Capture 2 (HC2) and hrHPV-APTIMA, anal cytology, and concurrent high-resolution anoscopy. Screening test characteristics for predicting hHSIL validated by central review of histologic diagnosis were estimated sensitivity, specificity, positive predictive value, and false-omission rate. Paired analyses compared sensitivity and specificity for hrHPV single tests to anal cytology alone.Results: 83% (229/276) of enrolled WLHIV had complete anal assessment data and were included in this analysis. Mean age was 50, 62% black and 60 (26%) had hHSIL. Anal cyotology (>atypical squamous cells of undetermined significance), hrHPV-HC2, and hrHPV-APTIMA sensitivity estimates were similarly high (83, 77, and 75%, respectively, P values > 0.2). Specificity was higher for both hrHPV-APTIMA and hrHPV-HC2 compared with anal cytology (67 vs. 50%, P < 0.001) and (61 vs. 50%, P = 0.020), respectively.Conclusion: Anal hrHPV testing demonstrated similar sensitivity for anal cytology (>atypical squamous cells of undetermined significance) to predict anal hHSIL. Among tests with similar sensitivity, the specificity was significantly higher for hrHPV-APTIMA and hrHPV-HC2. Thus, anal hrHPV testing may be an important alternative strategy to anal cytology for anal hHSIL screening among WLHIV.
Keywords: Papillomavirus Infections -- Pathology; Anus Neoplasms; HIV Infections -- Pathology; Anus Neoplasms -- Pathology; Anus Neoplasms -- Diagnosis; Female; Middle Age; Early Detection of Cancer; Human; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Scales

Sexual minority women's coping and psychological adjustment after a diagnosis of breast cancer. - Boehmer U; Linde R; Freund KM (Journal of Women's Health (15409996), 2005)
OBJECTIVE: To determine factors that influence sexual minority women's coping responses and adjustment to breast cancer. METHODS: We conducted a cross-sectional study with 64 sexual minority women with breast cancer who were recruited through targeted community-based sampling. In this study, sexual minority women consisted of three sexual orientation groups: those who self-reported partnering with women and those with a lesbian or bisexual identity. We determined the number of years of sexual minority status and disclosure of sexual orientation and used standardized measures to assess these women's coping and adjustment to breast cancer. Data were analyzed using statistical methods as appropriate for the level of data. RESULTS: We determined that sexual minority factors, such as sexual orientation group, influenced coping and adjustment even after illness and social support factors were controlled. In multivariate analyses, women who identified as lesbians or bisexuals used less maladaptive coping compared with women who reported partnering with women. The association between reporting a lesbian identity and lower distress approached significance in multivariate regression equations. CONCLUSIONS: Of the sexual minority factors that were considered, sexual orientation group, number of years of sexual minority status, and disclosure of sexual minority status, only sexual orientation group was related to coping and lower distress. Contrary to expectations, disclosure of sexual orientation did not relate to coping and lower distress. The findings support the need for future studies to include different aspects of sexual minority status, in particular, clearly defined sexual orientation groups.
Keywords: Attitude to Illness; Breast Neoplasms -- Psychosocial Factors; Minority Groups -- Psychosocial Factors; Adaptation, Psychological; Analysis of Variance; Attitude Measures; Audiorecording; Bisexuality; Black Persons; Breast Neoplasms -- Drug Therapy; Breast Neoplasms -- Surgery; Breast Neoplasms -- Therapy; Confidence Intervals; Coping; Dependent Variable; Descriptive Statistics; Female; Fisher's Exact Test; Hispanic Americans; Independent Variable; Lesbians; Odds Ratio; Pearson's Correlation Coefficient; Psychological Tests; Questionnaires; Research Subject Recruitment; Scales; Secondary Analysis; Self Report; Semi-Structured Interview; Stress, Psychological; Support, Psychosocial; T-Tests; Human

Short- and long-term risk of colorectal adenoma recurrence among whites and blacks. - Laiyemo, Adeyinka O.; Doubeni, Chyke; Brim, Hassan; Ashktorab, Hassan; Schoen, Robert E.; Gupta, Samir; Charabaty, Aline; Lanza, Elaine; Smoot, Duane T.; Platz, Elizabeth; Cross, Amanda J. (Gastrointestinal Endoscopy, 2013)
Background: It is unclear whether the higher burden from colorectal cancer among blacks is due to an increased biological susceptibility. Objective: To determine whether non-Hispanic blacks (blacks) have a higher risk of adenoma recurrence than non-Hispanic whites (whites) after removal of colorectal adenoma. Design: Secondary analysis of the Polyp Prevention Trial (PPT) data. Setting: United States. Patients: Patients were 1668 self-identified whites and 153 blacks who completed the 4-year trial. Of these, 688 whites and 55 blacks enrolled in a posttrial, passive Polyp Prevention Trial Continued Follow-up Study (PPT-CFS) and underwent another colonoscopy. Main Outcome Measurements: Recurrence and location of the adenoma and advanced adenoma by race-ethnicity during PPT and cumulative recurrence over a mean follow-up of 8.3 years (range, 4.9-12.4 years) among PPT-CFS enrollees. Results: Blacks had similar risk of recurrence of adenoma (39.2% vs 39.4%; incidence risk ratio [RR] = .98; 95% CI, .80-1.20) and advanced adenoma (8.5% vs 6.4%; RR = 1.18; 95% CI, .68-2.05) as whites at the end of PPT. Recurrence risk did not differ by colon subsite. Among PPT-CFS enrollees, the cumulative recurrence rate over a maximal follow-up period of 12 years was similar for blacks and whites for adenoma (67.3% vs 67.0%; RR = 1.01; 95% CI, .84-1.21) and advanced adenoma (14.5% vs 16.9%; RR = 1.03; 95% CI, .60-1.79). Limitation: There were few blacks in the long-term follow-up study. Conclusions: Adenoma and advanced adenoma recurrence did not differ by race. Our study does not support more frequent surveillance colonoscopies for blacks with a personal history of adenoma as an intervention to reduce colorectal cancer disparity.
Keywords: Colorectal Neoplasms -- Prognosis; Adenoma -- Risk Factors; Recurrence; Human; White Persons; Black Persons; Education, Continuing (Credit); United States; Academic Medical Centers; Quality of Health Care; Wilcoxon Rank Sum Test; Mann-Whitney U Test; Poisson Distribution; Regression; Confidence Intervals; Relative Risk; Data Analysis Software; Sensitivity and Specificity; Male; Female; Middle Age; Aged; Descriptive Statistics; Funding Source

Simulation-based training for thoracoscopic lobectomy: a randomized controlled trial: virtual-reality versus black-box simulation. - Jensen, Katrine; Ringsted, Charlotte; Hansen, Henrik Jessen; Petersen, René Horsleben; Konge, Lars (Surgical Endoscopy, 2014)
Background: Video-assisted thoracic surgery is gradually replacing conventional open thoracotomy as the method of choice for the treatment of early-stage non-small cell lung cancers, and thoracic surgical trainees must learn and master this technique. Simulation-based training could help trainees overcome the first part of the learning curve, but no virtual-reality simulators for thoracoscopy are commercially available. This study aimed to investigate whether training on a laparoscopic simulator enables trainees to perform a thoracoscopic lobectomy.Methods: Twenty-eight surgical residents were randomized to either virtual-reality training on a nephrectomy module or traditional black-box simulator training. After a retention period they performed a thoracoscopic lobectomy on a porcine model and their performance was scored using a previously validated assessment tool.Results: The groups did not differ in age or gender. All participants were able to complete the lobectomy. The performance of the black-box group was significantly faster during the test scenario than the virtual-reality group: 26.6 min (SD 6.7 min) versus 32.7 min (SD 7.5 min). No difference existed between the two groups when comparing bleeding and anatomical and non-anatomical errors.Conclusion: Simulation-based training and targeted instructions enabled the trainees to perform a simulated thoracoscopic lobectomy. Traditional black-box training was more effective than virtual-reality laparoscopy training. Thus, a dedicated simulator for thoracoscopy should be available before establishing systematic virtual-reality training programs for trainees in thoracic surgery.
Keywords: Computer Simulation; Computer Assisted Instruction; Internship and Residency; Pneumonectomy -- Methods; Thoracic Surgery -- Education; Thoracoscopy -- Education; User-Computer Interface; Adult; Animals; Carcinoma, Non-Small-Cell Lung -- Surgery; Female; Human; Learning; Male; Swine

Sistas Inspiring Sistas Through Activity and Support (SISTAS): Study Design and Demographics of Participants. - Bevel, Malcolm; Babatunde, Oluwole A.; Heiney, Sue P.; Brandt, Heather M.; Wirth, Michael D.; Hurley, Thomas G.; Khan, Samira; Johnson, Hiluv; Wineglass, Cassandra M.; Warren, Tatiana Y.; Murphy, E. Angela; Sercy, Erica; et al. (Ethnicity & Disease, 2018)
Introduction: Recruiting racial, ethnic, and other underserved minorities into conventional clinic-based and other trials is known to be challenging. The Sistas Inspiring Sistas Through Activity and Support (SISTAS) Program was a one-year randomized controlled trial (RCT) to promote physical activity and healthy eating among AA women in SC to reduce inflammatory biomarkers, which are linked to increased breast cancer (BrCa) risk and mortality. This study describes the development, recruitment, and implementation of the SISTAS clinical trial and provides baseline characteristics of the study participants.Methods: SISTAS was developed using community-based participatory research (CBPR) approaches. At baseline, study participants completed assessments and underwent clinical measurements and blood draws to measure C-reactive protein (CRP) and interleukin-6 (IL-6). Participants randomized to the intervention received 12 weekly classes followed by nine monthly booster sessions. Post-intervention measurements were assessed at 12-week and 12-month follow-ups.Results: We recruited a total of 337 women who tended to: be middle-aged (mean age 48.2 years); have some college education; be employed full-time; have Medicare as their primary insurance; be non-smokers; and perceive their personal health as good. On average, the women were pre-hypertensive at baseline (mean systolic blood pressure = 133.9 mm Hg; mean diastolic blood pressure = 84.0 mm Hg) and morbidly obese (mean BMI >40.0 kg/m2); the mean fat mass and fat-free mass among participants were 106.4 lb and 121.0 lb, respectively.Conclusion: The SISTAS RCT addresses some of the gaps in the literature with respect to CBPR interventions targeting AA women, such as implementing diet and physical activity in CBPR-based studies to decrease BrCa risk.
Keywords: Obesity, Morbid -- Psychosocial Factors; Exercise; Obesity, Morbid -- Ethnology; Obesity, Morbid -- Diagnosis; Exercise -- Psychosocial Factors; United States; Outcome Assessment; Black Persons -- Statistics and Numerical Data; Patient Selection; Human; Health Services Research; Female; Middle Age; Black Persons -- Psychosocial Factors; Health Promotion -- Methods; Attitude to Health; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Personal Resource Questionnaire; Scales

Sisterhood is powerful: the Sister Study breast cancer research. - Wessling S (Minority Nurse, 2006)
The Sister Study, a landmark national study investigating the causes of breast cancer, wants to recruit as ethnically diverse a participant sample as possible. And nurses can help spread the word.
Keywords: Breast Neoplasms -- Familial and Genetic; Minority Groups; Research Subject Recruitment; Siblings; Adult; Aged; Asians; Black Persons; Cultural Diversity; Environment; Female; Hispanic Americans; Middle Age; National Institutes of Health (U.S.); Native Americans; Prospective Studies; Puerto Rico; Transcultural Nursing; United States; White Persons

Smoking trends in the United States between 1969 and 1995 based on patients hospitalized with non-smoking-related diseases. - Zang EA; Wynder EL (Preventive Medicine, 1998)
BACKGROUND: This study examines smoking trends in the United States by race, gender, education, and occupation. METHODS: The data were collected between 1969 and 1995 through a hospital-based case-control study on tobacco-related cancers, including 21,057 male and 14,448 female control subjects who had been diagnosed of non-smoking-related diseases. Smoking measures were adjusted through direct standardization and regression methods. RESULTS: Despite the decline in smoking, daily cigarette consumption remained high among current smokers. Women's smoking prevalence decreased more slowly than men's and their age at smoking initiation also declined, while the inverse effects on smoking by education and occupation were more pronounced in men than in women. Smoking prevalence was higher, but daily cigarette consumption was lower in blacks compared to caucasians. CONCLUSIONS: Despite an overall downward trend in smoking, lung cancer remains a major public health concern, particularly among women, blacks, and white men with low education. The development of a systematic mechanism for more detailed, regular monitoring of tobacco use by various subpopulations is, therefore, crucial to future public health planning. Copyright (c) 1998 by Academic Press
Keywords: Smoking -- Trends; Case Control Studies; Research Subject Recruitment; Interviews; Data Analysis, Statistical; Race Factors; Sex Factors; Socioeconomic Factors; Black Persons; White Persons; Inpatients; Male; Female; Funding Source; Human

Social and racial differences in selection of breast cancer adjuvant chemotherapy regimens. - Griggs JJ; Culakova E; Sorbero ME; Poniewierski MS; Wolff DA; Crawford J; Dale DC; Lyman GH (Journal of Clinical Oncology, 2007)
PURPOSE: Breast cancer outcomes are worse among black women and women of lower socioeconomic status. The purpose of this study was to investigate racial and social differences in selection of breast cancer adjuvant chemotherapy regimens. METHODS: Detailed information on patient, disease, and treatment factors was collected prospectively on 957 patients who were receiving breast cancer adjuvant chemotherapy in 101 oncology practices throughout the United States. Adjuvant chemotherapy regimens included in any of several published guidelines were considered standard. Receipt of nonstandard regimens was examined according to clinical and nonclinical factors. Differences between groups were assessed using chi2 tests. Multivariate logistic regression was used to identify factors associated with use of nonstandard regimens. RESULTS: Black race (P = .008), lower educational attainment (P = .003), age 70 years (P = .001), higher stage (P < .0001), insurance type (P = .048), employment status (P = .045), employment type (P = .025), and geographic location (P = .021) were associated with the use of nonstandard regimens in univariate analyses. In multivariate analysis, black race (P = .020), lower educational attainment (P = .024), age > or = 70 years (P = .032), and higher stage (P < .0001) were associated with receipt of nonstandard regimens. CONCLUSION: The more frequent use of non-guideline-concordant adjuvant chemotherapy regimens in black women and women with lower educational attainment may contribute to less favorable outcomes in these populations. Addressing such differences in care may improve cancer outcomes in vulnerable populations.
Keywords: Antineoplastic Agents, Combined -- Therapeutic Use; Breast Neoplasms -- Drug Therapy; Breast Neoplasms -- Ethnology; Adult; Age Factors; Aged; Aged, 80 and Over; Chemotherapy, Adjuvant; Chi Square Test; Educational Status; Employment; Female; Insurance, Health; Logistic Regression; Middle Age; Neoplasm Staging; Patient Selection; Prospective Studies; Risk Factors; Treatment Outcomes; United States; Human

Social factors affecting interest in participating in a prostate cancer chemoprevention trial. - Lee MM; Chamberlain RM; Catchatourian R; Hiang J; Kopnick M; Ray P; Vijayakumar S (Journal of Cancer Education, 1999)
PURPOSE: A sample survey was conducted to assess the feasibility of recruiting participants, specifically African Americans, and to determine social factors influencing participation in a prostate cancer chemoprevention trial. METHODS: A convenience sample of adults visiting a hospital was identified and asked to participate in the survey. The survey included brief background information about prostate cancer and questions concerning four independent (age, marital status, race, insurance status) and three dependent (willingness to join a trial, involvement in long-term drug intake, interest in receiving more information) variables. RESULTS: The study analyzed 165 responses. Of the 165 respondents, 67% were African American. Marital status was a significant predictor of general willingness to participate (p = 0.047) for male respondents. No significant predictor was found for female respondents. Furthermore, for men, ethnicity/race showed a significant difference (30% white men vs 70% of minority men) for willingness to take the pills. CONCLUSION: The results suggest that African Americans are receptive to participating in chemopreventive trials. Thus, future studies exploring chemoprevention trials as an effective tool for reaching African Americans are warranted.
Keywords: Research Subjects -- Psychosocial Factors; Consumer Participation; Preventive Trials; Prostatic Neoplasms -- Prevention and Control; Exploratory Research; Research Subject Recruitment; Chemoprevention; Surveys; Convenience Sample; Questionnaires; Univariate Statistics; Bivariate Statistics; Data Analysis Software; Pearson's Correlation Coefficient; P-Value; Logistic Regression; Age Factors; Sex Factors; Race Factors; Marital Status; Middle Age; Male; Female; Black Persons; Poverty Areas; Hospitals, Urban; Illinois; Human

Social factors matter in cancer risk and survivorship. - Dean, Lorraine T.; Gehlert, Sarah; Neuhouser, Marian L.; Oh, April; Zanetti, Krista; Goodman, Melody; Thompson, Beti; Visvanathan, Kala; Schmitz, Kathryn H. (Cancer Causes & Control, 2018)
Greater attention to social factors, such as race/ethnicity, socioeconomic position, and others, are needed across the cancer continuum, including breast cancer, given differences in tumor biology and genetic variants have not completely explained the persistent Black/White breast cancer mortality disparity. In this commentary, we use examples in breast cancer risk assessment and survivorship to demonstrate how the failure to appropriately incorporate social factors into the design, recruitment, and analysis of research studies has resulted in missed opportunities to reduce persistent cancer disparities. The conclusion offers recommendations for how to better document and use information on social factors in cancer research and care by (1) increasing education and awareness about the importance of inclusion of social factors in clinical research; (2) improving testing and documentation of social factors by incorporating them into journal guidelines and reporting stratified results; and (3) including social factors to refine extant tools that assess cancer risk and assign cancer care. Implementing the recommended changes would enable more effective design and implementation of interventions and work toward eliminating cancer disparities by accounting for the social and environmental contexts in which cancer patients live and are treated.
Keywords: Neoplasms -- Psychosocial Factors; Ethnic Groups; Socioeconomic Factors; Neoplasms -- Ethnology; Population; Risk Factors; Scales; Social Readjustment Rating Scale

Social processes used by African American women in making decisions about mammography screening. - Fowler BA (Journal of Nursing Scholarship, 2006)
Purpose: To describe the social processes used by African American (AA) women ages >=50 years in making decisions about mammography screening. Design: Grounded theory methodology. Methods: Tape-recorded interviews with a researcher-designed, semi-structured interview guide with an initial and theoretical sample of 30 AA women ages 52 to 71 of diverse socioeconomic status. Interviews occurred in various settings such as the church rectory, women's homes, and work settings. Extensive written field notes and tapes were transcribed verbatim immediately after the interviews by an experienced transcriptionist. Findings: The women's decisions about mammography screening were associated with five social processes: (a) acknowledging prior experiences with healthcare providers and systems; (b) reporting fears and fatalistic beliefs of breast cancer and related treatment; (c) valuing the opinions of significant others; (d) relying on religious beliefs and supports; and (e) caregiving responsibilities of significant others. The processes were further differentiated by three distinct decision-making styles: taking charge, enduring, and protesting. Conclusions: Each of the social processes was reported equally and emphasized by the diverse sample of AA women in decisions related to mammography screening. Mammography screening decisions were heavily influenced by caregiving responsibilities. Further research is needed to explain and understand this social process on the health and well-being of AA women over time.
Keywords: Black Persons; Decision Making; Mammography; Aged; Audiorecording; Churches; Coding; Constant Comparative Method; Decision Making -- Classification; Female; Field Notes; Funding Source; Grounded Theory; Health Beliefs; Interview Guides; Knowledge; Middle Age; Qualitative Validity; Research Subject Recruitment; Semi-Structured Interview; Socialization; Socioeconomic Factors; Theoretical Sample; Human

Social workers as patient navigators for breast cancer survivors: what do African-American medically underserved women think of this idea? - Davis C; Darby K; Likes W; Bell J (Social Work in Health Care, 2009)
Patient navigation (PN) is a new initiative in health care aimed at reducing disparities by assisting patients in overcoming barriers within the health care system. As PN programs grow around the country, it is important to consult the key stakeholders in the development of these programs. The purpose of this qualitative study was to discuss the needs of medically underserved cancer patients and allow them the opportunity to provide input on models of care to meet their needs. Four focus groups were conducted in three major cities across Tennessee. Research participants (n = 36) were recruited by the staff in area cancer support programs and treatment programs across the state and through recruitment flyers at various treatment centers and community organizations. Findings revealed four key themes in the development of PN programs: (1) the PN needs to address access to quality care issues; (2) the PN needs to address the emotional and practical concerns of the cancer survivor; (3) the PN needs to address family concerns; (4) the PN needs to be involved across the continuum of care from time of diagnosis into long-term survivorship. Oncology social workers have a unique opportunity to meet the needs of medically underserved cancer patients through the PN movement. Our profession is a key stakeholder in this movement. We need to advocate for trained oncology social workers to actively pursue the role of patient navigators to ensure that the needs of medically underserved cancer survivors and their families are met.
Keywords: Black Persons; Cancer Patients; Health Services Accessibility; Patient Advocacy; Social Workers; Breast Neoplasms; Cancer Survivors; Continuity of Patient Care; Exploratory Research; Family Relations; Female; Focus Groups -- Tennessee; Funding Source; Health Care Delivery -- Methods; Health Services Needs and Demand; Holistic Care; Medically Uninsured; Poverty; Professional Role; Program Development; Qualitative Studies; Quality Assurance; Support Groups; Tennessee; Thematic Analysis; Treatment Delay -- Prevention and Control; Human

Spiritual support and African American breast cancer survivors. - Roff LL; Simon CE; Nelson-Gardell D; Pleasants HM (Affilia: Journal of Women & Social Work, 2009)
The qualitative study used data from interviews with 18 African American breast cancer survivors in the southeast regarding the women's live experiences of spiritual support during the process of breast cancer diagnosis and treatment. Through a thematic content analysis, four primary sources of spiritual support were identified: God, members of religious communities, family members and friends, and health care professionals. Some participants reported negative experiences associated with the reactions of religious community members to their breast cancer. Those who received spiritual support from their health care providers reported welcoming such support.
Keywords: Breast Neoplasms; Cancer Survivors; Spirituality; Support, Psychosocial; Advertising; Audiorecording; Black Persons; Churches; Coding; Content Analysis; Data Analysis Software; Descriptive Statistics; Educational Status; Female; Funding Source; Interviews; Marital Status; Middle Age; Neoplasm Staging; Public Health; Qualitative Studies; Research Subject Recruitment; Research Subjects -- Economics; Sample Size; Human

Spirituality, breast cancer beliefs and mammography utilization among urban African American women. - Holt CL; Lukwago SN; Kreuter MW (Journal of Health Psychology, 2003)
Spirituality has been shown to be associated with health, and is an important component in the lives of many African Americans. Recent research proposes that spirituality is a multidimensional construct. The present study proposes a two-dimensional model in which spirituality encompasses a belief and behavioral dimension. This hypothesis was examined, as were relationships between these dimensions and spiritual health locus of control, breast cancer beliefs and mammography utilization among African American women. The belief dimension played a more important role in adaptive breast cancer beliefs and mammography utilization that did the behavioral dimension. These findings suggest the importance of spiritual belief systems for health, and implications for spiritual cancer communication interventions are discussed.
Keywords: Black Persons -- Missouri; Breast Neoplasms -- Prevention and Control; Health Beliefs -- Evaluation; Mammography -- Utilization; Spirituality; Adult; Age Factors; Chi Square Test; Christianity; Confidence Intervals; Descriptive Statistics; Factor Analysis; Female; Health Knowledge -- Evaluation; Locus of Control -- Evaluation; Logistic Regression; Middle Age; Missouri; Models, Theoretical -- Evaluation; Multivariate Analysis of Covariance; Odds Ratio; Pearson's Correlation Coefficient; Questionnaires; Race Factors; Research Subject Recruitment; Rural Areas; Scales; Test-Retest Reliability; Theory Construction; Funding Source; Human

Spiritually based intervention to increase colorectal cancer awareness among african americans: intermediate outcomes from a randomized trial. - Holt CL; Scarinci IC; Debnam K; McDavid C; Litaker M; McNeal SF; Southward V; Lee C; Eloubeidi M; Crowther M; Bolland J; Martin MY; et al. (Journal of Health Communication, 2012)
Colorectal cancer screening, while effective for reducing mortality, remains underutilized particularly among underserved populations such as African Americans. The present study evaluated a spiritually based approach to increasing Health Belief Model-based pre-screening outcomes in a Community Health Advisor-led intervention conducted in African American churches. Sixteen urban churches were randomized to receive either the spiritually based intervention or a nonspiritual comparison of the same structure and core colorectal cancer content. Trained Community Health Advisors led a series of two educational sessions on colorectal cancer early detection. The educational sessions were delivered over a 1-month period. Participants (N = 316) completed a baseline survey at enrollment and a follow-up survey one month after the first session. Both interventions resulted in significant pre/post increases in knowledge, perceived benefits of screening, and decreases in perceived barriers to screening. Among women, the spiritually based intervention resulted in significantly greater increases in perceived benefits of screening relative to the nonspiritual comparison. This finding was marginal in the sample as a whole. In addition, perceived benefits to screening were associated with behavioral intention for screening. It is concluded that in this population, the spiritually based was generally as effective as the nonspiritual (secular) communication.
Keywords: Black Persons -- Education; Colorectal Neoplasms -- Ethnology; Health Education -- Methods; Attitude to Health -- Ethnology; Spirituality; Black Persons -- Psychosocial Factors; Aged; Female; Prospective Studies; Human; Male; Middle Age; Program Evaluation; Urban Population; Clinical Trials

Strategic recruitment of an ethnically diverse cohort of overweight survivors of breast cancer with lymphedema. - Sturgeon, Kathleen M.; Hackley, Renata; Fornash, Anna; Dean, Lorraine T.; Laudermilk, Monica; Brown, Justin C.; Sarwer, David B.; DeMichele, Angela M.; Troxel, Andrea B.; Schmitz, Kathryn H. (Cancer (0008543X), 2018)
Background: Black women are more likely to experience adverse effects from cancer treatment such as lymphedema. Thus, black women may particularly benefit from research regarding interventions to improve lymphedema. Herein, the authors report the challenges and strategies related to the recruitment of minority survivors of breast cancer and to the recruitment of survivors of breast cancer with lymphedema into the Women In Steady Exercise Research (WISER) Survivor Clinical Trial.Methods: Subjects for this community-based trial were recruited from the Philadelphia area through active (mailings) and passive (printed materials and Web site) recruitment strategies. In addition, education sessions coordinated through partner hospitals in communities with a predominantly minority population were conducted to increase awareness of lymphedema in survivors of breast cancer. Women who were interested in the study were screened for lymphedema via telephone questionnaire and invited to see a study-related certified lymphedema therapist to confirm the presence of lymphedema.Results: Screening was conducted among 2295 women: 628 were eligible, 450 consented, and 351 were randomized. Minority women comprised 38% of the study population. Letters to women on state and hospital registries resulted in a 0.4% randomization rate; education sessions yielded a 10% randomization rate. The authors observed that approximately 23.6% of the study sample had no previous diagnosis of lymphedema.Conclusions: The WISER Survivor Clinical Trial faced multiple recruitment challenges and used unique strategies to successfully enroll minority survivors of breast cancer into a lifestyle intervention. Cancer 2018;124:95-104. © 2017 American Cancer Society.
Keywords: White Persons; Patient Selection; Breast Neoplasms; Therapeutic Exercise; Black Persons; Obesity -- Therapy; Weight Reduction Programs; Weight Loss; Minority Groups; Female; Ethnic Groups; Obesity -- Complications; Clinical Trials; Aged; Middle Age; Exercise of Self-Care Agency Scale; Scales

Strategies for recruiting African American men into prostate cancer screening studies. - Jones RA; Steeves R; Williams I (Nursing Research, 2009)
BACKGROUND: Recruitment for research and clinical trials continues to be challenging. Prostate cancer is the most commonly diagnosed cancer in men and disproportionately affects African American men; thus, effective recruitment strategies are essential for this population. OBJECTIVES: The aim of this study was to focus on innovative and effective recruitment strategies for research on prostate cancer with minorities. METHODS: A systematic description is provided of the recruitment efforts for a hermeneutic phenomenological qualitative study of African American men's experiences in decision making on whether to have a prostate cancer screening. RESULTS: Seventeen African American men were enrolled from rural Central Virginia. Recruiting strategies were targeted on places where African American men usually are found but that are rarely used for recruitment: barbershops, community health centers, and churches. Word of mouth was also used, and most of the participants (n = 11) were reached through this method. DISCUSSION: Recruitment efforts have been noted to be particularly challenging among minorities, for numerous reasons. Making minority recruitment a priority in any research or clinical trial is essential in gaining a representative sample. Word of mouth is a powerful tool that is often forgotten but should be looked at in further detail.
Keywords: Black Persons -- Virginia; Cancer Screening; Decision Making; Prostatic Neoplasms -- Prevention and Control; Research Subject Recruitment -- Methods; Adult; Aged; Convenience Sample; Descriptive Statistics; Funding Source; Interpersonal Relations; Interviews; Male; Middle Age; Phenomenological Research; Public Spaces; Rural Areas -- Virginia; Trust; Virginia

Strategies for recruitment of healthy premenopausal women into the African American Nutrition for Life (A NULIFE) Study. - King DW; Duello TM; Miranda PY; Hodges KP; Shelton AJ; Chukelu P; Jones LA (Journal of Women's Health (15409996), 2010)
Background: Although African American women have an overall lower incidence of breast cancer, African American women <40 years of age are more likely than Caucasian women of all ages and postmenopausal African American women to be diagnosed with breast cancer and exhibit tumor characteristics associated with poorer survival. To begin to address this disparity, studies must be conducted to examine breast cancer preventive factors in this subpopulation of women. However, the strategies needed to recruit younger African American women have not been well defined. Methods: In this study, we assessed methods used for recruiting and retaining healthy premenopausal African American women into the African American Nutrition for Life (A NULIFE) Study. The number of women contacted, enrolled, and retained by each recruitment strategy and the efficiency of individual strategies were calculated. Results: Overall, recruitment through social networking was most effective in contacting large numbers of healthy premenopausal African American women. The worksite recruitment method was the most efficient recruitment strategy employed, with a ratio of 40%. The study participants ( n = 164) were more likely to be >=35 years of age and have completed some college. Additionally, the interpersonal relationships recruitment approach proved most efficient (33%) in retaining participants who completed the yearlong study. Conclusions: The findings from this study add to the evolving research literature on minority recruitment strategies for research studies but specifically address effective recruitment of healthy young premenopausal African American women. The results demonstrate the need to use multiple recruitment strategies when recruiting this subgroup of African American women.
Keywords: Black Persons; Nutrition; Premenopause; Research Subject Recruitment -- Methods; Adult; Breast Neoplasms -- Prevention and Control; Descriptive Statistics; Diabetes Mellitus -- Prevention and Control; Funding Source; Human; Interpersonal Relations; Organizational Efficiency; Paired T-Tests; Research Subject Retention -- Methods; Social Networks; Work Environment

Study design and protocol for moving forward: a weight loss intervention trial for African-American breast cancer survivors. - Stolley, Melinda R; Sharp, Lisa K; Fantuzzi, Giamila; Arroyo, Claudia; Sheean, Patricia; Schiffer, Linda; Campbell, Richard; Gerber, Ben (BMC Cancer, 2015)
Background: Breast cancer survival rates are significantly lower among African-American women compared to white women. In addition, African-American women with breast cancer are more likely than white women to die from co-morbid conditions. Obesity is common among African-American women, and it contributes to breast cancer progression and the development and exacerbation of many weight-related conditions. Intervening upon obesity may decrease breast cancer and all-cause mortality among African-American breast cancer survivors.Methods/design: Moving Forward is a weight loss intervention being evaluated in a randomized trial with a projected sample of 240 African American breast cancer survivors. Outcomes include body mass index, body composition, waist:hip ratio, and behavioral, psychosocial and physiological measures. Survivors are randomized to either a 6-month guided weight loss intervention that involves twice weekly classes and text messaging or a self-guided weight loss intervention based on the same materials offered in the guided program. The guided intervention is being conducted in partnership with the Chicago Park District at park facilities in predominantly African-American neighborhoods in Chicago. Recruitment strategies include direct contact to women identified in hospital cancer registries, as well as community-based efforts. Data collection occurs at baseline, post-intervention (6 months) and at a 12-month follow-up.Discussion: This study evaluates a community-based, guided lifestyle intervention designed to improve the health of African-American breast cancer survivors. Few studies have addressed behavioral interventions in this high-risk population. If successful, the intervention may help reduce the risk for breast cancer recurrence, secondary cancers, and co-morbid conditions, as well as improve quality of life.Trial Registration: U.S. Clinicaltrials.gov number: NCT02482506, April 2015.
Keywords: Breast Neoplasms -- Mortality; Survivors -- Psychosocial Factors; Black Persons -- Psychosocial Factors; Weight Loss; Female; Human; Breast Neoplasms -- Psychosocial Factors; Illinois -- Ethnology; Quality of Life; Random Assignment; Treatment Outcomes; Clinical Trials; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Funding Source

Study seeks to clarify genetic basis of prostate cancer in African Americans. - Reynolds, Tom (JNCI: Journal of the National Cancer Institute, 2003)
Focuses on the African American Hereditary Prostate Cancer study which will examine the genetic basis of prostate cancer in African Americans. Study background; Recruitment process; Prostate cancer incidence and mortality.
Keywords: Prostatic Neoplasms; Black Persons -- Statistics and Numerical Data; Patient Selection; Trust; Black Persons; Black Persons -- Psychosocial Factors; United States; Prostatic Neoplasms -- Ethnology; Male

Successful recruitment of African American breast cancer patients for telephone group intervention. - Heiney S; Wells L; Johnson H (Oncology Nursing Forum, 2008)
Keywords: Black Persons; Breast Neoplasms; Cancer Patients; Research Subject Recruitment; Social Marketing; Teleconferencing; Conceptual Framework; Descriptive Statistics; Print Materials; United States; Human

Successful Recruitment of Black Men to Prostate Cancer Clinical Trials—A Lesson in Achievement. - Hahn, Andrew W.; Bilen, Mehmet A.; Agarwal, Neeraj (JAMA Network Open, 2021)
Keywords: Research Subject Recruitment; Black Persons; Prostatic Neoplasms -- Drug Therapy; Neoplasm Metastasis -- Drug Therapy; Androgen Antagonists -- Therapeutic Use; Bicalutamide -- Therapeutic Use; Clinical Trials; Treatment Outcomes

Successful recruitment of healthy African American men to genomic studies from high-volume community health fairs: Implications for future genomic research in minority populations. - Patel YR; Carr KA; Magjuka D; Mohammadi Y; Dropcho EF; Reed AD; Moore ML; Waddell MJ; Shedd-Steele R; Sweeney CJ; Hahn NM (Cancer (0008543X), 2012)
Keywords: Black Persons; Research, Medical -- Trends; Community Health Services -- Trends; Genome; Minority Groups; Patient Selection; Prostatic Neoplasms; Age Factors; Educational Status; White Persons; Disease Susceptibility -- Ethnology; Disease Susceptibility; Human; Indiana; Male; Marital Status; Middle Age; Polymorphism, Genetic; Prostatic Neoplasms -- Epidemiology; Prostatic Neoplasms -- Ethnology; Retrospective Design; Risk Factors; Socioeconomic Factors

Successful subject recruitment for a prostate cancer behavioral intervention trial. - Heiney SP; Adams SA; Drake BF; Bryant LH; Bridges L; Herbert JR (Clinical Trials, 2010)
Keywords: Black Persons -- Psychosocial Factors; Prostatic Neoplasms; Research Subject Recruitment -- Methods; Social Marketing; Adult; Aged; Aged, 80 and Over; Behavior; Funding Source; Human; Information Systems; Male; Middle Age; Program Development; Program Implementation; Socioeconomic Factors; Study Design

Supportive-Affective Group Experience for persons with life-threatening illness: reducing spiritual, psychological, and death-related distress in dying patients. - Miller DK; Chibnall JT; Videen SD; Duckro PN (Journal of Palliative Medicine, 2005)
BACKGROUND: Attention to psycho-socio-spiritual needs is considered critical by patients with life-threatening illnesses and their caregivers. Palliative care interventions that address these needs--particularly spirituality--are lacking. OBJECTIVE: To evaluate the effects of an innovative program to address psycho-socio-spiritual needs in patients with life-threatening illnesses. DESIGN: A group intervention entitled Life-Threatening Illness Supportive-Affective Group Experience (LTI-SAGE) was developed for reducing patient spiritual, emotional, and death-related distress. SETTING/SUBJECTS: African American and Caucasian patients (n = 69) from two hospitals in St. Louis, Missouri, with life-threatening medical conditions (cancer; human immunodeficiency virus/acquired immune deficiency syndrome [HIV/AIDS]; geriatric frailty; liver, kidney, pulmonary, or cardiovascular disease) were randomly assigned to intervention or control groups. Intervention patients participated in a maximum of 12 LTI-SAGE groups over a 12-month period. Control patients received standard care. MEASUREMENTS: Outcome measures were depression symptoms, anxiety, spiritual well-being, and death-related emotional distress. RESULTS: After attrition, 51 (73.9%) patients completed the trial. At the end of the trial, after factoring in compliance, intervention patients had significantly fewer depression symptoms and death-related feelings of meaninglessness and significantly better spiritual well-being than did control patients. CONCLUSIONS: The use of the LTI-SAGE model for enhancing the end-of-life illness experience is promising.
Keywords: Attitude to Death; Stress, Psychological -- Prevention and Control; Support Groups; Terminal Care -- Psychosocial Factors; Caregivers; Clinical Assessment Tools; Clinical Trials; Data Analysis, Statistical; Descriptive Statistics; Female; Health Status Indicators; Male; Middle Age; Missouri; Program Development; Psychological Tests; Scales; State-Trait Anxiety Inventory; Funding Source; Human

Surveillance viable in carefully selected PCa patients. - Binder, Stefanie Petrou (Urology Times, 2012)
Keywords: Prostatic Neoplasms -- Therapy; Disease Surveillance; Time Factors; Disease Progression; Black Persons; United States; Prostate-Specific Antigen; Patient Selection

Symptom distress, spirituality, and quality of life in African American breast cancer survivors. - Leak A; Hu J; King CR (Cancer Nursing, 2008)
This study examined the relationships among the demographic characteristics, symptom distress, spirituality, and quality of life (QOL) of African American breast cancer survivors. A convenience sample of 30 survivors with a mean age of 56 years and a mean survival of 6 years was recruited from African American breast cancer support groups and churches in the Southeastern United States. Data were collected through face-to-face interviews using a demographic questionnaire, the Quality of Life Index-Cancer Version, the Symptom Distress Scale, and the Spiritual Perspective Scale. Statistically significant relationships were found between symptoms and QOL (r = -0.62, P < .05) and between spirituality and QOL (r = 0.70, P < .05). No statistically significant relationships were found between age at diagnosis, income, or education and QOL. This research suggests that symptoms and spirituality are associated with QOL. Culturally appropriate care should be provided to these women to reduce health disparities and to improve their QOL.
Keywords: Black Persons -- United States; Breast Neoplasms; Cancer Survivors; Quality of Life; Spirituality; Symptom Distress; Adult; Aged; Coefficient Alpha; Conceptual Framework; Convenience Sample; Correlational Studies; Descriptive Research; Descriptive Statistics; Educational Status; Female; Ferrans and Powers Quality of Life Index; Income; Interviews; Middle Age; Models, Theoretical; Pearson's Correlation Coefficient; Quality of Life -- Evaluation; Questionnaires; Research Subject Recruitment; Scales; Southeastern United States; Summated Rating Scaling; Symptom Distress Scale; Symptom Distress -- Evaluation; United States; Human

Systematic Review of Interventions to Increase Stool Blood Colorectal Cancer Screening in African Americans. - Roy, Siddhartha; Dickey, Sabrina; Wang, Hsiao-Lan; Washington, Alexandria; Polo, Randy; Gwede, Clement K.; Luque, John S. (Journal of Community Health, 2021)
African Americans experience colorectal cancer (CRC) related disparities compared to other racial groups in the United States. African Americans are frequently diagnosed with CRC at a later stage, screening is underutilized, and mortality rates are highest in this group. This systematic review focused on intervention studies using stool blood CRC screening among African Americans in primary care and community settings. Given wide accessibility, low cost, and ease of dissemination of stool-based CRC screening tests, this review aims to determine effective interventions to improve participation rates. This systematic review included intervention studies published between January 1, 2000 and March 16, 2019. After reviewing an initial search of 650 studies, 11 studies were eventually included in this review. The included studies were studies conducted in community and clinical settings, using both inreach and outreach strategies to increase CRC screening. For each study, an unadjusted odds ratio (OR) for the CRC screening intervention compared to the control arm was calculated based on the data in each study to report effectiveness. The eleven studies together recruited a total of 3334 participants. The five studies using two-arm experimental designs ranged in effectiveness with ORs ranging from 1.1 to 13.0 using interventions such as mailed reminders, patient navigation, and tailored educational materials. Effective strategies to increase stool blood testing included mailed stool blood tests augmented by patient navigation, tailored educational materials, and follow-up calls or mailings to increase trust in the patient-provider relationship. More studies are needed on stool blood testing interventions to determine effectiveness in this population.
Keywords: Cancer Screening; Feces -- Analysis; Colorectal Neoplasms; Occult Blood -- Methods; Black Persons; Human; Systematic Review; CINAHL Database; Colonoscopy

Tamoxifen Dose Escalation in Patients With Diminished CYP2D6 Activity Normalizes Endoxifen Concentrations Without Increasing Toxicity. - Hertz, Daniel L.; Deal, Allison; Ibrahim, Joseph G.; Walko, Christine M.; Weck, Karen E.; Anderson, Steven; Magrinat, Gustav; Olajide, Oludamilola; Moore, Susan; Raab, Rachel; Carrizosa, Daniel R.; Corso, Steven; et al. (Oncologist, 2016)
Background. Polymorphic CYP2D6 is primarily responsible for metabolic activation of tamoxifen to endoxifen. We previously reported that by increasing the daily tamoxifen dose to 40 mg/day in CYP2D6 intermediate metabolizer (IM), but not poor metabolizer (PM), patients achieve endoxifen concentrations similar to those of extensive metabolizer patients on 20 mg/day. We expanded enrollment to assess the safety of CYP2D6 genotype-guided dose escalation and investigate concentration differences between races. Methods. PM and IM breast cancer patients currently receiving tamoxifen at 20 mg/day were enrolled for genotype-guided escalation to 40 mg/day. Endoxifen was measured at baseline and after 4 months. Quality-of-life data were collected using the Functional Assessment of Cancer Therapy-Breast (FACT-B) and Breast Cancer Prevention Trial Menopausal Symptom Scale at baseline and after 4 months. Results. In 353 newly enrolled patients, genotype-guided dose escalation eliminated baseline concentration differences in IM (p = .08), but not PM (p = .009), patients. Endoxifen concentrations were similar in black and white patients overall (p = .63) and within CYP2D6 phenotype groups (p > .05). In the quality-of-life analysis of 480 patients, dose escalation did not meaningfully diminish quality of life; in fact, improvements were seen in several measures including the FACT Breast Cancer subscale (p = .004) and limitations in range of motion (p < .0001) in IM patients. Conclusion. Differences in endoxifen concentration during treatment can be eliminated by doubling the tamoxifen dose in IM patients, without an appreciable effect on quality of life. Validation of the association between endoxifen concentration and efficacy or prospective demonstration of improved efficacy is necessary to warrant clinical uptake of this personalized treatment strategy.
Keywords: Tamoxifen -- Administration and Dosage; Tamoxifen -- Analogs and Derivatives; Tamoxifen -- Pharmacokinetics; Cytochrome P-450 Enzyme System -- Metabolism; Genotype; Polymorphism, Genetic; Pharmacogenetics; Dose-Response Relationship, Drug; Tamoxifen -- Adverse Effects; Cancer Patients; Quality of Life; Functional Assessment; Perimenopausal Symptoms; Clinical Assessment Tools; Scales; Prospective Studies; Secondary Analysis; Cancer Care Facilities; North Carolina; Chromatography, High Pressure Liquid; Mass Spectrometry; Summated Rating Scaling; Activities of Daily Living; Analysis of Variance; Paired T-Tests; Linear Regression; Data Analysis Software; Clinical Trials; Socioeconomic Factors; Treatment Duration; Chemotherapy, Cancer; P-Value; Female; Adult; Middle Age; Aged; Aged, 80 and Over; Breast Neoplasms -- Classification; Neoplasm Invasiveness; Carcinoma, Ductal, Breast; Carcinoma in Situ; Treatment Outcomes; Confidence Intervals; Neoplasm Recurrence, Local; Human

Teaching breast cancer screening to African American women in the Arkansas Mississippi River Delta. - Hall CP; Wimberley PD; Hall JD; Pfriemer JT; Hubbard EM; Stacy AS; Gilbert JD (Oncology Nursing Forum, 2005)
Purpose/Objectives: To determine the effectiveness of a multifaceted, culturally sensitive breast cancer education program for African American women in the Arkansas Mississippi River Delta. Design: Experimental (i.e., post-test only, control group design). Setting: African American churches and a county Extension Homemakers Club sponsored through the Arkansas Extension Homemakers council. Sample: 53 African American women. The experimental group included 30 participants who had a mean age of 56 years, and the control group consisted of 23 participants with a mean age of 51 years. Methods: After the presentation of a multifaceted, culturally sensitive breast cancer education program, a variety of instruments were administered to participants in the experimental group that measured dependent variables. Subjects in the control group completed the same instruments in the absence of a viable intervention. Data were analyzed using t tests. Main Research Variables: Knowledge and beliefs about breast cancer. Findings: The experimental group's mean scores were significantly higher than the control group's on the Breast Cancer Knowledge Test and the susceptibility scale of the Breast Cancer Screening Belief Scales. The experimental group also scored significantly higher than the control group on the confidence scale of the Breast Cancer Screening Belief Scales. Conclusions: The multifaceted, culturally sensitive breast cancer education program appeared to be responsible for the differences in scores between the experimental and control groups. Implications for Nursing: Culturally sensitive group educational programs aimed at helping African American women in the rural South become more knowledgeable about breast cancer and early detection clearly are needed. Such efforts also must focus on increasing women's confidence in effectively performing regular breast self-examination as well as their understanding of personal risk. Healthcare professionals play a major role in the development and implementation of these programs.
Keywords: Black Persons -- Arkansas; Breast Neoplasms -- Prevention and Control; Breast Self-Examination -- Education; Cancer Screening -- Education; Adult; Arkansas; Bandura's Social Cognitive Theory; Checklists; Chi Square Test; Conceptual Framework; Confidence -- Evaluation; Consumer Satisfaction -- Evaluation; Convenience Sample; Cultural Sensitivity; Data Analysis Software; Descriptive Statistics; Experimental Studies; Female; Fisher's Exact Test; Funding Source; Health Belief Model; Health Beliefs -- Evaluation; Health Knowledge -- Evaluation; Middle Age; Outcomes of Education -- Evaluation; Print Materials; Questionnaires; Random Assignment; Research Subject Recruitment; Summated Rating Scaling; T-Tests; Videorecording; Human

The attitudes, communication, treatment, and support intervention to reduce breast cancer treatment disparity. - Rosenzweig M; Brufsky A; Rastogi P; Puhalla S; Simon J; Underwood S (Oncology Nursing Forum, 2011)
Purpose/Objectives: To test the effect of a supportive, one-time psychoeducational intervention on treatment adherence among African American women receiving first adjuvant therapy for breast cancer.Design: A pilot, randomized, controlled clinical trial, two-group design, with one-time intervention and four data collection points.Setting: Two University of Pittsburgh Cancer Institute clinics.Sample: 24 African American women.Methods: The Attitudes, Communication, Treatment, and Support (ACTS) intervention is a 45-minute one-on-one session with an African American woman recommended to have chemotherapy for breast cancer. The interventionist is an African American breast cancer survivor. The intervention consists of a discussion about chemotherapy and the importance of communicating knowledge needs and distress, an explanation of the specific treatment plan according to pathology, and support through the survivor testimonial and video clips from the African American community.Main Research Variables: Dose of chemotherapy received and dose of chemotherapy prescribed.Findings: Twenty patients completed chemotherapy, and four chose not to begin or discontinued recommended chemotherapy. The groups were equal in key sociodemographic variables. Compared to usual care, the ACTS intervention participants demonstrated trends toward initiation of chemotherapy (100% versus 82%), overall adherence to chemotherapy (92% versus 73%), and percentage of total dose of chemotherapy received or prescribed (94% versus 74%). Compared to usual care, the ACTS intervention participants demonstrated more rapid initiation of chemotherapy and better overall adherence to chemotherapy.Conclusions: The pilot ACTS intervention shows promise as a psychoeducational intervention to assist with chemotherapy decision making among African American women.Implications for Nursing: African American women are at high risk of not receiving the full dose of prescribed chemotherapy for breast cancer for multiple reasons. Nurses must be sensitive to the unique fears and concerns of this population regarding chemotherapy decisions. An intervention addressing these fears and concerns may help to increase adherence.
Keywords: Breast Neoplasms -- Drug Therapy; Black Persons -- Pennsylvania; Psychoeducation; Medication Compliance; Human; Randomized Controlled Trials; Pennsylvania; Cancer Care Facilities; Descriptive Statistics; Chemotherapy, Cancer; Pilot Studies; Conceptual Framework; Models, Theoretical; Decision Making, Patient; Medication Compliance -- Evaluation; Wilcoxon Rank Sum Test; Fisher's Exact Test; Nonparametric Statistics; Female; Adult; Middle Age; Urban Areas; Research Subject Recruitment; Random Assignment; Communication; Teaching Methods

The deep South network for cancer control: eliminating cancer disparities through community-academic collaboration. - Partridge EE; Fouad MN; Hinton AW; Hardy CM; Liscovicz N; White-Johnson F; Higginbotham JC; Partridge, Edward E; Fouad, Mona N; Hinton, Agnes W; Hardy, Claudia M; Liscovicz, Nedra; et al. (Family & Community Health, 2005)
African Americans have a substantially increased mortality rate compared to Whites in many cancers, including breast and cervix. The Deep South Network for Cancer Control (the Network) was established to develop sustainable community infrastructure to promote cancer awareness, enhance participation of African Americans and other special populations in clinical trials, recruit and train minority investigators, and develop and test innovative community-based cancer control measures to eliminate cancer mortality disparities in special populations. This article describes the steps necessary to form the network and the process and activities required to establish it as an effective infrastructure for eliminating disparities between Whites and African Americans in the United States.
Keywords: Black Persons -- United States; Neoplasms -- Prevention and Control; Program Development; United States

The effect of demographics and patient location on the outcome of patients with acute respiratory distress syndrome. - El-Haddad, Haitham; Hyejeong Jang; Wei Chen; Haider, Samran; Soubani, Ayman O. (Annals of Thoracic Medicine, 2017)
OBJECTIVE: Outcome of acute respiratory distress syndrome (ARDS) in relation to age, gender, race, pre-Intensive Care Unit (ICU) location, and type of ICU. METHODS: Retrospective cohort study of patients enrolled in the ARDS network randomized controlled trials. RESULTS: A total of 2914 patients were included in these trials. Outcomes were adjusted to baseline covariates including APACHE III score, vasopressor use, cause of lung injury, lung injury score, diabetes, cancer status, body mass index, and study ID. Older patients had significantly higher mortality at both 28- and 60-day (odds ratio [OR] 2.59 [95% confidence interval [CI]: 2.12–3.18] P < 0.001 and 2.79, 95% CI: 2.29–3.39, P < 0.001, respectively); less ICU and ventilator free days (relative risk [RR] 0.92, 95% CI: 0.87–0.96, P < 0.001 and 0.92, 95% CI: 0.88–0.96, P < 0.001, respectively). For preadmission location, the 28- and 60-day mortality were lower if the patient was admitted from the operating room (OR)/recovery room (OR 0.65, 95% CI: 0.44–0.95, P = 0.026; and OR = 0.66, 95% CI: 0.46–0.95, P = 0.025, respectively) or emergency department (OR = 0.78, 95% CI: 0.61–0.99, P = 0.039; and OR = 0.71, 95% CI: 0.56–0.89, P = 0.004, respectively), but no statistical differences in ICU and ventilator free days between different preadmission locations. Races other than white and black had a statistically higher mortality (28- and 60-day mortality: OR = 1.47, 95% CI: 1.09–1.98, P = 0.011; and OR 1.53, 95% CI: 1.15–2.04, P = 0.004, respectively). Between whites and blacks, females and males there were no statistically significant differences in all outcomes. CONCLUSION: Older patients and races other than blacks and whites have higher mortality associated with ARDS. Mortality is affected by patients preadmission location. There are no differences in outcome in relation to the type of ICU, gender, or between blacks and whites.
Keywords: Respiratory Distress Syndrome, Acute -- Therapy; Treatment Outcomes -- Evaluation; Respiratory Distress Syndrome, Acute -- Epidemiology; Human; Geographic Locations; Nonconcurrent Prospective Studies; Male; Female; Odds Ratio; Confidence Intervals; Relative Risk; Descriptive Statistics; Race Factors; Age Factors; Respiratory Distress Syndrome, Acute -- Mortality

The effect of offering different numbers of colorectal cancer screening test options in a decision aid: a pilot randomized trial. - Griffith JM; Lewis CL; Brenner AR; Pignone MP; Griffith, Jennifer M; Lewis, Carmen L; Brenner, Alison R T; Pignone, Michael P (BMC Medical Informatics & Decision Making, 2008)
Background: Decision aids can improve decision making processes, but the amount and type of information that they should attempt to communicate is controversial. We sought to compare, in a pilot randomized trial, two colorectal cancer (CRC) screening decision aids that differed in the number of screening options presented.Methods: Adults ages 48-75 not currently up to date with screening were recruited from the community and randomized to view one of two versions of our previously tested CRC screening decision aid. The first version included five screening options: fecal occult blood test (FOBT), sigmoidoscopy, a combination of FOBT and sigmoidoscopy, colonoscopy, and barium enema. The second discussed only the two most frequently selected screening options, FOBT and colonoscopy. Main outcomes were differences in screening interest and test preferences between groups after decision aid viewing. Patient test preference was elicited first without any associated out-of-pocket costs (OPC), and then with the following costs: FOBT-$10, sigmoidoscopy-$50, barium enema-$50, and colonoscopy-$200.Results: 62 adults participated: 25 viewed the 5-option decision aid, and 37 viewed the 2-option version. Mean age was 54 (range 48-72), 58% were women, 71% were White, 24% African-American; 58% had completed at least a 4-year college degree. Comparing participants that viewed the 5-option version with participants who viewed the 2-option version, there were no differences in screening interest after viewing (1.8 vs. 1.9, t-test p = 0.76). Those viewing the 2-option version were somewhat more likely to choose colonoscopy than those viewing the 5-option version when no out of pocket costs were assumed (68% vs. 46%, p = 0.11), but not when such costs were imposed (41% vs. 42%, p = 1.00).Conclusion: The number of screening options available does not appear to have a large effect on interest in colorectal cancer screening. The effect of offering differing numbers of options may affect test choice when out-of-pocket costs are not considered.
Keywords: Colorectal Neoplasms -- Diagnosis; Consumer Participation -- Statistics and Numerical Data; Decision Support Techniques; Health Screening -- Methods; Patient Satisfaction -- Statistics and Numerical Data; Aged; Barium -- Diagnostic Use; Clinical Trials; Colonoscopy -- Economics; Colonoscopy -- Utilization; Consumer Participation -- Economics; Decision Making; Economics; Enema -- Economics; Enema -- Utilization; Female; Health Screening -- Economics; Male; Middle Age; North Carolina; Occult Blood; Patient Satisfaction -- Economics; Questionnaires; Sigmoidoscopy -- Economics; Sigmoidoscopy -- Utilization; Human

The Effectiveness of a Physician-Only and Physician-Patient Intervention on Colorectal Cancer Screening Discussions Between Providers and African American and Latino Patients. - Dolan, Nancy; Ramirez-Zohfeld, Vanessa; Rademaker, Alfred; Ferreira, M.; Galanter, William; Radosta, Jonathan; Eder, Milton; Cameron, Kenzie; Dolan, Nancy C; Rademaker, Alfred W; Ferreira, M Rosario; Galanter, William L; et al. (JGIM: Journal of General Internal Medicine, 2015)
Background: Physician recommendation of colorectal cancer (CRC) screening is a critical facilitator of screening completion. Providing patients a choice of screening options may increase CRC screening completion, particularly among racial and ethnic minorities.Objective: Our purpose was to assess the effectiveness of physician-only and physician-patient interventions on increasing rates of CRC screening discussions as compared to usual care.Design: This study was quasi-experimental. Clinics were allocated to intervention or usual care; patients in intervention clinics were randomized to receipt of patient intervention.Participants: Patients aged 50 to 75 years, due for CRC screening, receiving care at either a federally qualified health care center or an academic health center participated in the study.Intervention: Intervention physicians received continuous quality improvement and communication skills training. Intervention patients watched an educational video immediately before their appointment.Main Measures: Rates of patient-reported 1) CRC screening discussions, and 2) discussions of more than one screening test.Key Results: The physician-patient intervention (n = 167) resulted in higher rates of CRC screening discussions compared to both physician-only intervention (n = 183; 61.1 % vs.50.3 %, p = 0.008) and usual care (n = 153; 61.1 % vs. 34.0 % p = 0.03). More discussions of specific CRC screening tests and discussions of more than one test occurred in the intervention arms than in usual care (44.6 % vs. 22.9 %,p = 0.03) and (5.1 % vs. 2.0 %, p = 0.036), respectively, but discussion of more than one test was uncommon. Across all arms, 143 patients (28.4 %) reported discussion of colonoscopy only; 21 (4.2 %) reported discussion of both colonoscopy and stool tests.Conclusions: Compared to usual care and a physician-only intervention, a physician-patient intervention increased rates of CRC screening discussions, yet discussions overwhelmingly focused solely on colonoscopy. In underserved patient populations where access to colonoscopy may be limited, interventions encouraging discussions of both stool tests and colonoscopy may be needed.
Keywords: Black Persons -- Psychosocial Factors; Hispanic Americans -- Psychosocial Factors; Physician-Patient Relations; Early Detection of Cancer -- Psychosocial Factors; Colorectal Neoplasms -- Diagnosis; Colorectal Neoplasms -- Ethnology; Aged; Early Detection of Cancer -- Statistics and Numerical Data; Colonoscopy -- Statistics and Numerical Data; Human; Hispanic Americans -- Statistics and Numerical Data; Male; Black Persons -- Statistics and Numerical Data; Middle Age; Early Detection of Cancer -- Methods; Illinois; Patient Education -- Methods; Occult Blood; Communication; Prospective Studies; Patient Selection; Female; Colonoscopy -- Psychosocial Factors; Validation Studies; Comparative Studies; Evaluation Research; Multicenter Studies; Randomized Controlled Trials; Funding Source

The Effectiveness of Shared Compared to Informed Decision Making for Prostate Cancer Screening in a High-Risk African American Population: A Randomized Control Trial. - Carlson, Daniel S.; Grivas, Petros; Wei, Wei; Dhillon, Puneet K.; Abraksia, Samir (Cancer Investigation, 2021)
Prostate cancer incidence and mortality in the United States in African Americans (AA) are higher than in Caucasians. Eastern Cuyahoga County in Ohio is majority AA and is considered an underserved population particularly vulnerable to healthcare disparities. There is a paucity of data about shared decision making among high-risk AA men with regard to prostate cancer screening. This study aims to examine shared versus informed decision making (SDM versus IDM) in a randomized, control trial among a large, high-risk AA population. Patients were included in annual one-day outreach events, each held over 3 years (2017–2019), and were randomized at each event into IDM (control) and SDM (investigational) groups and then were offered screening via prostate specific antigen (PSA) and digital rectal exam (DRE). The primary endpoints were proportion of participants over 40 who did not demonstrate decisional conflict about prostate cancer screening measured by the SURE score, as well as change of knowledge score about prostate cancer screening. Overall, 175 patients were enrolled in the trial; 79 in the SDM arm and 96 in the IDM arm. The investigational (SDM) arm had 3/79 (3.9%) conflict versus 6/96 (6.4%) in the control (IDM) arm (p = 0.74). With regard to knowledge improvement, the SDM cohort demonstrated improvement following educational tools for 66/79 (81%) of participants versus 76/96 (79%) in the IDM cohort (p = 0.85). There was no difference in the proportion (63%) of participants in either group who found the information very helpful (using a Likert scale). Our education-based study showed no significant difference between SDM and IDM with regard to decisional conflict about prostate cancer screening. The study also demonstrated significant improvement in knowledge about prostate cancer screening in a high-risk AA population in both groups. Our results should be interpreted with caution due to several limitations; however, the study can serve as a benchmark for future studies in this very important topic.
Keywords: Prostatic Neoplasms -- Ethnology -- United States; Cancer Screening -- Methods; Decision Making, Shared -- Evaluation; Decision Making -- Evaluation; Black Persons; Outcome Assessment; Human; Male; United States; Random Assignment; Randomized Controlled Trials

The effects of message framing and ethnic targeting on mammography use among low-income women. - Schneider TR; Salovey P; Apanovitch AM; Pizarro J; McCarthy D; Zullo J; Rothman AJ (Health Psychology, 2001)
The authors examined the effects that differently framed and targeted health messages have on persuading low-income women to obtain screening mammograms. The authors recruited 752 women over 40 years of age from community health clinics and public housing developments and assigned the women randomly to view videos that were either gain or loss framed and either targeted specifically to their ethnic groups or multicultural. Loss-framed, multicultural messages were most persuasive. The advantage of loss-framed, multicultural messages was especially apparent for Anglo women and Latinas but not for African American women. These effects were stronger after 6 months than after 12 months. Copyright © 2000 by the American Psychological Association, Inc.
Keywords: Breast Neoplasms -- Education; Mammography; Teaching Methods; Female; Adult; Middle Age; Socioeconomic Factors; Motivation; Hispanic Americans; Asians; Black Persons; White Persons; Experimental Studies; Questionnaires; Pretest-Posttest Design; Videorecording -- Utilization; Chi Square Test; P-Value; Descriptive Statistics; Logistic Regression; Race Factors; Odds Ratio; Confidence Intervals; Funding Source; Human

The Elimination of Cancer Health Disparities: Are We Ready to Do the Heavy Lifting?...Tsao CK, Sfakianos J, Liaw B et al. Phase II clinical trial of abiraterone acetate plus prednisone in black men with metastatic prostate cancer. Oncologist. 2016 Dec; 21(12):1414-e9. - Jackson, Jonathan D.; Moy, Beverly; Evans, Michele K. (Oncologist, 2016)
Black Americans are under‐represented in cancer clinical trials because of myriad factors. Minority under‐representation in clinical trials likely contributes to the disparate cancer outcomes among minorities and the poor. This Commentary, in light of a clinical trial that was prematurely terminated because of poor accrual of black men, discusses strategies to identify and overcome barriers to enrollment for this particularly vulnerable population.
Keywords: Prostatic Neoplasms -- Drug Therapy; Neoplasm Metastasis -- Drug Therapy; Abiraterone Acetate -- Therapeutic Use; Prednisone -- Therapeutic Use; Black Persons; Drug Therapy; Androgens -- Metabolism; Polymorphism, Genetic; Male; Prostatic Neoplasms -- Mortality

The Federal Nursing Services Award. Enlisted women with breast cancer: balancing demands and expectations. - Wilmoth MC; Wilmoth, Margaret Chamberlain (Military Medicine, 2003)
Diagnosis with breast cancer is not an automatic cause for discharge from the military. Therefore, it is important to know how this disease impacts enlisted women in the military. This study describes how enlisted women manage diagnosis and treatment within the context of their military careers. Grounded theory guided the study methodology. Audiotaped semistructured interviews were conducted three times over 9 months to learn how treatment impacted work demands. Data saturation was attained after 46 interviews were conducted. Participants had to balance demands and expectations among the Military Career and Military Medical Subsystems and their Social Support Subsystem. Support from the chain of command was critical in women's ability to balance demands and expectations of career, family, and illness. Military nurses are in a unique position to create strategies that will assist enlisted women in coping with breast cancer.
Keywords: Adaptation, Psychological; Breast Neoplasms -- Psychosocial Factors; Military Personnel -- Psychosocial Factors; Women, Working -- Psychosocial Factors; Workload; Activities of Daily Living; Adult; Audiorecording; Black Persons; Breast Neoplasms -- Surgery; Chemotherapy, Cancer -- Adverse Effects; Coding; Demography; Female; Funding Source; Grounded Theory; Interviews; Life Change Events; Literature Review; Middle Age; Negotiation; Phenomenological Research; Purposive Sample; Questionnaires; Research Subject Recruitment; Research, Nursing; Self Care -- Psychosocial Factors; Telephone; United States; United States Air Force; United States Army; United States Navy; White Persons; Human

The impact of a culturally appropriate education video on beliefs about breast cancer in African American women ages 35-65. - Frazier, Linda M (Impact of a Culturally Appropriate Education Video on Beliefs About Breast Cancer in African American Women Ages 35-65, 2008)
African American women with breast cancer face a higher risk of dying from their disease compared to women of other racial/ethnic groups. Experts suggest that this excess mortality would be significantly reduced if screening were more effectively utilized. The recognition of the relationship between culture, community and cancer has resulted in the proposition of a variety of community-based breast cancer education programs for African American women. Much is assumed about the receptivity of African American women to community based breast education programs, yet few studies have been conducted to validate if and or to what degree this is so. This research project was undertaken to determine the impact of a culturally appropriate education video on beliefs about breast cancer and screening in African American women ages 35-65. Sixty-seven women were recruited from metropolitan churches in Columbus, Georgia and one local sorority, namely Alpha Kappa Alpha Sorority, Inc. In addition to Columbus, Georgia, there were women recruited from rural churches in Montezuma, Georgia. Fifty-seven women completed both pre-post tests.The Champion Health Belief Model Scales (CHBMS) was used as a pre-test/post-test to determine if there is a significant change in any of the subscales of the CHMBS in African American women who view the Witness ProjectRTM education video. Demographic characteristics were analyzed using descriptive statistics. A non-parametric equivalent of the paired sample t-test called the Wilcoxin Signed Ranks Test was used to examine change in the CHBMS over time. Changes over time in perceived susceptibility to breast cancer and seriousness of breast cancer were examined. There were no significant changes in perceived susceptibility, but there was a significant change in seriousness, with participants having significantly lower perceptions of seriousness of breast cancer at post-test than at pre-test (p=0.01).The remaining subscales were examined for changes over time. Results indicated that participants reported significantly greater perceptions of benefits of self breast examination and benefits of mammography at the post-test with p values of 0.03 and 0.05 respectively. There were no significant changes over time in confidence in performing self breast examination, health motivation, and barriers to self examination and barriers to mammography.
Keywords: Black Persons; Breast Neoplasms -- Education; Cultural Sensitivity -- Evaluation; Teaching Methods -- Evaluation; Videorecording -- Evaluation; Adult; Aged; Descriptive Statistics; Female; Georgia; Human; Middle Age; P-Value; Pretest-Posttest Design; T-Tests; Wilcoxon Signed Rank Test

The impact of a randomized dietary and physical activity intervention on chronic inflammation among obese African-American women. - Babatunde, Oluwole Adeyemi; Arp Adams, Swann; Truman, Samantha; Sercy, Erica; Murphy, Angela E.; Khan, Samira; Hurley, Thomas G.; Wirth, Michael D.; Choi, Seul Ki; Johnson, Hiluv; Hebert, James R. (Women & Health, 2020)
Lifestyle interventions may reduce inflammation and lower breast cancer (BrCa) risk. This randomized trial assessed the impact of the Sistas Inspiring Sistas Through Activity and Support (SISTAS) study on plasma C-reactive protein (CRP), interleukin-6 (IL-6) and Dietary Inflammatory Index (DII). This unblinded, dietary and physical activity trial was implemented in 337 obese (body mass index [BMI] ≥30 kg/m2) African American (AA) women recruited between 2011 and 2015 in South Carolina through a community-based participatory approach with measurements at baseline, 3 months, and 12 months. Participants were randomized into either intervention (n = 176) or wait-list control group (n = 161). Linear mixed-effect models were used for analyses of CRP and IL-6. Baseline CRP was significantly higher in those with greater obesity, body fat percentage, and waist circumference (all p <.01). No difference was observed between groups for CRP or IL-6 at 3 or 12 months; however, improvements in diet were observed in the intervention group compared to the control group (p =.02) at 3 months but were not sustained at 12 months. Although the intervention was not successful at reducing levels of CRP or IL-6, a significant decrease was observed in DII score for the intervention group, indicating short-term positive dietary change.
Keywords: Diet -- Evaluation -- United States; Physical Activity -- Evaluation -- United States; Inflammation -- Prevention and Control -- United States; Obesity -- Prevention and Control -- United States; Women's Health -- United States; Black Persons -- United States; Human; Randomized Controlled Trials; Adipose Tissue -- Analysis; Female; C-Reactive Protein -- Blood; Interleukins -- Blood; Scales; Body Mass Index; United States; Waist Circumference; Chronic Disease -- Prevention and Control; Breast Neoplasms -- Risk Factors; Breast Neoplasms -- Prevention and Control

The impact of the Women's Health Initiative on hormone replacement therapy in a Medicaid program. - Hillman JJ; Zuckerman IH; Lee E (Journal of Women's Health (15409996), 2004)
BACKGROUND: Observational studies suggest that hormone replacement therapy (HRT) reduces women's risk of cardiovascular disease (CVD). However the Women's Health Initiative (WHI) HRT arm was stopped early because of increased risk of CVD, stroke, pulmonary embolism, and breast cancer. Evaluating HRT-prescribing patterns in relation to the release of the WHI will help determine if these study results have influenced the use of HRT. METHODS: This is a descriptive time series analysis to primarily evaluate utilization trends of HRT in women > or =50 years enrolled in the Pennsylvania Medicaid Program. HRT was categorized as follows: conjugated equine estrogen (CEE) plus medroxyprogesterone acetate (MPA), CEE only, and other estrogens/progesterone combinations. RESULTS: The overall prevalence of HRT decreased significantly post-WHI study release for all age and racial groups. The prevalence of CEE plus MPA decreased throughout the study; however, the prevalence of HRT declined at a faster rate after the WHI study release among women in their 50s and 60s compared with women in their 70s and 80s. There was a statistically significant reduction in all types of HRT use. CONCLUSIONS: The WHI influenced all types of HRT use among postmenopausal women in a Medicaid program. Administrative claims data can be a useful tool for monitoring an immediate impact of national guidelines or a national level outcomes trial.
Keywords: Hormone Replacement Therapy -- Utilization; Estrogens, Conjugated -- Administration and Dosage; Women's Health; Aged; Attitude to Health; Black Persons; Comparative Studies; Descriptive Research; Epidemiological Research; Female; Funding Source; Linear Regression; Medicaid; Middle Age; Pennsylvania; Prescriptions, Drug; Prevalence; Prospective Studies; Risk Factors; Statistical Significance; T-Tests; Time Factors; White Persons; Human

The influence of social support on breast cancer screening in a multicultural community sample. - Katapodi MC; Facione NC; Miaskowski C; Dodd MJ; Waters C (Oncology Nursing Forum, 2002)
PURPOSE/OBJECTIVES: To examine the relationship between women's reported social support and their adherence to recommended breast cancer screening guidelines. DESIGN: Descriptive, cross-sectional survey. SETTING: Community women's organizations throughout the San Francisco Bay Area. SAMPLE: 833 mostly low-income women with a mean age of 46.2 years from three racial or ethnic groups (i.e., Latina, Caucasian, and African American) who were not breast cancer survivors. METHODS: Social support was measured with a five-item, four-point, Likert scale developed for the study (Cronbach's alpha = 0.7248). Adherence to screening guidelines was measured by asking frequency of performing breast self-examination (BSE) and frequency of obtaining a clinical breast examination (CBE) and a mammogram. Research assistants and leaders of women's organizations conducted the survey in work and community settings. MAIN RESEARCH VARIABLES: Social support, performance of BSE, obtaining a CBE and a mammogram, income, education, spoken language, and level of acculturation. FINDINGS: Higher levels of social support were related to higher income and higher education. Lower levels of social support were associated with being Latina, completing the survey in Spanish, and being born abroad. Women who did not adhere to screening guidelines (for BSE or CBE) reported less social support. CONCLUSIONS: Social support is associated with adherence to breast cancer screening guidelines. IMPLICATIONS FOR NURSING: Nurses should assess women's levels of social support as a factor when evaluating adherence to breast cancer screening guidelines.
Keywords: Support, Psychosocial; Cancer Screening; Breast Neoplasms -- Diagnosis; Cultural Diversity; World Wide Web; Information Resources; Descriptive Research; Cross Sectional Studies; California; Conceptual Framework; Research Subject Recruitment; Analysis of Variance; Acculturation; Data Analysis Software; T-Tests; Pearson's Correlation Coefficient; Mammography; Breast Self-Examination; Breast Examination; Research Instruments; Descriptive Statistics; Adult; Middle Age; Aged; Aged, 80 and Over; Female; Funding Source; Human

The Meaning of Breast Cancer Risk for African American Women. - Phillips, Janice; Cohen, Marlene Z. (Journal of Nursing Scholarship, 2011)
Purpose: To describe African American women's experience of being at high risk for breast cancer. Design: A hermeneutic phenomenological approach was used to guide in-depth interviews and analysis. Methods to ensure trustworthiness and rigor were included. Methods: Open interviews were conducted with 20 African American women who were at high risk for breast cancer (family history, personal history, genetic mutation). They were recruited from a cancer risk clinic and community-based settings. Data were transcribed verbatim, and themes were labeled among and between all interviews. Findings: Five themes were identified: (a) life-changing experience; (b) relationships: fears, support, and concerns; (c) the healthcare experience; (d) raising awareness; and (e) strong faith. Conclusions: Young women at high risk for breast cancer have unique emotional and support needs that are shaped by stage in life, relationships with significant others, their faith, and interactions with the healthcare delivery system. Clinical Relevance: Breast cancer does occur in young women. This highlights the need for timely and sensitive approaches to care when young women present with breast health concerns or abnormal breast findings.
Keywords: Breast Neoplasms; Black Persons -- United States; Attitude to Illness; Cancer Patients; Family History; Human; Attitude to Illness -- Evaluation; Female; Phenomenological Research; Information Resources; World Wide Web; Descriptive Research; Interviews; Thematic Analysis; Adult; Audiorecording; Questionnaires; Family Relations; Professional-Patient Relations; Health Services Accessibility; Cross Sectional Studies; United States; Research Subject Recruitment; Purposive Sample; Funding Source

The Neighborhood Voice: evaluating a mobile research vehicle for recruiting African Americans to participate in cancer control studies. - Alcaraz KI; Weaver NL; Andresen EM; Christopher K; Kreuter MW; Alcaraz, Kassandra I; Weaver, Nancy L; Andresen, Elena M; Christopher, Kara; Kreuter, Matthew W (Evaluation & the Health Professions, 2011)
The Neighborhood Voice is a vehicle customized for conducting health research in community settings. It brings research studies into neighborhoods affected most by health disparities and reaches groups often underrepresented in research samples. This paper reports on the experience and satisfaction of 599 African American women who participated in research on board the Neighborhood Voice. Using bivariate, psychometric, and logistic regression analyses, we examined responses to a brief post-research survey. Most women (71%) reported that they had never previously participated in research, and two-thirds (68%) rated their Neighborhood Voice experience as excellent. Satisfaction scores were highest among first-time research participants (p < .05). Women's ratings of the Neighborhood Voice on Comfort (OR = 4.9; 95% CI = 3.0, 7.9) and Convenience (OR = 1.8; 95% CI = 1.2, 2.9) significantly predicted having an excellent experience. Mobile research facilities may increase participation among disadvantaged and minority populations. Our brief survey instrument is a model for evaluating such outreach.
Keywords: Black Persons; Automobiles; Research, Medical -- Methods; Breast Neoplasms -- Ethnology; Patient Selection; Female; Health Status; Human; Middle Age; Missouri

The status of women's health research: where are African American women? - Pinn VW (Journal of National Black Nurses Association, 1996)
Keywords: Women's Health; Research; Black Persons; Female; National Institutes of Health (U.S.); Breast Neoplasms -- Ethnology; Breast Neoplasms -- Epidemiology; Mammography; Socioeconomic Factors; Clinical Trials; Research Subjects; Minority Groups

THRIVE study protocol: a randomized controlled trial evaluating a web-based app and tailored messages to improve adherence to adjuvant endocrine therapy among women with breast cancer. - Paladino, Andrew J.; Anderson, Janeane N.; Krukowski, Rebecca A.; Waters, Teresa; Kocak, Mehmet; Graff, Carolyn; Blue, Ryan; Jones, Tameka N.; Buzaglo, Joanne; Vidal, Gregory; Schwartzberg, Lee; Graetz, Ilana (BMC Health Services Research, 2019)
Background: Long-term use of adjuvant endocrine therapy (AET) among women with early-stage, hormone receptor-positive breast cancer significantly reduces the risk of hospitalizations, cancer recurrence, and mortality. AET is associated with adverse symptoms that often result in poor adherence. A web-enabled app offers a novel way to communicate and manage symptoms for women on AET. In a region with significant racial disparities in breast cancer outcomes, our study tests the impact of a web-enabled app that collects and transmits patient-reported symptoms to healthcare teams to facilitate timely and responsive symptom management on medication adherence.Methods: In this randomized controlled trial, we randomize 300 patients initiating AET to one of three arms: 1) an "App" group (n = 100) that receives weekly reminders to use the THRIVE study app; 2) an "App+Feedback" group (n = 100) that receives weekly reminders and tailored feedback based on their use of the app; or 3) a "Usual Care" group (n = 100) that receives usual care only. Participants are stratified by race: 50% White and 50% Black. The duration of the intervention is six months following enrollment, and outcomes are assessed at 12-months. The primary outcome is adherence, which is captured using an electronic monitoring pillbox. Secondary outcomes include symptom burden, quality of life, self-efficacy for managing symptoms, and healthcare costs. We also evaluate the impact of the intervention on racial disparities in adherence. Data are derived from three sources: electronic health record data to capture treatment changes, healthcare utilization, and health outcomes; self-report survey data related to adherence, symptom burden, and quality of life; and an electronic medication monitoring device that captures adherence.Discussion: A successful web-enabled intervention could be disseminated across systems, conditions, and populations. By evaluating the impact of this intervention on a comprehensive set of measures, including AET adherence, patient outcomes, and costs, our study will provide valuable and actionable results for providers, policy makers, and insurers who strive to achieve the "Triple Aim" - reduce costs while improving health outcomes and the patient care experience.Trial Registration: NCT03592771. Prospectively registered on July 19, 2018.
Keywords: Breast Neoplasms -- Drug Therapy; Mobile Applications; Clinical Trials; Quality of Life; Combined Modality Therapy; Reminder Systems; Medication Compliance; Black Persons -- Statistics and Numerical Data; Self Report; Breast Neoplasms -- Psychosocial Factors; White Persons -- Statistics and Numerical Data; Female; Internet; Patient Compliance; Neoplasm Recurrence, Local -- Drug Therapy; Ferrans and Powers Quality of Life Index; Impact of Events Scale

Tracking the Nonenrolled: Lung Cancer Screening Patterns Among Individuals not Accrued to a Clinical Trial. - Gerber, David E.; Hamann, Heidi A.; Chavez, Claudia; Dorsey, Olivia; Santini, Noel O.; Browning, Travis; Ochoa, Cristhiaan D.; Adesina, Joyce; Natchimuthu, Vijaya Subbu; Steen, Eric; Zhu, Hong; Lee, Simon J. Craddock (Clinical Lung Cancer, 2020)
Introduction: For lung cancer screening, the available data are often derived from patients enrolled prospectively in clinical trials. We, therefore, investigated lung cancer screening patterns among individuals eligible for, but not enrolled in, a screening trial.Patients and Methods: From February 2017 through February 2019, we enrolled subjects in a trial examining telephone-based navigation during low-dose computed tomography (LDCT) for lung cancer screening. We identified patients for whom LDCT was ordered and who were approached, but not enrolled, in the trial. We categorized nonenrollment as the patient had declined or could not be reached. We compared the characteristics and LDCT completion rates among these groups and the enrolled population using the 2-sample t test and χ2 test.Results: Of 900 individuals approached for participation (mean age, 62 years; 45% women, 53% black), 447 were enrolled in the screening clinical trial. No significant demographic differences were found between the enrolled and nonenrolled cohorts. Of the 453 individuals not enrolled, 251 (55%) had declined participation and 202 (45%) could not be reached, despite up to 6 attempts. LDCT completion was significantly associated with enrollment status: 81% of enrolled individuals, 73% of individuals who declined participation, and 49% of those who could not be reached (P < .001).Conclusions: In the present single-center study, demographic factors did not predict for participation in a lung cancer screening trial. Lung cancer screening adherence rates were substantially lower for those not enrolled in a screening trial, especially for those who could not be contacted. These findings may inform the broader implementation of screening programs.

Treatment of small cell lung cancer in academic and community settings: factors associated with receiving standard therapy and survival. - Parsons, Helen M; Harlan, Linda C; Stevens, Jennifer L; Ullmann, Claudio Dansky (Cancer Journal, 2014)
Purpose: Small cell lung cancer (SCLC) historically has had poor prognosis. Clinical trials have demonstrated improved survival among patients receiving standard platinum-/etoposide-based chemotherapy. Whereas treatment patterns and outcomes have been evaluated for patients with SCLC in clinical trials, population-based practice patterns are not well known.Methods: The National Cancer Institute's Patterns of Care study was used to evaluate patient and provider factors associated with standard treatment, clinical trial enrollment, and 12-month relative hazard of death.Results: Among 931 patients with SCLC diagnosed in 2007 in academic and community settings, 72.2% of patients with limited-stage (LS) disease received chemoradiation and 42.2% of patients with extensive-stage (ES) disease received chemotherapy only; the expected treatment scenarios by stage. Less than 1% of the patients enrolled in clinical trials and 2.1% of the patients with LS disease and 3.4% of the patients with ES disease refused any type of treatment. Patients 80 years or older at diagnosis and those with pneumonia/lung collapse were less likely to receive chemoradiation for LS disease. Patients treated in hospitals with residency programs were more likely to receive chemotherapy for ES disease, and patients 80 years or older were less likely to receive chemotherapy for ES disease. Finally, female patients with LS disease, black patients with ES disease, and all patients who received chemotherapy compared to receiving radiation alone or no therapy experienced significantly lower mortality.Discussion: Despite the demonstrated lower mortality, a relatively large proportion of patients with SCLC are not treated with a standard treatment regimen. Future studies should evaluate efforts to promote use of appropriate treatment regimens and encourage clinical trial participation.
Keywords: Carcinoma, Non-Small-Cell Lung -- Drug Therapy; Carcinoma, Non-Small-Cell Lung -- Epidemiology; Quality of Health Care; Adult; Aged; Aged, 80 and Over; Antineoplastic Agents, Combined -- Administration and Dosage; Cisplatin -- Administration and Dosage; Clinical Trials; Combined Modality Therapy; Etoposide -- Administration and Dosage; Female; Male; Middle Age; Neoplasm Staging; Carcinoma, Non-Small-Cell Lung -- Pathology

Treatment quality and outcomes of African American versus white breast cancer patients: retrospective analysis of Southwest Oncology studies S8814/S8897. - Hershman DL; Unger JM; Barlow WE; Hutchins LF; Martino S; Osborne CK; Livingston RB; Albain KS; Hershman, Dawn L; Unger, Joseph M; Barlow, William E; Hutchins, Laura F; et al. (Journal of Clinical Oncology, 2009)
Purpose: Women of African ancestry (AA) have lower WBC counts and are more likely to have treatment delays and discontinue adjuvant breast cancer therapy early compared with white women. We assessed the association between race and treatment discontinuation/delay, WBC counts, and survival in women enrolled onto breast cancer clinical trials.Patients and Methods: AA and white women from Southwest Oncology Group adjuvant breast cancer trials (S8814/S8897) were matched by age and protocol. Only the treatment arms in which patients were scheduled to receive six cycles of chemotherapy were analyzed.Results: A total of 317 pairs of patients (n = 634) were analyzed. At baseline, AA women had higher body-surface area (P < .0001) and lower WBC (P = .0009). AA women were more likely to have tumors that were > or = 2 cm (P = .01) and hormone receptor negative (P < .0001). AA women, versus white women, were marginally more likely to discontinue treatment early (11% v 7%, respectively; P = .07) or have one or more treatment delays (85% v 79%, respectively; P = .07) and were significantly more likely to experience the combined end point (discontinuation/delay; 87% v 81%, respectively; P = .04). The mean relative dose-intensity (RDI) was similar for both groups (87% in AA women v 86% in white women); however, overall, 43% had an RDI of less than 85%. After adjusting for baseline WBC and prognostic factors in a multivariate model, AA women had worse disease-free survival (hazard ratio [HR] = 1.56; 95% CI, 1.15 to 2.11; P = .005) and overall survival (HR = 1.95; 95% CI, 1.36 to 2.78; P = .0002). The inclusion of RDI and treatment delivery/quality in the regression had little impact on the results.Conclusion: On cooperative group breast cancer trials, AA and white women had similar RDIs, but AA women were more likely to experience early discontinuation or treatment delay. Despite correcting for these factors and known predictors of outcome, AA women still had worse survival.
Keywords: Black Persons; Breast Neoplasms -- Drug Therapy; Breast Neoplasms -- Ethnology; White Persons; Adult; Aged; Breast Neoplasms -- Blood; Breast Neoplasms -- Mortality; Chemotherapy, Adjuvant; Clinical Trials; Female; Health Status; Leukocyte Count; Middle Age; Treatment Outcomes; Human

Tuskegee redux: evolution of legal mandates for human experimentation. - Levine, Robert S; Williams, Jamila C; Kilbourne, Barbara A; Juarez, Paul D (Journal of Health Care for the Poor & Underserved, 2012)
Human health experiments systematically expose people to conditions beyond the boundaries of medical evidence. Such experiments have included legal-medical collaboration, exemplified in the U.S. by the Public Health Service (PHS) Syphilis Study (Tuskegee). That medical experiment was legal, conforming to segregationist protocols and specific legislative authorization which excluded a selected group of African Americans from any medical protection from syphilis. Subsequent corrective action outlawed unethical medical experiments but did not address other forms of collaboration, including PHS submission to laws which may have placed African American women at increased risk from AIDS and breast cancer. Today, anti-lobbying law makes it a felony for PHS workers to openly challenge legally anointed suspension of medical evidence. African Americans and other vulnerable populations may thereby face excess risks-not only from cancer, but also from motor vehicle crashes, firearm assault, end stage renal disease, and other problems-with PHS workers as silent partners.
Keywords: Black Persons; Breast Neoplasms; Health Policy; HIV Infections; Research Subjects; Syphilis; Adolescence; Adult; Aged; Alabama; Cancer Screening; Civil Rights; Comparative Studies; Confidence Intervals; Contact Tracing; Correlation Coefficient; Demography; Experimental Studies -- Legislation and Jurisprudence; Female; Health Services Accessibility; Health Status Disparities; HIV Infections -- Mortality; Human; Legislation; Male; Mammography; Medicare; Middle Age; Probability Sample; Prospective Studies; Race Factors; Research Ethics; Research Protocols; Research, Medical -- Legislation and Jurisprudence; Socioeconomic Factors; United States; United States Department of Health and Human Services; White Persons

UAB 0210: A phase I/II trial of induction chemotherapy followed by concomitant docetaxel/radiotherapy with subcutaneous amifostine for advanced squamous cell carcinoma of the head and neck (SCCHN). - Nabell, L M; Peters, G; Meredith, R; Carroll, W; Bonner, J; Ove, R; Spencer, S (Journal of Clinical Oncology, 2009)
6061 Background: Attempts to improve the outcome of locally advanced SCCHN have generally added chemotherapy to radiation, though the optimal manner of integration has been controversial. To impact distant and local control, we utilized neoadjuvant chemotherapy followed by concomitant boost radiation (CBR) with docetaxel as a radiosensitizer. To improve cytoprotection, subcutaneous amifostine was added during radiotherapy.Methods: From April 2003-March 2007 46 patients with stage III or IV newly diagnosed SCCHN were enrolled (30 Caucasian, 16 African-American). Treatment consisted of 3 cycles of neoadjuvant chemotherapy with cisplatin 75 mg/m2 and docetaxel 75 mg/m2 intravenously at 21 day intervals followed by CBR and concurrent dose-escalated weekly docetaxel starting at 20 mg/m2. Standard 2D radiotherapy was used in the majority of patients. Subcutaneous amifostine was administered at 500 mg during each day of radiation.Results: 39 patients were evaluable. The neoadjuvant chemotherapy was well tolerated by the majority of patients and appeared effective; no patient had progressive disease while on therapy. Three patients required a change to carboplatin due to toxicity. Weekly docetaxel during all weeks of CBR was not tolerable due to severe mucositis and the phase I component defined the MTD of concurrent docetaxel as 20 mg/m2 for 4 cycles during CBR. 4 patients (10%) had persistent disease at completion of treatment. Amifostine administration was well tolerated though 4 patients required discontinuation of the drug. The majority of recurrences have been localized at the primary site (6 patients). 3 patients developed isolated pulmonary metastasis. Only 2 patients remain PEG dependent with median follow-up of 24 months.Conclusions: Induction chemotherapy using cisplatin and docetaxel is feasible and easy to administer in the outpatient setting; those patients who had a major radiographic and clinical response did particularly well in follow-up. Weekly docetaxel can be safely and effectively administered during CBR with good local control. Amifostine can be safely administered via the subcutaneous route; the benefit in locally advanced patients is difficult to assess. No significant financial relationships to disclose.

Uncertainty and watchful waiting in men with prostate cancer. - Bailey DE Jr. (Uncertainty & Watchful Waiting in Men With Prostate Cancer, 2002)
Watchful waiting has been proposed as a reasonable alternative for older men with localized prostate cancer. However, this option is controversial, and men electing watchful waiting live with continual uncertainty. The purpose of this study was to test the efficacy of the Living with Uncertainty Intervention (LUI). The intervention was based on the Reconceptualized Uncertainty in Illness Theory and interviews with men electing watchful waiting (Bailey & Mishel, 1997; Mishel, 1990).The investigator used an experimental design and enrolled a convenience sample of 41 men. Experimental subjects received 5 weekly intervention calls from the nurse intervener. Thirty-seven subjects participated in a follow-up phone call at the end of the study to respond to interview questions concerning social support, religion, and their individual spiritual beliefs.Descriptive analyses were conducted for all demographic and outcome variables. Repeated measures of analyses of variance (ANOVA) were used to test the efficacy of the LUI. Functional status, number of health problems, and length of time since electing watchful were evaluated as moderators.The sample was 86% Caucasian and 14% African American, with an average age of 75.4 years. Intervention subjects came to view their lives in a new light (p = .02) and experienced a decrease in their confusion (p = .04) and depression (p = .06) levels from Time 1 to Time 2, as compared with controls. Additionally, intervention subjects reported an improvement in their quality of life over that reported by controls (p = .01) and believed their quality of life in the future (6 months) would be better than did the controls (p = .01).Low functional status moderated the effect of the LUI on confusion ( p =.03) and cognitive refraining (p = .08). High numbers of health problems moderated the effect of the LUI on depression ( p = .06) and future quality of life (p = .02). Greater length of time in watchful waiting moderated the effect of the intervention on cognitive reframing (p = .08). This study's findings documented the benefit of nursing intervention for patients living with continued uncertainty. The findings provided additional information about the experience of men electing watchful waiting and supported the theory (Mishel, 1990).
Keywords: Prostatic Neoplasms -- Psychosocial Factors; Uncertainty; Male; Conceptual Framework; Psychological Theory; Convenience Sample; Experimental Studies; Interviews; Quality of Life; Descriptive Statistics; Repeated Measures; Analysis of Variance; Functional Status; Time Factors; Aged; Support, Psychosocial; Telephone; Nursing Interventions; Human

Using a culturally relevant theory to recruit African American men for prostate cancer screening. - Lewis RK (Health Education & Behavior, 2005)
Keywords: Black Persons; Models, Theoretical; Research Subject Recruitment; Cancer Screening; Culture; Health Behavior; Male; Prostatic Neoplasms -- Prevention and Control

Using cancer registry data for recruitment of sexual minority women: successes and limitations. - Boehmer U; Clark M; Glickman M; Timm A; Sullivan M; Bradford J; Bowen DJ (Journal of Women's Health (15409996), 2010)
Objective: To identify and recruit an unknown and presumably small subgroup of survivors, that is, lesbian or bisexual women with breast cancer. Methods: This report describes our multistep approach to recruit a representative sample of heterosexual and sexual minority breast cancer survivors. We used census data to identify geographic areas with a greater prevalence of sexual minority women (SMW), that is, lesbian and bisexual women. We then obtained the breast cancer cases from a cancer registry for these geographic areas. In the absence of sexual orientation data in cancer registries, all potentially eligible women with breast cancer needed to be contacted by telephone to determine their sexual orientation. Results: Among the 1341 women screened who answered the question about sexual orientation, 6.3% were SMW. Overall, we processed 4143 cases to obtain completed data on 69 SMW and 257 heterosexual women with breast cancer. Conclusions: Our findings suggest that it is resource intensive but feasible to recruit a representative sample of breast cancer survivors of different sexual orientations. Our findings can inform future studies that seek to recruit sexual minority populations from cancer registries about some of the limitations to this approach.
Keywords: Bisexuals; Breast Neoplasms; Cancer Survivors; Lesbians; Registries, Disease; Research Subject Recruitment; Research Subjects; Adult; Aged; Aged, 80 and Over; Black Persons; Breast Neoplasms -- Classification; Chi Square Test; Confidence Intervals; Confidentiality (Research); Descriptive Statistics; Female; Funding Source; Hispanic Americans; Human; Marital Status; Massachusetts; Middle Age; Random Assignment; Self Report; Surveys; T-Tests; White Persons

Using focus groups to adapt ethnically appropriate, information-seeking and recruitment messages for a prostate cancer screening program for men at high risk. - Bryan CJ; Wetmore-Arkader L; Calvano T; Deatrick JA; Giri VN; Bruner DW; Bryan, Charlene J; Wetmore-Arkader, Lindsay; Calvano, Tammy; Deatrick, Janet A; Giri, Veda N; Bruner, Deborah Watkins (Journal of the National Medical Association, 2008)
Purpose: To adapt ethnically appropriate radio and newspaper messages in order to increase information-seeking and recruitment to the high-risk Prostate Cancer Risk Assessment Program (PRAP) using input from focus groups.Methods: We conducted four gender- and ethnic specific-focus groups composed of up to eight participants each. Group participants ranged in age from 35-69 and were either at risk for prostate cancer or were married to someone at risk. Participants evaluated both print and radio advertisements for a PRAP media recruitment campaign, and their recommendations were used to adapt the advertisements.Results: Trigger words, e.g,, "research program," were found to be a particular issue for African-American men who cited concerns about "experimentation," while the other groups cited concerns about time commitments and cost. In the print messages, familial themes garnered an overall favorable response, but Caucasian-American participants responded negatively to the use of photos of age-appropriate models.Conclusion: Focus groups are useful in checking health professional assumptions about health messages prior to developing awareness or recruitment advertisements or materials. There was an implied preference for "younger" models among Caucasian Americans. Radio and print messages were adapted using the focus group recommendations, i.e., focusing on familial themes, adding race-specific risk estimates and using younger-than-target group models.
Keywords: Cancer Screening; Culture; Program Development; Prostatic Neoplasms -- Prevention and Control; Adult; Aged; Cultural Diversity; Descriptive Research; Digital Rectal Examination; Early Intervention; Female; Focus Groups; Male; Middle Age; Minority Groups; Patient Selection; Prostate-Specific Antigen -- Blood; Prostatic Neoplasms -- Epidemiology; Qualitative Studies; Thematic Analysis; Human

Using self-reported data on the social determinants of health in primary care to identify cancer screening disparities: opportunities and challenges. - Lofters, A. K.; Schuler, A.; Slater, M.; Baxter, N. N.; Persaud, N.; Pinto, A. D.; Kucharski, E.; Davie, S.; Nisenbaum, R.; Kiran, T. (BMC Family Practice, 2017)
Background: Data on the social determinants of health can help primary care practices target improvement efforts, yet relevant data are rarely available. Our family practice located in Toronto, Ontario routinely collects patient-level sociodemographic data via a pilot-tested survey developed by a multi-organizational steering committee. We sought to use these data to assess the relationship between the social determinants and colorectal, cervical and breast cancer screening, and to describe the opportunities and challenges of using data on social determinants from a self-administered patient survey. Methods: Patients of the family practice eligible for at least one of the three cancer screening types, based on age and screening guidelines as of June 30, 2015 and who had answered at least one question on a socio-demographic survey were included in the study. We linked self-reported data from the sociodemographic survey conducted in the waiting room with patients' electronic medical record data and cancer screening records. We created an individual-level income variable (low-income cut-off) that defined a poverty threshold and took household size into account. The sociodemographic characteristics of patients who were overdue for screening were compared to those who were up-to-date for screening for each cancer type using chi-squared tests. Results: We analysed data for 5766 patients for whom we had survey data. Survey participants had significantly higher screening rates (72.9, 78.7, 74.4% for colorectal, cervical and breast cancer screening respectively) than the 13, 036 patients for whom we did not have survey data (59.2, 65.3, 58.9% respectively). Foreign-born patients were significantly more likely to be up-to-date on colorectal screening than their Canadian-born peers but showed no significant differences in breast or cervical cancer screening. We found a significant association between the low-income cut-off variable and cancer screening; neighbourhood income quintile was not significantly associated with cancer screening. Housing status was also significantly associated with colorectal, cervical and breast cancer screening. There was a large amount of missing data for the low-income cut-off variable, approximately 25% across the three cohorts. Conclusion: While we were able to show that neighbourhood income might under-estimate income-related disparities in screening, individual-level income was also the most challenging variable to collect. Future work in this area should target the income disparity in cancer screening and simultaneously explore how best to collect measures of poverty.
Keywords: Early Detection of Cancer -- Methods; Primary Health Care; Self Report; Social Determinants of Health; Breast Neoplasms -- Diagnosis; Canada; Cervix Neoplasms; Family Practice; Cancer Screening; Human; Income; Mammography; Ontario; Poverty; Residence Characteristics; Social Class; Socioeconomic Factors; Surveys; Healthcare Disparities -- Evaluation; Urban Areas; Geographic Locations; Research Subject Recruitment; Outcomes (Health Care); Data Analysis Software; Adult; Middle Age; Aged; Male; Female; Immigrants; White Persons; Asians; Black Persons; Hispanic Americans; Middle East; Funding Source

Vegetarian dietary patterns and the risk of colorectal cancers. - Orlich, Michael J; Singh, Pramil N; Sabaté, Joan; Fan, Jing; Sveen, Lars; Bennett, Hannelore; Knutsen, Synnove F; Beeson, W Lawrence; Jaceldo-Siegl, Karen; Butler, Terry L; Herring, R Patti; Fraser, Gary E (JAMA Internal Medicine, 2015)
Importance: Colorectal cancers are a leading cause of cancer mortality, and their primary prevention by diet is highly desirable. The relationship of vegetarian dietary patterns to colorectal cancer risk is not well established.Objective: To evaluate the association between vegetarian dietary patterns and incident colorectal cancers.Design, Setting, and Participants: The Adventist Health Study 2 (AHS-2) is a large, prospective, North American cohort trial including 96,354 Seventh-Day Adventist men and women recruited between January 1, 2002, and December 31, 2007. Follow-up varied by state and was indicated by the cancer registry linkage dates. Of these participants, an analytic sample of 77,659 remained after exclusions. Analysis was conducted using Cox proportional hazards regression, controlling for important demographic and lifestyle confounders. The analysis was conducted between June 1, 2014, and October 20, 2014.Exposures: Diet was assessed at baseline by a validated quantitative food frequency questionnaire and categorized into 4 vegetarian dietary patterns (vegan, lacto-ovo vegetarian, pescovegetarian, and semivegetarian) and a nonvegetarian dietary pattern.Main Outcomes and Measures: The relationship between dietary patterns and incident cancers of the colon and rectum; colorectal cancer cases were identified primarily by state cancer registry linkages.Results: During a mean follow-up of 7.3 years, 380 cases of colon cancer and 110 cases of rectal cancer were documented. The adjusted hazard ratios (HRs) in all vegetarians combined vs nonvegetarians were 0.78 (95% CI, 0.64-0.95) for all colorectal cancers, 0.81 (95% CI, 0.65-1.00) for colon cancer, and 0.71 (95% CI, 0.47-1.06) for rectal cancer. The adjusted HR for colorectal cancer in vegans was 0.84 (95% CI, 0.59-1.19); in lacto-ovo vegetarians, 0.82 (95% CI, 0.65-1.02); in pescovegetarians, 0.57 (95% CI, 0.40-0.82); and in semivegetarians, 0.92 (95% CI, 0.62-1.37) compared with nonvegetarians. Effect estimates were similar for men and women and for black and nonblack individuals.Conclusions and Relevance: Vegetarian diets are associated with an overall lower incidence of colorectal cancers. Pescovegetarians in particular have a much lower risk compared with nonvegetarians. If such associations are causal, they may be important for primary prevention of colorectal cancers.
Keywords: Colorectal Neoplasms -- Mortality; Colorectal Neoplasms -- Prevention and Control; Colorectal Neoplasms -- Psychosocial Factors; Food Habits; Life Style; Vegetarianism -- Psychosocial Factors; Adult; Aged; Data Collection; Female; Human; Incidence; Male; Middle Age; Mortality; Prospective Studies; Questionnaires; Relative Risk; United States; Funding Source

Voluntary participation and comprehension of informed consent in a genetic epidemiological study of breast cancer in Nigeria. - Marshall, Patricia A; Adebamowo, Clement A; Adeyemo, Adebowale A; Ogundiran, Temidayo O; Strenski, Teri; Zhou, Jie; Rotimi, Charles N (BMC Medical Ethics, 2014)
Background: Studies on informed consent to medical research conducted in low or middle-income settings have increased, including empirical investigations of consent to genetic research. We investigated voluntary participation and comprehension of informed consent among women involved in a genetic epidemiological study on breast cancer in an urban setting of Nigeria comparing women in the case and control groups.Methods: Surveys were administered in face-to-face interviews with 215 participants following their enrollment in the genetic study (106 patients, 109 controls). Audio-taped in-depth interviews were conducted with a sub-sample of 17 (8%) women who completed the survey.Results: The majority of all participants reported being told that participation in the genetic study was voluntary (97%), that they did not feel pressured to participate in the study (99%), and that they could withdraw from the study (81%). The majority of the breast cancer patients (83%) compared to 58% of women in the control group reported that the study purpose was to learn about the genetic inheritance of breast cancer (OR 3.44; 95% CI =1.66, 7.14, p value = 0.001). Most participants reported being told about study procedures (95%) and study benefits (98%). Sixty-eight percent of the patients, compared to 47% of the control group reported being told about study risks (p-value <0.001). Of the 165 married women, 19% reported asking permission from their husbands to enroll in the breast cancer study; no one sought permission from local elders. In-depth interviews highlight the use of persuasion and negotiation between a wife and her husband regarding study participation.Conclusions: The global expansion of genetic and genomic research highlights our need to understand informed consent practices for studies in ethnically diverse cultural environments such as Africa. Quantitative and qualitative empirical investigations of the informed consent process for genetic and genomic research will further our knowledge of complex issues associated with communication of information, comprehension, decisional authority and voluntary participation. In the future, the development and testing of innovative strategies to promote voluntary participation and comprehension of the goals of genomic research will contribute to our understanding of strategies that enhance the consent process.
Keywords: Breast Neoplasms -- Epidemiology; Breast Neoplasms; Readability; Genetic Research -- Ethical Issues; Consent -- Ethical Issues; Consent -- Statistics and Numerical Data; Adult; Black Persons; Breast Neoplasms -- Psychosocial Factors; Female; Disease Susceptibility; Attitude to Health; Human; Male; Epidemiology, Molecular; Nigeria; Nigeria -- Ethnology; Patient Selection; Questionnaires; Refusal to Participate

Why some women have an optimistic or a pessimistic bias about their breast cancer risk: experiences, heuristics, and knowledge of risk factors. - Katapodi MC; Dodd MJ; Facione NC; Humphreys JC; Lee KA (Cancer Nursing, 2010)
Perceived risk to a health problem is formed by inferential rules called heuristics and by comparative judgments that assess how one's risk compares to the risk of others. The purpose of this cross-sectional, community-based survey was to examine how experiences with breast cancer, knowledge of risk factors, and specific heuristics inform risk judgments for oneself, for friends/peers, and comparative judgments for breast cancer (risk friends/peers - risk self). We recruited an English-speaking, multicultural (57% nonwhite) sample of 184 middle-aged (47 + or - 12 years old), well-educated women. Fifty percent of participants perceived that their breast cancer risk was the same as the risk of their friends/peers; 10% were pessimistic (risk friends/peers - risk self < 0), whereas 40% were optimistic (risk friends/peers - risk self > 0). Family history of breast cancer and worry informed risk judgments for oneself. The availability and cultural heuristics specific for black women informed risk judgments for friends/peers. Knowledge of risk factors and interactions of knowledge with the availability, representativeness, and simulation heuristics informed comparative judgments (risk friends/peers - risk self). We discuss cognitive mechanisms with which experiences, knowledge, and heuristics influence comparative breast cancer risk judgments. Risk communication interventions should assess knowledge deficits, contextual variables, and specific heuristics that activate differential information processing mechanisms.
Keywords: Attitude to Illness; Breast Neoplasms -- Risk Factors; Adult; Aged; Aged, 80 and Over; Attitude to Illness -- Evaluation; Biopsy; California; Coefficient Alpha; Cross Sectional Studies; Descriptive Research; Descriptive Statistics; Effect Size; Family History; Female; Funding Source; Health Knowledge -- Evaluation; Human; Independent Variable; Judgment; Middle Age; Questionnaires; Regression; Research Subject Recruitment; T-Tests

Willingness to Discuss Clinical Trials Among Black vs White Men With Prostate Cancer. - Senft, Nicole; Hamel, Lauren M.; Manning, Mark A.; Kim, Seongho; Penner, Louis A.; Moore, Tanina Foster; Carducci, Michael A.; Heath, Elisabeth I.; Lansey, Dina G.; Albrecht, Terrance L.; Wojda, Mark; Jordan, Alice; et al. (JAMA Oncology, 2020)
This cross-sectional survey study examines whether Black and White men with prostate cancer differ in their willingness to discuss clinical trials with their physicians, and if so, whether patient-level barriers are associated with racial differences. Key Points: Question: Are Black men with prostate cancer less willing than White men to discuss clinical trials with their physicians, and are patient-level barriers associated with racial differences? Findings: In this cross-sectional survey study of 205 patients with prostate cancer, most participants reported being willing to discuss trials, but Black men were significantly less willing than White men. Racial differences were associated with greater medical suspicion among Black men. Meaning: Addressing Black patients' medical suspicion may promote equity in clinical trial participation. Importance: Black individuals are underrepresented in cancer clinical trials. Objective: To examine whether Black and White men with prostate cancer differ in their willingness to discuss clinical trials with their physicians and, if so, whether patient-level barriers statistically mediate racial differences. Design, Setting, and Participants: This cross-sectional survey study used baseline data from Partnering Around Cancer Clinical Trials, a randomized clinical trial to increase Black individuals' enrollment in prostate cancer clinical trials. Data were collected from 2016 through 2019 at 2 National Cancer Institute–designated comprehensive cancer centers; participants were Black and White men with intermediate-risk to high-risk prostate cancer. In mediation analysis, path models regressed willingness onto race and each potential mediator, simultaneously including direct paths from race to each mediator. Significant indirect effect sizes served as evidence for mediation. Exposures: Race was the primary exposure. Potential mediators included age, education, household income, perceived economic burden, pain/physical limitation, health literacy, general trust in physicians, and group-based medical suspicion. Main Outcomes and Measures: The primary outcome was the answer to a single question: "If you were offered a cancer clinical trial, would you be willing to hear more information about it?" Results: A total of 205 participants were included (92 Black men and 113 White men), with a mean (range) age of 65.7 (45-89) years; 32% had a high school education or lower, and 27.5% had a household income of less than $40 000. Most (88.3%) reported being definitely or probably willing to discuss trials, but White participants were more likely to endorse this highest category of willingness than Black participants (82% vs 64%; χ22 = 8.81; P =.01). Compared with White participants, Black participants were younger (F1,182 = 8.67; P <.001), less educated (F1,182 = 22.79; P <.001), with lower income (F1,182 = 79.59; P <.001), greater perceived economic burden (F1,182 = 42.46; P <.001), lower health literacy (F1,184 = 9.84; P =.002), and greater group-based medical suspicion (F1,184 = 21.48; P <.001). Only group-based medical suspicion significantly mediated the association between race and willingness to discuss trials (indirect effect, −0.22; P =.002). Conclusions and Relevance: In this study of men with prostate cancer, most participants were willing to discuss trials, but Black men were significantly less willing than White men. Black men were more likely to believe that members of their racial group should be suspicious of the health care system, and this belief was associated with lower willingness to discuss trials. Addressing medical mistrust may improve equity in clinical research.
Keywords: Men's Health; Black Persons; White Persons; Prostatic Neoplasms; Cancer Patients; Patient Attitudes; Clinical Trials; Physician-Patient Relations; Race Factors; Human; Male; Cross Sectional Studies; Mediation Analysis; Path Analysis; Socioeconomic Factors; Middle Age; Aged; Aged, 80 and Over; Chi Square Test; Multivariate Analysis of Variance; Data Analysis Software; Analysis of Variance; Funding Source

WOMEN AND BREAST CANCER RESEARCH. - Reifenstein, Karen; Asare, Matt; Millon-Underwood, Sandra (Journal of Cultural Diversity, 2019)
Lack of adequate participation by African American and Hispanic women in breast cancer genetic research studies sustains a knowledge gap in our understanding of new and innovative scientific advances and outcomes in breast cancer research/genomics. The purpose of this study is to suggest strategies to increase African American and Hispanic women's participation in breast cancer genetic research. A review of literature reveals that historical, community involvement, cultural, discrimination!somatizations concerns, and economic factors may impact participation in breast cancer genetic research investigations. Future research investigations should involve members of the minority community as recruiters, acknowledge anticipated historical concerns up-front, address anticipated concerns of discrimination/stigmatizations, and recognize and respect a person's culture and try to work within it when attempting to recruit minority women for breast cancer genetic research.
Keywords: Breast Neoplasms; Research, Medical; Women -- Psychosocial Factors; Consumer Participation -- Psychosocial Factors; Black Persons; Hispanic Americans; Human; Systematic Review; Psycinfo; Cochrane Library; PubMed; Medline; CINAHL Database; Decision Making

Women's decisions to seek evaluation of self discovered breast symptoms occurred in a complex social context [commentary on Facione NC, Giancarlo CA. Narratives of breast symptom discovery and cancer diagnosis: psychologic risk for advanced cancer at diagnosis. CANCER NURS 1998;21(6):430-40]. - Ingram C (Evidence Based Nursing, 1999)
Question: How do women decide whether and when to seek medical evaluation of self discovered breast symptoms? Design: Analysis of narratives generated from 16 focus groups. Setting: San Francisco, California, USA. Participants: 80 women aged >/=21 years who were recruited through community organisations, women's groups, churches, and senior centres. Methods: Focus groups (6 groups of black women, 4 groups of white women, and 6 groups of Latino women) were held in homes and community meeting rooms and lasted 90-120 minutes. Women were asked what it would be like to discover a problem in their breast, what they thought they would do, and to relate the experiences of women in their families or communities. Sessions were audiotaped, data were transcribed and narratives were independently analysed by 3 researchers. Main findings: Women related 101 narratives of personal experiences with self discovered breast symptoms, as well as those of friends and family. They gave vivid descriptions of the place and time of symptom discovery and understood that the passage of time without treatment added to the threat of the symptom. Some disclosed the symptom to partners or friends, which led to prompt, self initiated visits to a healthcare provider; others failed to disclose the discovery until their disease was advanced. Some women had difficulty interpreting the threat of the symptom and delayed evaluation. Some refused to give the symptom importance, and some blocked it from conscious awareness. Some avoided the term cancer, referring instead to 'the big C'; some thought that by avoiding the term, they could exert power over the cancer; and others thought that talking about cancer would cause women to get it. Women generally endorsed alternative therapies, often in conjunction with traditional medical treatments. Views on the role of God and spirituality varied, but none spoke of religious beliefs that prohibited evaluation or treatment of symptoms. Those who decided not to lose the breast through surgery were seen by some as making a breast conserving choice, by others as experiencing drastic repercussions, and by others as sparing the woman a loss of her femininity. Feelings about symptom discovery included fear of cancer and its treatment and guilt at not discovering symptoms earlier. Experiences with the provider visit included embarrassment during the physical examination, annoyance with the discomfort of the examination, and insensitive or rushed providers. Some women delayed or refused treatment because they feared abandonment by male partners. In some instances, male partners actually obstructed diagnosis or treatment. Poverty inhibited decisions to seek evaluation of symptoms because financial resources were needed for other family problems. Conclusion: Women's stories revealed several factors that delayed breast cancer diagnosis: unwillingness to disclose symptoms, incorrect interpretation of the threat of symptoms, a decision not to undergo surgery, embarrassment related to physical examination, fear of abandonment by male partners, and poverty. [Original article accession number: 1999008141 (research, tables/charts)]
Keywords: Breast Neoplasms -- Psychosocial Factors; Breast Neoplasms -- Diagnosis; Patient Attitudes; Help Seeking Behavior; Symptoms; Research Subject Recruitment; Focus Groups; California; Patient Attitudes -- Evaluation; Narratives; Thematic Analysis; Qualitative Studies; Adult; Middle Age; Female

Women's knowledge and sources of information on the risks and benefits of oral contraception. - Picardo CM; Nichols M; Edelman A; Jensen JT (Journal of the American Medical Women's Association, 2003)
OBJECTIVE: To assess the knowledge of the risks and benefits of oral contraceptives (OCs) in a heterogeneous group of women and to identify their sources of information. METHODS: A self-administered questionnaire assessing demographics, contraception history, knowledge of risks and benefits of OCs, and information sources was given to literate English- and Spanish-speaking women waiting for appointments at 4 clinics serving distinct populations in Portland, Oregon. RESULTS: Approximately half of the 211 women studied were of the opinion that OCs decreased the risk of acne, dysmenorrhea, and menorrhagia and increased the risk of weight gain, headaches, and thrombosis. Less than 15% knew of the decreased risk of anemia, endometrial cancer, colon cancer and pelvic inflammatory disease, but 28% understood the decreased risk of ovarian cancer. Seven percent to 36% of women used their own experiences in assessing the effect of OCs on a variety of general and reproductive factors. Women relied primarily on printed information for knowledge of OCs' effects on cardiovascular health and cancer. CONCLUSION: Women in this heterogeneous population of women were unaware of several benefits of OCs. Women relied heavily on their own experiences in assessing the risks and benefits of OCs. Women cited printed information more frequently than medical personnel as major sources of information on cardiovascular and oncological risks and benefits of OCs. The Internet, however, played a minimal, if any role in educating women about OCs.
Keywords: Contraceptives, Oral -- Therapeutic Use; Health Knowledge; Women's Health; Adolescence; Adult; Analysis of Variance; Attitude to Health; Black Persons; Cardiovascular Diseases -- Prevention and Control; Chi Square Test; Data Analysis Software; Descriptive Statistics; Evaluation Research; Female; Genital Neoplasms, Female -- Prevention and Control; Headache -- Chemically Induced; Hispanic Americans; Middle Age; Native Americans; Obesity -- Chemically Induced; Oregon; Questionnaires; Research Subject Recruitment; Self Report; Socioeconomic Factors; Surveys; Thrombosis -- Chemically Induced; White Persons; Funding Source; Human

Women's satisfaction with breast and gynecological cancer screening. - Foxall MJ; Barron CR; Houfek J (Women & Health, 2003)
PURPOSES: This study examined women's satisfaction with their breast and gynecological (GYN) cancer screening, clinical breast examination (CBE), mammogram (MAM), and pelvic examination (PE). Selected predictors (characteristics of the exam and characteristics of the health care provider) of satisfaction with their screening exams also were assessed. METHODS: Women (N = 242) ages 19 years and older were recruited from a residential mailing list, and from church and community organizations. Participants completed questionnaires in their homes or in the community setting where they had been recruited. Descriptive statistics were used to describe the level of women's satisfaction with their most recent exams. Hierarchical multiple regression was used to determine the influence of exam and health care provider characteristics on women's satisfaction with exams. RESULTS: We found that women were very satisfied with care received during all three screening exams. Women were more satisfied during CBE and PE if they perceived these exams as informative, clear and complete and if they perceived the provider as informative and responsive to them when they ask questions. Women also were more satisfied with all three exams when the provider was perceived as relaxed during these exams.
Keywords: Breast Neoplasms -- Diagnosis; Cancer Screening -- Standards; Mammography -- Standards; Physical Examination -- Standards; Uterine Neoplasms -- Diagnosis; Women's Health Services -- Standards; Adult; Aged; Black Persons; Clinical Competence; Content Validity; Convenience Sample; Descriptive Research; Descriptive Statistics; Female; Health Services Accessibility; Hispanic Americans; Literature Review; Mail; Mammography -- Psychosocial Factors; Middle Age; Midwestern United States; Multiple Regression; Native Americans; Palpation -- Psychosocial Factors; Palpation -- Standards; Physical Examination -- Psychosocial Factors; Power Analysis; Professional-Patient Relations; Questionnaires; Random Sample; Regression; Research Subject Recruitment; Research Subjects -- Economics; Sample Size; Scales; Secondary Analysis; Summated Rating Scaling; Surveys; United States; White Persons; Human

Yoga associated with improved social well-being for multi-ethnic women with breast cancer. - Stevinson C; Moadel AB; Hall CB (Focus on Alternative & Complementary Therapies, 2008)
Keywords: Cancer Survivors; Functional Status; Psychological Well-Being; Yoga; Affect; Black Persons; Breast Neoplasms; Clinical Trials; Fatigue; Female; Hispanic Americans; New York; Outpatients; Patient Compliance; Quality of Life; Research Subject Recruitment; Research Subject Retention; Spirituality; Waiting Lists